The halo light cone catalogues of ABACUSSUMMIT - Hadzhiyska, Boryana; Garrison, Lehman H.; Eisenstein, Daniel; Bose, Sownak (MNRAS)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; COSMOLOGY: THEORY; Galaxies: Formation; galaxies: haloes; large-scale structure of Universe; methods: data analysis; Methods: n-Body Simulations

First detection of the BAO signal from early DESI data - Moon, Jeongin; Valcin, David; Rashkovetskyi, Michael; Saulder, Christoph; Aguilar, Jessica Nicole; Ahlen, Steven; Alam, Shadab; Bailey, Stephen; Baltay, Charles; Blum, Robert; David Brooks; Burtin, Etienne; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
We present the first detection of the baryon acoustic oscillations (BAOs) signal obtained using unblinded data collected during the initial 2 months of operations of the Stage-IV ground-based Dark Energy Spectroscopic Instrument (DESI). From a selected sample of 261 291 luminous red galaxies spanning the redshift interval 0.4 < z < 1.1 and covering 1651 square degrees with a 57.9 per cent completeness level, we report a ~5σ level BAO detection and the measurement of the BAO location at a precision of 1.7 per cent. Using a bright galaxy sample of 109 523 galaxies in the redshift range 0.1 < z < 0.5, over 3677 square degrees with a 50.0 per cent completeness, we also detect the BAO feature at ~3σ significance with a 2.6 per cent precision. These first BAO measurements represent an important milestone, acting as a quality control on the optimal performance of the complex robotically actuated, fibre-fed DESI spectrograph, as well as an early validation of the DESI spectroscopic pipeline and data management system. Based on these first promising results, we forecast that DESI is on target to achieve a high-significance BAO detection at sub-per cent precision with the completed 5-yr survey data, meeting the top-level science requirements on BAO measurements. This exquisite level of precision will set new standards in cosmology and confirm DESI as the most competitive BAO experiment for the remainder of this decade.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

The galaxies missed by Hubble and ALMA: the contribution of extremely red galaxies to the cosmic census at 3 - Williams, Christina C.; Alberts, Stacey; Ji, Zhiyuan; Hainline, Kevin N.; Lyu, Jianwei; Rieke, George; Endsley, Ryan; Suess, Katherine A.; Johnson, Benjamin D.; Florian, Michael; Shivaei, Irene; Rujopakarn, Wiphu; et al. (arXiv e-prints, 2023)
Using deep JWST imaging from JADES, JEMS and SMILES, we characterize optically-faint and extremely red galaxies at $z>3$ that were previously missing from galaxy census estimates. The data indicate the existence of abundant, dusty and post-starburst-like galaxies down to $10^8$M$_\odot$, below the sensitivity limit of Spitzer and ALMA. Modeling the NIRCam and HST photometry of these red sources can result in extreme, high values for both stellar mass and star formation rate (SFR); however, including 7 MIRI filters out to 21$μ$m results in decreased mass (median 0.6 dex for log$_{10}$M$^*$/M$_{\odot}>$10), and SFR (median 10$×$ for SFR$>$100 M$_{\odot}$/yr). At $z>6$, our sample includes a high fraction of little red dots (LRDs; NIRCam-selected dust-reddened AGN candidates). We significantly measure older stellar populations in the LRDs out to rest-frame 3$μ$m (the stellar bump) and rule out a dominant contribution from hot dust emission, a signature of AGN contamination to stellar population measurements. This allows us to measure their contribution to the cosmic census at $z>3$, below the typical detection limits of ALMA ($L_{\rm IR}<10^{12}L_\odot$). We find that these sources, which are overwhelmingly missed by HST and ALMA, could effectively double the obscured fraction of the star formation rate density at $4<z<6$ compared to some estimates, showing that prior to JWST, the obscured contribution from fainter sources could be underestimated. Finally, we identify five sources with evidence for Balmer breaks and high stellar masses at $5.5<z<7.7$. While spectroscopy is required to determine their nature, we discuss possible measurement systematics to explore with future data.
Keywords: Astrophysics - Astrophysics of Galaxies

Identification of High-Redshift Galaxy Overdensities in GOODS-N and GOODS-S - Helton, Jakob M.; Sun, Fengwu; Charity Woodrum; Hainline, Kevin N.; Willmer, Christopher N. A.; Rieke, Marcia J.; Rieke, George H.; Alberts, Stacey; Daniel J. Eisenstein; Tacchella, Sandro; Robertson, Brant; Johnson, Benjamin D.; et al. (arXiv e-prints, 2023)
We conduct a systematic search for high-redshift galaxy overdensities at $4.9 < z_{\,\mathrm{spec}} < 8.9$ in both the GOODS-N and GOODS-S fields using JWST/NIRCam imaging from JADES and JEMS in addition to JWST/NIRCam wide field slitless spectroscopy from FRESCO. High-redshift galaxy candidates are identified using HST+JWST photometry spanning $\lambda = 0.4-5.0\ \mu\mathrm{m}$. We confirmed the redshifts for roughly a third of these galaxies using JWST/FRESCO spectroscopy over $\lambda = 3.9-5.0\ \mu\mathrm{m}$ through identification of either $\mathrm{H} \alpha$ or $\left[\mathrm{OIII}\right]\lambda5008$ around the best-fit photometric redshift. The rest-UV magnitudes and continuum slopes of these galaxies were inferred from the photometry: the brightest and reddest objects appear in more dense environments and thus are surrounded by more galaxy neighbors than their fainter and bluer counterparts, suggesting accelerated galaxy evolution within overdense environments. We find $17$ significant ($\delta_{\mathrm{gal}} \geq 3.04$, $N_{\mathrm{galaxies}} \geq 4$) galaxy overdensities across both fields ($7$ in GOODS-N and $10$ in GOODS-S), including the two highest redshift spectroscopically confirmed galaxy overdensities to date at $\left< z_{\mathrm{\,spec}} \right> = 7.955$ and $\left< z_{\mathrm{\,spec}} \right> = 8.222$ (representing densities around $\sim 6$ and $\sim 12$ times that of a random volume). We estimate the total halo mass of these large-scale structures to be $11.5 \leq \mathrm{log}_{10}\left(M_{\mathrm{halo}}/M_{\odot}\right) \leq 13.4$ using an empirical stellar mass to halo mass relation, which are likely underestimates as a result of incompleteness. These protocluster candidates are expected to evolve into massive galaxy clusters with $\mathrm{log}_{10}\left(M_{\mathrm{halo}}/M_{\odot}\right) rsim 14$ by $z = 0$.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES Initial Data Release for the Hubble Ultra Deep Field: Revealing the Faint Infrared Sky with Deep JWST NIRCam Imaging - Rieke, Marcia J.; Robertson, Brant; Tacchella, Sandro; Hainline, Kevin; Johnson, Benjamin D.; Hausen, Ryan; Ji, Zhiyuan; Willmer, Christopher N. A.; Daniel J. Eisenstein; Puskás, Dávid; Alberts, Stacey; Arribas, Santiago; et al. (The Astrophysical Journal Supplement Series, 2023)
JWST has revolutionized the field of extragalactic astronomy with its sensitive and high-resolution infrared view of the distant Universe. Adding to the new legacy of JWST observations, we present the first NIRCam imaging data release from the JWST Advanced Deep Extragalactic Survey (JADES), providing nine filters of infrared imaging of ~25 arcmin2 covering the Hubble Ultra Deep Field and portions of Great Observatories Origins Deep Survey South. Utilizing 87 on-sky dual-filter hours of exposure time, these images reveal the deepest ever near-infrared view of this iconic field. We supply carefully constructed nine-band mosaics of the JADES bands, as well as matching reductions of five additional bands from the JWST Extragalactic Medium-band Survey. Combining with existing Hubble Space Telescope imaging, we provide 23-band space-based photometric catalogs and photometric redshifts for ≈47,500 sources. To promote broad engagement with JADES, we have created an interactive FitsMap website to provide an interface for professional researchers and the public to experience these JWST data sets. Combined with the first JADES NIRSpec data release, these public JADES imaging and spectroscopic data sets provide a new foundation for discoveries of the infrared Universe by the worldwide scientific community.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

JADES: Using NIRCam Photometry to Investigate the Dependence of Stellar Mass Inferences on the IMF in the Early Universe - Charity Woodrum; Rieke, Marcia; Ji, Zhiyuan; Baker, William M.; Bhatawdekar, Rachana; Bunker, Andrew J.; Charlot, Stéphane; Curtis-Lake, Emma; Daniel J. Eisenstein; Hainline, Kevin; Hausen, Ryan; Helton, Jakob M.; et al. (arXiv e-prints, 2023)
The detection of numerous and relatively bright galaxies at redshifts z > 9 has prompted new investigations into the star-forming properties of high-redshift galaxies. Using local forms of the initial mass function (IMF) to estimate stellar masses of these galaxies from their light output leads to galaxy masses that are at the limit allowed for the state of the LambdaCDM Universe at their redshift. We explore how varying the IMF assumed in studies of galaxies in the early universe changes the inferred values for the stellar masses of these galaxies. We infer galaxy properties with the SED fitting code Prospector using varying IMF parameterizations for a sample of 102 galaxies from the JWST Advanced Deep Extragalactic Survey (JADES) spectroscopically confirmed to be at z > 6.7, with additional photometry from the JWST Extragalactic Medium Band Survey (JEMS) for twenty-one galaxies. We demonstrate that models with stellar masses reduced by a factor of three or more do not affect the modeled spectral energy distribution (SED).
Keywords: Astrophysics - Astrophysics of Galaxies

A Spectroscopic Search for Optical Emission Lines from Dark Matter Decay - Wang, Hanyue; Daniel J. Eisenstein; Aguilar, Jessica Nicole; Ahlen, Steven; Bailey, Stephen; David Brooks; Claybaugh, Todd; de la Macorra, Axel; Doel, Peter; Forero-Romero, Jaime E.; Kremin, Anthony; Levi, Michael E.; et al. (arXiv e-prints, 2023)
We search for narrow-line optical emission from dark matter decay by stacking dark-sky spectra from the Dark Energy Spectroscopic Instrument (DESI) at the redshift of nearby galaxies from DESI's Bright Galaxy and Luminous Red Galaxy samples. Our search uses regions separated by 5 to 20 arcsecond from the centers of the galaxies, corresponding to an impact parameter of approximately $50\,\rm kpc$. No unidentified spectral line shows up in the search, and we place a line flux limit of $10^{-19}\,\rm{ergs}/\rm{s}/\rm{cm}^{2}/\rm{arcsec}^{2}$ on emissions in the optical band ($3000\lesssim\lambda\lesssim9000 \,\mathring{\rm A}$), which corresponds to $34$ in AB magnitude in a normal broadband detection. This detection limit suggests that the line surface brightness contributed from all dark matter along the line of sight is two orders of magnitude lower than the measured extragalactic background light (EBL), which rules out the possibility that narrow optical-line emission from dark matter decay is a major source of the EBL.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

Synthetic light-cone catalogues of modern redshift and weak lensing surveys waith ABACUSSUMMIT - Hadzhiyska, Boryana; Yuan, S.; Blake, C.; Eisenstein, D. J.; Aguilar, J.; Ahlen, S.; Brooks, D.; Claybaugh, T.; de la Macorra, A.; Doel, P.; Emas, N.; Forero-Romero, J. E.; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
The joint analysis of different cosmological probes, such as galaxy clustering and weak lensing, can potentially yield invaluable insights into the nature of the primordial Universe, dark energy, and dark matter. However, the development of high-fidelity theoretical models is a necessary stepping stone. Here, we present public high-resolution weak lensing maps on the light-cone, generated using the N-body simulation suite ABACUSSUMMIT, and accompanying weak lensing mock catalogues, tuned to the Early Data Release small-scale clustering measurements of the Dark Energy Spectroscopic Instrument. Available in this release are maps of the cosmic shear, deflection angle, and convergence fields at source redshifts ranging from z = 0.15 to 2.45 as well as cosmic microwave background convergence maps for each of the 25 base-resolution simulations ($L_{\rm box} = 2000\, h^{-1}\, {\rm Mpc}$ and Npart = 69123) as well as for the two huge simulations ($L_{\rm box} = 7500\, h^{-1}\, {\rm Mpc}$ and Npart = 86403) at the fiducial ABACUSSUMMIT cosmology. The pixel resolution of each map is 0.21 arcmin, corresponding to a HEALPIX Nside of 16 384. The sky coverage of the base simulations is an octant until z ≈ 0.8 (decreasing to about 1800 deg2 at z ≈ 2.4), whereas the huge simulations offer full-sky coverage until z ≈ 2.2. Mock lensing source catalogues are sampled matching the ensemble properties of the Kilo-Degree Survey, Dark Energy Survey, and Hyper Suprime-Cam data sets. The mock catalogues are validated against theoretical predictions for various clustering and lensing statistics, such as correlation multipoles, galaxy-shear, and shear-shear, showing excellent agreement. All products can be downloaded via a Globus endpoint (see Data Availability section).
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

AGN Selection and Demographics: A New Age with JWST/MIRI - Lyu, Jianwei; Alberts, Stacey; Rieke, George H.; Shivaei, Irene; Perez-Gonzalez, Pablo G.; Sun, Fengwu; Hainline, Kevin N.; Baum, Stefi; Bonaventura, Nina; Bunker, Andrew J.; Egami, Eiichi; Daniel J. Eisenstein; et al. (arXiv e-prints, 2023)
Understanding the co-evolution of supermassive black holes (SMBHs) and their host systems requires a comprehensive census of active galactic nuclei (AGN) behavior across a wide range of redshift, luminosity, obscuration level and galaxy properties. We report significant progress with JWST towards this goal from the Systematic Mid-infrared Instrument Legacy Extragalactic Survey (SMILES). Based on comprehensive SED analysis of 3273 MIRI-detected sources, we identify 217 AGN candidates over a survey area of $\sim$34 arcmin$^2$, including a primary sample of 111 AGNs in normal massive galaxies ($M_{*}>10^{9.5}~M_\odot$) at $z\sim$0--4, an extended sample of 86 AGN {\it candidates} in low-mass galaxies ($M_{*}<10^{9.5}~M_\odot$) and a high-$z$ sample of 20 AGN {\it candidates} at $z\sim$4--8.4. Notably, about 80% of our MIRI-selected AGN candidates are new discoveries despite the extensive pre-JWST AGN searches. Even among the massive galaxies where the previous AGN search is believed to be thorough, 34% of the MIRI AGN identifications are new, highlighting the impact of obscuration on previous selections. By combining our results with the efforts at other wavelengths, we build the most complete AGN sample to date and examine the relative performance of different selection techniques. We find the obscured AGN fraction increases from $L_{\rm AGN, bol}\sim10^{10}~L_\odot$ to $10^{11}~L_\odot$ and then drops towards higher luminosity. Additionally, the obscured AGN fraction gradually increases from $z\sim0$ to $z\sim4$ with most high-$z$ AGNs obscured. We discuss how AGN obscuration, intrinsic SED variations, galaxy contamination, survey depth and selection techniques complicate the construction of a complete AGN sample.
Keywords: Nongalactic Astrophysics

Astrometric Calibration and Performance of the Dark Energy Spectroscopic Instrument Focal Plane - Kent, S.; Neilsen, E.; Honscheid, K.; Rabinowitz, D.; Schlafly, E. F.; Guy, J.; Schlegel, D.; García-Bellido, J.; Li, T. S.; Sanchez, E.; Silber, J.; Aguilar, J.; et al. (The Astronomical Journal, 2023)
The Dark Energy Spectroscopic Instrument, consisting of 5020 robotic fiber positioners and associated systems on the Mayall telescope at Kitt Peak, Arizona, is carrying out a survey to measure the spectra of 40 million galaxies and quasars and produce the largest 3D map of the universe to date. The primary science goal is to use baryon acoustic oscillations to measure the expansion history of the universe and the time evolution of dark energy. A key function of the online control system is to position each fiber on a particular target in the focal plane with an accuracy of 11 μm rms 2D. This paper describes the set of software programs used to perform this function along with the methods used to validate their performance.
Keywords: 1800; 2179; Astrophysics - Instrumentation and Methods for Astrophysics

Brown Dwarf Candidates in the JADES and CEERS Extragalactic Surveys - Hainline, Kevin N.; Helton, Jakob M.; Johnson, Benjamin D.; Sun, Fengwu; Topping, Michael W.; Leisenring, Jarron M.; Baker, William M.; Daniel J. Eisenstein; Hausen, Ryan; Hviding, Raphael E.; Lyu, Jianwei; Robertson, Brant; et al. (arXiv e-prints, 2023)
By combining the JWST/NIRCam JADES and CEERS extragalactic datasets, we have uncovered a sample of twenty-one T and Y brown dwarf candidates at best-fit distances between 0.1 - 4.2 kpc. These sources were selected by targeting the blue 1$μ$m - 2.5$μ$m colors and red 3$μ$m - 4.5$μ$m colors that arise from molecular absorption in the atmospheres of T$_{eff} < $ 1300K brown dwarfs. We fit these sources using multiple models of low-mass stellar atmospheres and present the resulting fluxes, sizes, effective temperatures and other derived properties for the sample. If confirmed, these fits place the majority of the sources in the Milky Way thick disk and halo. We observe proper motion for seven of the candidate brown dwarfs with directions in agreement with the plane of our galaxy, providing evidence that they are not extragalactic in nature. We demonstrate how the colors of these sources differ from selected high-redshift galaxies, and explore the selection of these sources in planned large-area JWST NIRCam surveys. Deep imaging with JWST/NIRCam presents an an excellent opportunity for finding and understanding these very cold low-mass stars at kpc distances.
Keywords: Astrophysics of Galaxies

Building the First Galaxies -- Chapter 2. Starbursts Dominate The Star Formation Histories of 6 < z - Dressler, Alan; Rieke, Marcia; Eisenstein, Daniel; Stark, Daniel P.; Burns, Chris; Bhatawdekar, Rachana; Bonaventura, Nina; Boyett, Kristan; Bunker, Andrew J.; Carniani, Stefano; Charlot, Stephane; Hausen, Ryan; et al. (arXiv e-prints, 2023)
We use SEDz* -- a code designed to chart star formation histories (SFHs) of 6<z<12 galaxies -- to analyze the SEDs of 894 galaxies with deep JWST/NIRCam imaging by JADES in the GOODS-S field. We show how SEDz* matches observed SEDs using stellar-population templates, graphing the contribution of each epoch-by-epoch to confirm the robustness of the technique. Very good SED fits for most SFHs demonstrates the compatibility of the templates with stars in the first galaxies -- as expected, because their light is primarily from main-sequence A-stars, free of post-main-sequence complexity and insensitive to heavy-element compositions. We confirm earlier results from Dressler(2023): (1) Four types of star formation histories: SFH1 -- burst; SFH2 -- stochastic; SFH3 -- `contiguous' (3-epochs); and SFH4 -- `continuous' (4-6 epochs); (2) Starbursts -- both single and multiple -- are predominate (~70%) in this critical period of cosmic history, although longer SFHs (0.5-1.0 Gyr) contribute one-third of the accumulated stellar mass. These 894 SFHs contribute log M/Msun = 11.14, 11.09, 11.00, and 10.60 for SFH1-4, respectively, adding up to 4x10^11 Msun by z=6 for this field. We suggest that the absence of rising SFHs could be explained as an intense dust-enshrouded phase of star formation lasting tens of Myr that preceded each of the SFHs we measure. We find no strong dependencies of SFH type with the large-scale environment, however, the discovery of a compact group of 30 galaxies, 11 of which had first star formation at z=11-12, suggests that long SFHs could dominate in rare, dense environments.
Keywords: Astrophysics - Astrophysics of Galaxies

Carbonaceous dust grains seen in the first billion years of cosmic time - Witstok, Joris; Shivaei, Irene; Smit, Renske; Maiolino, Roberto; Carniani, Stefano; Curtis-Lake, Emma; Ferruit, Pierre; Arribas, Santiago; Bunker, Andrew J.; Cameron, Alex J.; Charlot, Stephane; Chevallard, Jacopo; et al. (Nature, 2023)
Large dust reservoirs (up to approximately 108 M⊙) have been detected1-3 in galaxies out to redshift z ≃ 8, when the age of the Universe was only about 600 Myr. Generating substantial amounts of dust within such a short timescale has proven challenging for theories of dust formation4,5 and has prompted the revision of the modelling of potential sites of dust production6-8, such as the atmospheres of asymptotic giant branch stars in low-metallicity environments, supernova ejecta and the accelerated growth of grains in the interstellar medium. However, degeneracies between different evolutionary pathways remain when the total dust mass of galaxies is the only available observable. Here we report observations of the 2,175 Å dust attenuation feature, which is well known in the Milky Way and galaxies at z ≲ 3 (refs. 9-11), in the near-infrared spectra of galaxies up to z ≃ 7, corresponding to the first billion years of cosmic time. The relatively short timescale implied for the formation of carbonaceous grains giving rise to this feature12 suggests a rapid production process, possibly in Wolf-Rayet stars or supernova ejecta.
Keywords: Astrophysics - Astrophysics of Galaxies

Constraining accuracy of the pairwise velocities in N-body simulations using scale-free models - Maleubre, Sara; Daniel J. Eisenstein; Garrison, Lehman H.; Joyce, Michael (Monthly Notices of the Royal Astronomical Society, 2023)
We present a continuation of an analysis that aims to quantify resolution of N-body simulations by exploiting large (up to N = 40963) simulations of scale-free cosmologies run using ABACUS. Here, we focus on radial pairwise velocities of the matter field, both by direct estimation and through the cumulative two-point correlation function (using the pair conservation equation). We find that convergence at the 1 per cent level of the mean relative pairwise velocity can be demonstrated over a range of scales, evolving from a few times the grid spacing at early times to slightly below this scale at late times. We show the analysis of two different box sizes as well as from averaging results from the smaller boxes, and compare the power of the two aforementioned estimators in constraining accuracy at each scale. Down to scales of the order of the smoothing parameter, convergence is obtained at ~$5~{{\rm per\, cent}}$ precision, and shows a behaviour indicating asymptotic stable clustering. We also infer for LCDM simulations conservative estimates on the evolution of the lower cut-off to resolution (at 1 and 5 per cent precision) as a function of redshift.
Keywords: Cosmology and Nongalactic Astrophysics

Cosmological constraints from density-split clustering in the BOSS CMASS galaxy sample - Paillas, Enrique; Cuesta-Lazaro, Carolina; Will J. Percival; Nadathur, Seshadri; Cai, Yan-Chuan; Sihan Yuan; Beutler, Florian; de Mattia, Arnaud; Eisenstein, Daniel; Forero-Sanchez, Daniel; Padilla, Nelson; Pinon, Mathilde; et al. (arXiv e-prints, 2023)
We present a clustering analysis of the BOSS DR12 CMASS galaxy sample, combining measurements of the galaxy two-point correlation function and density-split clustering down to a scale of $1\,h^{-1}{\rm Mpc}$. Our theoretical framework is based on emulators trained on high-fidelity mock galaxy catalogues that forward model the cosmological dependence of the clustering statistics within an extended-$Λ$CDM framework, including redshift-space and Alcock-Paczynski distortions. Our base-$Λ$CDM analysis finds $ω_{\rm cdm} = 0.1201± 0.0022$, $σ_8 = 0.792± 0.034$, and $n_s = 0.970± 0.018$, corresponding to $fσ_8 = 0.462± 0.020$ at $z ≈ 0.525$, which is in agreement with Planck 2018 predictions and various clustering studies in the literature. We test single-parameter extensions to base-$Λ$CDM, varying the running of the spectral index, the dark energy equation of state, and the density of massless relic neutrinos, finding no compelling evidence for deviations from the base model. We model the galaxy-halo connection using a halo occupation distribution framework, finding signatures of environment-based assembly bias in the data. We validate our pipeline against mock catalogues that match the clustering and selection properties of CMASS, showing that we can recover unbiased cosmological constraints even with a volume 84 times larger than the one used in this study.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

The Cosmos in its Infancy: JADES Galaxy Candidates at z > 8 in GOODS-S and GOODS-N - Hainline, Kevin N.; Johnson, Benjamin D.; Robertson, Brant; Tacchella, Sandro; Helton, Jakob M.; Sun, Fengwu; Daniel J. Eisenstein; Simmonds, Charlotte; Topping, Michael W.; Whitler, Lily; Willmer, Christopher N. A.; Rieke, Marcia; et al. (arXiv e-prints, 2023)
We present a catalog of 717 candidate galaxies at $z > 8$ selected from 125 square arcminutes of NIRCam imaging as part of the JWST Advanced Deep Extragalactic Survey (JADES). We combine the full JADES imaging dataset with data from the JEMS and FRESCO JWST surveys along with extremely deep existing observations from HST/ACS for a final filter set that includes fifteen JWST/NIRCam filters and five HST/ACS filters. The high-redshift galaxy candidates were selected from their estimated photometric redshifts calculated using a template fitting approach, followed by visual inspection from seven independent reviewers. We explore these candidates in detail, highlighting interesting resolved or extended sources, sources with very red long-wavelength slopes, and our highest redshift candidates, which extend to $z_{phot} = 18$. We also investigate potential contamination by stellar objects, and do not find strong evidence from SED fitting that these faint high-redshift galaxy candidates are low-mass stars. Over 93% of the sources are newly identified from our deep JADES imaging, including 31 new galaxy candidates at $z_{phot} > 12$. Using 42 sources in our sample with measured spectroscopic redshifts from NIRSpec and FRESCO, we find excellent agreement to our photometric redshift estimates, with no catastrophic outliers and an average difference of $\langle Δ z = z_{phot}- z_{spec} \rangle= 0.26$. These sources comprise one of the most robust samples for probing the early buildup of galaxies within the first few hundred million years of the Universe's history.
Keywords: Astrophysics - Astrophysics of Galaxies

The DESI Bright Galaxy Survey: Final Target Selection, Design, and Validation - Hahn, ChangHoon; Wilson, Michael J.; Ruiz-Macias, Omar; Cole, Shaun; Weinberg, David H.; Moustakas, John; Kremin, Anthony; Tinker, Jeremy L.; Smith, Alex; Wechsler, Risa H.; Ahlen, Steven; Alam, Shadab; et al. (The Astronomical Journal, 2023)
Over the next 5 yr, the Dark Energy Spectroscopic Instrument (DESI) will use 10 spectrographs with 5000 fibers on the 4 m Mayall Telescope at Kitt Peak National Observatory to conduct the first Stage IV dark energy galaxy survey. At z < 0.6, the DESI Bright Galaxy Survey (BGS) will produce the most detailed map of the universe during the dark-energy-dominated epoch with redshifts of >10 million galaxies spanning 14,000 deg2. In this work, we present and validate the final BGS target selection and survey design. From the Legacy Surveys, BGS will target an r < 19.5 mag limited sample (BGS Bright), a fainter 19.5 < r < 20.175 color-selected sample (BGS Faint), and a smaller low-z quasar sample. BGS will observe these targets using exposure times scaled to achieve homogeneous completeness and cover the footprint three times. We use observations from the Survey Validation programs conducted prior to the main survey along with simulations to show that BGS can complete its strategy and make optimal use of "bright" time. BGS targets have stellar contamination <1%, and their densities do not depend strongly on imaging properties. BGS Bright will achieve >80% fiber assignment efficiency. Finally, BGS Bright and BGS Faint will achieve >95% redshift success over any observing condition. BGS meets the requirements for an extensive range of scientific applications. BGS will yield the most precise baryon acoustic oscillation and redshift-space distortion measurements at z < 0.4. It presents opportunities for new methods that require highly complete and dense samples (e.g., N-point statistics, multitracers). BGS further provides a powerful tool to study galaxy populations and the relations between galaxies and dark matter.
Keywords: Galaxies

The DESI One-Percent survey: exploring the Halo Occupation Distribution of Emission Line Galaxies with ABACUSSUMMIT simulations - Rocher, Antoine; Ruhlmann-Kleider, Vanina; Burtin, Etienne; Sihan Yuan; de Mattia, Arnaud; Ashley J. Ross; Aguilar, Jessica; Ahlen, Steven; Alam, Shadab; Bianchi, Davide; David Brooks; Cole, Shaun; et al. (Journal of Cosmology and Astroparticle Physics, 2023)
The One-Percent survey of the Dark Energy Spectroscopic Instrument collected ~ 270k emission line galaxies (ELGs) at 0.8 < z < 1.6. The high completeness of the sample allowed the clustering to be measured down to scales never probed before, 0.04 Mpc/h in rp for the projected 2-point correlation function (2PCF) and 0.17 Mpc/h in galaxy pair separation s for the 2PCF monopole and quadrupole. The most striking feature of the measurements is a strong signal at the smallest scales, below 0.2 Mpc/h in rp and 1 Mpc/h in s. We analyse these data in the halo occupation distribution framework. We consider different distributions for central galaxies, a standard power law for satellites with no condition on the presence of a central galaxy and explore several extensions of these models. For all considered models, the mean halo mass of the sample is found to be log10 ⟨Mh ⟩ ~ 11.9. We obtain a satellite mean occupation function which agrees with physically motivated ELG models only if we introduce central-satellite conformity, meaning that the satellite occupation is conditioned by the presence of central galaxies of the same type. To achieve in addition a good modelling of the clustering between 0.1 and 1 Mpc/h in rp , we allow for ELG positioning outside of the halo virial radius and find 0.5% of ELGs residing in the outskirts of halos. Furthermore, the satellite velocity dispersion inside halos is found to be ~ 30% larger than that of the halo dark matter particles. These are the main findings of our work. We investigate assembly bias as a function of halo concentration, local density or local density anisotropies and observe no significant change in our results. We split the data sample in two redshift bins and report no significant evolution with redshift. Lastly, changing the cosmology in the modelling impacts only slightly our results.
Keywords: redshift surveys; Astrophysics - Cosmology and Nongalactic Astrophysics

Discovery of a quiescent galaxy at z=7.3 - Looser, Tobias J.; D'Eugenio, Francesco; Maiolino, Roberto; Witstok, Joris; Sandles, Lester; Curtis-Lake, Emma; Chevallard, Jacopo; Tacchella, Sandro; Johnson, Benjamin D.; Baker, William M.; Suess, Katherine A.; Carniani, Stefano; et al. (arXiv e-prints, 2023)
Local galaxies are known to broadly follow a bimodal distribution: actively star forming and quiescent systems (i.e. galaxies with no or negligible star formation activity at the epoch of observation). Why, when and how such bimodality was established, and whether it has been associated with different processes at different cosmic epochs, is still a key open question in extragalactic astrophysics. Directly observing early quiescent galaxies in the primordial Universe is therefore of utmost importance to constraining models of galaxy formation and transformation. Early quiescent galaxies have been identified out to redshift $z < 5$, and these are all found to be massive ($M_{*}>10^{10}~M_{\odot}$). Here we report the discovery of a quiescent galaxy at z$=$7.3, when the Universe was only 700 Myr old - about 5% of its current age. The JWST/NIRSpec spectrum of this galaxy from our JADES programme exhibits a complete absence of nebular emission lines, while the Balmer break and Ly$α$ drop are unambiguously detected. We infer that this galaxy experienced a short and intense burst of star formation followed by rapid quenching, about 10-20 Myr before the epoch of observation. Particularly interesting is that the mass of this quiescent galaxy is only $\sim$4-6$× 10^8~M_{\odot}$. This mass range is sensitive to various feedback mechanisms that can result in temporary or permanent quiescence. Therefore this galaxy represents a unique opportunity to learn more about galaxy formation and transformation in the early Universe.
Keywords: Astrophysics - Astrophysics of Galaxies

Earliest Galaxies in the JADES Origins Field: Luminosity Function and Cosmic Star-Formation Rate Density 300 Myr after the Big Bang - Robertson, Brant; Johnson, Benjamin D.; Tacchella, Sandro; Daniel J. Eisenstein; Hainline, Kevin; Arribas, Santiago; Baker, William M.; Bunker, Andrew J.; Carniani, Stefano; Carreira, Courtney; Cargile, Phillip A.; Charlot, Stéphane; et al. (arXiv e-prints, 2023)
We characterize the earliest galaxy population in the JADES Origins Field (JOF), the deepest imaging field observed with JWST. We make use of the ancillary Hubble optical images (5 filters spanning $0.4-0.9μm$) and novel JWST images with 14 filters spanning $0.8-5μm$, including 7 medium-band filters, and reaching total exposure times of up to 46 hours per filter. We combine all the imaging data at $>2μm$ to construct the deepest imaging ever taken at these wavelengths, reaching as deep as $≈31.4$ AB mag in the stack and 30.1-30.8 AB mag ($5σ$, $r=0.1"$ circular aperture) in individual filters. We measure photometric redshifts and use robust selection criteria to identify a sample of eight galaxy candidates at redshifts $z=11.5-15$. These objects show compact half-light radii of $R_{1/2}\sim50-200$pc, stellar masses of $M_\star\sim10^7-10^8M_\odot$, and star-formation rates of $SFR\sim0.1-1~M_\odot~yr^{-1}$. Our search finds no candidates at $15<z<20$, placing upper limits at these redshifts. We develop a forward modeling approach to infer the properties of the evolving luminosity function without binning in redshift or luminosity that marginalizes over the photometric redshift uncertainty of our candidate galaxies and incorporates the impact of non-detections. We find a $z=12$ luminosity function in good agreement with prior results, and that the luminosity function normalization and UV luminosity density decline by a factor of $\sim2.5$ from $z=12$ to $z=14$. We discuss the possible implications of our results in the context of theoretical models for evolution of the dark matter halo mass function.
Keywords: Nongalactic Astrophysics

The Early Data Release of the Dark Energy Spectroscopic Instrument - DESI Collaboration; Adame, A. G.; Aguilar, J.; Ahlen, S.; Alam, S.; Aldering, G.; Alexander, D. M.; Alfarsy, R.; Allende Prieto, C.; Alvarez, M.; Alves, O.; Anand, A.; et al. (arXiv e-prints, 2023)
The Dark Energy Spectroscopic Instrument (DESI) completed its five-month Survey Validation in May 2021. Spectra of stellar and extragalactic targets from Survey Validation constitute the first major data sample from the DESI survey. This paper describes the public release of those spectra, the catalogs of derived properties, and the intermediate data products. In total, the public release includes good-quality spectral information from 466,447 objects targeted as part of the Milky Way Survey, 428,758 as part of the Bright Galaxy Survey, 227,318 as part of the Luminous Red Galaxy sample, 437,664 as part of the Emission Line Galaxy sample, and 76,079 as part of the Quasar sample. In addition, the release includes spectral information from 137,148 objects that expand the scope beyond the primary samples as part of a series of secondary programs. Here, we describe the spectral data, data quality, data products, Large-Scale Structure science catalogs, access to the data, and references that provide relevant background to using these spectra.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

First detection of the BAO signal from early DESI data - Moon, Jeongin; Valcin, David; Rashkovetskyi, Michael; Saulder, Christoph; Aguilar, Jessica Nicole; Ahlen, Steven; Alam, Shadab; Bailey, Stephen; Baltay, Charles; Blum, Robert; David Brooks; Burtin, Etienne; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
We present the first detection of the baryon acoustic oscillations (BAOs) signal obtained using unblinded data collected during the initial 2 months of operations of the Stage-IV ground-based Dark Energy Spectroscopic Instrument (DESI). From a selected sample of 261 291 luminous red galaxies spanning the redshift interval 0.4 < z < 1.1 and covering 1651 square degrees with a 57.9 per cent completeness level, we report a ~5σ level BAO detection and the measurement of the BAO location at a precision of 1.7 per cent. Using a bright galaxy sample of 109 523 galaxies in the redshift range 0.1 < z < 0.5, over 3677 square degrees with a 50.0 per cent completeness, we also detect the BAO feature at ~3σ significance with a 2.6 per cent precision. These first BAO measurements represent an important milestone, acting as a quality control on the optimal performance of the complex robotically actuated, fibre-fed DESI spectrograph, as well as an early validation of the DESI spectroscopic pipeline and data management system. Based on these first promising results, we forecast that DESI is on target to achieve a high-significance BAO detection at sub-per cent precision with the completed 5-yr survey data, meeting the top-level science requirements on BAO measurements. This exquisite level of precision will set new standards in cosmology and confirm DESI as the most competitive BAO experiment for the remainder of this decade.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

First Sample of Hα+[O III]λ5007 Line Emitters at z > 6 Through JWST/NIRCam Slitless Spectroscopy: Physical Properties and Line-luminosity Functions - Sun, Fengwu; Egami, Eiichi; Pirzkal, Nor; Rieke, Marcia; Baum, Stefi; Boyer, Martha; Boyett, Kristan; Bunker, Andrew J.; Cameron, Alex J.; Curti, Mirko; Daniel J. Eisenstein; Gennaro, Mario; et al. (The Astrophysical Journal, 2023)
We present a sample of four emission-line galaxies at z = 6.11-6.35 that were serendipitously discovered using the commissioning data for the James Webb Space Telescope (JWST)/NIRCam wide-field slitless spectroscopy mode. One of them (at z = 6.11) has been reported previously, while the others are new discoveries. These sources are selected by the secure detections of both [O III] λ5007 and Hα lines with other fainter lines, which were tentatively detected in some cases (e.g., [O II] λ3727, [O III] λ4959). In the [O III]/Hβ-[N II]/Hα Baldwin-Phillips-Terlevich diagram, these galaxies occupy the same parameter space as that of z ~ 2 star-forming galaxies, indicating that they have been enriched rapidly to subsolar metallicities (~0.4 Z ⊙), similar to galaxies with comparable stellar masses at much lower redshifts. The detection of strong Hα lines suggests a higher ionizing photon production efficiency within galaxies in the early universe. We find brightening of the [O III] λ5007 line-luminosity function (LF) from z = 3 to 6, and weak or no redshift evolution of the Hα line LF from z = 2 to 6. Both LFs are underpredicted at z ~ 6 by a factor of ~10 in certain cosmological simulations. This further indicates a global Lyα photon escape fraction of 7%-10% at z ~ 6, which is slightly lower than previous estimates through the comparison of the UV-derived star formation rate density and Lyα luminosity density. Our sample recovers ${66}_{-44}^{+128}$ % of z = 6.0-6.6 galaxies in the survey volume with stellar masses greater than 5 × 108 M ⊙, suggesting the ubiquity of strong Hα and [O III] line emitters in the Epoch of Reionization, which will be further uncovered in the era of JWST.
Keywords: 1570; 2171; Astrophysics - Astrophysics of Galaxies

FRESCO: An extended, massive, rapidly rotating galaxy at z=5.3 - Nelson, Erica J.; Brammer, Gabriel; Gimenez-Arteaga, Clara; Oesch, Pascal A.; Ubler, Hannah; de Graaff, Anna; Matharu, Jasleen; Naidu, Rohan P.; Shapley, Alice E.; Whitaker, Katherine E.; Wisnioski, Emily; Forster Schreiber, Natascha M.; et al. (arXiv e-prints, 2023)
With the remarkable sensitivity and resolution of JWST in the infrared, measuring rest-optical kinematics of galaxies at $z>5$ has become possible for the first time. This study pilots a new method for measuring galaxy dynamics for highly multiplexed, unbiased samples by combining FRESCO NIRCam grism spectroscopy and JADES medium-band imaging. Here we present one of the first JWST kinematic measurements for a galaxy at $z>5$. We find a significant velocity gradient, which, if interpreted as rotation yields $V_{rot} = 240±50$km/s and we hence refer to this galaxy as Twister-z5. With a rest-frame optical effective radius of $r_e=2.25$kpc, the high rotation velocity in this galaxy is not due to a compact size as may be expected in the early universe but rather a high total mass, ${\rm log(M}_{dyn}/{\rm M}_\odot)=11.0±0.2$. This is a factor of roughly 4x higher than the stellar mass within the effective radius. We also observe that the radial H$α$ equivalent width profile and the specific star formation rate map from resolved stellar population modeling is centrally depressed by a factor of $\sim1.5$ from the center to $r_e$. Combined with the morphology of the line-emitting gas in comparison to the continuum, this centrally suppressed star formation is consistent with a star-forming disk surrounding a bulge growing inside-out. While large, rapidly rotating disks are common to z~2, the existence of one after only 1Gyr of cosmic time, shown for the first time in ionized gas, adds to the growing evidence that some galaxies matured earlier than expected in the history of the universe.
Keywords: Astrophysics - Astrophysics of Galaxies

The galaxies missed by Hubble and ALMA: the contribution of extremely red galaxies to the cosmic census at 3 - Williams, Christina C.; Alberts, Stacey; Ji, Zhiyuan; Hainline, Kevin N.; Lyu, Jianwei; Rieke, George; Endsley, Ryan; Suess, Katherine A.; Johnson, Benjamin D.; Florian, Michael; Shivaei, Irene; Rujopakarn, Wiphu; et al. (arXiv e-prints, 2023)
Using deep JWST imaging from JADES, JEMS and SMILES, we characterize optically-faint and extremely red galaxies at $z>3$ that were previously missing from galaxy census estimates. The data indicate the existence of abundant, dusty and post-starburst-like galaxies down to $10^8$M$_\odot$, below the sensitivity limit of Spitzer and ALMA. Modeling the NIRCam and HST photometry of these red sources can result in extreme, high values for both stellar mass and star formation rate (SFR); however, including 7 MIRI filters out to 21$μ$m results in decreased mass (median 0.6 dex for log$_{10}$M$^*$/M$_{\odot}>$10), and SFR (median 10$×$ for SFR$>$100 M$_{\odot}$/yr). At $z>6$, our sample includes a high fraction of little red dots (LRDs; NIRCam-selected dust-reddened AGN candidates). We significantly measure older stellar populations in the LRDs out to rest-frame 3$μ$m (the stellar bump) and rule out a dominant contribution from hot dust emission, a signature of AGN contamination to stellar population measurements. This allows us to measure their contribution to the cosmic census at $z>3$, below the typical detection limits of ALMA ($L_{\rm IR}<10^{12}L_\odot$). We find that these sources, which are overwhelmingly missed by HST and ALMA, could effectively double the obscured fraction of the star formation rate density at $4<z<6$ compared to some estimates, showing that prior to JWST, the obscured contribution from fainter sources could be underestimated. Finally, we identify five sources with evidence for Balmer breaks and high stellar masses at $5.5<z<7.7$. While spectroscopy is required to determine their nature, we discuss possible measurement systematics to explore with future data.
Keywords: Astrophysics - Astrophysics of Galaxies

GN-z11: The environment of an AGN at $z=$10.603 - Scholtz, Jan; Witten, Callum; Laporte, Nicolas; Ubler, Hannah; Perna, Michele; Maiolino, Roberto; Arribas, Santiago; Baker, William; Bennett, Jake; D'Eugenio, Francesco; Tacchella, Sandro; Witstok, Joris; et al. (arXiv e-prints, 2023)
Recent observations with the James Webb Space Telescope (JWST) have further refined the spectroscopic redshift of GN-z11, one of the most distant galaxies identified with the Hubble Space Telescope (HST) at $z=10.603$. The presence of extremely dense gas ($>10^{10}$ cm$^{-3}$), the detection of high-ionisation lines and of CII*1335 emission, as well as the presence of an ionisation cone, indicate that GN-z11 also hosts an Active Galactic Nucleus (AGN). Further photometric and spectroscopic follow-up demonstrates that it lies in a large-scale, overdense structure with possible signatures of Population III (PopIII) stars in its halo. Surprisingly, Ly$α$ has also been detected despite the expected largely neutral inter-galactic medium at such a redshift. We exploit recent JWST/NIRSpec IFU observations to demonstrate that the Ly$α$ emission in GN-z11 is part of an extended halo with a minimum size of 0.8--3.2 kpc, depending on the definition used to derive the halo size. The surface brightness of the Ly$α$ halo around GN-z11 appears consistent with Ly$α$ halos observed around $z\sim6$ quasars. At the wavelength of Ly$α$ at $z\sim$10.6, we identify three other emission line candidates within the IFU Field-of-View with no UV rest-frame counterpart visible in deep images from the JWST/NIRCam. If confirmed, this could be the first evidence that the local region of GN-z11 represents a candidate protocluster core, forming just 400 Myr after the Big Bang. We give a first estimate of the dark matter halo mass of this structure ($M_h$=2.96$^{+0.44}_{-0.39} ×$10$^{10}$ M$_{\odot}$), consistent with a Coma-like cluster progenitor.
Keywords: Astrophysics - Astrophysics of Galaxies

Identification and properties of intense star-forming galaxies at redshifts z > 10 - Robertson, B. E.; Tacchella, S.; Johnson, B. D.; Hainline, K.; Whitler, L.; Eisenstein, D. J.; Endsley, R.; Rieke, M.; Stark, D. P.; Alberts, S.; Dressler, A.; Egami, E.; et al. (Nature Astronomy, 2023)
Surveys with the James Webb Space Telescope (JWST) have discovered candidate galaxies in the first 400 Myr of cosmic time. Preliminary indications have suggested these candidate galaxies may be more massive and abundant than previously thought. However, without confirmed distances, their inferred properties remain uncertain. Here we identify four galaxies located in the JWST Advanced Deep Extragalactic Survey Near-Infrared Camera imaging with photometric redshifts z of roughly 10-13. These galaxies include the first redshift z > 12 systems discovered with distances spectroscopically confirmed by JWST in a companion paper. Using stellar population modelling, we find the galaxies typically contain 100 million solar masses in stars, in stellar populations that are less than 100 million years old. The moderate star-formation rates and compact sizes suggest elevated star-formation rate surface densities, a key indicator of their formation pathways. Taken together, these measurements show that the first galaxies contributing to cosmic reionization formed rapidly and with intense internal radiation fields.
Keywords: Nongalactic Astrophysics

Identification of High-Redshift Galaxy Overdensities in GOODS-N and GOODS-S - Helton, Jakob M.; Sun, Fengwu; Charity Woodrum; Hainline, Kevin N.; Willmer, Christopher N. A.; Rieke, Marcia J.; Rieke, George H.; Alberts, Stacey; Daniel J. Eisenstein; Tacchella, Sandro; Robertson, Brant; Johnson, Benjamin D.; et al. (arXiv e-prints, 2023)
We conduct a systematic search for high-redshift galaxy overdensities at $4.9 < z_{\,\mathrm{spec}} < 8.9$ in both the GOODS-N and GOODS-S fields using JWST/NIRCam imaging from JADES and JEMS in addition to JWST/NIRCam wide field slitless spectroscopy from FRESCO. High-redshift galaxy candidates are identified using HST+JWST photometry spanning $\lambda = 0.4-5.0\ \mu\mathrm{m}$. We confirmed the redshifts for roughly a third of these galaxies using JWST/FRESCO spectroscopy over $\lambda = 3.9-5.0\ \mu\mathrm{m}$ through identification of either $\mathrm{H} \alpha$ or $\left[\mathrm{OIII}\right]\lambda5008$ around the best-fit photometric redshift. The rest-UV magnitudes and continuum slopes of these galaxies were inferred from the photometry: the brightest and reddest objects appear in more dense environments and thus are surrounded by more galaxy neighbors than their fainter and bluer counterparts, suggesting accelerated galaxy evolution within overdense environments. We find $17$ significant ($\delta_{\mathrm{gal}} \geq 3.04$, $N_{\mathrm{galaxies}} \geq 4$) galaxy overdensities across both fields ($7$ in GOODS-N and $10$ in GOODS-S), including the two highest redshift spectroscopically confirmed galaxy overdensities to date at $\left< z_{\mathrm{\,spec}} \right> = 7.955$ and $\left< z_{\mathrm{\,spec}} \right> = 8.222$ (representing densities around $\sim 6$ and $\sim 12$ times that of a random volume). We estimate the total halo mass of these large-scale structures to be $11.5 \leq \mathrm{log}_{10}\left(M_{\mathrm{halo}}/M_{\odot}\right) \leq 13.4$ using an empirical stellar mass to halo mass relation, which are likely underestimates as a result of incompleteness. These protocluster candidates are expected to evolve into massive galaxy clusters with $\mathrm{log}_{10}\left(M_{\mathrm{halo}}/M_{\odot}\right) rsim 14$ by $z = 0$.
Keywords: Astrophysics - Astrophysics of Galaxies

On the impact of the galaxy window function on cosmological parameter estimation - Karim, Tanveer; Rezaie, Mehdi; Singh, Sukhdeep; Eisenstein, Daniel (Monthly Notices of the Royal Astronomical Society, 2023)
One important source of systematics in galaxy redshift surveys comes from the estimation of the galaxy window function. Up until now, the impact of the uncertainty in estimating the galaxy window function on parameter inference has not been properly studied. In this paper, we show that the uncertainty and the bias in estimating the galaxy window function will be salient for ongoing and next-generation galaxy surveys using a simulation-based approach. With a specific case study of cross-correlating emission-line galaxies from the DESI Legacy Imaging Surveys and the Planck cosmic microwave background lensing map, we show that neural network-based regression approaches to modelling the window function are superior in comparison to linear regression-based models. We additionally show that the definition of the galaxy overdensity estimator can impact the overall signal-to-noise of observed power spectra. Finally, we show that the additive biases coming from the window functions can significantly bias the modes of the inferred parameters and also degrade their precision. Thus, a careful understanding of the window functions will be essential to conduct cosmological experiments.
Keywords: Cosmology and Nongalactic Astrophysics

Inside-out growth in the early Universe: a core in a vigorously star-forming disc - Baker, William M.; Tacchella, Sandro; Johnson, Benjamin D.; Nelson, Erica; Suess, Katherine A.; D'Eugenio, Francesco; Curti, Mirko; de Graaff, Anna; Ji, Zhiyuan; Maiolino, Roberto; Robertson, Brant; Scholtz, Jan; et al. (arXiv e-prints, 2023)
The physical processes that establish the morphological evolution and the structural diversity of galaxies are key unknowns in extragalactic astrophysics. Here we report the finding of the morphologically-mature galaxy JADES-GS+53.18343-27.79097, which existed within the first 700 million years of the Universe's history. This star-forming galaxy with a stellar mass of $10^{8.6}$ solar masses consists of three components, a highly-compact core with a half-light radius of 144 pc, a strongly star-forming disc with a radius of 468 pc, and a star-forming clump, which all show distinctive star-formation histories. The central stellar mass density of this galaxy is within a factor of two of the most massive present-day ellipticals, while being globally 1000 times less massive. The radial profile of the specific star-formation rate is strongly rising toward the outskirts. This evidence strongly suggests the first detection of inside-out growth of a galaxy as a proto-bulge and a star-forming disc in the Epoch of Reionization.
Keywords: Nongalactic Astrophysics

Intrinsic alignment as an RSD contaminant in the DESI survey - Lamman, Claire; Eisenstein, Daniel; Aguilar, Jessica Nicole; David Brooks; de la Macorra, Axel; Doel, Peter; Font-Ribera, Andreu; Gontcho, Satya Gontcho A.; Honscheid, Klaus; Kehoe, Robert; Kisner, Theodore; Kremin, Anthony; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
We measure the tidal alignment of the major axes of luminous red galaxies (LRGs) from the Legacy Imaging Survey and use it to infer the artificial redshift-space distortion signature that will arise from an orientation-dependent, surface-brightness selection in the Dark Energy Spectroscopic Instrument (DESI) survey. Using photometric redshifts to downweight the shape-density correlations due to weak lensing, we measure the intrinsic tidal alignment of LRGs. Separately, we estimate the net polarization of LRG orientations from DESI's fibre-magnitude target selection to be of order 10-2 along the line of sight. Using these measurements and a linear tidal model, we forecast a 0.5 per cent fractional decrease on the quadrupole of the two-point correlation function for projected separations of 40-80 h-1 Mpc. We also use a halo catalogue from the ABACUSSUMMIT cosmological simulation suite to reproduce this false quadrupole.
Keywords: Nongalactic Astrophysics

Ionised gas kinematics and dynamical masses of $zrsim6$ galaxies from JADES/NIRSpec high-resolution spectroscopy - de Graaff, Anna; Rix, Hans-Walter; Carniani, Stefano; Suess, Katherine A.; Charlot, Stéphane; Curtis-Lake, Emma; Arribas, Santiago; Baker, William M.; Boyett, Kristan; Bunker, Andrew J.; Cameron, Alex J.; Chevallard, Jacopo; et al. (arXiv e-prints, 2023)
We explore the kinematic gas properties of six $5.5<z<7.4$ galaxies in the JWST Advanced Deep Extragalactic Survey (JADES), using high-resolution JWST/NIRSpec multi-object spectroscopy of the rest-frame optical emission lines [OIII] and H$α$. The objects are small and of low stellar mass ($\sim 1\,$kpc; $M_*\sim10^{7-9}\,{\rm M_\odot}$), less massive than any galaxy studied kinematically at $z>1$ thus far. The cold gas masses implied by the observed star formation rates are $\sim 10×$ larger than the stellar masses. We find that their ionised gas is spatially resolved by JWST, with evidence for broadened lines and spatial velocity gradients. Using a simple thin-disc model, we fit these data with a novel forward modelling software that accounts for the complex geometry, point spread function, and pixellation of the NIRSpec instrument. We find the sample to include both rotation- and dispersion-dominated structures, as we detect velocity gradients of $v(r_{\rm e})≈100-150\,{\rm km\,s^{-1}}$, and find velocity dispersions of $σ_0≈ 30-70\,{\rm km\,s^{-1}}$ that are comparable to those at cosmic noon. The dynamical masses implied by these models ($M_{\rm dyn}\sim10^{9-10}\,{\rm M_\odot}$) are larger than the stellar masses by up to a factor 40, and larger than the total baryonic mass (gas + stars) by a factor of $\sim 3$. Qualitatively, this result is robust even if the observed velocity gradients reflect ongoing mergers rather than rotating discs. Unless the observed emission line kinematics is dominated by outflows, this implies that the centres of these galaxies are dark-matter dominated or that star formation is $3×$ less efficient, leading to higher inferred gas masses.
Keywords: Astrophysics - Astrophysics of Galaxies

The ionizing photon production efficiency at z 6 for Lyman-alpha emitters using JEMS and MUSE - Simmonds, C.; Tacchella, S.; Maseda, M.; Williams, C. C.; Baker, W. M.; Witten, C. E. C.; Johnson, B. D.; Robertson, B.; Saxena, A.; Sun, F.; Witstok, J.; Bhatawdekar, R.; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
We study the ionizing photon production efficiency at the end of the Epoch of Reionization (z ~ 5.4 - 6.6) for a sample of 30 Ly α emitters. This is a crucial quantity to infer the ionizing photon budget of the universe. These objects were selected to have reliable spectroscopic redshifts, assigned based on the profile of their Ly α emission line, detected in the MUSE deep fields. We exploit medium-band observations from the JWST Extragalactic Medium-band Survey (JEMS) to find the flux excess corresponding to the redshifted Hα emission line. We estimate the ultraviolet (UV) luminosity by fitting the full JEMS photometry, along with several HST photometric points, with Prospector. We find a median UV continuum slope of $β = -2.09^{+0.23}_{-0.21}$, indicating young stellar populations with little-to-no dust attenuation. Supported by this, we derive ξion,0 with no dust attenuation and find a median value of log$\frac{ξ _{ion,0}}{\text{Hz erg}^{-1}} = 25.44^{+0.21}_{-0.15}$. If we perform dust attenuation corrections and assume a Calzetti attenuation law, our values are lowered by ~0.1 dex. Our results suggest Ly α emitters at the Epoch of Reionization have slightly enhanced ξion,0 compared to previous estimations from literature, in particular, when compared to the non-Ly α emitting population. This initial study provides a promising outlook on the characterization of ionizing photon production in the early universe. In the future, a more extensive study will be performed on the entire data set provided by the JWST Advanced Deep Extragalactic Survey (JADES). Thus, for the first time, allowing us to place constraints on the wider galaxy populations driving reionization.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES: A large population of obscured, narrow line AGN at high redshift - Scholtz, Jan; Maiolino, Roberto; D'Eugenio, Francesco; Curtis-Lake, Emma; Carniani, Stefano; Charlot, Stephane; Curti, Mirko; Silcock, Maddie S.; Arribas, Santiago; Baker, William; Bhatawdekar, Rachana; Boyett, Kristan; et al. (arXiv e-prints, 2023)
We present the identification of 42 narrow-line active galactic nuclei (type-2 AGN) candidates in the two deepest observations of the JADES spectroscopic survey with JWST/NIRSpec. The spectral coverage and the depth of our observations allow us to select narrow-line AGNs based on both rest-frame optical and UV emission lines up to z=10. Due to the metallicity decrease of galaxies, at $z>3$ the standard optical diagnostic diagrams (N2-BPT or S2-VO87) become unable to distinguish many AGN from other sources of photoionisation. Therefore, we also use high ionisation lines, such as HeII$λ$4686, HeII$λ$1640, NeIV$λ$2422, NeV$λ$3420, and NV$λ$1240, also in combination with other UV transitions, to trace the presence of AGN. Out of a parent sample of 209 galaxies, we identify 42 type-2 AGN (although 10 of them are tentative), giving a fraction of galaxies in JADES hosting type-2 AGN of about $20±3$%, which does not evolve significantly in the redshift range between 2 and 10. The selected type-2 AGN have estimated bolometric luminosities of $10^{41.3-44.9}$ erg s$^{-1}$ and host-galaxy stellar masses of $10^{7.2-9.3}$ M$_{\odot}$. The star formation rates of the selected AGN host galaxies are consistent with those of the star-forming main sequence. The AGN host galaxies at z=4-6 contribute $\sim$8-30 % to the UV luminosity function, slightly increasing with UV luminosity.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES: Balmer Decrement Measurements at redshifts 4 < z < 7 - Sandles, Lester; D'Eugenio, Francesco; Maiolino, Roberto; Looser, Tobias J.; Arribas, Santiago; Baker, William M.; Bonaventura, Nina; Bunker, Andrew J.; Cameron, Alex J.; Carniani, Stefano; Charlot, Stephane; Chevallard, Jacopo; et al. (arXiv e-prints, 2023)
We present Balmer decrement H$α$/ H$β$ measurements for a sample of 51 galaxies at redshifts z = 4-7 observed with the JWST/NIRSpec MSA, as part of the JADES survey. Leveraging 28-hour long exposures and the efficiency of the prism/clear configuration (but also using information from the medium-resolution gratings), we are able to probe directly the low-mass end of the galaxy population, reaching stellar masses Mstar as low as 10^7 Msun . We find that the correlation between Balmer decrement and Mstar is already established at these high redshifts, indicating a rapid build up of dust in moderately massive galaxies at such early epochs. The lowest-mass galaxies in our sample (Mstar = 1-3 x 10^7 Msun ) display a remarkably low Balmer decrement of 2.88 $±$ 0.08, consistent with case B, suggesting very little dust content. However, we warn that such a low observed Balmer decrement may also partly be a consequence of an intrinsically lower H$α$/ H$β$, resulting from the extreme conditions of the ionized gas in these primeval and unevolved systems. We further compare the Balmer decrement to continuum-derived star-formation rates (SFR), finding tentative evidence of a correlation, which likely traces the underlying connection between SFR and mass of cold gas. However, we note that larger samples are required to distinguish between direct and primary correlations from indirect and secondary dependencies at such high redshifts.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES: Carbon enrichment 350 Myr after the Big Bang in a gas-rich galaxy - D'Eugenio, Francesco; Maiolino, Roberto; Carniani, Stefano; Curtis-Lake, Emma; Witstok, Joris; Chevallard, Jacopo; Charlot, Stephane; Baker, William M.; Arribas, Santiago; Boyett, Kristan; Bunker, Andrew J.; Curti, Mirko; et al. (arXiv e-prints, 2023)
Finding the emergence of the first generation of metals in the early Universe, and identifying their origin, are some of the most important goals of modern astrophysics. We present deep JWST/NIRSpec spectroscopy of GS-z12, a galaxy at z=12.5, in which we report the detection of C III]${λ}{λ}$1907,1909 nebular emission. This is the most distant detection of a metal transition and the most distant redshift determination via emission lines. In addition, we report tentative detections of [O II]${λ}{λ}$3726,3729 and [Ne III]${λ}$3869, and possibly O III]${λ}{λ}$1661,1666. By using the accurate redshift from C III], we can model the Ly${α}$ drop to reliably measure an absorbing column density of hydrogen of $N_{HI} ≈ 10^{22}$ cm$^{-2}$ - too high for an IGM origin and implying abundant ISM in GS-z12 or CGM around it. We infer a lower limit for the neutral gas mass of about $10^7$ MSun which, compared with a stellar mass of $≈4 × 10^7$ MSun inferred from the continuum fitting, implies a gas fraction higher than about 0.1-0.5. We derive a solar or even super-solar carbon-to-oxygen ratio, tentatively [C/O]>0.15. This is higher than the C/O measured in galaxies discovered by JWST at z=6-9, and higher than the C/O arising from Type-II supernovae enrichment, while AGB stars cannot contribute to carbon enrichment at these early epochs and low metallicities. Such a high C/O in a galaxy observed 350 Myr after the Big Bang may be explained by the yields of extremely metal poor stars, and may even be the heritage of the first generation of supernovae from Population III progenitors.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES: deep spectroscopy of a low-mass galaxy at redshift 2.3 quenched by environment - Sandles, Lester; D'Eugenio, Francesco; Helton, Jakob M.; Maiolino, Roberto; Hainline, Kevin; Baker, William M.; Williams, Christina C.; Alberts, Stacey; Bunker, Andrew J.; Carniani, Stefano; Charlot, Stephane; Chevallard, Jacopo; et al. (arXiv e-prints, 2023)
We report the discovery of a quiescent galaxy at $z=2.34$ with a stellar mass of only $M_\star = 9.5^{+1.8}_{-1.2} × 10^{8} M_\odot$, based on deep JWST/NIRSpec spectroscopy. This is the least massive quiescent galaxy found so far at high redshift. We use a Bayesian approach to model the spectrum and photometry, and find the target to have been quiescent for 0.6 Gyr with a mass-weighted average stellar age of 0.8-1.7 Gyr (dominated by systematics). The galaxy displays an inverse colour gradient with radius, consistent with environment-driven quenching. Based on a combination of spectroscopic and robust (medium- and broad-band) photometric redshifts, we identify a galaxy overdensity near the location of the target (5-$σ$ above the background level at this redshift). We stress that had we been specifically targetting galaxies within overdensities, the main target would not have been selected on photometry alone; therefore, environment studies based on photometric redshifts are biased against low-mass quiescent galaxies. The overdensity contains three spectroscopically confirmed, massive, old galaxies ($M_\star = 8-17 × 10^{10} M_\odot$). The presence of these evolved systems points to accelerated galaxy evolution in overdensities at redshifts z > 2, in agreement with previous works. In projection, our target lies only 35 pkpc away from the most massive galaxy in this overdensity (spectroscopic redshift z = 2.349) which is located close to overdensity's centre. This suggests the low-mass galaxy was quenched by environment, making it possibly the earliest evidence for environment-driven quenching to date.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES: Detecting [OIII]$λ 4363$ Emitters and Testing Strong Line Calibrations in the High-$z$ Universe with Ultra-deep JWST/NIRSpec Spectroscopy up to $z \sim 9.5$ - Laseter, Isaac H.; Maseda, Michael V.; Curti, Mirko; Maiolino, Roberto; D'Eugenio, Francesco; Cameron, Alex J.; Looser, Tobias J.; Arribas, Santiago; Baker, William M.; Bhatawdekar, Rachana; Boyett, Kristan; Bunker, Andrew J.; et al. (arXiv e-prints, 2023)
We present 10 novel [OIII]$λ 4363$ auroral line detections up to $z\sim 9.5$ measured from ultra-deep JWST/NIRSpec MSA spectroscopy from the JWST Advanced Deep Extragalactic Survey (JADES). We leverage the deepest spectroscopic observations yet taken with NIRSpec to determine electron temperatures and oxygen abundances using the direct T$_e$ method. We directly compare against a suite of locally calibrated strong-line diagnostics and recent high-$z$ calibrations. We find the calibrations fail to simultaneously match our JADES sample, thus warranting a self-consistent revision of these calibrations for the high-$z$ Universe. We find weak dependence between R2 and O3O2 with metallicity, thus suggesting these line-ratios are ineffective in the high-$z$ Universe as metallicity diagnostics and degeneracy breakers. We find R3 and R23 still correlate with metallicity, but we find tentative flattening of these diagnostics, thus suggesting future difficulties when applying these strong-line ratios as metallicity indicators in the high-$z$ Universe. We also propose and test an alternative diagnostic based on a different combination of R3 and R2 with a higher dynamic range. We find a reasonably good agreement (median offset of 0.002 dex, median absolute offset of 0.13 dex) with the JWST sample at low metallicity. Our sample demonstrates higher ionization/excitation ratios than local galaxies with rest-frame EWs(H$β$) $≈ 200 -300$ Angstroms. However, we find the median rest-frame EWs(H$β$) of our sample to be $\sim 2\text{x}$ less than the galaxies used for the local calibrations. This EW discrepancy combined with the high ionization of our galaxies does not present a clear description of [OIII]$λ 4363$ production in the high-$z$ Universe, thus warranting a much deeper examination into the factors affecting production.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES: Differing assembly histories of galaxies -- Observational evidence for bursty SFHs and (mini-)quenching in the first billion years of the Universe - Looser, Tobias J.; D'Eugenio, Francesco; Maiolino, Roberto; Tacchella, Sandro; Curti, Mirko; Arribas, Santiago; Baker, William M.; Baum, Stefi; Bonaventura, Nina; Boyett, Kristan; Bunker, Andrew J.; Carniani, Stefano; et al. (arXiv e-prints, 2023)
We use deep NIRSpec spectroscopic data from the JADES survey to derive the star formation histories (SFHs) of a sample of 200 galaxies at 0.6$<$z$<$11 and spanning stellar masses from $\rm 10^6$ to $\rm 10^{9.5}~M_\odot$. We find that galaxies at high-redshift, galaxies above the Main Sequence (MS) and low-mass galaxies tend to host younger stellar populations than their low-redshift, massive, and below the MS counterparts. Interestingly, the correlation between age, M$_*$ and SFR existed even earlier than Cosmic Noon, out to the earliest cosmic epochs. However, these trends have a large scatter. Indeed, there are examples of young stellar populations also below the MS, indicating recent (bursty) star formation in evolved systems. We explore further the burstiness of the SFHs by using the ratio between SFR averaged over the last 10 Myr and averaged between 10 Myr and 100 Myr before the epoch of observation ($\mathrm{SFR_{cont, 10}/SFR_{cont, 90}}$). We find that high-redshift and low-mass galaxies have particularly bursty SFHs, while more massive and lower-redshift systems evolve more steadily. We also present the discovery of another (mini-)quenched galaxy at z = 4.4 (in addition to the one at z=7.3 reported by Looser et al. 2023), which might be only temporarily quiescent as a consequence of the extremely bursty evolution. Finally, we also find a steady decline of dust reddening of the stellar population approaching the earliest cosmic epochs, although some dust reddening is still observed in some of the highest redshift and most star forming systems.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES: Discovery of extremely high equivalent width Lyman-α emission from a faint galaxy within an ionized bubble at z = 7.3 - Saxena, Aayush; Robertson, Brant E.; Bunker, Andrew J.; Endsley, Ryan; Cameron, Alex J.; Charlot, Stephane; Simmonds, Charlotte; Tacchella, Sandro; Witstok, Joris; Willott, Chris; Carniani, Stefano; Curtis-Lake, Emma; et al. (Astronomy and Astrophysics, 2023)
We report the discovery of a remarkable Lyα emitting galaxy at z = 7.2782, JADES-GS+53.16746−27.7720 (shortened to JADES-GS-z7-LA), with rest-frame equivalent width, EW0(Lyα) = 388.0 ± 88.8 Å and UV magnitude −17.0. The spectroscopic redshift is confirmed via rest-frame optical lines [O II], Hβ and [O III] in its JWST/NIRSpec Micro-Shutter Assembly (MSA) spectrum. The Lyα line is detected in both lower resolution (R ∼ 100) PRISM as well as medium resolution (R ∼ 1000) G140M grating spectra. The line spread function-deconvolved Lyα full width at half maximum in the grating is 383.9 ± 56.2 km s−1 and the Lyα velocity offset compared to the systemic redshift is 113.3 ± 80.0 km s−1, indicative of very little neutral gas or dust within the galaxy. We estimate the Lyα escape fraction to be > 70%. JADES-GS-z7-LA has a [O III]/[O II] ratio (O32) of 11.1 ± 2.2 and a ([O III] + [O II])/Hβ ratio (R23) of 11.2 ± 2.6, consistent with low metallicity and high ionization parameters. Deep NIRCam imaging also revealed a close companion source (separated by 0.23″), which exhibits similar photometry to that of JADES-GS-z7-LA, with a photometric excess in the F410M NIRCam image consistent with [O III] + Hβ emission at the same redshift. The spectral energy distribution of JADES-GS-z7-LA indicates a "bursty" star formation history, with a low stellar mass of ≈107 M⊙. Assuming that the Lyα transmission through the intergalactic medium is the same as its measured escape fraction, an ionized region of size > 1.5 pMpc is needed to explain the high Lyα EW and low velocity offset compared to systemic seen in JADES-GS-z7-LA. Owing to its UV-faintness, we show that it is incapable of single-handedly ionizing a region large enough to explain its Lyα emission. Therefore, we suggest that JADES-GS-z7-LA (and possibly the companion source) may be a part of a larger overdensity, presenting direct evidence of overlapping ionized bubbles at z > 7.
Keywords: Astrophysics

JADES Imaging of GN-z11: Revealing the Morphology and Environment of a Luminous Galaxy 430 Myr after the Big Bang - Tacchella, Sandro; Daniel J. Eisenstein; Hainline, Kevin; Johnson, Benjamin D.; Baker, William M.; Helton, Jakob M.; Robertson, Brant; Suess, Katherine A.; Chen, Zuyi; Nelson, Erica; Puskás, Dávid; Sun, Fengwu; et al. (The Astrophysical Journal, 2023)
We present JWST NIRCam nine-band near-infrared imaging of the luminous z = 10.6 galaxy GN-z11 from the JWST Advanced Deep Extragalactic Survey of the GOODS-N field. We find a spectral energy distribution (SED) entirely consistent with the expected form of a high-redshift galaxy: a clear blue continuum from 1.5 to 4 μm with a complete dropout in F115W. The core of GN-z11 is extremely compact in JWST imaging. We analyze the image with a two-component model, using a point source and a Sérsic profile that fits to a half-light radius of 200 pc and an index n = 0.9. We find a low-surface-brightness haze about 0.″4 to the northeast of the galaxy, which is most likely a foreground object but might be a more extended component of GN-z11. At a spectroscopic redshift of 10.60 (Bunker et al. 2023), the comparison of the NIRCam F410M and F444W images spans the Balmer jump. From population-synthesis modeling, here assuming no light from an active galactic nucleus, we reproduce the SED of GN-z11, finding a stellar mass of ~109 M ⊙, a star formation rate of ~20 M ⊙ yr-1, and a young stellar age of ~20 Myr. Since massive galaxies at high redshift are likely to be highly clustered, we search for faint neighbors of GN-z11, finding nine galaxies out to ~5 comoving Mpc transverse with photometric redshifts consistent with z = 10.6, and a tenth more tentative dropout only 3″ away. This is consistent with GN-z11 being hosted by a massive dark-matter halo (≈8 × 1010 M ⊙), though lower halo masses cannot be ruled out.
Keywords: Astrophysics of Galaxies

JADES Initial Data Release for the Hubble Ultra Deep Field: Revealing the Faint Infrared Sky with Deep JWST NIRCam Imaging - Rieke, Marcia J.; Robertson, Brant; Tacchella, Sandro; Hainline, Kevin; Johnson, Benjamin D.; Hausen, Ryan; Ji, Zhiyuan; Willmer, Christopher N. A.; Daniel J. Eisenstein; Puskás, Dávid; Alberts, Stacey; Arribas, Santiago; et al. (The Astrophysical Journal Supplement Series, 2023)
JWST has revolutionized the field of extragalactic astronomy with its sensitive and high-resolution infrared view of the distant Universe. Adding to the new legacy of JWST observations, we present the first NIRCam imaging data release from the JWST Advanced Deep Extragalactic Survey (JADES), providing nine filters of infrared imaging of ~25 arcmin2 covering the Hubble Ultra Deep Field and portions of Great Observatories Origins Deep Survey South. Utilizing 87 on-sky dual-filter hours of exposure time, these images reveal the deepest ever near-infrared view of this iconic field. We supply carefully constructed nine-band mosaics of the JADES bands, as well as matching reductions of five additional bands from the JWST Extragalactic Medium-band Survey. Combining with existing Hubble Space Telescope imaging, we provide 23-band space-based photometric catalogs and photometric redshifts for ≈47,500 sources. To promote broad engagement with JADES, we have created an interactive FitsMap website to provide an interface for professional researchers and the public to experience these JWST data sets. Combined with the first JADES NIRSpec data release, these public JADES imaging and spectroscopic data sets provide a new foundation for discoveries of the infrared Universe by the worldwide scientific community.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

JADES: Insights on the low-mass end of the mass--metallicity--star-formation rate relation at $3 < z < 10$ from deep JWST/NIRSpec spectroscopy - Curti, Mirko; Maiolino, Roberto; Curtis-Lake, Emma; Chevallard, Jacopo; Carniani, Stefano; D'Eugenio, Francesco; Looser, Tobias J.; Scholtz, Jan; Charlot, Stephane; Cameron, Alex; Übler, Hannah; Witstok, Joris; et al. (arXiv e-prints, 2023)
We analyse the gas-phase metallicity properties of a sample of low stellar mass (log M*/M_sun <= 9) galaxies at 3 < z < 10, observed with JWST/NIRSpec as part of the JADES programme in its deep GOODS-S tier. By combining this sample with more massive galaxies at similar redshifts from other programmes, we study the scaling relations between stellar mass, oxygen abundance (O/H), and star-formation rate (SFR) for 146 galaxies, spanning across three orders of magnitude in stellar mass and out to the epoch of early galaxy assembly. We find evidence for a shallower slope at the low-mass-end of the mass-metallicity relation (MZR), with 12 + log(O/H) = (7.72+-0.02) + (0.17+-0.03) log(M* / 10^8 M_sun), in good agreement with the MZR probed by local analogues of high-redshift systems like 'Green Pea' and 'Blueberry' galaxies. The inferred slope is well matched by models including 'momentum-driven' SNe winds, suggesting that feedback mechanisms in dwarf galaxies (and at high-z) might be different from those in place at higher masses. The evolution in the normalisation is observed to be relatively mild compared to previous determinations of the MZR at z~3 (~ 0.1 - 0.2 dex across the explored mass regime). We observe a deviation from the local fundamental metallicity relation (FMR) for our sample at high redshift, especially at z > 6, with galaxies significantly less enriched (with a median offset in log(O/H) of ~ 0.5 dex, significant at ~ 5 sigma) than predicted given their M* and SFR. These observations are consistent with an enhanced stochasticity in the star-formation history, and/or with an increased efficiency in metal removals by outflows, prompting us to reconsider the nature of the relationship between M*, O/H, and SFR in the early Universe.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES + JEMS: A Detailed Look at the Buildup of Central Stellar Cores and Suppression of Star Formation in Galaxies at Redshifts 3 < z < 4.5 - Ji, Zhiyuan; Williams, Christina C.; Tacchella, Sandro; Suess, Katherine A.; Baker, William M.; Alberts, Stacey; Bunker, Andrew J.; Johnson, Benjamin D.; Robertson, Brant; Sun, Fengwu; Daniel J. Eisenstein; Rieke, Marcia; et al. (arXiv e-prints, 2023)
We present a spatially resolved study of stellar populations in 6 galaxies with stellar masses $M_*\sim10^{10}M_\odot$ at $z\sim3.7$ using 14-filter JWST/NIRCam imaging from the JADES and JEMS surveys. The 6 galaxies are visually selected to have clumpy substructures with distinct colors over rest-frame $3600-4100$Å, including a bright dominant stellar core that is close to their stellar-light centroids. With 23-filter photometry from HST to JWST, we measure the stellar-population properties of individual structural components via SED fitting using Prospector. We find that the central stellar cores are $rsim2$ times more massive than the Toomre mass, indicating they may not form via in-situ fragmentation. The stellar cores have stellar ages of $0.4-0.7$ Gyr that are similar to the timescale of clump inward migration due to dynamical friction, suggesting that they likely instead formed through the coalescence of giant stellar clumps. While they have not yet quenched, the 6 galaxies are below the star-forming main sequence by $0.2-0.7$ dex. Within each galaxy, we find that the specific star formation rate is lower in the central stellar core, and the stellar-mass surface density of the core is already similar to quenched galaxies of the same masses and redshifts. Meanwhile, the stellar ages of the cores are either comparable to or younger than the extended, smooth parts of the galaxies. Our findings are consistent with model predictions of the gas-rich compaction scenario for the buildup of galaxies' central regions at high redshifts. We are likely witnessing the coeval formation of dense central cores, along with the onset of galaxy-wide quenching at $z>3$.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES NIRSpec Initial Data Release for the Hubble Ultra Deep Field: Redshifts and Line Fluxes of Distant Galaxies from the Deepest JWST Cycle 1 NIRSpec Multi-Object Spectroscopy - Bunker, Andrew J.; Cameron, Alex J.; Curtis-Lake, Emma; Jakobsen, Peter; Carniani, Stefano; Curti, Mirko; Witstok, Joris; Maiolino, Roberto; D'Eugenio, Francesco; Looser, Tobias J.; Willott, Chris; Bonaventura, Nina; et al. (arXiv e-prints, 2023)
We describe the NIRSpec component of the JWST Deep Extragalactic Survey (JADES), and provide deep spectroscopy of 253 sources targeted with the NIRSpec micro-shutter assembly in the Hubble Ultra Deep Field and surrounding GOODS-South. The multi-object spectra presented here are the deepest so far obtained with JWST, amounting to up to 28 hours in the low-dispersion ($R\sim 30-300$) prism, and up to 7 hours in each of the three medium-resolution $R≈ 1000$ gratings and one high-dispersion grating, G395H ($R≈2700$). Our low-dispersion and medium-dispersion spectra cover the wavelength range $0.6-5.3μ$m. We describe the selection of the spectroscopic targets, the strategy for the allocation of targets to micro-shutters, and the design of the observations. We present the public release of the reduced 2D and 1D spectra, and a description of the reduction and calibration process. We measure spectroscopic redshifts for 178 of the objects targeted extending up to $z=13.2$. We present a catalog of all emission lines detected at $S/N>5$, and our redshift determinations for the targets. Combined with the first JADES NIRCam data release, these public JADES spectroscopic and imaging datasets provide a new foundation for discoveries of the infrared universe by the worldwide scientific community.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES NIRSpec Spectroscopy of GN-z11: Lyman-α emission and possible enhanced nitrogen abundance in a z = 10.60 luminous galaxy - Bunker, Andrew J.; Saxena, Aayush; Cameron, Alex J.; Willott, Chris J.; Curtis-Lake, Emma; Jakobsen, Peter; Carniani, Stefano; Smit, Renske; Maiolino, Roberto; Witstok, Joris; Curti, Mirko; D'Eugenio, Francesco; et al. (Astronomy and Astrophysics, 2023)
We present JADES JWST/NIRSpec spectroscopy of GN-z11, the most luminous candidate z > 10 Lyman break galaxy in the GOODS-North field with MUV = −21.5. We derive a redshift of z = 10.603 (lower than previous determinations) based on multiple emission lines in our low and medium resolution spectra over 0.7 − 5.3 μm. We significantly detect the continuum and measure a blue rest-UV spectral slope of β = −2.4. Remarkably, we see spatially extended Lyman-α in emission (despite the highly neutral intergalactic medium expected at this early epoch), offset 555 km s−1 redwards of the systemic redshift. From our measurements of collisionally excited lines of both low and high ionisation (including [O II] λ3727, [Ne III] λ3869, and C III] λ1909), we infer a high ionisation parameter (log U ∼ −2). We detect the rarely seen N IV] λ1486 and N III] λ1748 lines in both our low and medium resolution spectra, with other high ionisation lines seen in the low resolution spectrum, such as He II (blended with O III]) and C IV (with a possible P-Cygni profile). Based on the observed rest-UV line ratios, we cannot conclusively rule out photoionisation from an active galactic nucleus (AGN), although the high C III]/He II and N III]/He II ratios are compatible with a star formation explanation. If the observed emission lines are powered by star formation, then the strong N III] λ1748 observed may imply an unusually high N/O abundance. Balmer emission lines (Hγ, Hδ) are also detected, and if powered by star formation rather than an AGN, we infer a star formation rate of ∼20 − 30 M⊙ yr−1 (depending on the initial mass function) and low dust attenuation. Our NIRSpec spectroscopy confirms that GN-z11 is a remarkable galaxy with extreme properties seen 430 Myr after the Big Bang.
Keywords: galaxies; Astrophysics - Cosmology and Nongalactic Astrophysics

The JADES Origins Field: A New JWST Deep Field in the JADES Second NIRCam Data Release - Daniel J. Eisenstein; Johnson, Benjamin D.; Robertson, Brant; Tacchella, Sandro; Hainline, Kevin; Jakobsen, Peter; Maiolino, Roberto; Bonaventura, Nina; Bunker, Andrew J.; Cameron, Alex J.; Cargile, Phillip A.; Curtis-Lake, Emma; et al. (arXiv e-prints, 2023)
We summarize the properties and initial data release of the JADES Origins Field (JOF), which will soon be the deepest imaging field yet observed with the James Webb Space Telescope (JWST). This field falls within the GOODS-S region about 8' south-west of the Hubble Ultra Deep Field (HUDF), where it was formed initially in Cycle 1 as a parallel field of HUDF spectroscopic observations within the JWST Advanced Deep Extragalactic Survey (JADES). This imaging will be greatly extended in Cycle 2 program 3215, which will observe the JOF for 5 days in six medium-band filters, seeking robust candidates for z>15 galaxies. This program will also include ultra-deep parallel NIRSpec spectroscopy (up to 104 hours on-source, summing over the dispersion modes) on the HUDF. Cycle 3 observations from program 4540 will add 20 hours of NIRCam slitless spectroscopy to the JOF. With these three campaigns, the JOF will be observed for 380 open-shutter hours with NIRCam using 15 imaging filters and 2 grism bandpasses. Further, parts of the JOF have deep 43 hr MIRI observations in F770W. Taken together, the JOF will soon be one of the most compelling deep fields available with JWST and a powerful window into the early Universe. This paper presents the second data release from JADES, featuring the imaging and catalogs from the year 1 JOF observations.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES: Probing interstellar medium conditions at z ∼ 5.5-9.5 with ultra-deep JWST/NIRSpec spectroscopy - Cameron, Alex J.; Saxena, Aayush; Bunker, Andrew J.; D'Eugenio, Francesco; Carniani, Stefano; Maiolino, Roberto; Curtis-Lake, Emma; Ferruit, Pierre; Jakobsen, Peter; Arribas, Santiago; Bonaventura, Nina; Charlot, Stephane; et al. (Astronomy and Astrophysics, 2023)
We present emission-line ratios from a sample of 27 Lyman-break galaxies from z ∼ 5.5 − 9.5 with −17.0 < M1500 < −20.4, measured from ultra-deep JWST/NIRSpec multi-object spectroscopy from the JWST Advanced Deep Extragalactic Survey (JADES). We used a combination of 28 h deep PRISM/CLEAR and 7 h deep G395M/F290LP observations to measure, or place strong constraints on, ratios of widely studied rest-frame optical emission lines including Hα, Hβ, [O II] λλ3726, 3729, [Ne III] λ3869, [O III] λ4959, [O III] λ5007, [O I] λ6300, [N II] λ6583, and [S II] λλ6716, 6731 in individual z > 5.5 spectra. We find that the emission-line ratios exhibited by these z ∼ 5.5 − 9.5 galaxies occupy clearly distinct regions of line-ratio space compared to typical z ∼ 0 − 3 galaxies, instead being more consistent with extreme populations of lower-redshift galaxies. This is best illustrated by the [O III]/[O II] ratio, tracing interstellar medium (ISM) ionisation, in which we observe more than half of our sample to have [O III]/[O II] > 10. Our high signal-to-noise spectra reveal more than an order of magnitude of scatter in line ratios such as [O II]/Hβ and [O III]/[O II], indicating significant diversity in the ISM conditions within the sample. We find no convincing detections of [N II] λ6583 in our sample, either in individual galaxies, or a stack of all G395M/F290LP spectra. The emission-line ratios observed in our sample are generally consistent with galaxies with extremely high ionisation parameters (log U ∼ −1.5), and a range of metallicities spanning from ∼0.1 × Z⊙ to higher than ∼0.3 × Z⊙, suggesting we are probing low-metallicity systems undergoing periods of rapid star formation, driving strong radiation fields. These results highlight the value of deep observations in constraining the properties of individual galaxies, and hence probing diversity within galaxy population.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES. The diverse population of infant Black Holes at 4 - Maiolino, Roberto; Scholtz, Jan; Curtis-Lake, Emma; Carniani, Stefano; Baker, William; de Graaff, Anna; Tacchella, Sandro; Übler, Hannah; D'Eugenio, Francesco; Witstok, Joris; Curti, Mirko; Arribas, Santiago; et al. (arXiv e-prints, 2023)
We present 12 new AGN at 4<z<7 in the JADES survey (in addition to the previously identified AGN in GN-z11 at z=10.6) revealed through the detection of a Broad Line Region as seen in Halpha. The depth of JADES, together with the use of three different spectral resolutions, enables us to probe a lower mass regime relative to previous studies. In a few cases we find evidence for two broad components of Halpha which suggests that these could be candidate merging black holes (BHs). The inferred BH masses range between 8 x 10^7 Msun down to 4 x 10^5 Msun, interestingly probing the regime expected for Direct Collapse Black Holes (DCBHs). The inferred AGN bolometric luminosities (~10^44-10^45 erg/s) imply accretion rates that are < 0.5 times the Eddington rate in most cases. However, small BHs, with M_BH ~ 10^6 Msun, tend to accrete at Eddington or super-Eddington rates. These BH at z~4-11 are over-massive relative to their host galaxies stellar masses when compared to the local M_BH-Mstar relation, and even approaching M_BH~Mstar, as expected for DCBHs and super-Eddington scenarios. However, we find that these early BHs tend to be more consistent with the local relation between M_BH and velocity dispersion, as well as between M_BH and dynamical mass, suggesting that these are more fundamental and universal relations. On the BPT excitation-diagnostic diagram these AGN are located in the region that is that is locally occupied by star-forming galaxies, implying that they would be missed by the standard classification techniques if they did not display broad lines. Their location on the diagram is consistent with what expected for AGN hosted in metal poor galaxies (Z ~ 0.1-0.2 Zsun). The fraction of broad line AGN with L_AGN > 10^44 erg/s, among galaxies in the redshift range 4<z<6, is about 10%, suggesting that the contribution of AGN and their hosts to the reionization of the Universe is > 10%.
Keywords: Phenomena

JADES: The emergence and evolution of Ly$α$ emission and constraints on the IGM neutral fraction - Jones, Gareth C.; Bunker, Andrew J.; Saxena, Aayush; Witstok, Joris; Stark, Daniel P.; Arribas, Santiago; Baker, William M.; Bhatawdekar, Rachana; Bowler, Rebecca; Boyett, Kristan; Cameron, Alex J.; Carniani, Stefano; et al. (arXiv e-prints, 2023)
The rest-frame UV recombination emission line Ly$α$ can be powered by ionising photons from young massive stars in star forming galaxies, but its ability to be resonantly scattered by neutral gas complicates its interpretation. For reionization era galaxies, a neutral intergalactic medium (IGM) will scatter Ly$α$ from the line of sight, making Ly$α$ a useful probe of the neutral fraction evolution. Here, we explore Ly$α$ in JWST/NIRSpec spectra from the ongoing JADES programme, which targets hundreds of galaxies in the well-studied GOODS-S and GOODS-N fields. These sources are UV-faint ($-20.4<\rm M_{\rm UV}<-16.4$), and thus represent a poorly-explored class of galaxies. The low spectral resolution ($R\sim100$) spectra of a subset of 84 galaxies in GOODS-S with $z_{spec}>5.6$ (as derived with optical lines) are fit with line and continuum models, in order to search for significant line emission. Through exploration of the R100 data, we find evidence for Ly$α$ in 17 sources. This sample allows us to place observational constraints on the fraction of galaxies with Ly$α$ emission in the redshift range $5.6<z<7.5$, with a decrease from $z=6$ to $z=7$. We also find a positive correlation between Ly$α$ equivalent width and M$_{UV}$, as seen in other samples. These results are used to estimate the neutral gas fraction at $z\sim7$, agreeing with previous results ($X_{HI}\sim0.5-0.9$).
Keywords: Astrophysics - Astrophysics of Galaxies

JADES: The incidence rate and properties of galactic outflows in low-mass galaxies across 3 < z < 9 - Carniani, Stefano; Venturi, Giacomo; Parlanti, Eleonora; de Graaff, Anna; Maiolino, Roberto; Arribas, Santiago; Bonaventura, Nina; Boyett, Kristan; Bunker, Andrew J.; Cameron, Alex J.; Charlot, Stephane; Chevallard, Jacopo; et al. (arXiv e-prints, 2023)
We investigate the incidence and properties of ionized gas outflows in a sample of 52 galaxies with stellar mass between $10^7$ M$_{\odot}$ and $10^9$ M$_{\odot}$ observed with ultra-deep JWST/NIRSpec MSA spectroscopy as part of the JWST Advanced Deep Extragalactic Survey (JADES). The high-spectral resolution (R2700) NIRSpec observations allowed us to identify for the first time the signature of outflows in the rest-frame optical nebular lines in low-mass galaxies at $z>3$. The incidence fraction of ionized outflows, traced by broad components, is about 25-40$%$ depending on the intensity of the emission lines. The low incidence fraction might be due to both the sensitivity limit and the fact that outflows are not isotropic but have a limited opening angle which results in a detection only when this is directed toward our line of sight. Evidence for outflows increases slightly with stellar mass and star-formation rate. The median velocity and mass loading factor (i.e., the ratio between mass outflow rate and star formation rate) of the outflowing ionized gas are 500 km s$^{-1}$ and $η=2.1^{+2.5}_{-1.6}$, respectively. These are two and 100 times higher, respectively than the typical values observed in local dwarf galaxies. These outflows are able to escape the gravitational potential of the galaxy and enrich the circum-galactic medium and, potentially, the inter-galactic medium. Our results indicate that outflows can significantly impact the star formation activity in low-mass galaxies within the first 2 Gyr of the Universe.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES: The production and escape of ionizing photons from faint Lyman-alpha emitters in the epoch of reionization - Saxena, Aayush; Bunker, Andrew J.; Jones, Gareth C.; Stark, Daniel P.; Cameron, Alex J.; Witstok, Joris; Arribas, Santiago; Baker, William M.; Baum, Stefi; Bhatawdekar, Rachana; Bowler, Rebecca; Boyett, Kristan; et al. (arXiv e-prints, 2023)
We present the properties of 16 faint Lyman-$α$ emitting galaxies (LAEs) at $z>5.8$ from the JWST Advanced Deep Extragalactic Survey (JADES) spectroscopic data in the Hubble Ultra Deep Field/GOODS-S. These LAEs span a redshift range $z≈5.8-8.0$ and UV magnitude range $M_{UV} ≈ -17$ to $-20.6$, with Ly$α$ equivalent width (EW) in the range $≈ 25-350$ Å. The detection of other rest-optical emission lines in the spectra of these LAEs enables the determination of accurate systemic redshifts and Ly$α$ velocity offsets, as well as the physical and chemical composition of their stars and interstellar media. These faint LAEs are consistent with metal-poor systems with high ionization parameters, similar to the general galaxy population at $z>6$. We measure an average ionizing photon production efficiency, log($ξ_{ion}$/erg$^{-1}$ Hz) $≈ 25.56$ across our LAEs, which does not evolve strongly with redshift. We report an anti-correlation between Ly$α$ escape fraction and velocity offset from systemic, consistent with model expectations. We further find that the strength and velocity offset of Ly$α$ are not correlated with galaxy spectroscopic properties nor with $ξ_{ion}$. We find a decrease in Ly$α$ escape fractions with redshift, indicative of decreasing sizes of ionized bubbles around LAEs at high redshifts. We use a range of galaxy properties to predict Lyman continuum escape fractions for our LAEs, finding that the ionizing photon output into the intergalactic medium from our LAEs remains roughly constant across the observed UV magnitude and Ly$α$ equivalent width, showing a mild increase with redshift. We derive correlations between the ionizing photon output from LAEs and UV magnitude Ly$α$ strengths and redshift, which can be used to build realistic reionization models.
Keywords: Astrophysics - Astrophysics of Galaxies

JADES: Using NIRCam Photometry to Investigate the Dependence of Stellar Mass Inferences on the IMF in the Early Universe - Charity Woodrum; Rieke, Marcia; Ji, Zhiyuan; Baker, William M.; Bhatawdekar, Rachana; Bunker, Andrew J.; Charlot, Stéphane; Curtis-Lake, Emma; Daniel J. Eisenstein; Hainline, Kevin; Hausen, Ryan; Helton, Jakob M.; et al. (arXiv e-prints, 2023)
The detection of numerous and relatively bright galaxies at redshifts z > 9 has prompted new investigations into the star-forming properties of high-redshift galaxies. Using local forms of the initial mass function (IMF) to estimate stellar masses of these galaxies from their light output leads to galaxy masses that are at the limit allowed for the state of the LambdaCDM Universe at their redshift. We explore how varying the IMF assumed in studies of galaxies in the early universe changes the inferred values for the stellar masses of these galaxies. We infer galaxy properties with the SED fitting code Prospector using varying IMF parameterizations for a sample of 102 galaxies from the JWST Advanced Deep Extragalactic Survey (JADES) spectroscopically confirmed to be at z > 6.7, with additional photometry from the JWST Extragalactic Medium Band Survey (JEMS) for twenty-one galaxies. We demonstrate that models with stellar masses reduced by a factor of three or more do not affect the modeled spectral energy distribution (SED).
Keywords: Astrophysics - Astrophysics of Galaxies

The James Webb Space Telescope Mission - Gardner, Jonathan P.; Mather, John C.; Abbott, Randy; Abell, James S.; Abernathy, Mark; Abney, Faith E.; Abraham, John G.; Abraham, Roberto; Abul-Huda, Yasin M.; Acton, Scott; Adams, Cynthia K.; Adams, Evan; et al. (Publications of the Astronomical Society of the Pacific, 2023)
Twenty-six years ago a small committee report, building on earlier studies, expounded a compelling and poetic vision for the future of astronomy, calling for an infrared-optimized space telescope with an aperture of at least 4 m. With the support of their governments in the US, Europe, and Canada, 20,000 people realized that vision as the 6.5 m James Webb Space Telescope. A generation of astronomers will celebrate their accomplishments for the life of the mission, potentially as long as 20 yr, and beyond. This report and the scientific discoveries that follow are extended thank-you notes to the 20,000 team members. The telescope is working perfectly, with much better image quality than expected. In this and accompanying papers, we give a brief history, describe the observatory, outline its objectives and current observing program, and discuss the inventions and people who made it possible. We cite detailed reports on the design and the measured performance on orbit.
Keywords: Instrumentation and Methods for Astrophysics

JEMS: A Deep Medium-band Imaging Survey in the Hubble Ultra Deep Field with JWST NIRCam and NIRISS - Williams, Christina C.; Tacchella, Sandro; Maseda, Michael V.; Robertson, Brant E.; Johnson, Benjamin D.; Willott, Chris J.; Daniel J. Eisenstein; Willmer, Christopher N. A.; Ji, Zhiyuan; Hainline, Kevin N.; Helton, Jakob M.; Alberts, Stacey; et al. (The Astrophysical Journal Supplement Series, 2023)
We present JWST Extragalactic Medium-band Survey, the first public medium-band imaging survey carried out using JWST/NIRCam and NIRISS. These observations use ~2 and ~4 μm medium-band filters (NIRCam F182M, F210M, F430M, F460M, F480M; and NIRISS F430M and F480M in parallel) over 15.6 arcmin2 in the Hubble Ultra Deep Field (UDF), thereby building on the deepest multiwavelength public data sets available anywhere on the sky. We describe our science goals, survey design, NIRCam and NIRISS image reduction methods, and describe our first data release of the science-ready mosaics, which reach 5σ point-source limits (AB mag) of ~29.3-29.4 in 2 μm filters and ~28.2-28.7 at 4 μm. Our chosen filters create a JWST imaging survey in the UDF that enables novel analysis of a range of spectral features potentially across the redshift range of 0.3 < z < 20, including Paschen-α, Hα+[N II], and [O III]+Hβ emission at high spatial resolution. We find that our JWST medium-band imaging efficiently identifies strong line emitters (medium-band colors >1 mag) across redshifts 1.5 < z < 9.3, most prominently Hα+[N II] and [O III]+Hβ. We present our first data release including science-ready mosaics of each medium-band image available to the community, adding to the legacy value of past and future surveys in the UDF. This survey demonstrates the power of medium-band imaging with JWST, informing future extragalactic survey strategies using JWST observations.
Keywords: Astrophysics of Galaxies

The JWST Advanced Deep Extragalactic Survey: Discovery of an Extreme Galaxy Overdensity at $z = 5.4$ with JWST/NIRCam in GOODS-S - Helton, Jakob M.; Sun, Fengwu; Charity Woodrum; Hainline, Kevin N.; Willmer, Christopher N. A.; Rieke, George H.; Rieke, Marcia J.; Tacchella, Sandro; Robertson, Brant; Johnson, Benjamin D.; Alberts, Stacey; Daniel J. Eisenstein; et al. (arXiv e-prints, 2023)
We report the discovery of an extreme galaxy overdensity at $z = 5.4$ in the GOODS-S field using JWST/NIRCam imaging from JADES and JEMS alongside JWST/NIRCam wide field slitless spectroscopy from FRESCO. We identified potential members of the overdensity using HST+JWST photometry spanning $λ = 0.4-5.0\ μm$. These data provide accurate and well-constrained photometric redshifts down to $m ≈ 29-30\,mag$. We subsequently confirmed $N = 81$ galaxies at $5.2 < z < 5.5$ using JWST slitless spectroscopy over $λ = 3.9-5.0\ μm$ through a targeted line search for $H α$ around the best-fit photometric redshift. We verified that $N = 42$ of these galaxies reside in the field while $N = 39$ galaxies reside in a density around $\sim 10$ times that of a random volume. Stellar populations for these galaxies were inferred from the photometry and used to construct the star-forming main sequence, where protocluster members appeared more massive and exhibited earlier star formation (and thus older stellar populations) when compared to their field galaxy counterparts. We estimate the total halo mass of this large-scale structure to be $12.6 \lesssim log_{10} \left( M_{halo}/M_{\odot} \right) \lesssim 12.8$ using an empirical stellar mass to halo mass relation, which is likely an underestimate as a result of incompleteness. Our discovery demonstrates the power of JWST at constraining dark matter halo assembly and galaxy formation at very early cosmic times.
Keywords: Astrophysics - Astrophysics of Galaxies

JWST NIRCam + NIRSpec: interstellar medium and stellar populations of young galaxies with rising star formation and evolving gas reservoirs - Tacchella, Sandro; Johnson, Benjamin D.; Robertson, Brant E.; Carniani, Stefano; D'Eugenio, Francesco; Kumari, Nimisha; Maiolino, Roberto; Nelson, Erica J.; Suess, Katherine A.; Übler, Hannah; Williams, Christina C.; Adebusola, Alabi; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
We present an interstellar medium and stellar population analysis of three spectroscopically confirmed z > 7 galaxies in the Early Release Observations JWST/NIRCam and JWST/NIRSpec data of the SMACS J0723.3-7327 cluster. We use the Bayesian spectral energy distribution-fitting code PROSPECTOR with a flexible star formation history (SFH), a variable dust attenuation law, and a self-consistent model of nebular emission (continuum and emission lines). Importantly, we self-consistently fit both the emission line fluxes from JWST/NIRSpec and the broad-band photometry from JWST/NIRCam, taking into account slit-loss effects. We find that these three z=7.6-8.5 galaxies (M⋆ ≈ 108 M⊙) are young with rising SFHs and mass-weighted ages of 3-4 Myr, though we find indications for underlying older stellar populations. The inferred gas-phase metallicities broadly agree with the direct metallicity estimates from the auroral lines. The galaxy with the lowest gas-phase metallicity (Zgas= 0.06 Z⊙) has a steeply rising SFH, is very compact (<0.2 kpc), and has a high star formation rate surface density (ΣSFR ≈ 22 M⊙ yr-1 kpc-2), consistent with rapid gas accretion. The two other objects with higher gas-phase metallicities show more complex multicomponent morphologies on kpc scales, indicating that their recent increase in star formation rate is driven by mergers or internal, gravitational instabilities. We discuss effects of assuming different SFH priors or only fitting the photometric data. Our analysis highlights the strength and importance of combining JWST imaging and spectroscopy for fully assessing the nature of galaxies at the earliest epochs.
Keywords: Galaxies

JWST Observations of the Enigmatic Y-Dwarf WISE 1828+2650. I. Limits to a Binary Companion - De Furio, Matthew; Lew, Ben; Beichman, Charles; Roellig, Thomas; Bryden, Geoffrey; Ciardi, David; Meyer, Michael; Rieke, Marcia; Greenbaum, Alexandra; Leisenring, Jarron; Llop-Sayson, Jorge; Ygouf, Marie; et al. (The Astrophysical Journal, 2023)
The Y-dwarf WISE 1828+2650 is one of the coldest known brown dwarfs with an effective temperature of ~300 K. Located at a distance of just 10 pc, previous model-based estimates suggest WISE1828+2650 has a mass of ~5-10 M J, making it a valuable laboratory for understanding the formation, evolution, and physical characteristics of gas giant planets. However, previous photometry and spectroscopy have presented a puzzle, with the near impossibility of simultaneously fitting both the short- (0.9-2.0 μm) and long-wavelength (3-5 μm) data. A potential solution to this problem has been the suggestion that WISE 1828+2650 is a binary system whose composite spectrum might provide a better match to the data. Alternatively, new models being developed to fit JWST/NIRSpec, and MIRI spectroscopy might provide new insights. This article describes JWST/NIRCam observations of WISE 1828+2650 in six filters to address the binarity question and to provide new photometry to be used in model fitting. We also report adaptive optics imaging with the Keck I0 m telescope. We find no evidence for multiplicity for a companion beyond 0.5 au with either JWST or Keck. Companion articles will present low- and high-resolution spectra of WISE 1828 obtained with both NIRSpec and MIRI.
Keywords: Astrophysics; Astrophysics - Earth and Planetary Astrophysics

JWST Reveals a Population of Ultrared, Flattened Galaxies at 2 ≲ z ≲ 6 Previously Missed by HST - Nelson, Erica J.; Suess, Katherine A.; Bezanson, Rachel; Price, Sedona H.; van Dokkum, Pieter; Leja, Joel; Wang, Bingjie; Whitaker, Katherine E.; Labbé, Ivo; Barrufet, Laia; Brammer, Gabriel; Daniel J. Eisenstein; et al. (The Astrophysical Journal, 2023)
With just a month of data, JWST is already transforming our view of the universe, revealing and resolving starlight in unprecedented populations of galaxies. Although "HST-dark" galaxies have previously been detected at long wavelengths, these observations generally suffer from a lack of spatial resolution, which limits our ability to characterize their sizes and morphologies. Here we report on a first view of starlight from a subset of the HST-dark population that is bright with JWST/NIRCam (4.4 μm < 24.5 mag) and very faint or even invisible with HST (<1.6 μm). In this Letter we focus on a dramatic and unanticipated population of physically extended galaxies (≳0.″25). These 12 galaxies have photometric redshifts 2 < z < 6, high stellar masses M ⋆ ≳ 1010 M ⊙, and significant dust-attenuated star formation. Surprisingly, the galaxies have elongated projected axis ratios at 4.4 μm, suggesting that the population is disk dominated or prolate and we hence refer to them as ultrared flattened objects. Most of the galaxies appear red at all radii, suggesting significant dust attenuation throughout. With R e (F444W) ~ 1-2 kpc, the galaxies are similar in size to compact massive galaxies at z ~ 2 and the cores of massive galaxies and S0s at z ~ 0. The stellar masses, sizes, and morphologies of the sample suggest that some could be progenitors of lenticular or fast-rotating galaxies in the local universe. The existence of this population suggests that our previous censuses of the universe may have missed massive, dusty edge-on disks, in addition to dust-obscured starbursts.
Keywords: Astrophysics - Astrophysics of Galaxies

JWST-JADES. Possible Population III signatures at z=10.6 in the halo of GN-z11 - Maiolino, Roberto; Uebler, Hannah; Perna, Michele; Scholtz, Jan; D'Eugenio, Francesco; Witten, Callum; Laporte, Nicolas; Witstok, Joris; Carniani, Stefano; Tacchella, Sandro; Baker, William; Arribas, Santiago; et al. (arXiv e-prints, 2023)
Finding the first generation of stars formed out of pristine gas in the early Universe, known as Population III (PopIII) stars, is one of the most important goals of modern astrophysics. Recent models suggest that PopIII stars may form in pockets of pristine gas in the halo of more evolved galaxies. Here we present NIRSpec-IFU and NIRSpec-MSA observations of the region around GN-z11, an exceptionally luminous galaxy at $z=10.6$, which reveal a $>$5$σ$ detection of a feature consistent with being HeII$λ$1640 emission at the redshift of GN-z11. The very high equivalent width of the putative HeII emission in this clump (170 A), and the lack of metal lines, can be explained in terms of photoionisation by PopIII stars, while photoionisation by PopII stars is inconsistent with the data. It would also indicate that the putative PopIII stars likely have a top-heavy initial mass function (IMF), with an upper cutoff reaching at least 500 M$_\odot$. The PopIII bolometric luminosity inferred from the HeII line would be $\sim 2× 10^{10}~L_\odot$, which (with a top-heavy IMF) would imply a total stellar mass formed in the burst of $\sim 6× 10^{5}~M_\odot$. We find that photoionisation by the Active Galactic Nucleus (AGN) in GN-z11 cannot account for the HeII luminosity observed in the clump, but can potentially be responsible for additional HeII emission observed closer to GN-z11. We also consider the possibility of in-situ photoionisation by an accreting Direct Collapse Black Hole (DCBH) hosted by the HeII clump; we find that this scenario is less favoured, but it remains a possible alternative interpretation. We also report the detection of a Ly$α$ halo stemming out of GN-z11 and extending out to $\sim$2 kpc, as well as resolved, funnel-shaped CIII] emission, likely tracing the ionisation cone of the AGN.
Keywords: Nongalactic Astrophysics

The MillenniumTNG Project: an improved two-halo model for the galaxy-halo connection of red and blue galaxies - Hadzhiyska, Boryana; Eisenstein, Daniel; Hernquist, Lars; Pakmor, Rüdiger; Bose, Sownak; Delgado, Ana Maria; Contreras, Sergio; Kannan, Rahul; White, Simon D. M.; Springel, Volker; Frenk, Carlos; Hernández-Aguayo, César; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
Approximate methods to populate dark-matter haloes with galaxies are of great utility to galaxy surveys. However, the limitations of simple halo occupation models (HODs) preclude a full use of small-scale galaxy clustering data and call for more sophisticated models. We study two galaxy populations, luminous red galaxies (LRGs) and star-forming emission-line galaxies (ELGs), at two epochs, z = 1 and z = 0, in the large-volume, high-resolution hydrodynamical simulation of the MillenniumTNG project. In a partner study we concentrated on the small-scale, one-halo regime down to r ~ 0.1 h-1 Mpc, while here we focus on modelling galaxy assembly bias in the two-halo regime, r ≳ 1 h-1 Mpc. Interestingly, the ELG signal exhibits scale dependence out to relatively large scales (r ~ 20 h-1 Mpc), implying that the linear bias approximation for this tracer is invalid on these scales, contrary to common assumptions. The 10-15 per cent discrepancy is only reconciled when we augment our halo occupation model with a dependence on extrinsic halo properties ('shear' being the best-performing one) rather than intrinsic ones (e.g. concentration, peak mass). We argue that this fact constitutes evidence for two-halo galaxy conformity. Including tertiary assembly bias (i.e. a property beyond mass and 'shear') is not an essential requirement for reconciling the galaxy assembly bias signal of LRGs, but the combination of external and internal properties is beneficial for recovering ELG the clustering. We find that centrals in low-mass haloes dominate the assembly bias signal of both populations. Finally, we explore the predictions of our model for higher order statistics such as nearest neighbour counts. The latter supplies additional information about galaxy assembly bias and can be used to break degeneracies between halo model parameters.
Keywords: Astrophysics - Astrophysics of Galaxies

The MillenniumTNG Project: refining the one-halo model of red and blue galaxies at different redshifts - Hadzhiyska, Boryana; Hernquist, Lars; Eisenstein, Daniel; Delgado, Ana Maria; Bose, Sownak; Kannan, Rahul; Pakmor, Rüdiger; Springel, Volker; Contreras, Sergio; Barrera, Monica; Ferlito, Fulvio; Hernández-Aguayo, César; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
Luminous red galaxies (LRGs) and blue star-forming emission-line galaxies (ELGs) are key tracers of large-scale structure used by cosmological surveys. Theoretical predictions for such data are often done via simplistic models for the galaxy-halo connection. In this work, we use the large, high-fidelity hydrodynamical simulation of the MillenniumTNG project (MTNG) to inform a new phenomenological approach for obtaining an accurate and flexible galaxy-halo model on small scales. Our aim is to study LRGs and ELGs at two distinct epochs, z = 1 and z = 0, and recover their clustering down to very small scales, $r \sim 0.1 \ h^{-1}\, {\rm Mpc}$, i.e. the one-halo regime, while a companion paper extends this to a two-halo model for larger distances. The occupation statistics of ELGs in MTNG inform us that (1) the satellite occupations exhibit a slightly super-Poisson distribution, contrary to commonly made assumptions, and (2) that haloes containing at least one ELG satellite are twice as likely to host a central ELG. We propose simple recipes for modelling these effects, each of which calls for the addition of a single free parameter to simpler halo occupation models. To construct a reliable satellite population model, we explore the LRG and ELG satellite radial and velocity distributions and compare them with those of subhaloes and particles in the simulation. We find that ELGs are anisotropically distributed within haloes, which together with our occupation results provides strong evidence for cooperative galaxy formation (manifesting itself as one-halo galaxy conformity); i.e. galaxies with similar properties form in close proximity to each other. Our refined galaxy-halo model represents a useful improvement of commonly used analysis tools and thus can be of help to increase the constraining power of large-scale structure surveys.
Keywords: Astrophysics - Astrophysics of Galaxies

Minor Merger Growth in Action: JWST Detects Faint Blue Companions around Massive Quiescent Galaxies at 0.5 ≤ z ≤ 3.0 - Suess, Katherine A.; Williams, Christina C.; Robertson, Brant; Ji, Zhiyuan; Johnson, Benjamin D.; Nelson, Erica; Alberts, Stacey; Hainline, Kevin; D'Eugenio, Francesco; Übler, Hannah; Rieke, Marcia; Rieke, George; et al. (The Astrophysical Journal, 2023)
Minor mergers are thought to drive the structural evolution of massive quiescent galaxies; however, existing Hubble Space Telescope (HST) imaging is primarily sensitive to stellar mass ratios ≳1:10. Here, we report the discovery of a large population of low-mass companions within 35 kpc of known $logM_{* }/M_{\odot }rsim 10.5$ quiescent galaxies at 0.5 ≤ z ≤ 3. While massive companions like those identified by HST are rare, JWST imaging from the JWST Advanced Deep Extragalactic Survey reveals that the average massive quiescent galaxy hosts approximately five nearby companions with stellar mass ratios <1:10. Despite a median stellar mass ratio of just 1:900, these tiny companions are so numerous that they represent at least 30% of the total mass being added to quiescent galaxies via minor mergers. While relatively massive companions have colors similar to their hosts, companions with mass ratios <1:10 typically have bluer colors and lower mass-to-light ratios than their host galaxies at similar radii. The accretion of these tiny companions is likely to drive evolution in the color gradients and stellar population properties of the host galaxies. Our results suggest that the well-established "minor merger growth" model for quiescent galaxies extends down to very low mass ratios of ≲1:100, and demonstrates the power of JWST to constrain both the spatially resolved properties of massive galaxies and the properties of low-mass companions beyond the local Universe.
Keywords: - Astrophysics of Galaxies

Morpheus Reveals Distant Disk Galaxy Morphologies with JWST: The First AI/ML Analysis of JWST Images - Robertson, Brant E.; Tacchella, Sandro; Johnson, Benjamin D.; Hausen, Ryan; Alabi, Adebusola B.; Boyett, Kristan; Bunker, Andrew J.; Carniani, Stefano; Egami, Eiichi; Daniel J. Eisenstein; Hainline, Kevin N.; Helton, Jakob M.; et al. (The Astrophysical Journal, 2023)
The dramatic first images with JWST demonstrated its power to provide unprecedented spatial detail for galaxies in the high-redshift universe. Here, we leverage the resolution and depth of the JWST Cosmic Evolution Early Release Science Survey data in the Extended Groth Strip to perform pixel-level morphological classifications of galaxies in JWST F150W imaging using the Morpheus deep-learning framework for astronomical image analysis. By cross-referencing with existing photometric redshift catalogs from the Hubble Space Telescope (HST) CANDELS survey, we show that JWST images indicate the emergence of disk morphologies before z ~ 2 and with candidates appearing as early as z ~ 5. By modeling the light profile of each object and accounting for the JWST point-spread function, we find the high-redshift disk candidates have exponential surface brightness profiles with an average Sérsic index <n> = 1.04 and >90% displaying "disky" profiles (n < 2). Comparing with prior Morpheus classifications in CANDELS we find that a plurality of JWST disk galaxy candidates were previously classified as compact based on the shallower HST imagery, indicating that the improved optical quality and depth of the JWST helps to reveal disk morphologies that were hiding in the noise. We discuss the implications of these early disk candidates on theories for cosmological disk galaxy formation.
Keywords: Astrophysics

Non-parametric Lagrangian biasing from the insights of neural nets - Wu, Xiaohan; Muñoz, Julian B.; Daniel J. Eisenstein (Journal of Cosmology and Astroparticle Physics, 2023)
We present a Lagrangian model of galaxy clustering bias in which we train a neural net using the local properties of the smoothed initial density field to predict the late-time mass-weighted halo field. By fitting the mass-weighted halo field in the ABACUSSUMMIT simulations at z = 0.5, we find that including three coarsely spaced smoothing scales gives the best recovery of the halo power spectrum. Adding more smoothing scales may lead to 2-5% underestimation of the large-scale power and can cause the neural net to overfit. We find that the fitted halo-to-mass ratio can be well described by two directions in the original high-dimension feature space. Projecting the original features into these two principal components and re-training the neural net either reproduces the original training result, or outperforms it with a better match of the halo power spectrum. The elements of the principal components are unlikely to be assigned physical meanings, partly owing to the features being highly correlated between different smoothing scales. Our work illustrates a potential need to include multiple smoothing scales when studying galaxy bias, and this can be done easily with machine-learning methods that can take in high dimensional input feature space.
Keywords: - Cosmology and Nongalactic Astrophysics

The Optical Corrector for the Dark Energy Spectroscopic Instrument - Miller, Timothy N.; Doel, Peter; Gutierrez, Gaston; Besuner, Robert; David Brooks; Gallo, Giuseppe; Heetderks, Henry; Jelinsky, Patrick; Kent, Stephen M.; Lampton, Michael; Levi, Michael; Liang, Ming; et al. (arXiv e-prints, 2023)
The Dark Energy Spectroscopic Instrument (DESI) is currently measuring the spectra of 40\,million galaxies and quasars, the largest such survey ever made to probe the nature of cosmological dark energy. The 4-meter Mayall telescope at Kitt Peak National Observatory has been adapted for DESI, including the construction of a 3.2-degree diameter prime focus corrector that focuses astronomical light onto a 0.8-meter diameter focal surface with excellent image quality over the DESI bandpass of 360-980nm. The wide-field corrector includes six lenses, as large as 1.1-meters in diameter and as heavy as 237\,kilograms, including two counter-rotating wedged lenses that correct for atmospheric dispersion over Zenith angles from 0 to 60 degrees. The lenses, cells, and barrel assembly all meet precise alignment tolerances on the order of tens of microns. The barrel alignment is maintained throughout a range of observing angles and temperature excursions in the Mayall dome by use of a hexapod, which is itself supported by a new cage, ring, and truss structure. In this paper we describe the design, fabrication, and performance of the new corrector and associated structure, focusing on how they meet DESI requirements. In particular we describe the prescription and specifications of the lenses, design choices and error budgeting of the barrel assembly, stray light mitigations, and integration and test at the Mayall telescope. We conclude with some validation highlights that demonstrate the successful corrector on-sky performance, and list some lessons learned during the multi-year fabrication phase.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

Overview of the DESI Milky Way Survey - Cooper, Andrew P.; Koposov, Sergey E.; Allende Prieto, Carlos; Manser, Christopher J.; Kizhuprakkat, Namitha; Myers, Adam D.; Dey, Arjun; Gänsicke, Boris T.; Li, Ting S.; Rockosi, Constance; Valluri, Monica; Najita, Joan; et al. (The Astrophysical Journal, 2023)
We describe the Milky Way Survey (MWS) that will be undertaken with the Dark Energy Spectroscopic Instrument (DESI) on the Mayall 4 m telescope at the Kitt Peak National Observatory. Over the next 5 yr DESI MWS will observe approximately seven million stars at Galactic latitudes |b| > 20°, with an inclusive target selection scheme focused on the thick disk and stellar halo. MWS will also include several high-completeness samples of rare stellar types, including white dwarfs, low-mass stars within 100 pc of the Sun, and horizontal branch stars. We summarize the potential of DESI to advance understanding of the Galactic structure and stellar evolution. We introduce the final definitions of the main MWS target classes and estimate the number of stars in each class that will be observed. We describe our pipelines for deriving radial velocities, atmospheric parameters, and chemical abundances. We use ≃500,000 spectra of unique stellar targets from the DESI Survey Validation program (SV) to demonstrate that our pipelines can measure radial velocities to ≃1 km s-1 and [Fe/H] accurate to ≃0.2 dex for typical stars in our main sample. We find the stellar parameter distributions from ≈100 deg2 of SV observations with ≳90% completeness on our main sample are in good agreement with expectations from mock catalogs and previous surveys.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

Overview of the JWST Advanced Deep Extragalactic Survey (JADES) - Daniel J. Eisenstein; Willott, Chris; Alberts, Stacey; Arribas, Santiago; Bonaventura, Nina; Bunker, Andrew J.; Cameron, Alex J.; Carniani, Stefano; Charlot, Stephane; Curtis-Lake, Emma; D'Eugenio, Francesco; Endsley, Ryan; et al. (arXiv e-prints, 2023)
We present an overview of the James Webb Space Telescope (JWST) Advanced Deep Extragalactic Survey (JADES), an ambitious program of infrared imaging and spectroscopy in the GOODS-S and GOODS-N deep fields, designed to study galaxy evolution from high redshift to cosmic noon. JADES uses about 770 hours of Cycle 1 guaranteed time largely from the Near-Infrared Camera (NIRCam) and Near-Infrared Spectrograph (NIRSpec) instrument teams. In GOODS-S, in and around the Hubble Ultra Deep Field and Chandra Deep Field South, JADES produces a deep imaging region of ~45 arcmin$^2$ with an average of 130 hrs of exposure time spread over 9 NIRCam filters. This is extended at medium depth in GOODS-S and GOODS-N with NIRCam imaging of ~175 arcmin$^2$ with an average exposure time of 20 hrs spread over 8-10 filters. In both fields, we conduct extensive NIRSpec multi-object spectroscopy, including 2 deep pointings of 55 hrs exposure time, 14 medium pointings of ~12 hrs, and 15 shallower pointings of ~4 hrs, targeting over 5000 HST and JWST-detected faint sources with 5 low, medium, and high-resolution dispersers covering 0.6-5.3 microns. Finally, JADES extends redward via coordinated parallels with the JWST Mid-Infrared Instrument (MIRI), featuring ~9 arcmin$^2$ with 43 hours of exposure at 7.7 microns and twice that area with 2-6.5 hours of exposure at 12.8 microns For nearly 30 years, the GOODS-S and GOODS-N fields have been developed as the premier deep fields on the sky; JADES is now providing a compelling start on the JWST legacy in these fields.
Keywords: Astrophysics - Astrophysics of Galaxies

Performance of NIRCam on JWST in Flight - Rieke, Marcia J.; Kelly, Douglas M.; Misselt, Karl; Stansberry, John; Boyer, Martha; Beatty, Thomas; Egami, Eiichi; Florian, Michael; Greene, Thomas P.; Hainline, Kevin; Leisenring, Jarron; Roellig, Thomas; et al. (Publications of the Astronomical Society of the Pacific, 2023)
The Near Infrared Camera for the James Webb Space Telescope (JWST) is delivering the imagery that astronomers have hoped for ever since JWST was proposed back in the 1990s. In the Commissioning Period that extended from right after launch to early 2022 July, NIRCam has been subjected to a number of performance tests and operational checks. The camera is exceeding prelaunch expectations in virtually all areas, with very few surprises discovered in flight. NIRCam also delivered the imagery needed by the Wavefront Sensing Team for use in aligning the telescope mirror segments.
Keywords: 1543; 1547; Astrophysics - Instrumentation and Methods for Astrophysics

Planting a Lyman alpha forest on ABACUSSUMMIT - Hadzhiyska, Boryana; Font-Ribera, A.; Cuceu, A.; Chabanier, S.; Aguilar, J.; Brooks, D.; de la Macorra, A.; Doel, P.; Eisenstein, D. J.; Forero-Romero, J. E.; Gontcho, S. Gontcho A; Honscheid, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
The full-shape correlations of the Lyman alpha (Ly α) forest contain a wealth of cosmological information through the Alcock-Paczyński effect. However, these measurements are challenging to model without robustly testing and verifying the theoretical framework used for analysing them. Here, we leverage the accuracy and volume of the N-body simulation suite ABACUSSUMMIT to generate high-resolution Ly α skewers and quasi-stellar object (QSO) catalogues. One of the main goals of our mocks is to aid in the full-shape Ly α analysis planned by the Dark Energy Spectroscopic Instrument (DESI) team. We provide optical depth skewers for six of the fiducial cosmology base-resolution simulations ($L_{\rm box} = 2\, h^{-1}\, {\rm Gpc}$, N = 69123) at z = 2.5. We adopt a simple recipe based on the Fluctuating Gunn-Peterson Approximation (FGPA) for constructing these skewers from the matter density in an N-body simulation and calibrate it against the 1D and 3D Ly α power spectra extracted from the hydrodynamical simulation IllustrisTNG (TNG; $L_{\rm box} = 205\, h^{-1}\, {\rm Mpc}$, N = 25003). As an important application, we study the non-linear broadening of the baryon acoustic oscillation (BAO) peak and show the cross-correlation between DESI-like QSOs and our Ly α forest skewers. We find differences on small scales between the Kaiser approximation prediction and our mock measurements of the Ly α × QSO cross-correlation, which would be important to account for in upcoming analyses. The ABACUSSUMMIT Ly α forest mocks open up the possibility for improved modelling of cross-correlations between Ly α and cosmic microwave background (CMB) lensing and Ly α and QSOs, and for forecasts of the 3-point Ly α correlation function. Our catalogues and skewers are publicly available on Globus via the National Energy Research Scientific Computing Center (NERSC) (full link under the section 'Data Availability').
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

Reconstructing cosmological initial conditions from late-time structure with convolutional neural networks - Shallue, Christopher J.; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2023)
We present a method to reconstruct the initial linear-regime matter density field from the late-time non-linearly evolved density field in which we channel the output of standard first-order reconstruction to a convolutional neural network (CNN). Our method shows dramatic improvement over the reconstruction of either component alone. We show why CNNs are not well-suited for reconstructing the initial density directly from the late-time density: CNNs are local models, but the relationship between initial and late-time density is not local. Our method leverages standard reconstruction as a preprocessing step, which inverts bulk gravitational flows sourced over very large scales, transforming the residual reconstruction problem from long-range to local and making it ideally suited for a CNN. We develop additional techniques to account for redshift distortions, which warp the density fields measured by galaxy surveys. Our method improves the range of scales of high-fidelity reconstruction by a factor of 2 in wavenumber above standard reconstruction, corresponding to a factor of 8 increase in the number of well-reconstructed modes. In addition, our method almost completely eliminates the anisotropy caused by redshift distortions. As galaxy surveys continue to map the Universe in increasingly greater detail, our results demonstrate the opportunity offered by CNNs to untangle the non-linear clustering at intermediate scales more accurately than ever before.
Keywords: Astrophysics - Instrumentation and Methods for Astrophysics

Redshift-dependent RSD bias from Intrinsic Alignment with DESI Year 1 Spectra - Lamman, Claire; Eisenstein, Daniel; Aguilar, Jessica Nicole; Ahlen, Steven; David Brooks; Claybaugh, Todd; de la Macorra, Axel; Dey, Arjun; Dey, Biprateep; Doel, Peter; Ferraro, Simone; Font-Ribera, Andreu; et al. (arXiv e-prints, 2023)
We estimate the redshift-dependent, anisotropic clustering signal in DESI's Year 1 Survey created by tidal alignments of Luminous Red Galaxies (LRGs) and a selection-induced galaxy orientation bias. To this end, we measured the correlation between LRG shapes and the tidal field with DESI's Year 1 redshifts, as traced by LRGs and Emission-Line Galaxies (ELGs). We also estimate the galaxy orientation bias of LRGs caused by DESI's aperture-based selection, and find it to increase by a factor of seven between redshifts 0.4 - 1.1 due to redder, fainter galaxies falling closer to DESI's imaging selection cuts. These effects combine to dampen measurements of the quadrupole of the correlation function caused by structure growth on scales of 10 - 80 Mpc/h by about 0.15% for low redshifts (0.4<z<0.6) and 0.8% for high (0.8<z<1.1). We provide estimates of the quadrupole signal created by intrinsic alignments that can be used to correct this effect, which is necessary to meet DESI's forecasted precision on measuring the growth rate of structure. While imaging quality varies across DESI's footprint, we find no significant difference in this effect between imaging regions in the Legacy Imaging Survey.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

The Robotic Multiobject Focal Plane System of the Dark Energy Spectroscopic Instrument (DESI) - Silber, Joseph Harry; Fagrelius, Parker; Fanning, Kevin; Schubnell, Michael; Aguilar, Jessica Nicole; Ahlen, Steven; Ameel, Jon; Ballester, Otger; Baltay, Charles; Bebek, Chris; Benton Beard, Dominic; Besuner, Robert; et al. (The Astronomical Journal, 2023)
A system of 5020 robotic fiber positioners was installed in 2019 on the Mayall Telescope, at Kitt Peak National Observatory. The robots automatically retarget their optical fibers every 10-20 minutes, each to a precision of several microns, with a reconfiguration time of fewer than 2 minutes. Over the next 5 yr, they will enable the newly constructed Dark Energy Spectroscopic Instrument (DESI) to measure the spectra of 35 million galaxies and quasars. DESI will produce the largest 3D map of the universe to date and measure the expansion history of the cosmos. In addition to the 5020 robotic positioners and optical fibers, DESI's Focal Plane System includes six guide cameras, four wave front cameras, 123 fiducial point sources, and a metrology camera mounted at the primary mirror. The system also includes associated structural, thermal, and electrical systems. In all, it contains over 675,000 individual parts. We discuss the design, construction, quality control, and integration of all these components. We include a summary of the key requirements, the review and acceptance process, on-sky validations of requirements, and lessons learned for future multiobject, fiber-fed spectrographs.
Keywords: Astrophysics

A small and vigorous black hole in the early Universe - Maiolino, Roberto; Scholtz, Jan; Witstok, Joris; Carniani, Stefano; D'Eugenio, Francesco; de Graaff, Anna; Uebler, Hannah; Tacchella, Sandro; Curtis-Lake, Emma; Arribas, Santiago; Bunker, Andrew; Charlot, Stéphane; et al. (arXiv e-prints, 2023)
Multiple theories have been proposed to describe the formation of black hole seeds in the early Universe and to explain the emergence of very massive black holes observed in the first billion years after Big Bang. Models consider different seeding and accretion scenarios, which require the detection and characterisation of black holes in the first few hundred million years after Big Bang to be validated. Here we present an extensive analysis of the JWST-NIRSpec spectrum of GN-z11, an exceptionally luminous galaxy at z=10.6, revealing the detection of the [NeIV]2423 and CII*1335 transitions (typical of Active Galactic Nuclei, AGN), as well as semi-forbidden nebular lines tracing gas densities higher than 10^9 cm-3, typical of the Broad Line Region of AGN. These spectral features indicate that GN-z11 hosts an accreting black hole. The spectrum also reveals a deep and blueshifted CIV1549 absorption trough, tracing an outflow with velocity 800-1000 km/s, likely driven by the AGN. Assuming local virial relations, we derive a black hole mass of log(M_BH/Msun) = 6.2 +- 0.3, accreting at about 5 times the Eddington rate. These properties are consistent with both heavy seeds scenarios, or scenarios envisaging intermediate/light seeds experiencing episodic super-Eddington phases. Our finding naturally explains the high luminosity of GN-z11 and can also provide an explanation for its exceptionally high nitrogen abundance.
Keywords: Phenomena

Spectroscopic confirmation of four metal-poor galaxies at z = 10.3-13.2 - Curtis-Lake, Emma; Carniani, Stefano; Cameron, Alex; Charlot, Stephane; Jakobsen, Peter; Maiolino, Roberto; Bunker, Andrew; Witstok, Joris; Smit, Renske; Chevallard, Jacopo; Willott, Chris; Ferruit, Pierre; et al. (Nature Astronomy, 2023)
Finding and characterizing the first galaxies that illuminated the early universe at cosmic dawn is pivotal to understand the physical conditions and the processes that led to the formation of the first stars. In the first few months of operations, imaging from the James Webb Space Telescope (JWST) has been used to identify tens of candidates of galaxies at redshift (z) greater than 10, less than 450 million years after the Big Bang. However, none of such candidates has yet been confirmed spectroscopically, leaving open the possibility that they are actually low-redshift interlopers. Here we present spectroscopic confirmation and analysis of four galaxies unambiguously detected at redshift 10.3 ≤ z ≤ 13.2, previously selected from JWST Near Infrared Camera imaging. The spectra reveal that these primeval galaxies are metal poor, have masses on the order of about 107-108 solar masses and young ages. The damping wings that shape the continuum close to the Lyman edge provide constraints on the neutral hydrogen fraction of the intergalactic medium from normal star-forming galaxies. These findings demonstrate the rapid emergence of the first generations of galaxies at cosmic dawn.
Keywords: Astrophysics - Astrophysics of Galaxies

The Spectroscopic Data Processing Pipeline for the Dark Energy Spectroscopic Instrument - Guy, J.; Bailey, S.; Kremin, A.; Alam, Shadab; Alexander, D. M.; Allende Prieto, C.; BenZvi, S.; Bolton, A. S.; Brooks, D.; Chaussidon, E.; Cooper, A. P.; Dawson, K.; et al. (The Astronomical Journal, 2023)
We describe the spectroscopic data processing pipeline of the Dark Energy Spectroscopic Instrument (DESI), which is conducting a redshift survey of about 40 million galaxies and quasars using a purpose-built instrument on the 4 m Mayall Telescope at Kitt Peak National Observatory. The main goal of DESI is to measure with unprecedented precision the expansion history of the universe with the baryon acoustic oscillation technique and the growth rate of structure with redshift space distortions. Ten spectrographs with three cameras each disperse the light from 5000 fibers onto 30 CCDs, covering the near-UV to near-infrared (3600-9800 Å) with a spectral resolution ranging from 2000 to 5000. The DESI data pipeline generates wavelength- and flux-calibrated spectra of all the targets, along with spectroscopic classifications and redshift measurements. Fully processed data from each night are typically available to the DESI collaboration the following morning. We give details about the pipeline's algorithms, and provide performance results on the stability of the optics, the quality of the sky background subtraction, and the precision and accuracy of the instrumental calibration. This pipeline has been used to process the DESI Survey Validation data set, and has exceeded the project's requirements for redshift performance, with high efficiency and a purity greater than 99% for all target classes.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

A Spectroscopic Search for Optical Emission Lines from Dark Matter Decay - Wang, Hanyue; Daniel J. Eisenstein; Aguilar, Jessica Nicole; Ahlen, Steven; Bailey, Stephen; David Brooks; Claybaugh, Todd; de la Macorra, Axel; Doel, Peter; Forero-Romero, Jaime E.; Kremin, Anthony; Levi, Michael E.; et al. (arXiv e-prints, 2023)
We search for narrow-line optical emission from dark matter decay by stacking dark-sky spectra from the Dark Energy Spectroscopic Instrument (DESI) at the redshift of nearby galaxies from DESI's Bright Galaxy and Luminous Red Galaxy samples. Our search uses regions separated by 5 to 20 arcsecond from the centers of the galaxies, corresponding to an impact parameter of approximately $50\,\rm kpc$. No unidentified spectral line shows up in the search, and we place a line flux limit of $10^{-19}\,\rm{ergs}/\rm{s}/\rm{cm}^{2}/\rm{arcsec}^{2}$ on emissions in the optical band ($3000\lesssim\lambda\lesssim9000 \,\mathring{\rm A}$), which corresponds to $34$ in AB magnitude in a normal broadband detection. This detection limit suggests that the line surface brightness contributed from all dark matter along the line of sight is two orders of magnitude lower than the measured extragalactic background light (EBL), which rules out the possibility that narrow optical-line emission from dark matter decay is a major source of the EBL.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

The Star-forming and Ionizing Properties of Dwarf z~6-9 Galaxies in JADES: Insights on Bursty Star Formation and Ionized Bubble Growth - Endsley, Ryan; Stark, Daniel P.; Whitler, Lily; Topping, Michael W.; Johnson, Benjamin D.; Robertson, Brant; Tacchella, Sandro; Alberts, Stacey; Baker, William M.; Bhatawdekar, Rachana; Boyett, Kristan; Bunker, Andrew J.; et al. (arXiv e-prints, 2023)
Reionization is thought to be driven by faint star-forming galaxies, but characterizing this population in detail has long remained very challenging. Here we utilize deep nine-band NIRCam imaging from JADES to study the star-forming and ionizing properties of 756 $z\sim6-9$ galaxies, including hundreds of very UV-faint objects ($M_UV>-18$). The faintest ($m\sim30$) galaxies in our sample typically have stellar masses of $M_*\sim(1-3)×10^7$ $M_\odot$ and young light-weighted ages ($\sim$50 Myr), though some show strong Balmer breaks implying much older ages ($\sim$500 Myr). We find no evidence for extremely massive galaxies ($>3×10^{10}$ $M_\odot$) in our sample. We infer a strong (factor $>$2) decline in the typical [OIII]$+$H$β$ EWs towards very faint $z\sim6-9$ galaxies, yet a weak UV luminosity dependence on the H$α$ EWs at $z\sim6$. We demonstrate that these EW trends can be explained if fainter galaxies have systematically lower metallicities as well as more recently-declining star formation histories relative to the most UV-luminous galaxies in our sample. Our data provide evidence that the brightest galaxies are frequently experiencing a recent strong upturn in SFR. We also discuss how the EW trends may be influenced by a strong correlation between $M_UV$ and Lyman continuum escape fraction. This alternative explanation has dramatically different implications for the contribution of galaxies along the luminosity function to cosmic reionization, highlighting the need for deep spectroscopic follow-up. Finally, we quantify the photometric overdensities around two $z>7$ strong Ly$α$ emitters in the JADES footprint. One Ly$α$ emitter lies close to a strong photometric overdensity while the other shows no significant nearby overdensity, perhaps implying that not all strong $z>7$ Ly$α$ emitters reside in large ionized bubbles.
Keywords: Astrophysics - Astrophysics of Galaxies

SUNBIRD: A simulation-based model for full-shape density-split clustering - Cuesta-Lazaro, Carolina; Paillas, Enrique; Sihan Yuan; Cai, Yan-Chuan; Nadathur, Seshadri; Will J. Percival; Beutler, Florian; de Mattia, Arnaud; Eisenstein, Daniel; Forero-Sanchez, Daniel; Padilla, Nelson; Pinon, Mathilde; et al. (arXiv e-prints, 2023)
Combining galaxy clustering information from regions of different environmental densities can help break cosmological parameter degeneracies and access non-Gaussian information from the density field that is not readily captured by the standard two-point correlation function (2PCF) analyses. However, modelling these density-dependent statistics down to the non-linear regime has so far remained challenging. We present a simulation-based model that is able to capture the cosmological dependence of the full shape of the density-split clustering (DSC) statistics down to intra-halo scales. Our models are based on neural-network emulators that are trained on high-fidelity mock galaxy catalogues within an extended-$Λ$CDM framework, incorporating the effects of redshift-space, Alcock-Paczynski distortions and models of the halo-galaxy connection. Our models reach sub-percent level accuracy down to $1\,h^{-1}{\rm Mpc}$ and are robust against different choices of galaxy-halo connection modelling. When combined with the galaxy 2PCF, DSC can tighten the constraints on $ω_{\rm cdm}$, $σ_8$, and $n_s$ by factors of 2.9, 1.9, and 2.1, respectively, compared to a 2PCF-only analysis. DSC additionally puts strong constraints on environment-based assembly bias parameters. Our code is made publicly available on Github.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

Synthetic light-cone catalogues of modern redshift and weak lensing surveys waith ABACUSSUMMIT - Hadzhiyska, Boryana; Yuan, S.; Blake, C.; Eisenstein, D. J.; Aguilar, J.; Ahlen, S.; Brooks, D.; Claybaugh, T.; de la Macorra, A.; Doel, P.; Emas, N.; Forero-Romero, J. E.; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
The joint analysis of different cosmological probes, such as galaxy clustering and weak lensing, can potentially yield invaluable insights into the nature of the primordial Universe, dark energy, and dark matter. However, the development of high-fidelity theoretical models is a necessary stepping stone. Here, we present public high-resolution weak lensing maps on the light-cone, generated using the N-body simulation suite ABACUSSUMMIT, and accompanying weak lensing mock catalogues, tuned to the Early Data Release small-scale clustering measurements of the Dark Energy Spectroscopic Instrument. Available in this release are maps of the cosmic shear, deflection angle, and convergence fields at source redshifts ranging from z = 0.15 to 2.45 as well as cosmic microwave background convergence maps for each of the 25 base-resolution simulations ($L_{\rm box} = 2000\, h^{-1}\, {\rm Mpc}$ and Npart = 69123) as well as for the two huge simulations ($L_{\rm box} = 7500\, h^{-1}\, {\rm Mpc}$ and Npart = 86403) at the fiducial ABACUSSUMMIT cosmology. The pixel resolution of each map is 0.21 arcmin, corresponding to a HEALPIX Nside of 16 384. The sky coverage of the base simulations is an octant until z ≈ 0.8 (decreasing to about 1800 deg2 at z ≈ 2.4), whereas the huge simulations offer full-sky coverage until z ≈ 2.2. Mock lensing source catalogues are sampled matching the ensemble properties of the Kilo-Degree Survey, Dark Energy Survey, and Hyper Suprime-Cam data sets. The mock catalogues are validated against theoretical predictions for various clustering and lensing statistics, such as correlation multipoles, galaxy-shear, and shear-shear, showing excellent agreement. All products can be downloaded via a Globus endpoint (see Data Availability section).
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

Target Selection and Validation of DESI Emission Line Galaxies - Raichoor, A.; Moustakas, J.; Newman, Jeffrey A.; Karim, T.; Ahlen, S.; Alam, Shadab; Bailey, S.; Brooks, D.; Dawson, K.; de la Macorra, A.; de Mattia, A.; Dey, A.; et al. (The Astronomical Journal, 2023)
The Dark Energy Spectroscopic Instrument (DESI) will precisely constrain cosmic expansion and the growth of structure by collecting ~40 million extragalactic redshifts across ~80% of cosmic history and one-third of the sky. The Emission Line galaxy (ELG) sample, which will comprise about one-third of all DESI tracers, will be used to probe the universe over the 0.6 < z < 1.6 range, including the 1.1 < z < 1.6 range, which is expected to provide the tightest constraints. We present the target selection for the DESI Survey Validation (SV) and Main Survey ELG samples, which relies on the imaging of the Legacy Surveys. The Main ELG selection consists of a g-band magnitude cut and a (g - r) versus (r - z) color box, while the SV selection explores extensions of the Main selection boundaries. The Main ELG sample is composed of two disjoint subsamples, which have target densities of about 1940 deg-2 and 460 deg-2, respectively. We first characterize their photometric properties and density variations across the footprint. We then analyze the DESI spectroscopic data that have been obtained from 2020 December to 2021 December in the SV and Main Survey. We establish a preliminary criterion for selecting reliable redshifts, based on the [O II] flux measurement, and assess its performance. Using this criterion, we are able to present the spectroscopic efficiency of the Main ELG selection, along with its redshift distribution. We thus demonstrate that the Main selection 1940 deg-2 subsample alone should provide 400 deg-2 and 460 deg-2 reliable redshifts in the 0.6 < z < 1.1 and the 1.1 < z < 1.6 ranges, respectively.
Keywords: Astrophysics

Target Selection and Validation of DESI Luminous Red Galaxies - Zhou, Rongpu; Dey, Biprateep; Newman, Jeffrey A.; Daniel J. Eisenstein; Dawson, K.; Bailey, S.; Berti, A.; Guy, J.; Lan, Ting-Wen; Zou, H.; Aguilar, J.; Ahlen, S.; et al. (The Astronomical Journal, 2023)
The Dark Energy Spectroscopic Instrument (DESI) is carrying out a five-year survey that aims to measure the redshifts of tens of millions of galaxies and quasars, including 8 million luminous red galaxies (LRGs) in the redshift range 0.4 < z ≲ 1.0. Here we present the selection of the DESI LRG sample and assess its spectroscopic performance using data from Survey Validation (SV) and the first two months of the Main Survey. The DESI LRG sample, selected using g, r, z, and W1 photometry from the DESI Legacy Imaging Surveys, is highly robust against imaging systematics. The sample has a target density of 605 deg-2 and a comoving number density of 5 × 10-4 h 3 Mpc-3 in 0.4 < z < 0.8; this is a significantly higher density than previous LRG surveys (such as SDSS, BOSS, and eBOSS) while also extending to z ~ 1. After applying a bright star veto mask developed for the sample, 98.9% of the observed LRG targets yield confident redshifts (with a catastrophic failure rate of 0.2% in the confident redshifts), and only 0.5% of the LRG targets are stellar contamination. The LRG redshift efficiency varies with source brightness and effective exposure time, and we present a simple model that accurately characterizes this dependence. In the appendices, we describe the extended LRG samples observed during SV.
Keywords: Nongalactic Astrophysics; Astrophysics - Astrophysics of Galaxies

Target Selection and Validation of DESI Quasars - Chaussidon, Edmond; Yèche, Christophe; Palanque-Delabrouille, Nathalie; Alexander, David M.; Yang, Jinyi; Ahlen, Steven; Bailey, Stephen; David Brooks; Cai, Zheng; Chabanier, Solène; Davis, Tamara M.; Dawson, Kyle; et al. (The Astrophysical Journal, 2023)
The Dark Energy Spectroscopic Instrument (DESI) survey will measure large-scale structures using quasars as direct tracers of dark matter in the redshift range 0.9 < z < 2.1 and using Lyα forests in quasar spectra at z > 2.1. We present several methods to select candidate quasars for DESI, using input photometric imaging in three optical bands (g, r, z) from the DESI Legacy Imaging Surveys and two infrared bands (W1, W2) from the Wide-field Infrared Survey Explorer. These methods were extensively tested during the Survey Validation of DESI. In this paper, we report on the results obtained with the different methods and present the selection we optimized for the DESI main survey. The final quasar target selection is based on a random forest algorithm and selects quasars in the magnitude range of 16.5 < r < 23. Visual selection of ultra-deep observations indicates that the main selection consists of 71% quasars, 16% galaxies, 6% stars, and 7% inconclusive spectra. Using the spectra based on this selection, we build an automated quasar catalog that achieves a fraction of true QSOs higher than 99% for a nominal effective exposure time of ~1000 s. With a 310 deg-2 target density, the main selection allows DESI to select more than 200 deg-2 quasars (including 60 deg-2 quasars with z > 2.1), exceeding the project requirements by 20%. The redshift distribution of the selected quasars is in excellent agreement with quasar luminosity function predictions.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

To high redshift and low mass: exploring the emergence of quenched galaxies and their environments at $3 - Alberts, Stacey; Williams, Christina C.; Helton, Jakob M.; Suess, Katherine A.; Ji, Zhiyuan; Shivaei, Irene; Lyu, Jianwei; Rieke, George; Baker, William M.; Bonaventura, Nina; Bunker, Andrew J.; Carniani, Stefano; et al. (arXiv e-prints, 2023)
We present the robust selection of quiescent (QG) and post-starburst (PSB) galaxies using ultra-deep NIRCam and MIRI imaging from the JWST Advanced Deep Extragalactic Survey (JADES). Key to this is MIRI 7.7$μ$m imaging which breaks the degeneracy between old stellar populations and dust attenuation at $3<z<6$ by providing rest-frame $J$-band. Using this, we identify 23 passively evolving galaxies in UVJ color space in a mass-limited (log $M_{\star}/M_{\odot}≥8.5$) sample over 8.8 arcmin$^2$. Evaluation of this selection with and without 7.7$\,μ$m shows that dense wavelength coverage with NIRCam ($8-11$ bands including $1-4$ medium-bands) can compensate for lacking the $J-$band anchor, meaning that robust selection of high-redshift QGs is possible with NIRCam alone. Our sample is characterized by rapid quenching timescales ($\sim100-600$ Myr) with formation redshifts $z_{\rm f}\lesssim8.5$ and includes a potential record-holding massive QG at $z_{\rm phot}=5.33_{-0.17}^{+0.16}$ and two QGs with evidence for significant residual dust content ($A_{\rm V}\sim1-2$). In addition, we present a large sample of 12 log $M_{\star}/M_{\odot}=8.5-9.5$ PSBs, demonstrating that UVJ selection can be extended to low mass. Analysis of the environment of our sample reveals that the group known as the Cosmic Rose contains a massive QG and a dust-obscured star-forming galaxy (a so-called Jekyll and Hyde pair) plus three additional QGs within $\sim20$ kpc. Moreover, the Cosmic Rose is part of a larger overdensity at $z\sim3.7$ which contains 7/12 of our low-mass PSBs. Another 4 low-mass PSBs are members of an overdensity at $z\sim3.4$; this result strongly indicates low-mass PSBs are preferentially associated with overdense environments at $z>3$.
Keywords: Astrophysics - Astrophysics of Galaxies

The UV Continuum Slopes of Early Star-Forming Galaxies in JADES - Topping, Michael W.; Stark, Daniel P.; Endsley, Ryan; Whitler, Lily; Hainline, Kevin; Johnson, Benjamin D.; Robertson, Brant; Tacchella, Sandro; Chen, Zuyi; Alberts, Stacey; Baker, William M.; Bunker, Andrew J.; et al. (arXiv e-prints, 2023)
The power-law slope of the rest-UV continuum ($f_{λ}\proptoλ^{β}$) is a key metric of early star forming galaxies, providing one of our only windows into the stellar populations and physical conditions of $z>10$ galaxies. Expanding upon previous studies with limited sample sizes, we leverage deep imaging from JADES to investigate the UV slopes of 179 $z>9$ galaxies with apparent magnitudes of $m_{\rm F200W}=26-31$, which display a median UV slope of $β=-2.4$. We compare to a statistical sample of $z=5-9$ galaxies, finding a shift toward bluer rest-UV colors at all $\rm~M_{UV}$. The most UV-luminous $z>9$ galaxies are significantly bluer than their lower-redshift counterparts, representing a dearth of moderately-red galaxies in the first $500~$Myr. At yet earlier times, the $z>11$ galaxy population exhibits very blue UV slopes, implying very low attenuation from dust. We identify a robust sample of 44 galaxies with $β<-2.8$, which have SEDs requiring models of density-bounded HII regions and median ionizing photon escape fractions of $0.51$ to reproduce. Their rest-optical colors imply that this sample has weaker emission lines (median $m_{\rm F356W}-m_{\rm F444W}=0.19$ mag) than typical galaxies (median $m_{\rm F356W}-m_{\rm F444W}=0.39$ mag), consistent with the inferred escape fractions. This sample has relatively low stellar masses (median $\log(M/M_{\odot})=7.5$), and specific star-formation rates (median$=79\rm/Gyr$) nearly twice that of our full sample (median$=44\rm/Gyr$), suggesting they are more common among systems experiencing a recent upturn in star formation. We demonstrate that the shutoff of star formation provides an alternative solution for modelling of extremely blue UV colors, making distinct predictions for the rest-optical emission of these galaxies. Future spectroscopy will be required to distinguish between these physical pictures.
Keywords: Astrophysics - Astrophysics of Galaxies

Validation of semi-analytical, semi-empirical covariance matrices for two-point correlation function for early DESI data - Rashkovetskyi, Michael; Daniel J. Eisenstein; Aguilar, Jessica Nicole; David Brooks; Claybaugh, Todd; Cole, Shaun; Dawson, Kyle; de la Macorra, Axel; Doel, Peter; Fanning, Kevin; Font-Ribera, Andreu; Forero-Romero, Jaime E.; et al. (Monthly Notices of the Royal Astronomical Society, 2023)
We present an extended validation of semi-analytical, semi-empirical covariance matrices for the two-point correlation function (2PCF) on simulated catalogs representative of luminous red galaxies (LRGs) data collected during the initial 2 months of operations of the Stage-IV ground-based Dark Energy Spectroscopic Instrument (DESI). We run the pipeline on multiple effective Zel'dovich (EZ) mock galaxy catalogs with the corresponding cuts applied and compare the results with the mock sample covariance to assess the accuracy and its fluctuations. We propose an extension of the previously developed formalism for catalogs processed with standard reconstruction algorithms. We consider methods for comparing covariance matrices in detail, highlighting their interpretation and statistical properties caused by sample variance, in particular, non-trivial expectation values of certain metrics even when the external covariance estimate is perfect. With improved mocks and validation techniques, we confirm a good agreement between our predictions and sample covariance. This allows one to generate covariance matrices for comparable data sets without the need to create numerous mock galaxy catalogs with matching clustering, only requiring 2PCF measurements from the data itself. The code used in this paper is publicly available at https://github.com/oliverphilcox/RascalC.
Keywords: Statistics Theory; Physics - Data Analysis; Statistics and Probability

ABACUSHOD: a highly efficient extended multitracer HOD framework and its application to BOSS and eBOSS data - Sihan Yuan; Garrison, Lehman H.; Hadzhiyska, Boryana; Bose, Sownak; Daniel J. Eisenstein (\mnras, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; Dark matter; galaxies: haloes; gravitational lensing: weak; large-scale structure of Universe; methods: numerical; Methods: Statistical

Accuracy of power spectra in dissipationless cosmological simulations - Maleubre, Sara; Eisenstein, Daniel; Garrison, Lehman H.; Joyce, Michael (\mnras, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; large-scale structure of Universe; methods: numerical

COMPASO: A new halo finder for competitive assignment to spherical overdensities - Hadzhiyska, Boryana; Eisenstein, Daniel; Bose, Sownak; Garrison, Lehman H.; Maksimova, Nina (\mnras, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; Astrophysics - Instrumentation and Methods for Astrophysics; COSMOLOGY: THEORY; galaxies: haloes; large-scale structure of Universe; methods: data analysis

A Conditional Autoencoder for Galaxy Photometric Parameter Estimation - Yin, Jun E.; Daniel J. Eisenstein; Finkbeiner, Douglas P.; Pavlos Protopapas (\pasp, 2022)
Keywords: 1234; 582; 611; Galaxy classification systems; Galaxy photometry; Photometry

Constraining accuracy of pairwise velocities using scale-free models - Maleubre, Sara; Daniel J. Eisenstein; Garrison, Lehman H.; Joyce, Michael (arXiv e-prints, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

Constructing high-fidelity halo merger trees in ABACUSSUMMIT - Bose, Sownak; Daniel J. Eisenstein; Hadzhiyska, Boryana; Garrison, Lehman H.; Sihan Yuan (\mnras, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; COSMOLOGY: THEORY; large-scale structure of the Universe; methods: numerical

Cosmological Constraints from Cross-Correlation of Planck CMB lensing and DESI-like Emission-Line Galaxies in Legacy Surveys - Karim, Tanveer; Singh, Sukhdeep; Rezaie, Mehdi; Hadzhiyska, Boryana; Eisenstein, Daniel (APS April Meeting Abstracts, 2022)

DESI Bright Galaxy Survey: Final Target Selection, Design, and Validation - Hahn, ChangHoon; Wilson, Michael J.; Ruiz-Macias, Omar; Cole, Shaun; Weinberg, David H.; Moustakas, John; Kremin, Anthony; Tinker, Jeremy L.; Smith, Alex; Wechsler, Risa H.; Ahlen, Steven; Alam, Shadab; et al. (arXiv e-prints, 2022)
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - Cosmology and Nongalactic Astrophysics

The DESI N-body simulation project - I. Testing the robustness of simulations for the DESI dark time survey - Grove, Cameron; Chuang, Chia-Hsun; Chandrachani Devi, Ningombam; Garrison, Lehman; L'Huillier, Benjamin; Feng, Yu; Helly, John; Hernández-Aguayo, César; Alam, Shadab; Zhang, Hanyu; Yu, Yu; Cole, Shaun; et al. (\mnras, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; COSMOLOGY: THEORY; galaxies: haloes; large-scale structure of Universe; methods: numerical

The DESI N-body Simulation Project - II. Suppressing sample variance with fast simulations - Ding, Zhejie; Chuang, Chia-Hsun; Yu, Yu; Garrison, Lehman H.; Bayer, Adrian E.; Feng, Yu; Modi, Chirag; Daniel J. Eisenstein; White, Martin; Variu, Andrei; Zhao, Cheng; Zhang, Hanyu; et al. (\mnras, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; COSMOLOGY: THEORY; galaxies: haloes; large-scale structure of Universe; Methods: Statistical

Discovery and properties of the earliest galaxies with confirmed distances - Robertson, B. E.; Tacchella, S.; Johnson, B. D.; Hainline, K.; Whitler, L.; Eisenstein, D. J.; Endsley, R.; Rieke, M.; Stark, D. P.; Alberts, S.; Dressler, A.; Egami, E.; et al. (arXiv e-prints, 2022)
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - Cosmology and Nongalactic Astrophysics

ENCORE: an O (N$_g$$^2$) estimator for galaxy N-point correlation functions - Philcox, Oliver H. E.; Slepian, Zachary; Hou, Jiamin; Warner, Craig; Cahn, Robert N.; Daniel J. Eisenstein (\mnras, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; Astrophysics - Instrumentation and Methods for Astrophysics; COSMOLOGY: THEORY; GALAXIES: STATISTICS; General Relativity and Quantum Cosmology; large-scale structure of Universe; methods: numerical; Methods: Statistical; Physics - Computational Physics

First Sample of H$α$+[O III] $łambda$5007 Line Emitters at $z > 6$ through JWST/NIRCam Slitless Spectroscopy: Physical Properties and Line Luminosity Functions - Sun, Fengwu; Egami, Eiichi; Pirzkal, Nor; Rieke, Marcia; Baum, Stefi; Boyer, Martha; Boyett, Kristan; Bunker, Andrew J.; Cameron, Alex J.; Curti, Mirko; Daniel J. Eisenstein; Gennaro, Mario; et al. (arXiv e-prints, 2022)
Keywords: Astrophysics - Astrophysics of Galaxies

A fully Lagrangian, non-parametric bias model for dark matter halos - Wu, Xiaohan; Muñoz, Julian B.; Eisenstein, Daniel (\jcap, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; cosmic web; Cosmological simulations; power spectrum

The halo light-cone catalogues of ABACUSSUMMIT - Hadzhiyska, Boryana; Garrison, Lehman H.; Eisenstein, Daniel; Bose, Sownak (\mnras, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; COSMOLOGY: THEORY; Galaxies: Formation; galaxies: haloes; large-scale structure of Universe; methods: data analysis; Methods: n-Body Simulations

Illustrating galaxy-halo connection in the DESI era with ILLUSTRISTNG - Sihan Yuan; Hadzhiyska, Boryana; Bose, Sownak; Daniel J. Eisenstein (\mnras, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; Dark matter; galaxies: haloes; large-scale structure of Universe; METHODS: ANALYTICAL; methods: numerical

Intrinsic Alignment as an RSD Contaminant in the DESI Survey - Lamman, Claire; Eisenstein, Daniel; Aguilar, Jessica Nicole; David Brooks; de la Macorra, Axel; Doel, Peter; Font-Ribera, Andreu; Gontcho, Satya Gontcho A.; Honscheid, Klaus; Kehoe, Robert; Kisner, Theodore; Kremin, Anthony; et al. (arXiv e-prints, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

JWST NIRCam+NIRSpec: Interstellar medium and stellar populations of young galaxies with rising star formation and evolving gas reservoirs - Tacchella, Sandro; Johnson, Benjamin D.; Robertson, Brant E.; Carniani, Stefano; D'Eugenio, Francesco; Kumar, Nimisha; Maiolino, Roberto; Nelson, Erica J.; Suess, Katherine A.; Übler, Hannah; Williams, Christina C.; Adebusola, Alabi; et al. (arXiv e-prints, 2022)
Keywords: Astrophysics - Astrophysics of Galaxies

JWST reveals a population of ultra-red, flattened disk galaxies at 2 - Nelson, Erica J.; Suess, Katherine A.; Bezanson, Rachel; Price, Sedona H.; van Dokkum, Pieter; Leja, Joel; Wang, Bingjie; Whitaker, Katherine E.; abbé, Ivo; Barrufet, Laia; Brammer, Gabriel; Daniel J. Eisenstein; et al. (arXiv e-prints, 2022)
Keywords: Astrophysics - Astrophysics of Galaxies

The MillenniumTNG Project: An improved two-halo model for the galaxy-halo connection of red and blue galaxies - Hadzhiyska, Boryana; Eisenstein, Daniel; Hernquist, Lars; Pakmor, Rüdiger; Bose, Sownak; Delgado, Ana Maria; Contreras, Sergio; Kannan, Rahul; White, Simon D. M.; Springel, Volker; Frenk, Carlos; Hernández-Aguayo, César; et al. (arXiv e-prints, 2022)
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - Cosmology and Nongalactic Astrophysics

The MillenniumTNG Project: Refining the one-halo model of red and blue galaxies at different redshifts - Hadzhiyska, Boryana; Hernquist, Lars; Eisenstein, Daniel; Delgado, Ana Maria; Bose, Sownak; Kannan, Rahul; Pakmor, Rüdiger; Springel, Volker; Contreras, Sergio; Barrera, Monica; Ferlito, Fulvio; Hernández-Aguayo, César; et al. (arXiv e-prints, 2022)
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - Cosmology and Nongalactic Astrophysics

Non-parametric Lagrangian biasing from the insights of neural nets - Wu, Xiaohan; Munoz, Julian B.; Daniel J. Eisenstein (arXiv e-prints, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

Overview and operation of the DESI focal plane - Fanning, K.; Besuner, R.; Eisenstein, D. J.; Fagrelius, P.; Honscheid, K.; Kirkby, D.; Landriau, M.; Levi, M. E.; Poppett, C.; Rabinowitz, D.; Schubnell, M.; Silber, J. H. (Ground-based and Airborne Instrumentation for Astronomy IX, 2022)

Overview of the DESI Milky Way Survey - Cooper, Andrew P.; Koposov, Sergey E.; Allende Prieto, Carlos; Manser, Christopher J.; Kizhuprakkat, Namitha; Myers, Adam D.; Dey, Arjun; Gaensicke, Boris T.; Li, Ting S.; Rockosi, Constance; Valluri, Monica; Najita, Joan; et al. (arXiv e-prints, 2022)
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - Cosmology and Nongalactic Astrophysics

Overview of the Instrumentation for the Dark Energy Spectroscopic Instrument - Abareshi, B.; Aguilar, J.; Ahlen, S.; Alam, Shadab; Alexander, David M.; Alfarsy, R.; Allen, L.; Allende Prieto, C.; Alves, O.; Ameel, J.; Armengaud, E.; Asorey, J.; et al. (\aj, 2022)
Keywords: 1174; 1554; 1558; 351; 799; Astronomical instrumentation; Astrophysics - Cosmology and Nongalactic Astrophysics; Astrophysics - Instrumentation and Methods for Astrophysics; dark energy; Optical telescopes; Spectrometers; Spectroscopy

Reconstructing Cosmological Initial Conditions from Late-Time Structure with Convolutional Neural Networks - Shallue, Christopher J.; Daniel J. Eisenstein (arXiv e-prints, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; Astrophysics - Instrumentation and Methods for Astrophysics

A Referee Primer for Early Career Astronomers - Ntampaka, Michelle; Bonaca, Ana; Bose, Sownak; Daniel J. Eisenstein; Hadzhiyska, Boryana; Mason, Charlotte; Nagai, Daisuke; Speagle, Joshua S. (arXiv e-prints, 2022)
Keywords: Astrophysics - Instrumentation and Methods for Astrophysics

A Referee Primer for Early Career Astronomers - Ntampaka, Michelle; Bonaca, Ana; Bose, Sownak; Daniel J. Eisenstein; Hadzhiyska, Boryana; Mason, Charlotte; Nagai, Daisuke; Speagle, Joshua S. (Bulletin of the American Astronomical Society, 2022)

SEGUE-2: Old Milky Way Stars Near and Far - Rockosi, Constance M.; Lee, Young Sun; Morrison, Heather L.; Yanny, Brian; Johnson, Jennifer A.; Lucatello, Sara; Sobeck, Jennifer; Beers, Timothy C.; Allende Prieto, Carlos; An, Deokkeun; Bizyaev, Dmitry; Blanton, Michael R.; et al. (\apjs, 2022)
Keywords: 1054; 1332; 1464; 1558; 224; Chemical abundances; Milky Way Galaxy; Radial Velocity; sky surveys; Spectroscopy

Self-similarity of k-nearest neighbour distributions in scale-free simulations - Garrison, Lehman H.; Abel, Tom; Daniel J. Eisenstein (\mnras, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; COSMOLOGY: THEORY; methods: numerical

The Seventeenth Data Release of the Sloan Digital Sky Surveys: Complete Release of MaNGA, MaStar, and APOGEE-2 Data - Abdurro'uf; Accetta, Katherine; Aerts, Conny; Silva Aguirre, V'ıctor; Ahumada, Romina; Ajgaonkar, Nikhil; Filiz Ak, N.; Alam, Shadab; Allende Prieto, Carlos; Almeida, Andrés; Anders, Friedrich; Anderson, Scott F.; et al. (\apjs, 2022)
Keywords: 1671; 1860; 83; Astronomy data acquisition; Astronomy databases; Astrophysics - Astrophysics of Galaxies; Astrophysics - Instrumentation and Methods for Astrophysics; surveys

The Spectroscopic Data Processing Pipeline for the Dark Energy Spectroscopic Instrument - Guy, J.; Bailey, S.; Kremin, A.; Alam, Shadab; Alexander, D. M.; Allende Prieto, C.; BenZvi, S.; Bolton, A. S.; Brooks, D.; Chaussidon, E.; Cooper, A. P.; Dawson, K.; et al. (arXiv e-prints, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; Astrophysics - Instrumentation and Methods for Astrophysics

Spectroscopy of four metal-poor galaxies beyond redshift ten - Curtis-Lake, Emma; Carniani, Stefano; Cameron, Alex; Charlot, Stephane; Jakobsen, Peter; Maiolino, Roberto; Bunker, Andrew; Witstok, Joris; Smit, Renske; Chevallard, Jacopo; Willott, Chris; Ferruit, Pierre; et al. (arXiv e-prints, 2022)
Keywords: Astrophysics - Astrophysics of Galaxies

Stringent \ensuremathσ₈ constraints from small-scale galaxy clustering using a hybrid MCMC + emulator framework - Sihan Yuan; Garrison, Lehman H.; Daniel J. Eisenstein; Wechsler, Risa H. (\mnras, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; cosmological parameters; galaxies: haloes; large-scale structure of Universe; methods: numerical; Methods: Statistical

Target Selection and Validation of DESI Emission Line Galaxies - Raichoor, A.; Moustakas, J.; Newman, Jeffrey A.; Karim, T.; Ahlen, S.; Alam, Shadab; Bailey, S.; Brooks, D.; Dawson, K.; de la Macorra, A.; de Mattia, A.; Dey, A.; et al. (arXiv e-prints, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

Target Selection and Validation of DESI Quasars - Chaussidon, Edmond; Yèche, Christophe; Palanque-Delabrouille, Nathalie; Alexander, David M.; Yang, Jinyi; Ahlen, Steven; Bailey, Stephen.; David Brooks; Cai, Zheng; Chabanier, Solène; Davis, Tamara M.; Dawson, Kyle; et al. (arXiv e-prints, 2022)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

VizieR Online Data Catalog: SEGUE-2 updated stellar parameter pipeline (Rockosi+, 2022) - Rockosi, C. M.; Sun, Lee Y.; Morrison, H. L.; Yanny, B.; Johnson, J. A.; Lucatello, S.; Sobeck, J.; Beers, T. C.; Allende Prieto, C.; An, D.; Bizyaev, D.; Blanton, M. R.; et al. (VizieR Online Data Catalog, 2022)
Keywords: Abundances: [Fe/H]; Clusters: globular; Milky Way; Radial velocities; Spectra: optical; surveys

The ABACUS cosmological N-body code - Garrison, Lehman H.; Daniel J. Eisenstein; Ferrer, Douglas; Maksimova, Nina A.; Pinto, Philip A. (MNRAS, 2021)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; COSMOLOGY: THEORY; methods: numerical

ABACUSSUMMIT: a massive set of high-accuracy, high-resolution N-body simulations - Maksimova, Nina A.; Garrison, Lehman H.; Daniel J. Eisenstein; Hadzhiyska, Boryana; Bose, Sownak; Satterthwaite, Thomas P. (MNRAS, 2021)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; COSMOLOGY: THEORY; methods: numerical

On the accuracy of common moment-based radiative transfer methods for simulating reionization - Wu, Xiaohan; McQuinn, Matthew; Eisenstein, Daniel (JCAP, 2021)
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - Cosmology and Nongalactic Astrophysics

Active Optical Control with Machine Learning: A Proof of Concept for the Vera C. Rubin Observatory - Yin, Jun E.; Daniel J. Eisenstein; Finkbeiner, Douglas P.; Stubbs, Christopher W.; Wang, Yue (Astronomical Journal, 2021)
Keywords: 1080; 1145; 1174; 1933; 1938; 799; 88; Astronomical instrumentation; Astronomical optics; Convolutional neural networks; Multiple mirror telescopes; Neural networks; Observational astronomy; Optical telescopes

Baryon acoustic oscillations in the projected cross-correlation function between the eBOSS DR16 quasars and photometric galaxies from the DESI Legacy Imaging Surveys - Zarrouk, Pauline; Rezaie, Mehdi; Raichoor, Anand; Ashley J. Ross; Alam, Shadab; Blum, Robert; Brookes, David; Chuang, Chia-Hsun; Cole, Shaun; Dawson, Kyle S.; Daniel J. Eisenstein; Kehoe, Robert; et al. (MNRAS, 2021)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; cosmology: observations; dark energy; distance scale

Characterizing the target selection pipeline for the Dark Energy Spectroscopic Instrument Bright Galaxy Survey - Ruiz-Macias, Omar; Zarrouk, Pauline; Cole, Shaun; Baugh, Carlton M.; Norberg, Peder; Lucey, John; Dey, Arjun; Daniel J. Eisenstein; Doel, Peter; Gaztañaga, Enrique; Hahn, ChangHoon; Kehoe, Robert; et al. (MNRAS, 2021)
Keywords: Astrophysics - Astrophysics of Galaxies; CATALOGUES; large-scale structure of Universe; surveys

The completed SDSS-IV extended Baryon Oscillation Spectroscopic Survey: BAO and RSD measurements from anisotropic clustering analysis of the quasar sample in configuration space between redshift 0.8 and 2.2 - Hou, Jiamin; Sánchez, Ariel G.; Ashley J. Ross; Smith, Alex; Neveux, Richard; Bautista, Julian; Burtin, Etienne; Zhao, Cheng; Scoccimarro, Román; Dawson, Kyle S.; de Mattia, Arnaud; de la Macorra, Axel; et al. (MNRAS, 2021)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; cosmology: dark energy; Cosmology: Distance Scale; COSMOLOGY: LARGE-SCALE STRUCTURE OF UNIVERSE; cosmology: observations; methods: data analysis; quasars: general

Constructing high-fidelity halo merger trees in AbacusSummit - Bose, Sownak; Daniel J. Eisenstein; Hadzhiyska, Boryana; Garrison, Lehman H.; Sihan Yuan (arXiv e-prints, 2021)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

The DESI $N$-body Simulation Project I: Testing the Robustness of Simulations for the DESI Dark Time Survey - Grove, Cameron; Chuang, Chia-Hsun; Chandrachani Devi, Ningombam; Garrison, Lehman; L'Huillier, Benjamin; Feng, Yu; Helly, John; Hernández-Aguayo, César; Alam, Shadab; Zhang, Hanyu; Yu, Yu; Cole, Shaun; et al. (arXiv e-prints, 2021)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

Evidence for galaxy assembly bias in BOSS CMASS redshift-space galaxy correlation function - Sihan Yuan; Hadzhiyska, Boryana; Bose, Sownak; Daniel J. Eisenstein; Guo, Hong (MNRAS, 2021)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; Dark matter; galaxies: haloes; gravitational lensing: weak; large-scale structure of Universe; METHODS: ANALYTICAL; Methods: Statistical

Extensions to models of the galaxy-halo connection - Hadzhiyska, Boryana; Bose, Sownak; Eisenstein, Daniel; Hernquist, Lars (MNRAS, 2021)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; COSMOLOGY: LARGE-SCALE STRUCTURE OF UNIVERSE; COSMOLOGY: THEORY; galaxies: haloes; methods: numerical

A fully Lagrangian, non-parametric bias model for dark-matter halos - Wu, Xiaohan; Munoz, Julian B.; Eisenstein, Daniel (arXiv e-prints, 2021)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

Galaxy assembly bias and large-scale distribution: a comparison between IllustrisTNG and a semi-analytic model - Hadzhiyska, Boryana; Liu, Sonya; Somerville, Rachel S.; Gabrielpillai, Austen; Bose, Sownak; Eisenstein, Daniel; Hernquist, Lars (MNRAS, 2021)
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - Cosmology and Nongalactic Astrophysics; COSMOLOGY: THEORY; Galaxies: Formation; galaxies: haloes; large-scale structure of Universe

The galaxy-halo connection of emission-line galaxies in IllustrisTNG - Hadzhiyska, Boryana; Tacchella, Sandro; Bose, Sownak; Daniel J. Eisenstein (MNRAS, 2021)
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - Cosmology and Nongalactic Astrophysics; COSMOLOGY: THEORY; galaxies: haloes; large-scale structure of Universe; methods: numerical

Good and proper: self-similarity of N-body simulations with proper force softening - Garrison, Lehman H.; Joyce, Michael; Daniel J. Eisenstein (MNRAS, 2021)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; COSMOLOGY: THEORY; methods: numerical

The high-redshift tail of stellar reionization in LCDM is beyond the reach of the low-\ensuremath\ell CMB - Wu, Xiaohan; McQuinn, Matthew; Eisenstein, Daniel; Iršič, Vid (MNRAS, 2021)
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - Cosmology and Nongalactic Astrophysics; cosmology: cosmic background radiation; cosmology: dark ages; first stars; reionization; stars: Population III

Quantifying resolution in cosmological N-body simulations using self-similarity - Joyce, Michael; Garrison, Lehman; Eisenstein, Daniel (MNRAS, 2021)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; large-scale structure of Universe; methods: numerical

The Seventeenth Data Release of the Sloan Digital Sky Surveys: Complete Release of MaNGA, MaStar and APOGEE-2 Data - Abdurro'uf; Accetta, Katherine; Aerts, Conny; Silva Aguirre, Victor; Ahumada, Romina; Ajgaonkar, Nikhil; Filiz Ak, N.; Alam, Shadab; Allende Prieto, Carlos; Almeida, Andres; Anders, Friedrich; Anderson, Scott F.; et al. (arXiv e-prints, 2021)
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - Instrumentation and Methods for Astrophysics

Small-scale clumping at recombination and the Hubble tension - Rashkovetskyi, Michael; Muñoz, Julian B.; Daniel J. Eisenstein; Dvorkin, Cora (Physical Review D, 2021)
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; High Energy Physics - Phenomenology

Testing dark matter halo properties using self-similarity - Leroy, M.; Garrison, L.; Eisenstein, D.; Joyce, M.; Maleubre, S. (MNRAS, 2021)
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - Cosmology and Nongalactic Astrophysics; large-scale structure of Universe; methods: numerical

Snowmass2021-Letter of Interest Large-Scale Structure at high redshift: a probe of fundamental physics - Dvorkin, Cora; Ferraro, Simone; Flauger, Raphael; Green, Daniel; White, Martin (2020)

Snowmass2021-Letter of Interest Theory and Computing Across LSST, DESI, and CMB-S4 - Bean, Rachel; Borrill, Julian; Carlstrom, John; Dawson, Kyle; Eisenstein, Daniel; Jain, Bhuvnesh (2020)

Preliminary Target Selection for the DESI Luminous Red Galaxy (LRG) Sample - Zhou, Rongpu; Newman, Jeffrey A.; Dawson, Kyle S.; Eisenstein, Daniel J.; Brooks, David D; Dey, Arjun; Dey, Biprateep; Duan, Yutong; Eftekharzadeh, Sarah; Gaztañaga, Enrique; others (Research Notes of the AAS, 2020)

Preliminary Target Selection for the DESI Quasar (QSO) Sample - Yèche, Christophe; Palanque-Delabrouille, Nathalie; Claveau, Charles-Antoine; Brooks, David D; Chaussidon, Edmond; Davis, Tamara M; Dawson, Kyle S.; Dey, Arjun; Duan, Yutong; Eftekharzadeh, Sarah; others (Research Notes of the AAS, 2020)

HST Grism-derived Forecasts for Future Galaxy Redshift Surveys - Bagley, Micaela B; Scarlata, Claudia; Mehta, Vihang; Teplitz, Harry; Baronchelli, Ivano; Eisenstein, Daniel J.; Pozzetti, Lucia; Cimatti, Andrea; Rutkowski, Michael; Wang, Yun; others (The Astrophysical Journal, 2020)

Preliminary Target Selection for the DESI Emission Line Galaxy (ELG) Sample - Raichoor, Anand; Eisenstein, Daniel J.; Karim, Tanveer; Newman, Jeffrey A.; Moustakas, John; Brooks, David D; Dawson, Kyle S.; Dey, Arjun; Duan, Yutong; Eftekharzadeh, Sarah; others (Research Notes of the AAS, 2020)

Preliminary Target Selection for the DESI Bright Galaxy Survey (BGS) - Ruiz-Macias, Omar; Zarrouk, Pauline; Cole, Shaun; Norberg, Peder; Baugh, Carlton; David Brooks; Dey, Arjun; Duan, Yutong; Eftekharzadeh, Sarah; Eisenstein, Daniel J.; others (Research Notes of the AAS, 2020)

Preliminary Target Selection for the DESI Milky Way Survey (MWS) - Allende Prieto, Carlos; Cooper, Andrew P; Dey, Arjun; Gänsicke, Boris T.; Koposov, Sergey E; Li, Ting; Manser, Christopher; Nidever, David L.; Rockosi, Constance; Wang, Mei-Yu; others (Research Notes of the AAS, 2020)

Can assembly bias explain the lensing amplitude of the BOSS CMASS sample in a Planck cosmology? - Sihan Yuan; Eisenstein, Daniel J.; Leauthaud, Alexie (Monthly Notices of the Royal Astronomical Society, 2020)

rascalc: a jackknife approach to estimating single-and multitracer galaxy covariance matrices - Philcox, Oliver HE; Eisenstein, Daniel J.; O’Connell, Ross; Wiegand, Alexander (Monthly Notices of the Royal Astronomical Society, 2020)

Validation of emission-line galaxies target selection algorithms for the Dark Energy Spectroscopic Instrument using the MMT Binospec - Karim, Tanveer; Lee, Jae H; Eisenstein, Daniel J.; Burtin, Etienne; Moustakas, John; Raichoor, Anand; Yèche, Christophe (Monthly Notices of the Royal Astronomical Society, 2020)

Computing the small-scale galaxy power spectrum and bispectrum in configuration space - Philcox, Oliver HE; Eisenstein, Daniel J. (Monthly Notices of the Royal Astronomical Society, 2020)

Cosmology with stacked cluster weak lensing and cluster–galaxy cross-correlations - Salcedo, Andrés N; Wibking, Benjamin D; Weinberg, David H.; Wu, Hao-Yi; Ferrer, Douglas; Eisenstein, Daniel; Pinto, Philip (Monthly Notices of the Royal Astronomical Society, 2020)

A Hybrid Deep Learning Approach to Cosmological Constraints from Galaxy Redshift Surveys - Ntampaka, Michelle; Eisenstein, Daniel J.; Sihan Yuan; Garrison, Lehman H (The Astrophysical Journal, 2020)

Cosmology with galaxy–galaxy lensing on non-perturbative scales: emulation method and application to BOSS LOWZ - Wibking, Benjamin D; Weinberg, David H.; Salcedo, Andrés N; Wu, Hao-Yi; Singh, Sukhdeep; Rodr{\'ıguez-Torres, Sergio; Garrison, Lehman H; Eisenstein, Daniel J. (Monthly Notices of the Royal Astronomical Society, 2020)

Limitations to the ‘basic’HOD model and beyond - Hadzhiyska, Boryana; Bose, Sownak; Eisenstein, Daniel; Hernquist, Lars; Spergel, David N. (Monthly Notices of the Royal Astronomical Society, 2020)

The Apache Point Observatory Galactic Evolution Experiment (APOGEE) Spectrographs - Wilson, J. C.; Hearty, F. R.; Skrutskie, M. F.; Majewski, S. R.; Holtzman, J. A.; Eisenstein, D.; J. Gunn; Blank, B.; Henderson, C.; Smee, S.; Nelson, M.; Nidever, D.; et al. (Publications of the Astronomical Society of the Pacific, 2019)
We describe the design and performance of the near-infrared (1.51-1.70μm), fiber-fed, multi-object (300 fibers), high resolution (R = λ/∆λ ̃22,500) spectrograph built for the Apache Point Observatory GalacticEvolution Experiment (APOGEE). APOGEE is a survey of ̃105 redgiant stars that systematically sampled all Milky Way populations(bulge, disk, and halo) to study the Galaxy’s chemical and kinematicalhistory. It was part of the Sloan Digital Sky Survey III (SDSS-III) from2011 to 2014 using the 2.5 m Sloan Foundation Telescope at Apache PointObservatory, New Mexico. The APOGEE-2 survey is now using thespectrograph as part of SDSS-IV, as well as a second spectrograph, aclose copy of the first, operating at the 2.5 m du Pont Telescope at LasCampanas Observatory in Chile. Although several fiber-fed, multi-object,high resolution spectrographs have been built for visual wavelengthspectroscopy, the APOGEE spectrograph is one of the first suchinstruments built for observations in the near-infrared. Theinstrument’s successful development was enabled by several keyinnovations, including a “gang connector” to allow simultaneousconnections of 300 fibers; hermetically sealed feedthroughs to allowfibers to pass through the cryostat wall continuously; the firstcryogenically deployed mosaic volume phase holographic grating; and alarge refractive camera that includes mono-crystalline silicon and fusedsilica elements with diameters as large as ̃400 mm. This paper containsa comprehensive description of all aspects of the instrument includingthe fiber system, optics and opto-mechanics, detector arrays, mechanicsand cryogenics, instrument control, calibration system, opticalperformance and stability, lessons learned, and design changes for thesecond instrument.
Keywords: Astrophysics - Instrumentation and Methods for Astrophysics

Application of the iterative reconstruction to simulated galaxy fields - Hada, Ryuichiro; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2019)
We apply an iterative reconstruction method to galaxy mocks in redshiftspace obtained from N-body simulations. Comparing the two-pointcorrelation functions for the reconstructed density field, we find thatalthough the performance is limited by shot noise and galaxy biascompared to the matter field, the iterative method can still reconstructthe initial linear density field from the galaxy field better than thestandard method both in real and in redshift space. Furthermore, theiterative method is able to reconstruct both the monopole and quadrupolemore precisely, unlike the standard method. We see that as the numberdensity of galaxies gets smaller, the performance of reconstruction getsworse due to the sparseness. However, the precision in the determinationof bias ({̃ }20{{ per cent}}) hardly impacts on the reconstructionprocesses.
Keywords: of Universe; Astrophysics - Cosmology and Nongalactic Astrophysics

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: evolution of higher-order correlations demonstrated with Minkowski functionals - Sullivan, James M.; Wiegand, Alexander; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2019)
We probe the higher-order galaxy clustering in the final data release ofthe Sloan Digital Sky Survey Baryon Oscillation Spectroscopic Survey(BOSS) using germ-grain Minkowski functionals (MFs). Our data selectioncontains 979 430 BOSS galaxies from both the Northern and SouthernGalactic Caps over the redshift range z = 0.2-0.6. We extract thehigher-order part of the MFs, detecting the deviation from the purelyGaussian case with χ ^2 ̃ O(10^3) on 24 degrees of freedom across theentire data selection. We measure significant redshift evolution in thehigher-order functionals for the first time. We find 15-35{{ per cent}}growth, depending on functional and scale, between our redshift binscentred at z = 0.325 and z = 0.525. We show that the structure inhigher-order correlations grows faster than that in the two-pointcorrelations, especially on small scales where the excess approaches afactor of 2. We demonstrate how this trend is generalizable by findinggood agreement of the data with a hierarchical model in which the higherorders grow faster than the lower-order correlations. We find that thenon-Gaussianity of the underlying dark matter field grows even fasterthan the one of the galaxies. Our method can be adapted to study theredshift evolution of the three-point and higher functions individually.
Keywords: of Universe; cosmology: observations

Decorrelating the errors of the galaxy correlation function with compact transformation matrices - Sihan Yuan; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2019)
Covariance matrix estimation is a persistent challenge for cosmology,often requiring a large number of synthetic mock catalogues. The off-diagonal components of the covariance matrix also make it difficult toshow representative error bars on the 2-point correlation function(2PCF) since errors computed from the diagonal values of the covariancematrix greatly underestimate the uncertainties. We develop a routine fordecorrelating the projected and anisotropic 2PCF with simple and scale-compact transformations on the 2PCF. These transformation matrices aremodelled after the Cholesky decomposition and the symmetric square rootof the Fisher matrix. Using mock catalogues, we show that thetransformed projected and anisotropic 2PCF recover the same structure asthe original 2PCF while producing largely decorrelated error bars.Specifically, we propose simple Cholesky-based transformation matricesthat suppress the off-diagonal covariances on the projected 2PCF by {̃ }95{{ per cent}} and that on the anisotropic 2PCF by {̃ } 87{{ percent}}. These transformations also serve as highly regularized models ofthe Fisher matrix, compressing the degrees of freedom so that one canfit for the Fisher matrix with a much smaller number of mocks.
Keywords: Astrophysics

A Deep Learning Approach to Galaxy Cluster X-Ray Masses - Ntampaka, M.; ZuHone, J.; Eisenstein, D.; Nagai, D.; Vikhlinin, A.; Hernquist, L.; Marinacci, F.; Nelson, D.; Pakmor, R.; Pillepich, A.; Torrey, P.; Vogelsberger, M. (The Astrophysical Journal, 2019)
We present a machine-learning (ML) approach for estimating galaxycluster masses from Chandra mock images. We utilize a ConvolutionalNeural Network (CNN), a deep ML tool commonly used in image recognitiontasks. The CNN is trained and tested on our sample of 7896 Chandra X-raymock observations, which are based on 329 massive clusters from the{\text{}}{IllustrisTNG} simulation. Our CNN learns from a low resolutionspatial distribution of photon counts and does not use spectralinformation. Despite our simplifying assumption to neglect spectralinformation, the resulting mass values estimated by the CNN exhibitsmall bias in comparison to the true masses of the simulated clusters(-0.02 dex) and reproduce the cluster masses with low intrinsic scatter,
Keywords: clusters; Astrophysics - Cosmology and Nongalactic Astrophysics

Emulating galaxy clustering and galaxy-galaxy lensing into the deeply non-linear regime: methodology, information, and forecasts - Wibking, Benjamin D.; Salcedo, Andrés N.; Weinberg, David H.; Garrison, Lehman H.; Ferrer, Douglas; Tinker, Jeremy; Eisenstein, Daniel; Metchnik, Marc; Pinto, Philip (Monthly Notices of the Royal Astronomical Society, 2019)
The combination of galaxy-galaxy lensing (GGL) with galaxy clustering isone of the most promising routes to determining the amplitude of matterclustering at low redshifts. We show that extending clustering+GGLanalyses from the linear regime down to {̃ } 0.5 h^{-1} Mpc scalesincreases their constraining power considerably, even aftermarginalizing over a flexible model of non-linear galaxy bias. Using agrid of cosmological N-body simulations, we construct a Taylor-expansionemulator that predicts the galaxy autocorrelation ξgg(r) andgalaxy-matter cross-correlation ξgm(r) as a function ofσ8, Ωm, and halo occupation distribution (HOD)parameters, which are allowed to vary with large-scale environment torepresent possible effects of galaxy assembly bias. We present forecastsfor a fiducial case that corresponds to BOSS LOWZ galaxy clustering andSDSS-depth weak lensing (effective source density ̃0.3arcmin-2). Using tangential shear and projected correlationfunction measurements over 0.5 ≤ r_ p ≤ 30 h^{-1} Mpc yields a 2 percent constraint on the parameter combination σ _8Ω _ m^{0.6}, a factorof two better than a constraint that excludes non-linear scales (r_ p> 2 h^{-1} Mpc, 4 h^{-1} Mpc for γt, wp). Muchof this improvement comes from the non-linear clustering information,which breaks degeneracies among HOD parameters. Increasing the effectivesource density to 3 arcmin-2 sharpens the constraint on σ _8Ω_ m^{0.6} by a further factor of two. With robust modelling into thenon-linear regime, low-redshift measurements of matter clustering at the1-per cent level with clustering+GGL alone are well within reach ofcurrent data sets such as those provided by the Dark Energy Survey.
Keywords: Astrophysics

Estimating covariance matrices for two- and three-point correlation function moments in Arbitrary Survey Geometries - Philcox, Oliver H. E.; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2019)
We present configuration-space estimators for the auto- and cross-covariance of two- and three-point correlation functions (2PCF and 3PCF)in general survey geometries. These are derived in the Gaussian limit(setting higher order correlation functions to zero), but for arbitrarynon-linear 2PCFs (which may be estimated from the survey itself), with ashot-noise rescaling parameter included to capture non-Gaussianity. Wegeneralize previous approaches to include Legendre moments via ageometry-correction function calibrated from measured pair and triplecounts. Making use of importance sampling and random particlecatalogues, we can estimate model covariances in fractions of the timerequired to do so with mocks, obtaining estimates with negligiblesampling noise in ̃10 (̃100) CPU-hours for the 2PCF (3PCF)autocovariance. We compare results to sample covariances from a suite ofBOSS DR12 mocks and find the matrices to be in good agreement, assuminga shot-noise rescaling parameter of 1.03 (1.20) for the 2PCF (3PCF). Toobtain strongest constraints on cosmological parameters, we must usemultiple statistics in concert; having robust methods to measure theircovariances at low computational cost is thus of great relevance toupcoming surveys.
Keywords: and Methods for Astrophysics

Galaxy-Galaxy lensing in HSC: Validation tests and the impact of heterogeneous spectroscopic training sets - Speagle, Joshua S.; Leauthaud, Alexie; Huang, Song; Bradshaw, Christopher P.; Ardila, Felipe; Capak, Peter L.; Daniel J. Eisenstein; Masters, Daniel C.; Mandelbaum, Rachel; More, Surhud; Simet, Melanie; Sifón, Cristóbal (Monthly Notices of the Royal Astronomical Society, 2019)
Although photometric redshifts (photo-z's) are crucial ingredients forcurrent and upcoming large-scale surveys, the high-quality spectroscopicredshifts currently available to train, validate, and test them aresubstantially non-representative in both magnitude and colour. Weinvestigate the nature and structure of this bias by tracking howobjects from a heterogeneous training sample contribute to photo-zpredictions as a function of magnitude and colour, and illustrate thatthe underlying redshift distribution at fixed colour can evolve stronglyas a function of magnitude. We then test the robustness of the galaxy-galaxy lensing signal in 120 deg2 of HSC-SSP DR1 data tospectroscopic completeness and photo-z biases, and find that theirimpacts are sub-dominant to current statistical uncertainties. Ourmethodology provides a framework to investigate how spectroscopicincompleteness can impact photo-z-based weak lensing predictions infuture surveys such as LSST and WFIRST.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

Generating approximate halo catalogues for blind challenges in precision cosmology - Garrison, Lehman H.; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2019)
We present a method for generating suites of dark matter halo catalogueswith only a few N-body simulations, focusing on making small changes tothe underlying cosmology of a simulation with high precision. In thecontext of blind challenges, this allows us to re-use a simulation bygiving it a new cosmology after the original cosmology is revealed.Starting with full N-body realizations of an original cosmology and atarget cosmology, we fit a transfer function that displaces haloes inthe original so that the galaxy/HOD power spectrum matches that of thetarget cosmology. This measured transfer function can then be applied toa new realization of the original cosmology to create a new realizationof the target cosmology. For a 1 per cent change in σ8, weachieve 0.1 per cent accuracy to k = 1 h Mpc^{-1} in the real-spacepower spectrum; this degrades to 0.3 per cent when the transfer functionis applied to a new realization. We achieve similar accuracy in theredshift-space monopole and quadrupole. In all cases, the result isbetter than the sample variance of our 1.1 h^{-1} Gpc simulation boxes.
Keywords: Cosmology and Nongalactic Astrophysics

A high-fidelity realization of the Euclid code comparison N-body simulation with ABACUS - Garrison, Lehman H.; Daniel J. Eisenstein; Pinto, Philip A. (Monthly Notices of the Royal Astronomical Society, 2019)
We present a high-fidelity realization of the cosmological N-bodysimulation from the Schneider et al. code comparison project. Thesimulation was performed with our ABACUSN-body code, which offers high-force accuracy, high performance, and minimal particle integrationerrors. The simulation consists of 20483 particles in a 500h^{-1} Mpc box for a particle mass of 1.2× 10^9 h^{-1} M_\odot with 10h^{-1} kpc spline softening. ABACUS executed 1052 global time-steps to z= 0 in 107 h on one dual-Xeon, dual-GPU node, for a mean rate of 23million particles per second per step. We find ABACUS is in goodagreement with RAMSES and PKDGRAV3 and less so with GADGET3. We validateour choice of time-step by halving the step size and find sub-percentdifferences in the power spectrum and 2PCF at nearly all measuredscales, with {\lt }0.3{{ per cent}} errors at k\lt 10 Mpc^{-1} h. Onlarge scales, ABACUS reproduces linear theory better than 0.01 per cent.Simulation snapshots are available athttp://nbody.rc.fas.harvard.edu/public/S2016.
Keywords: and Methods for Astrophysics; Physics - Computational Physics

Large covariance matrices: accurate models without mocks - O'Connell, Ross; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2019)
Covariance matrix estimation is a persistent challenge for cosmology. Wefocus on a class of model covariance matrices that can be generated withhigh accuracy and precision, using a tiny fraction of the computationalresources that would be required to achieve comparably precisecovariance matrices using mock catalogues. In previous work, the freeparameters in these models were determined using sample covariancematrices computed using a large number of mocks, but we demonstrate thatthose parameters can be estimated consistently and with good precisionby applying jackknife methods to a single survey volume. This enablesmodel covariance matrices that are calibrated from data alone, with noreference to mocks.
Keywords: - Cosmology and Nongalactic Astrophysics

Overview of the DESI Legacy Imaging Surveys - Dey, Arjun; Schlegel, David J.; Lang, Dustin; Blum, Robert; Burleigh, Kaylan; Fan, Xiaohui; Findlay, Joseph R.; Finkbeiner, Doug; Herrera, David; Juneau, Stéphanie; Landriau, Martin; Levi, Michael; et al. (The Astronomical Journal, 2019)
The DESI Legacy Imaging Surveys (<Ahref="http://legacysurvey.org/">http://legacysurvey.org/) are acombination of three public projects (the Dark Energy Camera LegacySurvey, the Beijing-Arizona Sky Survey, and the Mayall z-band LegacySurvey) that will jointly image ≈14,000 deg2 of theextragalactic sky visible from the northern hemisphere in three opticalbands (g, r, and z) using telescopes at the Kitt Peak NationalObservatory and the Cerro Tololo Inter-American Observatory. Thecombined survey footprint is split into two contiguous areas by theGalactic plane. The optical imaging is conducted using a unique strategyof dynamically adjusting the exposure times and pointing selectionduring observing that results in a survey of nearly uniform depth. Inaddition to calibrated images, the project is delivering a catalog,constructed by using a probabilistic inference-based approach toestimate source shapes and brightnesses. The catalog includes photometryfrom the grz optical bands and from four mid-infrared bands (at 3.4,4.6, 12, and 22 μm) observed by the Wide-field Infrared Survey Explorersatellite during its full operational lifetime. The project plans twopublic data releases each year. All the software used to generate thecatalogs is also released with the data. This paper provides an overviewof the Legacy Surveys project.
Keywords: Astrophysics

Revealing the galaxy-halo connection in IllustrisTNG - Bose, Sownak; Daniel J. Eisenstein; Hernquist, Lars; Pillepich, Annalisa; Nelson, Dylan; Marinacci, Federico; Springel, Volker; Vogelsberger, Mark (Monthly Notices of the Royal Astronomical Society, 2019)
We use the IllustrisTNG (TNG) simulations to explore the galaxy-haloconnection as inferred from state-of-the-art cosmological,magnetohydrodynamical simulations. With the high-mass resolution andlarge volume achieved by combining the 100 Mpc (TNG100) and 300 Mpc(TNG300) volumes, we establish the mean occupancy of central andsatellite galaxies and their dependence on the properties of the darkmatter haloes hosting them. We derive best-fitting HOD parameters fromTNG100 and TNG300 for target galaxy number densities of \bar{n}_g =0.032 and \bar{n}_g = 0.016 h^3 Mpc-3, respectively,corresponding to a minimum galaxy stellar mass of M_\star ̃ 1.9× 10^9and M_\star ̃ 3.5× 10^9 M_☉, respectively, in hosts more massive than10^{11} M_☉. Consistent with previous work, we find that haloes locatedin dense environments, with low concentrations, later formation times,and high angular momenta are richest in their satellite population. Atlow mass, highly concentrated haloes and those located in overdenseregions are more likely to contain a central galaxy. The degree ofenvironmental dependence is sensitive to the definition adopted for thephysical boundary of the host halo. We examine the extent to whichcorrelations between galaxy occupancy and halo properties areindependent and demonstrate that HODs predicted by halo mass andpresent-day concentration capture the qualitative dependence on theremaining halo properties. At fixed halo mass, concentration is a strongpredictor of the stellar mass of the central galaxy, which may play adefining role in the fate of the satellite population. The radialdistribution of satellite galaxies, which exhibits a universal formacross a wide range of host halo mass, is described accurately by thebest-fitting NFW density profile of their host haloes.
Keywords: Astrophysics; Astrophysics - Astrophysics of Galaxies

Testing the Detection Significance on the Large-scale Structure by a JWST Deep Field Survey - Hao Zhang; Daniel J. Eisenstein; Garrison, Lehman H.; Ferrer, Douglas W. (The Astrophysical Journal, 2019)
In preparation for deep extragalactic imaging with the James Webb SpaceTelescope, we explore the clustering of massive halos at z = 8 and 10using a large N-body simulation. We find that halos with masses of109-1011 h -1 M ☉, which arethose expected to host galaxies detectable with JWST, are highlyclustered with bias factors ranging from 5 to 30 depending strongly onmass, as well as on redshift and scale. This results in correlationlengths of 5-10 h -1 Mpc, similar to those of today’sgalaxies. Our results are based on a simulation of 130 billion particlesin a box of size 250 h -1 Mpc using our new high-accuracyABACUS simulation code, the corrections to cosmological initialconditions of Garrison et al., and the Planck 2015 cosmology. We usevariations between sub-volumes to estimate the detectability of theclustering. Because of the very strong interhalo clustering, we findthat a medium-sized survey with a transverse size of the order of 25 h-1 comoving Mpc (about 13′) may be able to detect theclustering of z = 8-10 galaxies with only 500-1000 survey objects if thegalaxies indeed occupy the most massive dark matter halos.
Keywords: large-scale structure of Universe

Tests of acoustic scale shifts in halo-based mock galaxy catalogues - Duan, Yutong; Eisenstein, Daniel (Monthly Notices of the Royal Astronomical Society, 2019)
We utilize mock catalogues from high-accuracy cosmological N-bodysimulations to quantify shifts in the recovery of the acoustic scalethat could potentially result from galaxy clustering bias. Therelationship between galaxies and dark matter haloes presents acomplicated source of systematic errors in modern redshift surveys,particularly when aiming to make cosmological measurements to sub-percent precision. Apart from a scalar, linear bias parameter accountingfor the density contrast ratio between matter tracers and the truematter distribution, other types of galaxy bias, such as assembly andvelocity biases, may also significantly alter clustering signals fromsmall to large scales. We create mocks based on generalized halooccupation populations of 36 periodic boxes from the ABACUSCOSMOSrelease, and test various biased models along with an unbiasedbase case in a total volume of 48 h^{-3} Gpc3. Tworeconstruction methods are applied to galaxy samples and the apparentacoustic scale is derived by fitting the two-point correlation functionmultipoles. With respect to the baseline, we find a 0.3 per cent shiftin the line-of-sight acoustic scale for one variation in the satellitegalaxy population, and we find a 0.7 per cent shift for an extreme levelof velocity bias of the central galaxies. All other bias models areconsistent with zero shift at the 0.2 per cent level afterreconstruction. We note that the bias models explored are relativelylarge variations, producing sizeable and likely distinguishable changesin small-scale clustering, the modelling of which would furthercalibrate the baryon acoustic oscillations standard ruler.
Keywords: Cosmology and Nongalactic Astrophysics

The Abacus Cosmos: A Suite of Cosmological N-body Simulations - Garrison, Lehman H.; Daniel J. Eisenstein; Ferrer, Douglas; Tinker, Jeremy L.; Pinto, Philip A.; Weinberg, David H. (The Astrophysical Journal Supplement Series, 2018)
We present a public data release of halo catalogs from a suite of 125cosmological N-body simulations from the ABACUS project. The simulationsspan 40 wCDM cosmologies centered on the Planck 2015 cosmology at twomass resolutions, 4 × 1010 h -1 M⊙ and 1 × 1010 h -1 M⊙, in 1.1 h -1 Gpc and 720 h-1 Mpc boxes, respectively. The boxes are phase-matchedto suppress sample variance and isolate cosmology dependence. Additionalvolume is available via 16 boxes of fixed cosmology and varied phase; afew boxes of single-parameter excursions from Planck 2015 are alsoprovided. Catalogs spanning z = 1.5 to 0.1 are available forfriends-of-friends and ROCKSTAR halo finders and include particlesubsamples. All data products are available at https://lgarrison.github.io/AbacusCosmos.
Keywords: large-scale structure of universe; methods: numerical

Analysing baryon acoustic oscillations in sparse spectroscopic samples via cross-correlation with dense photometry - Patej, A.; Eisenstein, D. J. (Monthly Notices of the Royal Astronomical Society, 2018)
We develop a formalism for measuring the cosmological distance scalefrom baryon acoustic oscillations (BAO) using the cross-correlation of asparse redshift survey with a denser photometric sample. This reducesthe shot noise that would otherwise affect the autocorrelation of thesparse spectroscopic map. As a proof of principle, we make the firston-sky application of this method to a sparse sample defined as the z> 0.6 tail of the Sloan Digital Sky Survey's (SDSS) BOSS/CMASS sampleof galaxies and a dense photometric sample from SDSS DR9. We find a2.8σ preference for the BAO peak in the cross-correlation at aneffective z = 0.64, from which we measure the angular diameter distanceDM(z = 0.64) = (2418 ± 73 Mpc)(rs/rs,fid). Accordingly, we expect that using this method to combinesparse spectroscopy with the deep, high-quality imaging that is just nowbecoming available will enable higher precision BAO measurements thanpossible with the spectroscopy alone.
Keywords: distance scale; large-scale structure of Universe

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: theoretical systematics and Baryon Acoustic Oscillations in the galaxy correlation function - Vargas-Magaña, Mariana; Ho, Shirley; Antonio J. Cuesta; O'Connell, Ross; Ashley J. Ross; Daniel J. Eisenstein; Will J. Percival; Niklas Grieb, Jan; Sánchez, Ariel G.; Tinker, Jeremy L.; Tojeiro, Rita; Beutler, Florian; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
We investigate the potential sources of theoretical systematics in theanisotropic Baryon Acoustic Oscillation (BAO) distance scalemeasurements from the clustering of galaxies in configuration spaceusing the final Data Release (DR12) of the Baryon OscillationSpectroscopic Survey (BOSS). We perform a detailed study of the impacton BAO measurements from choices in the methodology such as fiducialcosmology, clustering estimators, random catalogues, fitting templates,and covariance matrices. The theoretical systematic uncertainties in BAOparameters are found to be 0.002 in the isotropic dilation α and0.003 in the quadrupolar dilation ɛ. The leading source ofsystematic uncertainty is related to the reconstruction techniques.Theoretical uncertainties are sub-dominant compared with the statisticaluncertainties for BOSS survey, accounting 0.2σstat forα and 0.25σstat for ɛ(σα, stat ˜ 0.010 andσɛ, stat ˜ 0.012, respectively). We alsopresent BAO-only distance scale constraints from the anisotropicanalysis of the correlation function. Our constraints on the angulardiameter distance DA(z) and the Hubble parameter H(z),including both statistical and theoretical systematic uncertainties, are1.5 per cent and 2.8 per cent at zeff = 0.38, 1.4 per centand 2.4 per cent at zeff = 0.51, and 1.7 per cent and 2.6 percent at zeff = 0.61. This paper is part of a set thatanalyses the final galaxy clustering data set from BOSS. Themeasurements and likelihoods presented here are cross-checked with otherBAO analysis in Alam et al. The systematic error budget concerning themethodology on post-reconstruction BAO analysis presented here is usedin Alam et al. to produce the final cosmological constraints from BOSS.
Keywords: surveys; galaxies: distances and redshifts; cosmology: observations

The clustering of the SDSS-IV extended Baryon Oscillation Spectroscopic Survey DR14 quasar sample: first measurement of baryon acoustic oscillations between redshift 0.8 and 2.2 - Ata, Metin; Baumgarten, Falk; Bautista, Julian; Beutler, Florian; Bizyaev, Dmitry; Blanton, Michael R.; Blazek, Jonathan A.; Bolton, Adam S.; Brinkmann, Jonathan; Brownstein, Joel R.; Burtin, Etienne; Chuang, Chia-Hsun; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
We present measurements of the Baryon Acoustic Oscillation (BAO) scalein redshift-space using the clustering of quasars. We consider a sampleof 147 000 quasars from the extended Baryon Oscillation SpectroscopicSurvey (eBOSS) distributed over 2044 square degrees with redshifts 0.8< z < 2.2 and measure their spherically averaged clustering inboth configuration and Fourier space. Our observational data set and the1400 simulated realizations of the data set allow us to detect apreference for BAO that is greater than 2.8σ. We determine thespherically averaged BAO distance to z = 1.52 to 3.8 per cent precision:DV(z = 1.52) = 3843 ± 147(rd/rd,fid)Mpc. This is the first time the location of the BAO featurehas been measured between redshifts 1 and 2. Our result is fullyconsistent with the prediction obtained by extrapolating the Planck flatΛCDM best-fitting cosmology. All of our results are consistentwith basic large-scale structure (LSS) theory, confirming quasars to bea reliable tracer of LSS, and provide a starting point for numerouscosmological tests to be performed with eBOSS quasar samples. We combineour result with previous, independent, BAO distance measurements toconstruct an updated BAO distance-ladder. Using these BAO data alone andmarginalizing over the length of the standard ruler, we findΩΛ > 0 at 6.6σ significance whentesting a ΛCDM model with free curvature.
Keywords: cosmology: observations; dark energy; distance scale; large-scale structure of Universe

Constraining the baryon-dark matter relative velocity with the large-scale three-point correlation function of the SDSS BOSS DR12 CMASS galaxies - Slepian, Zachary; Daniel J. Eisenstein; Blazek, Jonathan A.; Brownstein, Joel R.; Chuang, Chia-Hsun; Gil-Marín, Héctor; Ho, Shirley; Francisco-Shu Kitaura; McEwen, Joseph E.; Will J. Percival; Ashley J. Ross; Rossi, Graziano; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
We search for a galaxy clustering bias due to a modulation of galaxynumber with the baryon-dark matter relative velocity resulting fromrecombination-era physics. We find no detected signal and place theconstraint bv < 0.01 on the relative velocity bias for theCMASS galaxies. This bias is an important potential systematic of baryonacoustic oscillation (BAO) method measurements of the cosmic distancescale using the two-point clustering. Our limit on the relative velocitybias indicates a systematic shift of no more than 0.3 per cent rms inthe distance scale inferred from the BAO feature in the BOSS two-pointclustering, well below the 1 per cent statistical error of thismeasurement. This constraint is the most stringent currently availableand has important implications for the ability of upcoming large-scalestructure surveys such as the Dark Energy Spectroscopic Instrument(DESI) to self-protect against the relative velocity as a possiblesystematic.
Keywords: cosmological parameters; cosmology: observations

Exploring the squeezed three-point galaxy correlation function with generalized halo occupation distribution models - Sihan Yuan; Daniel J. Eisenstein; Garrison, Lehman H. (Monthly Notices of the Royal Astronomical Society, 2018)
We present the GeneRalized ANd Differentiable Halo OccupationDistribution (GRAND-HOD) routine that generalizes the standard fiveparameter halo occupation distribution (HOD) model with varioushalo-scale physics and assembly bias. We describe the methodology offour different generalizations: satellite distribution generalization,velocity bias, closest approach distance generalization, and assemblybias. We showcase the signatures of these generalizations in the 2-pointcorrelation function (2PCF) and the squeezed 3-point correlationfunction (squeezed 3PCF). We identify generalized HOD prescriptions thatare nearly degenerate in the projected 2PCF and demonstrate that thesedegeneracies are broken in the redshift-space anisotropic 2PCF and thesqueezed 3PCF. We also discuss the possibility of identifyingdegeneracies in the anisotropic 2PCF and further demonstrate the extraconstraining power of the squeezed 3PCF on galaxy-halo connectionmodels. We find that within our current HOD framework, the anisotropic2PCF can predict the squeezed 3PCF better than its statistical error.This implies that a discordant squeezed 3PCF measurement could falsifythe particular HOD model space. Alternatively, it is possible thatfurther generalizations of the HOD model would open opportunities forthe squeezed 3PCF to provide novel parameter measurements. The GRAND-HODPYTHON package is publicly available athttps://github.com/SandyYuan/GRAND-HOD.
Keywords: methods: analytical; galaxies: haloes; (cosmology): dark matter; (cosmology): large-scale structure of Universe

The Fourteenth Data Release of the Sloan Digital Sky Survey: First Spectroscopic Data from the Extended Baryon Oscillation Spectroscopic Survey and from the Second Phase of the Apache Point Observatory Galactic Evolution Experiment - Abolfathi, Bela; Aguado, D. S.; Aguilar, Gabriela; Allende Prieto, Carlos; Almeida, Andres; Ananna, Tonima Tasnim; Anders, Friedrich; Anderson, Scott F.; Andrews, Brett H.; Anguiano, Borja; Aragón-Salamanca, Alfonso; Argudo-Fernández, Maria; et al. (The Astrophysical Journal Supplement Series, 2018)
The fourth generation of the Sloan Digital Sky Survey (SDSS-IV) has beenin operation since 2014 July. This paper describes the second datarelease from this phase, and the 14th from SDSS overall (making thisData Release Fourteen or DR14). This release makes the data taken bySDSS-IV in its first two years of operation (2014-2016 July)public. Like all previous SDSS releases, DR14 is cumulative, includingthe most recent reductions and calibrations of all data taken by SDSSsince the first phase began operations in 2000. New in DR14 is the firstpublic release of data from the extended Baryon OscillationSpectroscopic Survey; the first data from the second phase of the ApachePoint Observatory (APO) Galactic Evolution Experiment (APOGEE-2),including stellar parameter estimates from an innovative data-drivenmachine-learning algorithm known as “The Cannon” and almosttwice as many data cubes from the Mapping Nearby Galaxies at APO (MaNGA)survey as were in the previous release (N = 2812 in total). This paperdescribes the location and format of the publicly available data fromthe SDSS-IV surveys. We provide references to the important technicalpapers describing how these data have been taken (both targeting andobservation details) and processed for scientific use. The SDSS web site(www.sdss.org) has been updated forthis release and provides links to data downloads, as well as tutorialsand examples of data use. SDSS-IV is planning to continue to collectastronomical data until 2020 and will be followed by SDSS-V.
Keywords: atlases; catalogs; surveys

An iterative reconstruction of cosmological initial density fields - Hada, Ryuichiro; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2018)
We present an iterative method to reconstruct the linear-theory initialconditions from the late-time cosmological matter density field, withthe intent of improving the recovery of the cosmic distance scale fromthe baryon acoustic oscillations. We present tests using the dark matterdensity field in both real and redshift space generated from an N-bodysimulation. In redshift space at z = 0.5, we find that the reconstructeddisplacement field using our iterative method are more than 80 per centcorrelated with the true displacement field of the dark matter particleson scales k < 0.10 h Mpc-1. Furthermore, we show that thetwo-point correlation function of our reconstructed density fieldmatches that of the initial density field substantially better,especially on small scales (<40 h-1 Mpc). Ourredshift-space results are improved if we use an anisotropic smoothingso as to account for the reduced small-scale information along the lineof sight in redshift space.
Keywords: dark matter; distance scale; large-scale structure of Universe; cosmology:theory

The JWST Extragalactic Mock Catalog: Modeling Galaxy Populations from the UV through the Near-IR over 13 Billion Years of Cosmic History - Williams, Christina C.; Curtis-Lake, Emma; Hainline, Kevin N.; Chevallard, Jacopo; Robertson, Brant E.; Charlot, Stephane; Endsley, Ryan; Stark, Daniel P.; Willmer, Christopher N. A.; Alberts, Stacey; Amorin, Ricardo; Arribas, Santiago; et al. (The Astrophysical Journal Supplement Series, 2018)
We present an original phenomenological model to describe the evolutionof galaxy number counts, morphologies, and spectral energy distributionsacross a wide range of redshifts (0.2< z< 15) and stellar masses[{log}(M/M⊙ )≥slant 6]. Our model follows observedmass and luminosity functions of both star-forming and quiescentgalaxies, and reproduces the redshift evolution of colors, sizes, starformation, and chemical properties of the observed galaxy population.Unlike other existing approaches, our model includes a self-consistenttreatment of stellar and photoionized gas emission and dust attenuationbased on the BEAGLE tool. The mock galaxy catalogs generated with ournew model can be used to simulate and optimize extragalactic surveyswith future facilities such as the James Webb Space Telescope (JWST),and to enable critical assessments of analysis procedures,interpretation tools, and measurement systematics for both photometricand spectroscopic data. As a first application of this work, we makepredictions for the upcoming JWST Advanced Deep Extragalactic Survey(JADES), a joint program of the JWST/NIRCam and NIRSpec Guaranteed TimeObservations teams. We show that JADES will detect, with NIRCam imaging,1000s of galaxies at z ≳ 6, and 10s at z ≳ 10 atmAB≲ 30 (5σ) within the 236 arcmin2of the survey. The JADES data will enable accurate constraints on theevolution of the UV luminosity function at z > 8, and resolve thecurrent debate about the rate of evolution of galaxies at z ≳ 8.Ready-to-use mock catalogs and software to generate new realizations arepublicly available as the JAdes extraGalactic Ultradeep ArtificialRealizations (JAGUAR) package.
Keywords: galaxies: evolution; galaxies: high-redshift; galaxies: photometry

Overview of the Dark Energy Spectroscopic Instrument - Martini, Paul; Bailey, Stephen; Besuner, Robert W.; David Brooks; Doel, Peter; Edelstein, Jerry; Eisenstein, Daniel; Flaugher, Brenna; Gutierrez, Gaston; Harris, Stewart E.; Honscheid, Klaus; Jelinsky, Patrick; et al. (Ground-based and Airborne Instrumentation for Astronomy VII, 2018)
The Dark Energy Spectroscopic Instrument (DESI) is under construction tomeasure the expansion history of the Universe using the Baryon AcousticOscillation technique. The spectra of 35 million galaxies and quasarsover 14000 square degrees will be measured during the life of theexperiment. A new prime focus corrector for the KPNO Mayall telescopewill deliver light to 5000 fiber optic positioners. The fibers in turnfeed ten broad-band spectrographs. We present an overview of theinstrumentation, the main technical requirements and challenges, and thecurrent status of the project.

A practical computational method for the anisotropic redshift-space three-point correlation function - Slepian, Zachary; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2018)
We present an algorithm enabling computation of the anisotropicredshift-space galaxy three-point correlation function (3PCF) scaling asN2, with N the number of galaxies. Our previous work showedhow to compute the isotropic 3PCF with this scaling by expanding theradially binned density field around each galaxy in the survey intospherical harmonics and combining these coefficients to form multipolemoments. The N2 scaling occurred because this approach neverexplicitly required the relative angle between a galaxy pair about theprimary galaxy. Here, we generalize this work, demonstrating that in thepresence of azimuthally symmetric anisotropy produced by redshift-spacedistortions (RSD), the 3PCF can be described by two triangle sidelengths, two independent total angular momenta, and a spin. This basisfor the anisotropic 3PCF allows its computation with negligibleadditional work over the isotropic 3PCF. We also present the covariancematrix of the anisotropic 3PCF measured in this basis. Our algorithmtracks the full 5D redshift-space 3PCF, uses an accurate line of sightto each triplet, is exact in angle, and easily handles edge correction.It will enable use of the anisotropic large-scale 3PCF as a probe of RSDin current and upcoming large-scale redshift surveys.
Keywords: cosmology: observations; distance scale; large-scale structure of Universe

Redshift Evolution of Non-Gaussianity in Cosmic Large-Scale Structure - Sullivan, James; Wiegand, Alexander; Eisenstein, Daniel (American Astronomical Society Meeting Abstracts #231, 2018)
We probe the higher-order galaxy clustering in the final data release(DR12) of the Sloan Digital Sky Survey using germ-grain MinkowskiFunctionals (MFs). Our data selection contains 979,430 BOSS galaxiesfrom both the northern and southern galactic caps over the redshiftrange 0.2 - 0.6. We extract the higher-order parts of the MFs and finddeviations from the case without higher order MFs with chi-squaredvalues of order 1000 for 24 degrees of freedom across the entire dataselection. We show the MFs to be sensitive to contributions up to thefive-point correlation function across the entire data selection. Wemeasure significant redshift evolution in the higher-order functionalsfor the first time, with a percentage growth between redshift bins of

A Redshift-independent Efficiency Model: Star Formation and Stellar Masses in Dark Matter Halos at z ≳ 4 - Tacchella, Sandro; Bose, Sownak; Conroy, Charlie; Daniel J. Eisenstein; Johnson, Benjamin D. (The Astrophysical Journal, 2018)
We explore the connection between the UV luminosity functions (LFs) ofhigh-z galaxies and the distribution of stellar masses and starformation histories (SFHs) in their host dark matter halos. We provide abaseline for a redshift-independent star formation efficiency model towhich observations and models can be compared. Our model assigns a starformation rate (SFR) to each dark matter halo based on the growth rateof the halo and a redshift-independent star formation efficiency. Thedark matter halo accretion rate is obtained from a high-resolutionN-body simulation in order to capture the stochasticity in accretionhistories and to obtain spatial information for the distribution ofgalaxies. The halo mass dependence of the star formation efficiency iscalibrated at z = 4 by requiring a match to the observed UV LF at thisredshift. The model then correctly predicts the observed UV LF at z =5–10. We present predictions for the UV luminosity and stellarmass functions, JWST number counts, and SFHs. In particular, we find astellar-to-halo mass relation at z = 4–10 that scales with halomass at M h < 1011 M ⊙ as M⋆ ∝ M h 2, with anormalization that is higher than the relation inferred at z = 0. Theaverage SFRs increase as a function of time to z = 4, although there is
Keywords: cosmology: theory; galaxies: evolution; galaxies: formation; galaxies: high-redshift; stars: formation

They Might Be Giants: An Efficient Color-based Selection of Red Giant Stars - Conroy, Charlie; Bonaca, Ana; Naidu, Rohan P.; Daniel J. Eisenstein; Johnson, Benjamin D.; Dotter, Aaron; Finkbeiner, Douglas P. (The Astrophysical Journal Letters, 2018)
We present a color-based method for identifying red giants based on thePan-STARRS grz and WISE W1 and W2 photometry. We utilize a subsample ofbright stars with precise parallaxes from Gaia’s second datarelease (DR2) to verify that the color-based selection reliablyseparates dwarfs from giants. The selection is conservative in the sense
Keywords: Galaxy: halo; Galaxy: kinematics and dynamics

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: baryon acoustic oscillations in the Fourier space - Beutler, Florian; Seo, Hee-Jong; Ashley J. Ross; McDonald, Patrick; Saito, Shun; Bolton, Adam S.; Brownstein, Joel R.; Chuang, Chia-Hsun; Antonio J. Cuesta; Daniel J. Eisenstein; Font-Ribera, Andreu; Niklas Grieb, Jan; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We analyse the baryon acoustic oscillation (BAO) signal of the finalBaryon Oscillation Spectroscopic Survey (BOSS) data release (DR12). Ouranalysis is performed in the Fourier space, using the power spectrummonopole and quadrupole. The data set includes 1198 006 galaxies overthe redshift range 0.2 < z < 0.75. We divide this data set intothree (overlapping) redshift bins with the effective redshiftszeff = 0.38, 0.51 and 0.61. We demonstrate the reliability ofour analysis pipeline using N-body simulations as well as ˜1000MultiDark-Patchy mock catalogues that mimic the BOSS-DR12 targetselection. We apply density field reconstruction to enhance the BAOsignal-to-noise ratio. By including the power spectrum quadrupole we canseparate the line of sight and angular modes, which allows us toconstrain the angular diameter distance DA(z) and the Hubbleparameter H(z) separately. We obtain two independent 1.6 and 1.5 percent constraints on DA(z) and 2.9 and 2.3 per centconstraints on H(z) for the low (zeff = 0.38) and high(zeff = 0.61) redshift bin, respectively. We obtain twoindependent 1 and 0.9 per cent constraints on the angular averageddistance DV(z), when ignoring the Alcock-Paczynski effect.The detection significance of the BAO signal is of the order of 8σ(post-reconstruction) for each of the three redshift bins. Our resultsare in good agreement with the Planck prediction within Λ colddark matter. This paper is part of a set that analyses the final galaxyclustering data set from BOSS. The measurements and likelihoodspresented here are combined with others in Alam et al. to produce thefinal cosmological constraints from BOSS.
Keywords: gravitation; surveys; cosmological parameters; cosmology: observations; dark energy; large-scale structure of Universe

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: on the measurement of growth rate using galaxy correlation functions - Satpathy, Siddharth; Alam, Shadab; Ho, Shirley; White, Martin; Bahcall, Neta A.; Beutler, Florian; Brownstein, Joel R.; Chuang, Chia-Hsun; Daniel J. Eisenstein; Niklas Grieb, Jan; Kitaura, Francisco; Olmstead, Matthew D.; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We present a measurement of the linear growth rate of structure, f, fromthe Sloan Digital Sky Survey III (SDSS-III) Baryon OscillationSpectroscopic Survey (BOSS) Data Release 12 (DR12) using convolutionLagrangian perturbation theory (CLPT) with Gaussian streaming redshiftspace distortions (GSRSD) to model the two-point statistics of BOSSgalaxies in DR12. The BOSS-DR12 data set includes 1198 006 massivegalaxies spread over the redshift range 0.2 < z < 0.75. Thesegalaxy samples are categorized in three redshift bins. Using CLPT-GSRSDin our analysis of the combined sample of the three redshift bins, wereport measurements of fσ8 for the three redshift bins.We find fσ8 = 0.430 ± 0.054 at zeff =0.38, fσ8 = 0.452 ± 0.057 at zeff =0.51 and fσ8 = 0.457 ± 0.052 at zeff= 0.61. Our results are consistent with the predictions of PlanckΛ cold dark matter-general relativity. Our constraints on thegrowth rates of structure in the Universe at different redshifts serveas a useful probe, which can help distinguish between a model of theUniverse based on dark energy and models based on modified theories ofgravity. This paper is part of a set that analyses the final galaxyclustering data set from BOSS. The measurements and likelihoodspresented here are combined with others in Alam et al., to produce thefinal cosmological constraints from BOSS.
Keywords: galaxies: statistics; dark energy; large-scale structure of Universe

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: Cosmological implications of the Fourier space wedges of the final sample - Niklas Grieb, Jan; Sánchez, Ariel G.; Salazar-Albornoz, Salvador; Scoccimarro, Román; Crocce, Martín; Dalla Vecchia, Claudio; Montesano, Francesco; Gil-Marín, Héctor; Ashley J. Ross; Beutler, Florian; Rodríguez-Torres, Sergio; Chuang, Chia-Hsun; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We extract cosmological information from the anisotropic power-spectrummeasurements from the recently completed Baryon OscillationSpectroscopic Survey (BOSS), extending the concept of clustering wedgesto Fourier space. Making use of new fast-Fourier-transform-basedestimators, we measure the power-spectrum clustering wedges of the BOSSsample by filtering out the information of Legendre multipoles ℓ> 4. Our modelling of these measurements is based on novel approachesto describe non-linear evolution, bias and redshift-space distortions,which we test using synthetic catalogues based on large-volume N-bodysimulations. We are able to include smaller scales than in previousanalyses, resulting in tighter cosmological constraints. Using threeoverlapping redshift bins, we measure the angular-diameter distance, theHubble parameter and the cosmic growth rate, and explore thecosmological implications of our full-shape clustering measurements incombination with cosmic microwave background and Type Ia supernova data.Assuming a Λ cold dark matter (ΛCDM) cosmology, weconstrain the matter density to Ω M=0.311_{-0.010}^{+0.009} and the Hubble parameter to H_0 =67.6_{-0.6}^{+0.7} km s^{-1 Mpc^{-1}}, at a confidence level of 68 percent. We also allow for non-standard dark energy models andmodifications of the growth rate, finding good agreement with theΛCDM paradigm. For example, we constrain the equation-of-stateparameter to w = -1.019_{-0.039}^{+0.048}. This paper is part of a setthat analyses the final galaxy-clustering data set from BOSS. Themeasurements and likelihoods presented here are combined with others inAlam et al. to produce the final cosmological constraints from BOSS.
Keywords: cosmology: observations; cosmological parameters; dark energy; large-scale structure of Universe

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: observational systematics and baryon acoustic oscillations in the correlation function - Ashley J. Ross; Beutler, Florian; Chuang, Chia-Hsun; Pellejero-Ibanez, Marcos; Seo, Hee-Jong; Vargas-Magaña, Mariana; Antonio J. Cuesta; Will J. Percival; Burden, Angela; Sánchez, Ariel G.; Niklas Grieb, Jan; Reid, Beth; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We present baryon acoustic oscillation (BAO) scale measurementsdetermined from the clustering of 1.2 million massive galaxies withredshifts 0.2 < z < 0.75 distributed over 9300 deg2, asquantified by their redshift-space correlation function. In order tofacilitate these measurements, we define, describe, and motivate theselection function for galaxies in the final data release (DR12) of theSDSS III Baryon Oscillation Spectroscopic Survey (BOSS). This includesthe observational footprint, masks for image quality and Galacticextinction, and weights to account for density relationships intrinsicto the imaging and spectroscopic portions of the survey. We simulate theobserved systematic trends in mock galaxy samples and demonstrate thatthey impart no bias on BAO scale measurements and have a minor impact onthe recovered statistical uncertainty. We measure transverse and radialBAO distance measurements in 0.2 < z < 0.5, 0.5 < z < 0.75,and (overlapping) 0.4 < z < 0.6 redshift bins. In each redshiftbin, we obtain a precision that is 2.7 per cent or better on the radialdistance and 1.6 per cent or better on the transverse distance. Thecombination of the redshift bins represents 1.8 per cent precision onthe radial distance and 1.1 per cent precision on the transversedistance. This paper is part of a set that analyses the final galaxyclustering data set from BOSS. The measurements and likelihoodspresented here are combined with others in Alam et al. to produce thefinal cosmological constraints from BOSS.
Keywords: cosmology: observations; large-scale structure of Universe

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: towards a computationally efficient analysis without informative priors - Pellejero-Ibanez, Marcos; Chuang, Chia-Hsun; Rubiño-Martín, J. A.; Antonio J. Cuesta; Wang, Yuting; Zhao, Gongbo; Ashley J. Ross; Rodríguez-Torres, Sergio; Prada, Francisco; Slosar, Anže; Vazquez, Jose A.; Alam, Shadab; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We develop a new computationally efficient methodology calleddouble-probe analysis with the aim of minimizing informative priors(those coming from extra probes) in the estimation of cosmologicalparameters. Using our new methodology, we extract the dark energymodel-independent cosmological constraints from the joint data sets ofthe Baryon Oscillation Spectroscopic Survey (BOSS) galaxy sample andPlanck cosmic microwave background (CMB) measurements. We measure themean values and covariance matrix of {R, la,Ωbh2, ns, log(As),Ωk, H(z), DA(z),f(z)σ8(z)}, which give an efficient summary of thePlanck data and two-point statistics from the BOSS galaxy sample. TheCMB shift parameters are R=√{Ω _m H_0^2} r(z_*) andla = πr(z*)/rs(z*), wherez* is the redshift at the last scattering surface, andr(z*) and rs(z*) denote our comovingdistance to the z* and sound horizon at z*,respectively; Ωb is the baryon fraction at z = 0. Thisapproximate methodology guarantees that we will not need to putinformative priors on the cosmological parameters that galaxy clusteringis unable to constrain, I.e. Ωbh2 andns. The main advantage is that the computational timerequired for extracting these parameters is decreased by a factor of 60with respect to exact full-likelihood analyses. The results obtainedshow no tension with the flat Λ cold dark matter (ΛCDM)cosmological paradigm. By comparing with the full-likelihood exactanalysis with fixed dark energy models, on one hand we demonstrate thatthe double-probe method provides robust cosmological parameterconstraints that can be conveniently used to study dark energy models,and on the other hand we provide a reliable set of measurements assumingdark energy models to be used, for example, in distance estimations. Weextend our study to measure the sum of the neutrino mass using differentmethodologies, including double-probe analysis (introduced in thisstudy), full-likelihood analysis and single-probe analysis. Fromfull-likelihood analysis, we obtain Σmν < 0.12(68 per cent), assuming ΛCDM and Σmν <0.20 (68 per cent) assuming owCDM. We also find that there is degeneracybetween observational systematics and neutrino masses, which suggeststhat one should take great care when estimating these parameters in thecase of not having control over the systematics of a given sample.
Keywords: cosmological parameters; distance scale; large-scale structure of Universe; cosmology: observations

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: combining correlated Gaussian posterior distributions - Sánchez, Ariel G.; Niklas Grieb, Jan; Salazar-Albornoz, Salvador; Alam, Shadab; Beutler, Florian; Ashley J. Ross; Brownstein, Joel R.; Chuang, Chia-Hsun; Antonio J. Cuesta; Daniel J. Eisenstein; Francisco-Shu Kitaura; Will J. Percival; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
The cosmological information contained in anisotropic galaxy clusteringmeasurements can often be compressed into a small number of parameterswhose posterior distribution is well described by a Gaussian. We presenta general methodology to combine these estimates into a single set ofconsensus constraints that encode the total information of theindividual measurements, taking into account the full covariance betweenthe different methods. We illustrate this technique by applying it tocombine the results obtained from different clustering analyses,including measurements of the signature of baryon acoustic oscillationsand redshift-space distortions, based on a set of mock catalogues of thefinal SDSS-III Baryon Oscillation Spectroscopic Survey (BOSS). Ourresults show that the region of the parameter space allowed by theconsensus constraints is smaller than that of the individual methods,highlighting the importance of performing multiple analyses on galaxysurveys even when the measurements are highly correlated. This paper ispart of a set that analyses the final galaxy clustering data set fromBOSS. The methodology presented here is used in Alam et al. to producethe final cosmological constraints from BOSS.
Keywords: cosmological parameters; large-scale structure of Universe

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: tomographic BAO analysis of DR12 combined sample in Fourier space - Zhao, Gong-bo; Wang, Yuting; Saito, Shun; Wang, Dandan; Ashley J. Ross; Beutler, Florian; Niklas Grieb, Jan; Chuang, Chia-Hsun; Francisco-Shu Kitaura; Rodriguez-Torres, Sergio; Will J. Percival; Brownstein, Joel R.; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We perform a tomographic baryon acoustic oscillations (BAO) analysisusing the monopole, quadrupole and hexadecapole of the redshift-spacegalaxy power spectrum measured from the pre-reconstructed combinedgalaxy sample of the completed Sloan Digital Sky Survey BaryonOscillation Spectroscopic Survey (BOSS) Data Release12 covering theredshift range of 0.20 < z < 0.75. By allowing for overlap betweenneighbouring redshift slices, we successfully obtained the isotropic andanisotropic BAO distance measurements within nine redshift slices to aprecision of 1.5-3.4 per cent for DV/rd, 1.8-4.2per cent for DA/rd and 3.7-7.5 per cent for Hrd, depending on effective redshifts. We provide our BAOmeasurement of DA/rd and H rd with thefull covariance matrix, which can be used for cosmological implications.Our measurements are consistent with those presented in Alam et al., inwhich the BAO distances are measured at three effective redshifts. Weconstrain dark energy parameters using our measurements and find animprovement of the Figure-of-Merit of dark energy in general due to thetemporal BAO information resolved. This paper is a part of a set thatanalyses the final galaxy clustering data set from BOSS.
Keywords: galaxies: distances and redshifts; cosmological parameters; cosmology: observations; dark energy; distance scale; large-scale structure of Universe

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: tomographic BAO analysis of DR12 combined sample in configuration space - Wang, Yuting; Zhao, Gong-bo; Chuang, Chia-Hsun; Ashley J. Ross; Will J. Percival; Gil-Marín, Héctor; Antonio J. Cuesta; Francisco-Shu Kitaura; Rodriguez-Torres, Sergio; Brownstein, Joel R.; Daniel J. Eisenstein; Ho, Shirley; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We perform a tomographic baryon acoustic oscillations (BAOs) analysisusing the two-point galaxy correlation function measured from thecombined sample of Baryon Oscillation Spectroscopic Survey Data Release12 (BOSS DR12), which covers the redshift range of 0.2 < z < 0.75.Upon splitting the sample into multiple overlapping redshift slices toextract the redshift information of galaxy clustering, we obtain ameasurement of DA(z)/rd and H(z)rd atnine effective redshifts with the full covariance matrix calibratedusing MultiDark-Patchy mock catalogues. Using the reconstructed galaxycatalogues, we obtain the precision of 1.3-2.2 per cent forDA(z)/rd and 2.1-6.0 per cent forH(z)rd. To quantify the gain from the tomographicinformation, we compare the constraints on the cosmological parametersusing our nine-bin BAO measurements, the consensus three-bin BAO andredshift space distortion measurements at three effective redshifts inAlam et al., and the non-tomographic (one-bin) BAO measurement at asingle effective redshift. Comparing the nine-bin with one-binconstraint result, it can improve the dark energy Figure of Merit by afactor of 1.24 for the Chevallier-Polarski-Linder parametrization forequation-of-state parameter wDE. The errors of w0and wa from nine-bin constraints are slightly improved whencompared to the three-bin constraint result.
Keywords: dark energy; distance scale

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: cosmic flows and cosmic web from luminous red galaxies - Ata, Metin; Francisco-Shu Kitaura; Chuang, Chia-Hsun; Rodríguez-Torres, Sergio; Angulo, Raul E.; Ferraro, Simone; Gil-Marín, Hector; McDonald, Patrick; Hernández Monteagudo, Carlos; Müller, Volker; Yepes, Gustavo; Autefage, Mathieu; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We present a Bayesian phase-space reconstruction of the cosmiclarge-scale matter density and velocity fields from the Sloan DigitalSky Survey-III Baryon Oscillations Spectroscopic Survey Data Release 12CMASS galaxy clustering catalogue. We rely on a given Λ cold darkmatter cosmology, a mesh resolution in the range of 6-10 h-1Mpc, and a lognormal-Poisson model with a redshift-dependent non-linearbias. The bias parameters are derived from the data and a generalrenormalized perturbation theory approach. We use combined Gibbs andHamiltonian sampling, implemented in the argo code, to iterativelyreconstruct the dark matter density field and the coherent peculiarvelocities of individual galaxies, correcting hereby for coherentredshift space distortions. Our tests relying on accurate N-body-basedmock galaxy catalogues show unbiased real space power spectra of thenon-linear density field up to k ˜ 0.2 h Mpc-1, andvanishing quadrupoles down to r ˜ 20 h-1 Mpc. We alsodemonstrate that the non-linear cosmic web can be obtained from thetidal field tensor based on the Gaussian component of the reconstructeddensity field. We find that the reconstructed velocities have astatistical correlation coefficient compared to the true velocities ofeach individual light-cone mock galaxy of r ˜ 0.68 including about10 per cent of satellite galaxies with virial motions (about r = 0.75without satellites). The power spectra of the velocity divergence agreewell with theoretical predictions up to k ˜ 0.2 h Mpc-1.This work will be especially useful to improve, for example, baryonacoustic oscillation reconstructions, kinematic Sunyaev-Zeldovich,integrated Sachs-Wolfe measurements or environmental studies.
Keywords: methods: numerical; catalogues; galaxies: statistics; cosmology: theory; large-scale structure of Universe

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: Cosmological implications of the configuration-space clustering wedges - Sánchez, Ariel G.; Scoccimarro, Román; Crocce, Martín; Niklas Grieb, Jan; Salazar-Albornoz, Salvador; Dalla Vecchia, Claudio; Lippich, Martha; Beutler, Florian; Brownstein, Joel R.; Chuang, Chia-Hsun; Daniel J. Eisenstein; Francisco-Shu Kitaura; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We explore the cosmological implications of anisotropic clusteringmeasurements in configuration space of the final galaxy samples fromData Release 12 of the Sloan Digital Sky Survey III Baryon OscillationSpectroscopic Survey. We implement a new detailed modelling of theeffects of non-linearities, bias and redshift-space distortions that canbe used to extract unbiased cosmological information from ourmeasurements for scales s ≳ 20 h-1 Mpc. We combined theinformation from Baryon Oscillation Spectroscopic Survey (BOSS) with thelatest cosmic microwave background (CMB) observations and Type Iasupernovae samples and found no significant evidence for a deviationfrom the Λ cold dark matter (ΛCDM) cosmological model. Inparticular, these data sets can constrain the dark energyequation-of-state parameter to wDE = -0.996 ± 0.042when to be assumed time independent, the curvature of the Universe toΩk = -0.0007 ± 0.0030 and the sum of theneutrino masses to ∑mν < 0.25 eV at 95 per centconfidence levels. We explore the constraints on the growth rate ofcosmic structures assuming f(z) =Ωm(z)γ and obtain γ = 0.609± 0.079, in good agreement with the predictions of generalrelativity of γ = 0.55. We compress the information of ourclustering measurements into constraints on the parameter combinationsDV(z)/rd, FAP(z) andfσ8(z) at zeff = 0.38, 0.51 and 0.61 withtheir respective covariance matrices and find good agreement with thepredictions for these parameters obtained from the best-fittingΛCDM model to the CMB data from the Planck satellite. This paperis part of a set that analyses the final galaxy clustering data set fromBOSS. The measurements and likelihoods presented here are combined withothers by Alam et al. to produce the final cosmological constraints fromBOSS.
Keywords: cosmological parameters; large-scale structure of Universe

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: anisotropic galaxy clustering in Fourier space - Beutler, Florian; Seo, Hee-Jong; Saito, Shun; Chuang, Chia-Hsun; Antonio J. Cuesta; Daniel J. Eisenstein; Gil-Marín, Héctor; Niklas Grieb, Jan; Hand, Nick; Francisco-Shu Kitaura; Modi, Chirag; Robert C. Nichol; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We investigate the anisotropic clustering of the Baryon OscillationSpectroscopic Survey (BOSS) Data Release 12 sample, which consists of1198 006 galaxies in the redshift range 0.2 < z < 0.75 and a skycoverage of 10 252 deg2. We analyse this data set in Fourierspace, using the power-spectrum multipoles to measure redshift-spacedistortions simultaneously with the Alcock-Paczynski effect and thebaryon acoustic oscillation scale. We include the power-spectrummonopole, quadrupole and hexadecapole in our analysis and compare ourmeasurements with a perturbation-theory-based model, while properlyaccounting for the survey window function. To evaluate the reliabilityof our analysis pipeline, we participate in a mock challenge, whichresults in systematic uncertainties significantly smaller than thestatistical uncertainties. While the high-redshift constraint onfσ8 at zeff = 0.61 indicates a small(˜1.4σ) deviation from the prediction of the PlanckΛCDM (Λ cold dark matter) model, the low-redshiftconstraint is in good agreement with Planck ΛCDM. This paper ispart of a set that analyses the final galaxy clustering data set fromBOSS. The measurements and likelihoods presented here are combined withothers in Alam et al. to produce the final cosmological constraints fromBOSS.
Keywords: gravitation; surveys; cosmological parameters; cosmology: observations; dark energy; large-scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: higher order correlations revealed by germ-grain Minkowski functionals - Wiegand, Alexander; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2017)
We probe the higher order clustering of the galaxies in the final datarelease (DR12) of the Sloan Digital Sky Survey Baryon OscillationSpectroscopic Survey (BOSS), using the method of germ-grain Minkowskifunctionals (MFs). Our sample consists of 410 615 BOSS galaxies from thenorthern Galactic cap in the redshift range 0.450-0.595. We show the MFsto be sensitive to contributions up to the six-point correlationfunction for this data set. We ensure with a custom angular mask thatthe results are more independent of boundary effects than in previousanalyses of this type. We extract the higher order part of the MFs andquantify the difference to the case without higher order correlations.The resulting χ2 value of over 10 000 for a modest numberof degrees of freedom, O(200), indicates a 100σ deviation anddemonstrates that we have a highly significant signal of thenon-Gaussian contributions to the galaxy distribution. This statisticalpower can be useful in testing models with differing higher ordercorrelations. Comparing the galaxy data to the quick particle mesh andMultiDark(MD)-Patchy mocks, we find that the latter better describes theobserved structure. From an order-by-order decomposition, we expectthat, for example, already a reduction of the amplitude of the MD-Patchymock power spectrum by 5 per cent would remove the remaining tension.
Keywords: methods: data analysis; methods: statistical; cosmology: observations; large-scale structure of Universe

The Color and Stellar Mass Dependence of Small-scale Galaxy Clustering in SDSS-III BOSS - Law-Smith, Jamie; Daniel J. Eisenstein (The Astrophysical Journal, 2017)
We measure the color and stellar mass dependence of clustering inspectroscopic galaxies at 0.6 < z < 0.65 using data from theBaryon Oscillation Spectroscopic Survey component of the Sloan DigitalSky Survey. We greatly increase the statistical precision of ourclustering measurements by using the cross-correlation of 66,657spectroscopic galaxies to a sample of 6.6 million fainter photometricgalaxies. The clustering amplitude w(R) is measured as the ratio of themean excess number of photometric galaxies found within a specifiedradius annulus around a spectroscopic galaxy to that from a randomphotometric galaxy distribution. We recover many of the familiar trendsat high signal-to-noise ratio. We find the ratio of the clusteringamplitudes of red and blue massive galaxies to bewred/{w}{blue}=1.92+/- 0.11 in our smallestannulus of 75-125 kpc. At our largest radii (2-4 Mpc), wefind {w}{red}/{w}{blue}=1.24+/- 0.05. Red galaxiestherefore have denser environments than their blue counterparts at z˜ 0.625, and this effect increases with decreasing radius.Irrespective of color, we find that w(R) does not obey a simplepower-law relation with radius, showing a dip around 1 Mpc. Holdingstellar mass fixed, we find a clear differentiation between clusteringin red and blue galaxies, showing that clustering is not solelydetermined by stellar mass. Holding color fixed, we find that clusteringincreases with stellar mass, especially for red galaxies at small scales(more than a factor of 2 effect over 0.75 dex in stellar mass).
Keywords: cosmology: observations; galaxies: evolution; galaxies: halos; large-scale structure of universe; methods: statistical

Deriving photometric redshifts using fuzzy archetypes and self-organizing maps - I. Methodology - Speagle, Joshua S.; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2017)
We propose a method to substantially increase the flexibility and powerof template fitting-based photometric redshifts by transforming a largenumber of galaxy spectral templates into a corresponding collection of'fuzzy archetypes' using a suitable set of perturbative priors designedto account for empirical variation in dust attenuation and emission-linestrengths. To bypass widely separated degeneracies in parameter space(e.g. the redshift-reddening degeneracy), we train self-organizing maps(SOMs) on large 'model catalogues' generated from Monte Carlo samplingof our fuzzy archetypes to cluster the predicted observables in atopologically smooth fashion. Subsequent sampling over the SOM thenallows full reconstruction of the relevant probability distributionfunctions (PDFs). This combined approach enables the multimodalexploration of known variation among galaxy spectral energydistributions with minimal modelling assumptions. We demonstrate thepower of this approach to recover full redshift PDFs using discreteMarkov chain Monte Carlo sampling methods combined with SOMs constructedfrom Large Synoptic Survey Telescope ugrizY and Euclid YJH mockphotometry.
Keywords: methods: statistical; techniques: photometric; galaxies: distances and redshifts

Deriving photometric redshifts using fuzzy archetypes and self-organizing maps - II. Implementation - Speagle, Joshua S.; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2017)
With an eye towards the computational requirements of future large-scalesurveys such as Euclid and Large Synoptic Survey Telescope (LSST) thatwill require photometric redshifts (photo-z's) for ≳ 109objects, we investigate a variety of ways that 'fuzzy archetypes' can beused to improve photometric redshifts and explore their respectivestatistical interpretations. We characterize their relative performanceusing an idealized LSST ugrizY and Euclid YJH mock catalogue of 10 000objects spanning z = 0-6 at Y = 24 mag. We find most schemes are able torobustly identify redshift probability distribution functions that aremultimodal and/or poorly constrained. Once these objects are flagged andremoved, the results are generally in good agreement with the strictaccuracy requirements necessary to meet Euclid weak lensing goals formost redshifts between 0.8 ≲ z ≲ 2. These results demonstratethe statistical robustness and flexibility that can be gained bycombining template-fitting and machine-learning methods and provideuseful insights into how astronomers can further exploit thecolour-redshift relation.
Keywords: methods: statistical; techniques: photometric; galaxies: distances and redshifts

Detection of baryon acoustic oscillation features in the large-scale three-point correlation function of SDSS BOSS DR12 CMASS galaxies - Slepian, Zachary; Daniel J. Eisenstein; Brownstein, Joel R.; Chuang, Chia-Hsun; Gil-Marín, Héctor; Ho, Shirley; Francisco-Shu Kitaura; Will J. Percival; Ashley J. Ross; Rossi, Graziano; Seo, Hee-Jong; Slosar, Anže; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We present the large-scale three-point correlation function (3PCF) ofthe Sloan Digital Sky Survey DR12 Constant stellar Mass (CMASS) sampleof 777 202 Luminous Red Galaxies, the largest-ever sample used for a3PCF or bispectrum measurement. We make the first high-significance(4.5σ) detection of baryon acoustic oscillations (BAO) in the3PCF. Using these acoustic features in the 3PCF as a standard ruler, wemeasure the distance to z = 0.57 to 1.7 per cent precision (statisticalplus systematic). We find DV = 2024 ± 29 Mpc (stat)± 20 Mpc (sys) for our fiducial cosmology (consistent with Planck2015) and bias model. This measurement extends the use of the BAOtechnique from the two-point correlation function (2PCF) and powerspectrum to the 3PCF and opens an avenue for deriving additionalcosmological distance information from future large-scale structureredshift surveys such as DESI. Our measured distance scale from the 3PCFis fairly independent from that derived from the pre-reconstruction 2PCFand is equivalent to increasing the length of BOSS by roughly 10 percent; reconstruction appears to lower the independence of the distancemeasurements. Fitting a model including tidal tensor bias yields amoderate-significance (2.6σ) detection of this bias with a valuein agreement with the prediction from local Lagrangian biasing.
Keywords: cosmology: observations; distance scale; large-scale structure of Universe

The large-scale three-point correlation function of the SDSS BOSS DR12 CMASS galaxies - Slepian, Zachary; Daniel J. Eisenstein; Beutler, Florian; Chuang, Chia-Hsun; Antonio J. Cuesta; Ge, Jian; Gil-Marín, Héctor; Ho, Shirley; Francisco-Shu Kitaura; Cameron K. McBride; Robert C. Nichol; Will J. Percival; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report a measurement of the large-scale three-point correlationfunction of galaxies using the largest data set for this purpose todate, 777 202 luminous red galaxies in the Sloan Digital Sky SurveyBaryon Acoustic Oscillation Spectroscopic Survey (SDSS BOSS) DR12 CMASSsample. This work exploits the novel algorithm of Slepian &Eisenstein to compute the multipole moments of the 3PCF in O(N^2) time,with N the number of galaxies. Leading-order perturbation theory modelsthe data well in a compressed basis where one triangle side isintegrated out. We also present an accurate and computationallyefficient means of estimating the covariance matrix. With thesetechniques, the redshift-space linear and non-linear bias are measured,with 2.6 per cent precision on the former if σ8 isfixed. The data also indicate a 2.8σ preference for the BAO,confirming the presence of BAO in the three-point function.
Keywords: cosmology: observations; distance scale; large-scale structure of Universe

Measurement of baryon acoustic oscillation correlations at z = 2.3 with SDSS DR12 Lyα-Forests - Bautista, Julian E.; Busca, Nicolás G.; Guy, Julien; Rich, James; Blomqvist, Michael; du Mas des Bourboux, Hélion; Pieri, Matthew M.; Font-Ribera, Andreu; Bailey, Stephen; Delubac, Timothée; Kirkby, David; Le Goff, Jean-Marc; et al. (Astronomy and Astrophysics, 2017)
We have used flux-transmission correlations in Lyα forests tomeasure the imprint of baryon acoustic oscillations (BAO). The studyuses spectra of 157 783 quasars in the redshift range 2.1 ≤ z ≤3.5 from the Sloan Digital Sky Survey (SDSS) data release 12 (DR12).Besides the statistical improvements on our previous studies using SDSSDR9 and DR11, we have implemented numerous improvements in the analysisprocedure, allowing us to construct a physical model of the correlationfunction and to investigate potential systematic errors in thedetermination of the BAO peak position. The Hubble distance,DH = c/H(z), relative to the sound horizon is DH(z= 2.33) /rd = 9.07 ± 0.31. The best-determinedcombination of comoving angular-diameter distance, DM, andthe Hubble distance is found to beDH0.7DM0.3 /rd =13.94 ± 0.35. This value is 1.028 ± 0.026 times theprediction of the flat-ΛCDM model consistent with the cosmicmicrowave background (CMB) anisotropy spectrum. The errors includemarginalization over the effects of unidentified high-density absorptionsystems and fluctuations in ultraviolet ionizing radiation.Independently of the CMB measurements, the combination of our resultsand other BAO observations determine the open-ΛCDM densityparameters to be ΩM = 0.296 ± 0.029,ΩΛ = 0.699 ± 0.100 andΩk = -0.002 ± 0.119.
Keywords: cosmological parameters; dark energy

Modelling the large-scale redshift-space 3-point correlation function of galaxies - Slepian, Zachary; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2017)
We present a configuration-space model of the large-scale galaxy 3-pointcorrelation function (3PCF) based on leading-order perturbation theoryand including redshift-space distortions (RSD). This model should beuseful in extracting distance-scale information from the 3PCF via thebaryon acoustic oscillation method. We include the first redshift-spacetreatment of biasing by the baryon-dark matter relative velocity.Overall, on large scales the effect of RSD is primarily arenormalization of the 3PCF that is roughly independent of both physicalscale and triangle opening angle; for our adopted Ωmand bias values, the rescaling is a factor of ˜1.8. We also presentan efficient scheme for computing 3PCF predictions from our model,important for allowing fast exploration of the space of cosmologicalparameters in future analyses.
Keywords: cosmology: theory; distance scale; large-scale structure of Universe

PRIMUS: One- and Two-halo Galactic Conformity at 0.2 < z < 1 - Berti, Angela M.; Coil, Alison L.; Behroozi, Peter S.; Daniel J. Eisenstein; Bray, Aaron D.; Cool, Richard J.; Moustakas, John (The Astrophysical Journal, 2017)
We test for galactic conformity at 0.2< z< 1.0 to a projecteddistance of 5 Mpc using spectroscopic redshifts from the PRismMUlti-object Survey (PRIMUS). Our sample consists of ˜60,000galaxies in five separate fields covering a total of ˜5.5 squaredegrees, which allows us to account for cosmic variance. We identifystar-forming and quiescent “isolated primary” (I.e.,central) galaxies using isolation criteria and cuts in specific starformation rate. We match the redshift and stellar mass distributions ofthese samples to control for correlations between quiescent fraction andredshift and stellar mass. We detect a significant (>3σ)one-halo conformity signal, or an excess of star-forming neighbors
Keywords: galaxies: evolution; galaxies: statistics

PRIMUS+DEEP2: The Dependence of Galaxy Clustering on Stellar Mass and Specific Star Formation Rate at 0.2 < z < 1.2 - Coil, Alison L.; Mendez, Alexander J.; Daniel J. Eisenstein; Moustakas, John (The Astrophysical Journal, 2017)
We present results on the clustering properties of galaxies as afunction of both stellar mass and specific star formation rate (sSFR)using data from the PRIMUS and DEEP2 galaxy redshift surveys spanning0.2< z< 1.2. We use spectroscopic redshifts of over 100,000galaxies covering an area of 7.2 deg2 over five separatefields on the sky, from which we calculate cosmic variance errors. Wefind that the galaxy clustering amplitude is as strong of a function ofsSFR as of stellar mass, and that at a given sSFR, it does notsignificantly depend on stellar mass within the range probed here. Wefurther find that within the star-forming population and at a givenstellar mass, galaxies above the main sequence of star formation withhigher sSFR are less clustered than galaxies below the main sequencewith lower sSFR. We also find that within the quiescent population,galaxies with higher sSFR are less clustered than galaxies with lowersSFR, at a given stellar mass. We show that the galaxy clusteringamplitude smoothly increases with both increasing stellar mass anddecreasing sSFR, implying that galaxies likely evolve across the mainsequence, not only along it, before galaxies eventually becomequiescent. These results imply that the relation of stellar mass to halomass, which connects galaxies to dark matter halos, likely depends onsSFR.
Keywords: galaxies: evolution; galaxies: halos; galaxies: high-redshift; large-scale structure of universe

Sloan Digital Sky Survey IV: Mapping the Milky Way, Nearby Galaxies, and the Distant Universe - Blanton, Michael R.; Bershady, Matthew A.; Abolfathi, Bela; Albareti, Franco D.; Allende Prieto, Carlos; Almeida, Andres; Alonso-García, Javier; Anders, Friedrich; Anderson, Scott F.; Andrews, Brett; Aquino-Ortíz, Erik; Aragón-Salamanca, Alfonso; et al. (The Astronomical Journal, 2017)
We describe the Sloan Digital Sky Survey IV (SDSS-IV), a projectencompassing three major spectroscopic programs. The Apache PointObservatory Galactic Evolution Experiment 2 (APOGEE-2) is observinghundreds of thousands of Milky Way stars at high resolution and highsignal-to-noise ratios in the near-infrared. The Mapping Nearby Galaxiesat Apache Point Observatory (MaNGA) survey is obtaining spatiallyresolved spectroscopy for thousands of nearby galaxies (median z˜0.03). The extended Baryon Oscillation Spectroscopic Survey (eBOSS) ismapping the galaxy, quasar, and neutral gas distributions between z˜0.6 and 3.5 to constrain cosmology using baryon acoustic oscillations,redshift space distortions, and the shape of the power spectrum. WithineBOSS, we are conducting two major subprograms: the SPectroscopicIDentification of eROSITA Sources (SPIDERS), investigating X-ray AGNsand galaxies in X-ray clusters, and the Time Domain Spectroscopic Survey(TDSS), obtaining spectra of variable sources. All programs use the 2.5m Sloan Foundation Telescope at the Apache Point Observatory;observations there began in Summer 2014. APOGEE-2 also operates a secondnear-infrared spectrograph at the 2.5 m du Pont Telescope at LasCampanas Observatory, with observations beginning in early 2017.Observations at both facilities are scheduled to continue through 2020.In keeping with previous SDSS policy, SDSS-IV provides regularlyscheduled public data releases; the first one, Data Release 13, was madeavailable in 2016 July.
Keywords: cosmology: observations; galaxies: general; Galaxy: general; instrumentation: spectrographs; stars: general; surveys

The Apache Point Observatory Galactic Evolution Experiment (APOGEE) - Majewski, Steven R.; Schiavon, Ricardo P.; Frinchaboy, Peter M.; Allende Prieto, Carlos; Barkhouser, Robert; Bizyaev, Dmitry; Blank, Basil; Brunner, Sophia; Burton, Adam; Carrera, Ricardo; Chojnowski, S. Drew; Cunha, Kátia; et al. (The Astronomical Journal, 2017)
The Apache Point Observatory Galactic Evolution Experiment (APOGEE), oneof the programs in the Sloan Digital Sky Survey III (SDSS-III), has nowcompleted its systematic, homogeneous spectroscopic survey sampling allmajor populations of the Milky Way. After a three-year observingcampaign on the Sloan 2.5 m Telescope, APOGEE has collected a halfmillion high-resolution (R ˜ 22,500), high signal-to-noise ratio(>100), infrared (1.51-1.70 μm) spectra for 146,000 stars,with time series information via repeat visits to most of these stars.This paper describes the motivations for the survey and its overalldesign—hardware, field placement, target selection,operations—and gives an overview of these aspects as well as thedata reduction, analysis, and products. An index is also given to thecomplement of technical papers that describe various critical surveycomponents in detail. Finally, we discuss the achieved surveyperformance and illustrate the variety of potential uses of the dataproducts by way of a number of science demonstrations, which span fromtime series analysis of stellar spectral variations and radial velocityvariations from stellar companions, to spatial maps of kinematics,metallicity, and abundance patterns across the Galaxy and as a functionof age, to new views of the interstellar medium, the chemistry of starclusters, and the discovery of rare stellar species. As part of SDSS-IIIData Release 12 and later releases, all of the APOGEE data products arepublicly available.
Keywords: Galaxy: abundances; Galaxy: evolution; Galaxy: formation; Galaxy: kinematics and dynamics; Galaxy: stellar content; Galaxy: structure

The 13th Data Release of the Sloan Digital Sky Survey: First Spectroscopic Data from the SDSS-IV Survey Mapping Nearby Galaxies at Apache Point Observatory - Albareti, Franco D.; Allende Prieto, Carlos; Almeida, Andres; Anders, Friedrich; Anderson, Scott; Andrews, Brett H.; Aragón-Salamanca, Alfonso; Argudo-Fernández, Maria; Armengaud, Eric; Aubourg, Eric; Avila-Reese, Vladimir; Badenes, Carles; et al. (The Astrophysical Journal Supplement Series, 2017)
The fourth generation of the Sloan Digital Sky Survey (SDSS-IV) beganobservations in 2014 July. It pursues three core programs: the ApachePoint Observatory Galactic Evolution Experiment 2 (APOGEE-2), MappingNearby Galaxies at APO (MaNGA), and the Extended Baryon OscillationSpectroscopic Survey (eBOSS). As well as its core program, eBOSScontains two major subprograms: the Time Domain Spectroscopic Survey(TDSS) and the SPectroscopic IDentification of ERosita Sources(SPIDERS). This paper describes the first data release from SDSS-IV,Data Release 13 (DR13). DR13 makes publicly available the first 1390spatially resolved integral field unit observations of nearby galaxiesfrom MaNGA. It includes new observations from eBOSS, completing theSloan Extended QUasar, Emission-line galaxy, Luminous red galaxy Survey(SEQUELS), which also targeted variability-selected objects andX-ray-selected objects. DR13 includes new reductions of the SDSS-IIIBOSS data, improving the spectrophotometric calibration and redshiftclassification, and new reductions of the SDSS-III APOGEE-1 data,improving stellar parameters for dwarf stars and cooler stars. DR13provides more robust and precise photometric calibrations. Value-addedtarget catalogs relevant for eBOSS, TDSS, and SPIDERS and an updatedred-clump catalog for APOGEE are also available. This paper describesthe location and format of the data and provides references to importanttechnical papers. The SDSS web site, <Ahref="http://www.sdss.org">http://www.sdss.org, provides links tothe data, tutorials, examples of data access, and extensivedocumentation of the reduction and analysis procedures. DR13 is thefirst of a scheduled set that will contain new data and analyses fromthe planned ∼6 yr operations of SDSS-IV.
Keywords: atlases; catalogs; surveys

Baryon acoustic oscillations from the complete SDSS-III Lyα-quasar cross-correlation function at z = 2.4 - du Mas des Bourboux, Hélion; Le Goff, Jean-Marc; Blomqvist, Michael; Busca, Nicolás G.; Guy, Julien; Rich, James; Yèche, Christophe; Bautista, Julian E.; Burtin, Étienne; Dawson, Kyle S.; Daniel J. Eisenstein; Font-Ribera, Andreu; et al. (Astronomy and Astrophysics, 2017)
We present a measurement of baryon acoustic oscillations (BAO) in thecross-correlation of quasars with the Lyα-forest flux transmissionat a mean redshift of z = 2.40. The measurement uses the complete SloanDigital Sky Survey (SDSS-III) data sample: 168 889 forests and 234 367quasars from the SDSS data release DR12. In addition to the statisticalimprovement on our previous study using DR11, we have implementednumerous improvements at the analysis level enabling a more accuratemeasurement of this cross-correlation. We have also developed the firstsimulations of the cross-correlation that allow us to test differentaspects of our data analysis and to search for potential systematicerrors in the determination of the BAO peak position. We measure the tworatios DH(z = 2.40) /rd = 9.01 ± 0.36 andDM(z = 2.40) /rd = 35.7 ± 1.7, where theerrors include marginalization over the non-linear velocity of quasarsand the cross-correlation of metals and quasars, among other effects.These results are within 1.8σ of the prediction of theflat-ΛCDM model describing the observed cosmic microwavebackground anisotropies. We combine this study with the Lyα-forestauto-correlation function, yielding DH(z = 2.40)/rd = 8.94 ± 0.22 and DM(z = 2.40)/rd = 36.6 ± 1.2, within 2.3σ of the sameflat-ΛCDM model.
Keywords: cosmological parameters; dark energy; large-scale structure of Universe

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: cosmological analysis of the DR12 galaxy sample - Alam, Shadab; Ata, Metin; Bailey, Stephen; Beutler, Florian; Bizyaev, Dmitry; Blazek, Jonathan A.; Bolton, Adam S.; Brownstein, Joel R.; Burden, Angela; Chuang, Chia-Hsun; Comparat, Johan; Antonio J. Cuesta; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We present cosmological results from the final galaxy clustering dataset of the Baryon Oscillation Spectroscopic Survey, part of the SloanDigital Sky Survey III. Our combined galaxy sample comprises 1.2 millionmassive galaxies over an effective area of 9329 deg2 andvolume of 18.7 Gpc3, divided into three partially overlappingredshift slices centred at effective redshifts 0.38, 0.51 and 0.61. Wemeasure the angular diameter distance DM and Hubble parameterH from the baryon acoustic oscillation (BAO) method, in combination witha cosmic microwave background prior on the sound horizon scale, afterapplying reconstruction to reduce non-linear effects on the BAO feature.Using the anisotropic clustering of the pre-reconstruction densityfield, we measure the product DMH from the Alcock-Paczynski(AP) effect and the growth of structure, quantified byfσ8(z), from redshift-space distortions (RSD). Wecombine individual measurements presented in seven companion papers intoa set of consensus values and likelihoods, obtaining constraints thatare tighter and more robust than those from any one method; inparticular, the AP measurement from sub-BAO scales sharpens constraintsfrom post-reconstruction BAOs by breaking degeneracy betweenDM and H. Combined with Planck 2016 cosmic microwavebackground measurements, our distance scale measurements simultaneouslyimply curvature ΩK = 0.0003 ± 0.0026 and a darkenergy equation-of-state parameter w = -1.01 ± 0.06, in strongaffirmation of the spatially flat cold dark matter (CDM) model with acosmological constant (ΛCDM). Our RSD measurements offσ8, at 6 per cent precision, are similarly consistentwith this model. When combined with supernova Ia data, we findH0 = 67.3 ± 1.0 km s-1 Mpc-1even for our most general dark energy model, in tension with some directmeasurements. Adding extra relativistic species as a degree of freedomloosens the constraint only slightly, to H0 = 67.8 ±1.2 km s-1 Mpc-1. Assuming flat ΛCDM, wefind Ωm = 0.310 ± 0.005 and H0 = 67.6± 0.5 km s-1 Mpc-1, and we find a 95 percent upper limit of 0.16 eV c-2 on the neutrino mass sum.
Keywords: distance scale; large-scale structure of Universe; cosmology: observations

The clustering of galaxies in the completed SDSS-III Baryon Oscillation Spectroscopic Survey: single-probe measurements from DR12 galaxy clustering - towards an accurate model - Chuang, Chia-Hsun; Pellejero-Ibanez, Marcos; Rodríguez-Torres, Sergio; Ashley J. Ross; Zhao, Gong-bo; Wang, Yuting; Antonio J. Cuesta; Rubiño-Martín, J. A.; Prada, Francisco; Alam, Shadab; Beutler, Florian; Daniel J. Eisenstein; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We analyse the broad-range shape of the monopole and quadrupolecorrelation functions of the Baryon Oscillation Spectroscopic SurveyData Release 12 (DR12) CMASS and LOWZ galaxy sample to obtainconstraints on the Hubble expansion rate H(z), the angular-diameterdistance DA(z), the normalized growth ratef(z)σ8(z) and the physical matter densityΩm h2. We adopt wide and flat priors on allmodel parameters in order to ensure the results are those of a'single-probe' galaxy clustering analysis. We also marginalize overthree nuisance terms that account for potential observationalsystematics affecting the measured monopole. However, such Monte CarloMarkov Chain analysis is computationally expensive for advancedtheoretical models. We develop a new methodology to speed up theanalysis. Using the range 40 h-1 Mpc < s < 180h-1 Mpc, we obtain{DA(z)rs,fid/rs (Mpc),H(z)rs/rs,fid km s-1 Mpc-1,f(z)σ8(z), Ωm h2} = {956± 28, 75.0 ± 4.0, 0.397 ± 0.073, 0.143 ±0.017} at z = 0.32 and {1421 ± 23, 96.7 ± 2.7, 0.497± 0.058, 0.137 ± 0.015} at z = 0.59 where rs isthe comoving sound horizon at the drag epoch and rs,fid =147.66 Mpc for the fiducial cosmology used in this study. Combining ourmeasurements with Planck data, we obtain Ωm = 0.306± 0.009, H0 = 67.9 ± 0.7 km s-1Mpc-1 and σ8 = 0.815 ± 0.009 assumingΛcold dark matter (CDM); Ωk = 0.000 ±0.003 and w = -1.02 ± 0.08 assuming owCDM. Our results show notension with the flat ΛCDM cosmological paradigm. This paper ispart of a set that analyses the final galaxy clustering data set fromBaryon Oscillation Spectroscopic Survey.
Keywords: cosmological parameters; distance scale; large-scale structure of Universe; cosmology: observations

Dynamical dark energy in light of the latest observations - Zhao, Gong-bo; Raveri, Marco; Pogosian, Levon; Wang, Yuting; Crittenden, Robert G.; Handley, Will J.; Will J. Percival; Beutler, Florian; Brinkmann, Jonathan; Chuang, Chia-Hsun; Antonio J. Cuesta; Daniel J. Eisenstein; et al. (Nature Astronomy, 2017)
A flat Friedmann-Robertson-Walker universe dominated by a cosmologicalconstant (Λ) and cold dark matter (CDM) has been the workingmodel preferred by cosmologists since the discovery of cosmicacceleration1,2. However, tensions of various degrees ofsignificance are known to be present among existing datasets within theΛCDM framework3-11. In particular, the Lyman-αforest measurement of the baryon acoustic oscillations (BAO) by theBaryon Oscillation Spectroscopic Survey3 prefers a smallervalue of the matter density fraction ΩM than thatpreferred by cosmic microwave background (CMB). Also, the recentlymeasured value of the Hubble constant, H0 = 73.24 ±1.74 km s-1 Mpc-1 (ref. 12), is3.4σ higher than the 66.93 ± 0.62 km s-1Mpc-1 inferred from the Planck CMB data7. In thiswork, we investigate whether these tensions can be interpreted asevidence for a non-constant dynamical dark energy. Using theKullback-Leibler divergence13 to quantify the tension betweendatasets, we find that the tensions are relieved by an evolving darkenergy, with the dynamical dark energy model preferred at a 3.5σsignificance level based on the improvement in the fit alone. While, atpresent, the Bayesian evidence for the dynamical dark energy isinsufficient to favour it over ΛCDM, we show that, if the currentbest-fit dark energy happened to be the true model, it would bedecisively detected by the upcoming Dark Energy Spectroscopic Instrumentsurvey14.

Using galaxy pairs to investigate the three-point correlation function in the squeezed limit - Sihan Yuan; Daniel J. Eisenstein; Garrison, Lehman H. (Monthly Notices of the Royal Astronomical Society, 2017)
We investigate the three-point correlation function (3PCF) in thesqueezed limit by considering galaxy pairs as discrete objects andcross-correlating them with the galaxy field. We develop an efficientalgorithm using fast Fourier transforms to compute suchcross-correlations and their associated pair-galaxy bias bp,g and the squeezed 3PCF coefficient Qeff. We implementour method using N-body cosmological simulations and a fiducial halooccupation distribution (HOD) and present the results in both the realspace and redshift space. In real space, we observe a peak in bp,g and Qeff at pair separation of ∼2 Mpc, attributedto the fact that galaxy pairs at 2 Mpc separation trace the most massivedark matter haloes. We also see strong anisotropy in the bp,g and Qeff signals that track the large-scalefilamentary structure. In redshift space, both the 2 Mpc peak and theanisotropy are significantly smeared out along the line of sight due tofinger-of-God effect. In both the real space and redshift space, thesqueezed 3PCF shows a factor of 2 variation, contradicting thehierarchical ansatz, but offering rich information on the galaxy-haloconnection. Thus, we explore the possibility of using the squeezed 3PCFto constrain the HOD. When we compare two simple HOD models that areclosely matched in their projected two-point correlation function(2PCF), we do not yet see a strong variation in the 3PCF that is clearlydisentangled from variations in the projected 2PCF. Nevertheless, wepropose that more complicated HOD models, e.g. those incorporatingassembly bias, can break degeneracies in the 2PCF and show adistinguishable squeezed 3PCF signal.
Keywords: methods: analytical; galaxies: haloes; dark matter; large-scale structure of Universe

Accelerating the two-point and three-point galaxy correlation functions using Fourier transforms - Slepian, Zachary; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2016)
Though Fourier transforms (FTs) are a common technique for findingcorrelation functions, they are not typically used in computations ofthe anisotropy of the two-point correlation function (2PCF) about theline of sight in wide-angle surveys because the line-of-sight directionis not constant on the Cartesian grid. Here we show how FTs can be usedto compute the multipole moments of the anisotropic 2PCF. We also showhow FTs can be used to accelerate the 3PCF algorithm of Slepian &Eisenstein. In both cases, these FT methods allow one to avoid thecomputational cost of pair counting, which scales as the square of thenumber density of objects in the survey. With the upcoming large datasets of Dark Energy Spectroscopic Instrument, Euclid, and Large SynopticSurvey Telescope, FT techniques will therefore offer an importantcomplement to simple pair or triplet counts.
Keywords: methods: data analysis; methods: statistical; large-scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: baryon acoustic oscillations in the correlation function of LOWZ and CMASS galaxies in Data Release 12 - Antonio J. Cuesta; Vargas-Magaña, Mariana; Beutler, Florian; Bolton, Adam S.; Brownstein, Joel R.; Daniel J. Eisenstein; Gil-Marín, Héctor; Ho, Shirley; Cameron K. McBride; Maraston, Claudia; Padmanabhan, Nikhil; Will J. Percival; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
We present distance scale measurements from the baryon acousticoscillation signal in the constant stellar mass and low-redshift samplesamples from the Data Release 12 of the Baryon Oscillation SpectroscopicSurvey. The total volume probed is 14.5 Gpc3, a 10 per centincrement from Data Release 11. From an analysis of the sphericallyaveraged correlation function, we infer a distance to z = 0.57 ofD_V(z)r^fid_d/r_d = 2028± 21 Mpc and a distance to z = 0.32 ofD_V(z)r^fid_d/r_d = 1264± 22 Mpc assuming a cosmology in whichr^fid_d = 147.10 Mpc. From the anisotropic analysis, we find an angulardiameter distance to z = 0.57 of D_A(z)r^fid_d/r_d = 1401± 21 Mpcand a distance to z = 0.32 of 981 ± 20 Mpc, a 1.5 and 2.0 percent measurement, respectively. The Hubble parameter at z = 0.57 isH(z)r_d/r^fid_d = 100.3± 3.7 km s-1 Mpc-1and its value at z = 0.32 is 79.2 ± 5.6 km s-1Mpc-1, a 3.7 and 7.1 per cent measurement, respectively.These cosmic distance scale constraints are in excellent agreement witha Λ cold dark matter model with cosmological parameters releasedby the recent Planck 2015 results.
Keywords: cosmology: observations; distance scale; large-scale structure of Universe

Large-scale clustering of Lyman α emission intensity from SDSS/BOSS - Croft, Rupert A. C.; Miralda-Escudé, Jordi; Zheng, Zheng; Bolton, Adam; Dawson, Kyle S.; Peterson, Jeffrey B.; York, Donald G.; Eisenstein, Daniel; Brinkmann, Jon; Brownstein, Joel; Renyue Cen; Delubac, Timothée; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
We present a tentative detection of the large-scale structure of Lyα emission in the Universe at redshifts z = 2-3.5 by measuring thecross-correlation of Ly α surface brightness with quasars in SloanDigital Sky Survey/Baryon Oscillation Spectroscopic Survey. We use amillion spectra targeting luminous red galaxies at z < 0.8, aftersubtracting a best-fitting model galaxy spectrum from each one, as anestimate of the high-redshift Ly α surface brightness. Thequasar-Ly α emission cross-correlation is detected on scales 1˜ 15 h-1 Mpc, with shape consistent with a ΛCDMmodel with Ω _m =0.30^{+0.10}_{-0.07}. The predicted amplitude ofthis cross-correlation is proportional to the product of the mean Lyα surface brightness, <μα>, theamplitude of mass fluctuations and the quasar and Ly α emissionbias factors. We infer <μα>(bα/3) = (3.9 ± 0.9) × 10-21erg s-1 cm-2 Å-1arcsec-2, where bα is the Ly αemission bias. If star-forming galaxies dominate this emission, we findρSFR = (0.28 ± 0.07)(3/bα)yr-1 Mpc-3. For bα = 3, thisvalue is ˜30 times larger than previous estimates fromindividually detected Ly α emitters, but consistent with the totalρSFR derived from dust-corrected, continuum UV galaxysurveys, if most of the Ly α photons from these galaxies avoiddust absorption and are reemitted after diffusing in large gas haloes.Heating of intergalactic gas by He II photoionization from quasarradiation or jets may alternatively explain the detected correlation,and cooling radiation from gas in galactic haloes may also contribute.We also detect redshift space anisotropy of the quasar-Ly αemission cross-correlation, finding evidence at the 3.0σ levelthat it is radially elongated, which may be explained byradiative-transfer effects. Our measurements represent the firstapplication of the intensity mapping technique to optical observations.
Keywords: cosmology: observations

Modelling galactic conformity with the colour-halo age relation in the Illustris simulation - Bray, Aaron D.; Pillepich, Annalisa; Sales, Laura V.; Zhu, Emily; Genel, Shy; Rodriguez-Gomez, Vicente; Torrey, Paul; Nelson, Dylan; Vogelsberger, Mark; Springel, Volker; Daniel J. Eisenstein; Hernquist, Lars (Monthly Notices of the Royal Astronomical Society, 2016)
Comparisons between observational surveys and galaxy formation modelsfind that dark matter haloes' mass can largely explain their galaxies'stellar mass. However, it remains uncertain whether additionalenvironmental variables, known as assembly bias, are necessary toexplain other galaxy properties. We use the Illustris simulation toinvestigate the role of assembly bias in producing galactic conformityby considering 18 000 galaxies with Mstellar > 2 ×109 M⊙. We find a significant signal ofgalactic conformity: out to distances of about 10 Mpc, the mean redfraction of galaxies around redder galaxies is higher than around bluergalaxies at fixed stellar mass. Dark matter haloes exhibit an analogousconformity signal, in which the fraction of haloes formed at earliertimes (old haloes) is higher around old haloes than around younger onesat fixed halo mass. A plausible interpretation of galactic conformity isthe combination of the halo conformity signal with the galaxycolour-halo age relation: at fixed stellar mass, particularly towardsthe low-mass end, Illustris' galaxy colours correlate with halo age,with the reddest galaxies (often satellites) preferentially found in theoldest haloes. We explain the galactic conformity effect with a simplesemi-empirical model, assigning stellar mass via halo mass (abundancematching) and galaxy colour via halo age (age matching). Regardingcomparison to observations, we conclude that the adoptedselection/isolation criteria, projection effects, and stackingtechniques can have a significant impact on the measured amplitude ofthe conformity signal.
Keywords: galaxies: formation; galaxies: haloes; cosmology: theory; dark matter

New white dwarf and subdwarf stars in the Sloan Digital Sky Survey Data Release 12 - Kepler, S. O.; Pelisoli, I.; Koester, D.; Ourique, G.; Romero, A. D.; Reindl, N.; Kleinman, S. J.; Eisenstein, D. J.; Valois, A. D. M.; Amaral, L. A. (Monthly Notices of the Royal Astronomical Society, 2016)
We report the discovery of 6576 new spectroscopically confirmed whitedwarf and subdwarf stars in the Sloan Digital Sky Survey Data Release12. We obtain Teff, log g and mass for hydrogen atmospherewhite dwarf stars (DAs) and helium atmosphere white dwarf stars (DBs),estimate the calcium/helium abundances for the white dwarf stars withmetallic lines (DZs) and carbon/helium for carbon-dominated spectra(DQs). We found one central star of a planetary nebula, one ultracompacthelium binary (AM CVn), one oxygen line-dominated white dwarf, 15 hotDO/PG1159s, 12 new cataclysmic variables, 36 magnetic white dwarf stars,54 DQs, 115 helium-dominated white dwarfs, 148 white dwarf +main-sequence star binaries, 236 metal-polluted white dwarfs, 300continuum spectra DCs, 230 hot subdwarfs, 2936 new hydrogen-dominatedwhite dwarf stars, and 2675 cool hydrogen-dominated subdwarf stars. Wecalculate the mass distribution of all 5883 DAs with S/N ≥ 15 inDR12, including the ones in DR7 and DR10, with an average S/N = 26,corrected to the 3D convection scale, and also the distribution aftercorrecting for the observed volume, using 1/Vmax.
Keywords: catalogues; stars: magnetic field; subdwarfs; white dwarfs

PRIMUS + DEEP2: Clustering of X-Ray, Radio, and IR-AGNs at z~0.7 - Mendez, Alexander J.; Coil, Alison L.; Aird, James; Skibba, Ramin A.; Diamond-Stanic, Aleksandar M.; Moustakas, John; Blanton, Michael R.; Cool, Richard J.; Daniel J. Eisenstein; Wong, Kenneth C.; Zhu, Guangtun (The Astrophysical Journal, 2016)
We measure the clustering of X-ray, radio, and mid-IR-selected activegalactic nuclei (AGNs) at 0.2\lt z\lt 1.2 using multi-wavelength imagingand spectroscopic redshifts from the PRIMUS and DEEP2 redshift surveys,covering seven separate fields spanning ∼10 deg 2 . Using thecross-correlation of AGNs with dense galaxy samples, we measure theclustering scale length and slope, as well as the bias, of AGNs selectedat different wavelengths. Similar to previous studies, we find thatX-ray and radio AGNs are more clustered than mid-IR-selected AGNs. Wefurther compare the clustering of each AGN sample with matched galaxysamples designed to have the same stellar mass, star-formation rate(SFR), and redshift distributions as the AGN host galaxies and find nosignificant differences between their clustering properties. Theobserved differences in the clustering of AGNs selected at differentwavelengths can therefore be explained by the clustering differences oftheir host populations, which have different distributions in bothstellar mass and SFR. Selection biases inherent in AGN selectiontherefore determine the clustering of observed AGN samples. We furtherfind no significant difference between the clustering of obscured andunobscured AGNs, using IRAC or Wide-field Infrared Survey Explorercolors or X-ray hardness ratio.
Keywords: galaxies: active; galaxies: evolution; infrared: galaxies; radio continuum: galaxies; X-rays: galaxies

SDSS-III Baryon Oscillation Spectroscopic Survey Data Release 12: galaxy target selection and large-scale structure catalogues - Reid, Beth; Ho, Shirley; Padmanabhan, Nikhil; Will J. Percival; Tinker, Jeremy; Tojeiro, Rita; White, Martin; Daniel J. Eisenstein; Maraston, Claudia; Ashley J. Ross; Sánchez, Ariel G.; Schlegel, David; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
The Baryon Oscillation Spectroscopic Survey (BOSS), part of the SloanDigital Sky Survey (SDSS) III project, has provided the largest surveyof galaxy redshifts available to date, in terms of both the number ofgalaxy redshifts measured by a single survey, and the effectivecosmological volume covered. Key to analysing the clustering of thesedata to provide cosmological measurements is understanding the detailedproperties of this sample. Potential issues include variations in thetarget catalogue caused by changes either in the targeting algorithm orproperties of the data used, the pattern of spectroscopic observations,the spatial distribution of targets for which redshifts were notobtained, and variations in the target sky density due to observationalsystematics. We document here the target selection algorithms used tocreate the galaxy samples that comprise BOSS. We also present thealgorithms used to create large-scale structure catalogues for the finalData Release (DR12) samples and the associated random catalogues thatquantify the survey mask. The algorithms are an evolution of those usedby the BOSS team to construct catalogues from earlier data, and havebeen designed to accurately quantify the galaxy sample. The code used,designated MKSAMPLE, is released with this paper.
Keywords: cosmology: observations; (cosmology:) large-scale structure of Universe

The SDSS-IV Extended Baryon Oscillation Spectroscopic Survey: Overview and Early Data - Dawson, Kyle S.; Kneib, Jean-Paul; Will J. Percival; Alam, Shadab; Albareti, Franco D.; Anderson, Scott F.; Armengaud, Eric; Aubourg, Éric; Bailey, Stephen; Bautista, Julian E.; Berlind, Andreas A.; Bershady, Matthew A.; et al. (The Astronomical Journal, 2016)
In a six-year program started in 2014 July, the Extended BaryonOscillation Spectroscopic Survey (eBOSS) will conduct novel cosmologicalobservations using the BOSS spectrograph at Apache Point Observatory.These observations will be conducted simultaneously with the Time DomainSpectroscopic Survey (TDSS) designed for variability studies and theSpectroscopic Identification of eROSITA Sources (SPIDERS) programdesigned for studies of X-ray sources. In particular, eBOSS will measurewith percent-level precision the distance-redshift relation with baryonacoustic oscillations (BAO) in the clustering of matter. eBOSS will usefour different tracers of the underlying matter density field to vastlyexpand the volume covered by BOSS and map the large-scale-structuresover the relatively unconstrained redshift range 0.6 < z < 2.2.Using more than 250,000 new, spectroscopically confirmed luminous redgalaxies at a median redshift z = 0.72, we project that eBOSS will yieldmeasurements of the angular diameter distance dA(z) to an
Keywords: cosmology: observations; surveys

A simple analytic treatment of linear growth of structure with baryon acoustic oscillations - Slepian, Zachary; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2016)
In linear perturbation theory, all information about the growth ofstructure is contained in the Green's function, or equivalently,transfer function. These functions are generally computed usingnumerical codes or by phenomenological fitting formula anchored inaccurate analytic results in the limits of large and small scale. Here,we present a framework for analytically solving all scales, inparticular the intermediate scales relevant for the baryon acousticoscillations (BAO). We solve for the Green's function and transferfunction using spherically averaged overdensities and the approximationthat the density of the coupled baryon-photon fluid is constant interiorto the sound horizon.
Keywords: cosmology: theory; large-scale structure of Universe

ASPCAP: The APOGEE Stellar Parameter and Chemical Abundances Pipeline - García Pérez, Ana E.; Allende Prieto, Carlos; Holtzman, Jon A.; Shetrone, Matthew; Mészáros, Szabolcs; Bizyaev, Dmitry; Carrera, Ricardo; Cunha, Katia; García-Hernández, D. A.; Johnson, Jennifer A.; Majewski, Steven R.; Nidever, David L.; et al. (The Astronomical Journal, 2016)
The Apache Point Observatory Galactic Evolution Experiment (APOGEE) hasbuilt the largest moderately high-resolution (R ≈ 22,500)spectroscopic map of the stars across the Milky Way, and includingdust-obscured areas. The APOGEE Stellar Parameter and ChemicalAbundances Pipeline (ASPCAP) is the software developed for the automatedanalysis of these spectra. ASPCAP determines atmospheric parameters andchemical abundances from observed spectra by comparing observed spectrato libraries of theoretical spectra, using χ2minimization in a multidimensional parameter space. The package consistsof a fortran90 code that does the actual minimization and a wrapper IDLcode for book-keeping and data handling. This paper explains in detailthe ASPCAP components and functionality, and presents results from anumber of tests designed to check its performance. ASPCAP providesstellar effective temperatures, surface gravities, and metallicities
Keywords: Galaxy: center; Galaxy: structure; methods: data analysis; stars: abundances; stars: atmospheres

Building a better understanding of the massive high-redshift BOSS CMASS galaxies as tools for cosmology - Favole, Ginevra; Cameron K. McBride; Daniel J. Eisenstein; Prada, Francisco; Swanson, Molly E.; Chuang, Chia-Hsun; Schneider, Donald P. (Monthly Notices of the Royal Astronomical Society, 2016)
We explore the massive bluer star-forming population of the SloanDigital Sky Survey (SDSS) III/BOSS CMASS DR11 galaxies at z > 0.55 toquantify their differences, in terms of redshift-space distortions andlarge-scale bias, with respect to the luminous red galaxy sample. Weperform a qualitative analysis to understand the significance of thesedifferences and whether we can model and reproduce them in mockcatalogues. Specifically, we measure galaxy clustering in CMASS on smalland intermediate scales (0.1 ≲ r ≲ 50 h-1 Mpc) bycomputing the two-point correlation function - both projected andredshift-space - of these galaxies, and a new statistic, Σ(π),able to separate the coherent and dispersed redshift-space distortioncontributions and the large-scale bias. We interpret our clusteringmeasurements by adopting a Halo Occupation Distribution (HOD) schemethat maps them on to high-resolution N-body cosmological simulations toproduce suitable mock galaxy catalogues. The traditional HODprescription can be applied to the red and the blue samples,independently, but this approach is unphysical since it allows the samemock galaxies to be either red or blue. To overcome this ambiguity, wemodify the standard formulation and infer the red and the blue models bysplitting the full mock catalogue into two complementary andnon-overlapping submocks. This separation is performed by constrainingthe HOD with the observed CMASS red and blue galaxy fractions andproduces reliable and accurate models.
Keywords: galaxies: distances and redshifts; galaxies: haloes; galaxies: statistics; cosmology: observations; cosmology: theory; large-scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: single-probe measurements from CMASS anisotropic galaxy clustering - Chuang, Chia-Hsun; Prada, Francisco; Pellejero-Ibanez, Marcos; Beutler, Florian; Antonio J. Cuesta; Daniel J. Eisenstein; Escoffier, Stephanie; Ho, Shirley; Francisco-Shu Kitaura; Kneib, Jean-Paul; Manera, Marc; Nuza, Sebastián E.; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
With the largest spectroscopic galaxy survey volume drawn from theSDSS-III Baryon Oscillation Spectroscopic Survey (BOSS), we can extractcosmological constraints from the measurements of redshift and geometricdistortions at quasi-linear scales (e.g. above 50 h-1 Mpc).We analyse the broad-range shape of the monopole and quadrupolecorrelation functions of the BOSS Data Release 12 (DR12) CMASS galaxysample, at the effective redshift z = 0.59, to obtain constraints on theHubble expansion rate H(z), the angular- diameter distanceDA(z), the normalized growth rate f(z)σ8(z),and the physical matter density Ωm h2. Weobtain robust measurements by including a polynomial as the model forthe systematic errors, and find it works very well against thesystematic effects, e.g. ones induced by stars and seeing. We provideaccurate measurements{DA(0.59)rs,fid/rs,H(0.59)rs/rs,fid,f(0.59)σ8(0.59), Ωm h2} ={1427 ± 26 Mpc, 97.3 ± 3.3 km s-1Mpc-1, 0.488 ± 0.060, 0.135 ± 0.016}, wherers is the comoving sound horizon at the drag epoch andrs,fid = 147.66 Mpc is the sound scale of the fiducialcosmology used in this study. The parameters which are not wellconstrained by our galaxy clustering analysis are marginalized over withwide flat priors. Since no priors from other data sets, e.g. cosmicmicrowave background (CMB), are adopted and no dark energy models areassumed, our results from BOSS CMASS galaxy clustering alone may becombined with other data sets, i.e. CMB, SNe, lensing or other galaxyclustering data to constrain the parameters of a given cosmologicalmodel. The uncertainty on the dark energy equation of state parameter,w, from CMB+CMASS is about 8 per cent. The uncertainty on the curvaturefraction, Ωk, is 0.3 per cent. We do not find deviationfrom flat ΛCDM.
Keywords: cosmological parameters; cosmology: observations; distance scale; large-scale structure of Universe

Clustering properties of g-selected galaxies at z ˜ 0.8 - Favole, Ginevra; Comparat, Johan; Prada, Francisco; Yepes, Gustavo; Jullo, Eric; Niemiec, Anna; Kneib, Jean-Paul; Rodríguez-Torres, Sergio A.; Klypin, Anatoly; Skibba, Ramin A.; Cameron K. McBride; Daniel J. Eisenstein; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
Current and future large redshift surveys, as the Sloan Digital SkySurvey IV extended Baryon Oscillation Spectroscopic Survey(SDSS-IV/eBOSS) or the Dark Energy Spectroscopic Instrument (DESI), willuse emission-line galaxies (ELGs) to probe cosmological models bymapping the large-scale structure of the Universe in the redshift range0.6 < z < 1.7. With current data, we explore the halo-galaxyconnection by measuring three clustering properties of g-selected ELGsas matter tracers in the redshift range 0.6 < z < 1: (i) theredshift-space two-point correlation function using spectroscopicredshifts from the BOSS ELG sample and VIPERS; (ii) the angulartwo-point correlation function on the footprint of the CFHT-LS; (iii)the galaxy-galaxy lensing signal around the ELGs using the CFHTLenS. Weinterpret these observations by mapping them on to the latesthigh-resolution MultiDark Planck N-body simulation, using a novel(Sub)Halo-Abundance Matching technique that accounts for the ELGincompleteness. ELGs at z ˜ 0.8 live in haloes of (1 ± 0.5)× 1012 h-1M⊙ and 22.5± 2.5 per cent of them are satellites belonging to a larger halo.The halo occupation distribution of ELGs indicates that we are samplingthe galaxies in which stars form in the most efficient way, according totheir stellar-to-halo mass ratio.
Keywords: galaxies: distances and redshifts; galaxies: haloes; galaxies: statistics; cosmology: observations; cosmology: theory; large-scale structure of Universe

Exploring photometric redshifts as an optimization problem: an ensemble MCMC and simulated annealing-driven template-fitting approach - Speagle, Joshua S.; Capak, Peter L.; Daniel J. Eisenstein; Masters, Daniel C.; Steinhardt, Charles L. (Monthly Notices of the Royal Astronomical Society, 2016)
Using a 4D grid of ˜2 million model parameters (Δz = 0.005)adapted from Cosmological Origins Survey photometric redshift (photo-z)searches, we investigate the general properties of template-basedphoto-z likelihood surfaces. We find these surfaces are filled withnumerous local minima and large degeneracies that generally confoundsimplistic gradient-descent optimization schemes. We combine ensembleMarkov Chain Monte Carlo sampling with simulated annealing to robustlyand efficiently explore these surfaces in approximately constant time.Using a mock catalogue of 384 662 objects, we show our approach samples˜40 times more efficiently compared to a `brute-force' counterpartwhile maintaining similar levels of accuracy. Our results representfirst steps towards designing template-fitting photo-z approacheslimited mainly by memory constraints rather than computation time.
Keywords: methods: statistical; techniques: photometric; galaxies: distances and redshifts

The high-mass end of the red sequence at z ˜ 0.55 from SDSS-III/BOSS: completeness, bimodality and luminosity function - Montero-Dorta, Antonio D.; Bolton, Adam S.; Brownstein, Joel R.; Swanson, Molly; Dawson, Kyle; Prada, Francisco; Eisenstein, Daniel; Maraston, Claudia; Thomas, Daniel; Comparat, Johan; Chuang, Chia-Hsun; Cameron K. McBride; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
We have developed an analytical method based on forward-modellingtechniques to characterize the high-mass end of the red sequence (RS)galaxy population at redshift z ˜ 0.55, from the DR10 BOSS (BaryonOscillation Spectroscopic Survey) CMASS spectroscopic sample, whichcomprises ˜600 000 galaxies. The method, which follows an unbinnedmaximum likelihood approach, allows the deconvolution of the intrinsicCMASS colour-colour-magnitude distributions from photometric errors andselection effects. This procedure requires modelling the covariancematrix for the i-band magnitude, g - r colour and r - i colour usingStripe 82 multi-epoch data. Our results indicate that theerror-deconvolved intrinsic RS distribution is consistent, within thephotometric uncertainties, with a single point (<0.05 mag) in thecolour-colour plane at fixed magnitude, for a narrow redshift slice. Wehave computed the high-mass end (0.55Mi ≲-22) of the 0.55i-band RS luminosity function (RS LF) inseveral redshift slices within the redshift range 0.52 < z < 0.63.In this narrow redshift range, the evolution of the RS LF is consistent,within the uncertainties in the modelling, with a passively evolvingmodel with Φ* = (7.248 ± 0.204) × 10-4 Mpc-3 mag-1, fading at a rate of 1.5± 0.4 mag per unit redshift. We report RS completeness as afunction of magnitude and redshift in the CMASS sample, which willfacilitate a variety of galaxy-evolution and clustering studies usingBOSS. Our forward-modelling method lays the foundations for futurestudies using other dark-energy surveys like the Extended BaryonOscillation Spectroscopic Survey or the Dark Energy SpectroscopicInstrument, which are affected by the same type of photometricblurring/selection effects.
Keywords: methods: analytical; methods: statistical; surveys; galaxies: evolution; galaxies: luminosity function; mass function; galaxies: statistics

Improving initial conditions for cosmological N-body simulations - Garrison, Lehman H.; Daniel J. Eisenstein; Ferrer, Douglas; Metchnik, Marc V.; Pinto, Philip A. (Monthly Notices of the Royal Astronomical Society, 2016)
In cosmological N-body simulations, the representation of dark matter asdiscrete `macroparticles' suppresses the growth of structure, such thatsimulations no longer reproduce linear theory on small scales nearkNyquist. Marcos et al. demonstrate that this is due tosparse sampling of modes near kNyquist and that theoften-assumed continuum growing modes are not proper growing modes ofthe particle system. We develop initial conditions (ICs) that respectthe particle linear theory growing modes and then rescale the modeamplitudes to account for growth suppression. These ICs also allow us totake advantage of our very accurate N-body code ABACUS to implementsecond-order Lagrangian perturbation theory (2LPT) in configurationspace. The combination of 2LPT and rescaling improves the accuracy ofthe late-time power spectra, halo mass functions, and halo clustering.In particular, we achieve 1 per cent accuracy in the power spectrum downto kNyquist, versus kNyquist/4 without rescalingor kNyquist/13 without 2LPT, relative to an oversampledreference simulation. We anticipate that our 2LPT will be useful forlarge simulations where fast Fourier transforms are expensive and thatrescaling will be useful for suites of medium-resolution simulationsused in cosmic emulators and galaxy survey mock catalogues. Code togenerate ICs is available at https://github.com/lgarrison/zeldovich-PLT.
Keywords: methods: numerical; galaxies: haloes; large-scale structure of Universe

Large covariance matrices: smooth models from the two-point correlation function - O'Connell, Ross; Eisenstein, Daniel; Vargas, Mariana; Ho, Shirley; Padmanabhan, Nikhil (Monthly Notices of the Royal Astronomical Society, 2016)
We introduce a new method for estimating the covariance matrix for thegalaxy correlation function in surveys of large-scale structure. Ourmethod combines simple theoretical results with a realisticcharacterization of the survey to dramatically reduce noise in thecovariance matrix. For example, with an investment of only ≈1000 CPUhours we can produce a model covariance matrix with noise levels thatwould otherwise require ˜35 000 mocks. Non-Gaussian contributionsto the model are calibrated against mock catalogues, after which themodel covariance is found to be in impressive agreement with the mockcovariance matrix. Since calibration of this method requires fewer mocksthan brute force approaches, we believe that it could dramaticallyreduce the number of mocks required to analyse future surveys.
Keywords: large-scale structure of Universe

Quantifying the colour-dependent stochasticity of large-scale structure - Patej, Anna; Eisenstein, Daniel (Monthly Notices of the Royal Astronomical Society, 2016)
We address the question of whether massive red and blue galaxies tracethe same large-scale structure at z ˜ 0.6 using the CMASS sampleof galaxies from Data Release 12 of the Sloan Digital Sky Survey III.After splitting the catalogue into subsamples of red and blue galaxiesusing a simple colour cut, we measure the clustering of both subsamplesand construct the correlation coefficient, r, using two statistics. Thecorrelation coefficient quantifies the stochasticity between the twosubsamples, which we examine over intermediate scales (20 ≲ R≲ 100 h-1 Mpc). We find that on these intermediatescales, the correlation coefficient is consistent with 1; in particular,we find r > 0.95 taking into account both statistics and r > 0.974using the favoured statistic.
Keywords: galaxies: statistics; large-scale structure of Universe

Signatures of the Primordial Universe from Its Emptiness: Measurement of Baryon Acoustic Oscillations from Minima of the Density Field - Francisco-Shu Kitaura; Chuang, Chia-Hsun; Liang, Yu; Zhao, Cheng; Tao, Charling; Rodríguez-Torres, Sergio; Daniel J. Eisenstein; Gil-Marín, Héctor; Kneib, Jean-Paul; McBride, Cameron; Will J. Percival; Ashley J. Ross; et al. (Physical Review Letters, 2016)
Sound waves from the primordial fluctuations of the Universe imprintedin the large-scale structure, called baryon acoustic oscillations(BAOs), can be used as standard rulers to measure the scale of theUniverse. These oscillations have already been detected in thedistribution of galaxies. Here we propose to measure BAOs from thetroughs (minima) of the density field. Based on two sets of accuratemock halo catalogues with and without BAOs in the seed initialconditions, we demonstrate that the BAO signal cannot be obtained fromthe clustering of classical disjoint voids, but it is clearly detectedfrom overlapping voids. The latter represent an estimate of all troughsof the density field. We compute them from the empty circumspherecenters constrained by tetrahedra of galaxies using Delaunaytriangulation. Our theoretical models based on an unprecedented largeset of detailed simulated void catalogues are remarkably well confirmedby observational data. We use the largest recently publicly availablesample of luminous red galaxies from SDSS-III BOSS DR11 to unveil forthe first time a >3 σ BAO detection from voids in observations.Since voids are nearly isotropically expanding regions, their centersrepresent the most quiet places in the Universe, keeping in mind thecosmos origin and providing a new promising window in the analysis ofthe cosmological large-scale structure from galaxy surveys.

Abundances, Stellar Parameters, and Spectra from the SDSS-III/APOGEE Survey - Holtzman, Jon A.; Shetrone, Matthew; Johnson, Jennifer A.; Allende Prieto, Carlos; Anders, Friedrich; Andrews, Brett; Beers, Timothy C.; Bizyaev, Dmitry; Blanton, Michael R.; Bovy, Jo; Carrera, Ricardo; Chojnowski, S. Drew; et al. (The Astronomical Journal, 2015)
The SDSS-III/Apache Point Observatory Galactic Evolution Experiment(APOGEE) survey operated from 2011-2014 using the APOGEEspectrograph, which collects high-resolution (R ˜ 22,500), near-IR(1.51-1.70 μm) spectra with a multiplexing (300 fiber-fedobjects) capability. We describe the survey data products that arepublicly available, which include catalogs with radial velocity, stellarparameters, and 15 elemental abundances for over 150,000 stars, as wellas the more than 500,000 spectra from which these quantities arederived. Calibration relations for the stellar parameters(Teff, {log} g, [M/H], [α/M]) and abundances (C, N,O, Na, Mg, Al, Si, S, K, Ca, Ti, V, Mn, Fe, Ni) are presented anddiscussed. The internal scatter of the abundances within clustersindicates that abundance precision is generally between 0.05 and 0.09dex across a broad temperature range; it is smaller for some elementalabundances within more limited ranges and at high signal-to-noise ratio.We assess the accuracy of the abundances using comparison of meancluster metallicities with literature values, APOGEE observations of thesolar spectrum and of Arcturus, comparison of individual star abundanceswith other measurements, and consideration of the locus of derivedparameters and abundances of the entire sample, and find that it ischallenging to determine the absolute abundance scale; external accuracymay be good to 0.1-0.2 dex. Uncertainties may be larger at coolertemperatures (Teff \lt 4000 K). Access to thepublic data release and data products is described, and some guidancefor using the data products is provided.
Keywords: astronomical databases: miscellaneous; Galaxy: abundances; stars: abundances; surveys

Computing the three-point correlation function of galaxies in O(N^2) time - Slepian, Zachary; Daniel J. Eisenstein (Monthly Notices of the Royal Astronomical Society, 2015)
We present an algorithm that computes the multipole coefficients of thegalaxy three-point correlation function (3PCF) without explicitlyconsidering triplets of galaxies. Rather, centring on each galaxy in thesurvey, it expands the radially binned density field in sphericalharmonics and combines these to form the multipoles without everrequiring the relative angle between a pair about the central. Thisapproach scales with number and number density in the same way as thetwo-point correlation function, allowing run-times that are comparable,and 500 times faster than a naive triplet count. It is exact in angleand easily handles edge correction. We demonstrate the algorithm on theLasDamas SDSS-DR7 mock catalogues, computing an edge corrected 3PCF outto 90 Mpc h-1 in under an hour on modest computing resources.We expect this algorithm will render it possible to obtain thelarge-scale 3PCF for upcoming surveys such as Euclid, Large SynopticSurvey Telescope (LSST), and Dark Energy Spectroscopic Instrument.
Keywords: methods: data analysis; cosmology: large-scale structure of Universe; methods: data analysis

Dark Matter Halo Models of Stellar Mass-dependent Galaxy Clustering in PRIMUS+DEEP2 at 0.2>z>1.2 - Skibba, Ramin A.; Coil, Alison L.; Mendez, Alexander J.; Blanton, Michael R.; Bray, Aaron D.; Cool, Richard J.; Daniel J. Eisenstein; Guo, Hong; Miyaji, Takamitsu; Moustakas, John; Zhu, Guangtun (The Astrophysical Journal, 2015)
We utilize ΛCDM halo occupation models of galaxy clustering toinvestigate the evolving stellar mass dependent clustering of galaxiesin the PRIsm MUlti-object Survey (PRIMUS) and DEEP2 Redshift Survey overthe past eight billion years of cosmic time, between 0.2\lt z\lt 1.2.These clustering measurements provide new constraints on the connectionsbetween dark matter halo properties and galaxy properties in the contextof the evolving large-scale structure of the universe. Using both ananalytic model and a set of mock galaxy catalogs, we find a strongcorrelation between central galaxy stellar mass and dark matter halomass over the range Mhalo˜{10}11-{10}13 {h}-1M⊙ , approximately consistent with previousobservations and theoretical predictions. However, the stellar-to-halomass relation and the mass scale where star formation efficiency reachesa maximum appear to evolve more strongly than predicted by other models,including models based primarily on abundance-matching constraints. Wefind that the fraction of satellite galaxies in halos of a given massdecreases significantly from z˜ 0.5 to z˜ 0.9, partly due to thefact that halos at fixed mass are rarer at higher redshift and havelower abundances. We also find that the{M}1/Mmin ratio, a model parameter thatquantifies the critical mass above which halos host at least onesatellite, decreases from ≈ 20 at z˜ 0 to ≈ 13 at z˜ 0.9.Considering the evolution of the subhalo mass function vis-à-vissatellite abundances, this trend has implications for relations betweensatellite galaxies and halo substructures and for intracluster mass,which we argue has grown due to stripped and disrupted satellitesbetween z˜ 0.9 and z˜ 0.5.
Keywords: dark matter; galaxies: evolution; galaxies: halos; large-scale structure of universe; methods: analytical; methods: statistical

The Eleventh and Twelfth Data Releases of the Sloan Digital Sky Survey: Final Data from SDSS-III - Alam, Shadab; Albareti, Franco D.; Allende Prieto, Carlos; Anders, F.; Anderson, Scott F.; Anderton, Timothy; Andrews, Brett H.; Armengaud, Eric; Aubourg, Éric; Bailey, Stephen; Basu, Sarbani; Bautista, Julian E.; et al. (The Astrophysical Journal Supplement Series, 2015)
The third generation of the Sloan Digital Sky Survey (SDSS-III) tookdata from 2008 to 2014 using the original SDSS wide-field imager, theoriginal and an upgraded multi-object fiber-fed optical spectrograph, anew near-infrared high-resolution spectrograph, and a novel opticalinterferometer. All of the data from SDSS-III are now made public. Inparticular, this paper describes Data Release 11 (DR11) including alldata acquired through 2013 July, and Data Release 12 (DR12) adding dataacquired through 2014 July (including all data included in previous datareleases), marking the end of SDSS-III observing. Relative to ourprevious public release (DR10), DR12 adds one million new spectra ofgalaxies and quasars from the Baryon Oscillation Spectroscopic Survey(BOSS) over an additional 3000 deg2 of sky, more than triplesthe number of H-band spectra of stars as part of the Apache PointObservatory (APO) Galactic Evolution Experiment (APOGEE), and includesrepeated accurate radial velocity measurements of 5500 stars from theMulti-object APO Radial Velocity Exoplanet Large-area Survey (MARVELS).The APOGEE outputs now include the measured abundances of 15 differentelements for each star. In total, SDSS-III added 5200 deg2 ofugriz imaging; 155,520 spectra of 138,099 stars as part of the SloanExploration of Galactic Understanding and Evolution 2 (SEGUE-2) survey;2,497,484 BOSS spectra of 1,372,737 galaxies, 294,512 quasars, and247,216 stars over 9376 deg2; 618,080 APOGEE spectra of156,593 stars; and 197,040 MARVELS spectra of 5513 stars. Since itsfirst light in 1998, SDSS has imaged over 1/3 of the Celestial sphere infive bands and obtained over five million astronomical spectra.
Keywords: atlases; catalogs; surveys

Measuring the Luminosity and Virial Black Hole Mass Dependence of Quasar-Galaxy Clustering At z ˜ 0.8 - Krolewski, Alex G.; Daniel J. Eisenstein (The Astrophysical Journal, 2015)
We study the dependence of quasar clustering on quasar luminosity andblack hole mass by measuring the angular overdensity of photometricallyselected galaxies imaged by the Wide-field Infrared Survey Explorer(WISE) about z ˜ 0.8 quasars from SDSS. By measuring thequasar-galaxy cross-correlation function and using photometricallyselected galaxies, we achieve a higher density of tracer objects and amore sensitive detection of clustering than measurements of the quasarautocorrelation function. We test models of quasar formation andevolution by measuring the luminosity dependence of clusteringamplitude. We find a significant overdensity of WISE galaxies about z˜ 0.8 quasars at 0.2-6.4 h-1 Mpc in projectedcomoving separation. We find no appreciable increase in clusteringamplitude with quasar luminosity across a decade in luminosity, and apower-law fit between luminosity and clustering amplitude gives anexponent of -0.01 ± 0.06 (1 σ error). We also fail tofind a significant relationship between clustering amplitude and blackhole mass, although our dynamic range in true mass is suppressed due tothe large uncertainties in virial black hole mass estimates. Our resultsindicate that a small range in host dark matter halo mass maps to alarge range in quasar luminosity.
Keywords: galaxies: active; large-scale structure of universe; quasars: general

PRIMUS: Effects of Galaxy Environment on the Quiescent Fraction Evolution at z < 0.8 - Hahn, ChangHoon; Blanton, Michael R.; Moustakas, John; Coil, Alison L.; Cool, Richard J.; Daniel J. Eisenstein; Skibba, Ramin A.; Wong, Kenneth C.; Zhu, Guangtun (The Astrophysical Journal, 2015)
We investigate the effects of galaxy environment on the evolution of thequiescent fraction ({fQ}) from z=0.8 to 0.0 usingspectroscopic redshifts and multi-wavelength imaging data from the PRIsmMUlti-object Survey (PRIMUS) and the Sloan Digital Sky Survey (SDSS).Our stellar mass limited galaxy sample consists of ˜14,000 PRIMUSgalaxies within z = 0.2-0.8 and ˜64,000 SDSS galaxies within z= 0.05-0.12. We classify the galaxies as quiescent or star-forming(SF) based on an evolving specific star formation cut, and as low orhigh density environments based on fixed cylindrical apertureenvironment measurements on a volume-limited environment definingpopulation. For quiescent and SF galaxies in low or high densityenvironments, we examine the evolution of their stellar mass function(SMF). Then using the SMFs we computefQ({M*}) and quantify its evolution withinour redshift range. We find that the quiescent fraction is higher athigher masses and in denser environments. The quiescent fraction riseswith cosmic time for all masses and environments. At a fiducial mass of{{10}10.5} M⊙ , from z˜ 0.7 to 0.1,
Keywords: cosmology: observations; galaxies: evolution; galaxies: groups: general; galaxies: star formation; galaxies: statistics

PRIMUS: The Effect of Physical Scale on the Luminosity Dependence of Galaxy Clustering via Cross-correlations - Bray, Aaron D.; Daniel J. Eisenstein; Skibba, Ramin A.; Blanton, Michael R.; Coil, Alison L.; Cool, Richard J.; Mendez, Alexander J.; Moustakas, John; Zhu, Guangtun (The Astrophysical Journal, 2015)
We report small-scale clustering measurements from the PRIsmMUlti-object Survey (PRIMUS) spectroscopic redshift survey as a functionof color and luminosity. We measure the real-space cross-correlationsbetween 62,106 primary galaxies with PRIMUS redshifts and a tracerpopulation of ∼545,000 photometric galaxies over redshifts from z =0.2 to z = 1. We separately fit a power-law model in redshift andluminosity to each of three independent color-selected samples ofgalaxies. We report clustering amplitudes at fiducial values of z = 0.5and L=1.5L*. The clustering of the red galaxies is ∼ 3times as strong as that of the blue galaxies and ∼ 1.5 as strong asthat of the green galaxies. We also find that the luminosity dependenceof the clustering is strongly dependent on physical scale, with greaterluminosity dependence being found between r=0.0625 {h}-1Mpc and r=0.25 {h}-1 Mpc, compared to the r=0.5{h}-1 Mpc to r=2 {h}-1 Mpc range. Moreover,over a range of two orders of magnitude in luminosity, a singlepower-law fit to the luminosity dependence is not sufficient to explainthe increase in clustering at both the bright and faint ends at thesmaller scales. We argue that luminosity-dependent clustering at smallscales is a necessary component of galaxy-halo occupation models forblue, star-forming galaxies as well as for red, quenched galaxies.
Keywords: cosmology: observations; galaxies: statistics; galaxies: evolution; galaxies: high-redshift; cosmology: large-scale structure of universe; surveys

PRIMUS: The Relationship between Star Formation and AGN Accretion - Azadi, Mojegan; Aird, James; Coil, Alison L.; Moustakas, John; Mendez, Alexander J.; Blanton, Michael R.; Cool, Richard J.; Daniel J. Eisenstein; Wong, Kenneth C.; Zhu, Guangtun (The Astrophysical Journal, 2015)
We study the evidence for a connection between active galactic nuclei(AGNs) fueling and star formation by investigating the relationshipbetween the X-ray luminosities of AGNs and the star formation rates(SFRs) of their host galaxies. We identify a sample of 309 AGNs with{10}41\lt {L}X\lt {10}44 ergs-1 at 0.2\lt z\lt 1.2 in the PRIMUS redshift survey.We find AGNs in galaxies with a wide range of SFR at a givenLX. We do not find a significant correlation between SFR andthe observed instantaneous LX for star-forming AGN hostgalaxies. However, there is a weak but significant correlation betweenthe mean LX and SFR of detected AGNs in star-forminggalaxies, which likely reflects that LX varies on shortertimescales than SFR. We find no correlation between stellar mass andLX within the AGN population. Within both populations ofstar-forming and quiescent galaxies, we find a similar power-lawdistribution in the probability of hosting an AGN as a function ofspecific accretion rate. Furthermore, at a given stellar mass, we find astar-forming galaxy ˜2-3 more likely than a quiescent galaxyto host an AGN of a given specific accretion rate. The probability of agalaxy hosting an AGN is constant across the main sequence of starformation. These results indicate that there is an underlying connectionbetween star formation and the presence of AGNs, but AGNs are oftenhosted by quiescent galaxies.
Keywords: galaxies: active; galaxies: evolution; X-rays: galaxies

Cosmological implications of baryon acoustic oscillation measurements - Aubourg, Éric; Bailey, Stephen; Bautista, Julian E.; Beutler, Florian; Bhardwaj, Vaishali; Bizyaev, Dmitry; Blanton, Michael; Blomqvist, Michael; Bolton, Adam S.; Bovy, Jo; Brewington, Howard; Brinkmann, J.; et al. (Physical Review D, 2015)
We derive constraints on cosmological parameters and tests of darkenergy models from the combination of baryon acoustic oscillation (BAO)measurements with cosmic microwave background (CMB) data and a recentreanalysis of Type Ia supernova (SN) data. In particular, we takeadvantage of high-precision BAO measurements from galaxy clustering andthe Lyman-α forest (LyaF) in the SDSS-III Baryon OscillationSpectroscopic Survey (BOSS). Treating the BAO scale as an uncalibratedstandard ruler, BAO data alone yield a high confidence detection of darkenergy; in combination with the CMB angular acoustic scale they furtherimply a nearly flat universe. Adding the CMB-calibrated physical scaleof the sound horizon, the combination of BAO and SN data into an"inverse distance ladder" yields a measurement of H0=67.3
Keywords: Cosmology; Dark energy

Baryon acoustic oscillations in the Lyα forest of BOSS DR11 quasars - Delubac, Timothée; Bautista, Julian E.; Busca, Nicolás G.; Rich, James; Kirkby, David; Bailey, Stephen; Font-Ribera, Andreu; Slosar, Anže; Lee, Khee-Gan; Pieri, Matthew M.; Hamilton, Jean-Christophe; Aubourg, Éric; et al. (Astronomy and Astrophysics, 2015)
We report a detection of the baryon acousticoscillation (BAO) feature inthe flux-correlation function of the Lyα forest of high-redshiftquasars with a statistical significance of five standard deviations. Thestudy uses 137 562 quasars in the redshift range 2.1 ≤ z ≤ 3.5from the data release 11 (DR11) of the Baryon Oscillation SpectroscopicSurvey (BOSS) of SDSS-III. This sample contains three times the numberof quasars used in previous studies. The measured position of the BAOpeak determines the angular distance, DA(z = 2.34) andexpansion rate, H(z = 2.34), both on a scale set by the sound horizon atthe drag epoch, rd. We find DA/rd =11.28 ± 0.65(1σ)+2.8-1.2 (2σ)and DH/rd = 9.18 ± 0.28(1σ) ±0.6(2σ) where DH = c/H. The optimal combination,~DH0.7DA0.3/rd is
Keywords: cosmology: observations; dark energy; large-scale structure of Universe; cosmological parameters

Distance probes of dark energy - Kim, A. G.; Padmanabhan, N.; Aldering, G.; Allen, S. W.; Baltay, C.; Cahn, R. N.; D'Andrea, C. B.; Dalal, N.; Dawson, K. S.; Denney, K. D.; Eisenstein, D. J.; Finley, D. A.; et al. (Astroparticle Physics, 2015)
This document presents the results from the Distances subgroup of theCosmic Frontier Community Planning Study (Snowmass 2013). We summarizethe current state of the field as well as future prospects andchallenges. In addition to the established probes using Type Iasupernovae and baryon acoustic oscillations, we also considerprospective methods based on clusters, active galactic nuclei,gravitational wave sirens and strong lensing time delays.

New white dwarf stars in the Sloan Digital Sky Survey Data Release 10 - Kepler, S. O.; Pelisoli, I.; Koester, D.; Ourique, G.; Kleinman, S. J.; Romero, A. D.; Nitta, A.; Eisenstein, D. J.; Costa, J. E. S.; Külebi, B.; S. Jordan; Dufour, P.; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
We report the discovery of 9088 new spectroscopically confirmed whitedwarfs and subdwarfs in the Sloan Digital Sky Survey Data Release 10. Weobtain Teff, log g and mass for hydrogen atmosphere whitedwarf stars (DAs) and helium atmosphere white dwarf stars (DBs), andestimate the calcium/helium abundances for the white dwarf stars withmetallic lines (DZs) and carbon/helium for carbon-dominated spectra DQs.We found 1 central star of a planetary nebula, 2 new oxygen spectra onhelium atmosphere white dwarfs, 71 DQs, 42 hot DO/PG1159s, 171 whitedwarf+main-sequence star binaries, 206 magnetic DAHs, 327continuum-dominated DCs, 397 metal-polluted white dwarfs, 450helium-dominated white dwarfs, 647 subdwarfs and 6887 newhydrogen-dominated white dwarf stars.
Keywords: catalogues; stars: magnetic field; subdwarfs; white dwarfs

On the signature of the baryon-dark matter relative velocity in the two- and three-point galaxy correlation functions - Slepian, Zachary; Eisenstein, Daniel J. (Monthly Notices of the Royal Astronomical Society, 2015)
We develop a configuration-space picture of the relative velocitybetween baryons and dark matter that clearly explains how it can shiftthe baryon acoustic oscillation (BAO) scale in the galaxy-galaxycorrelation function. The shift occurs because the relative velocity isnon-zero only within the sound horizon and thus adds to the correlationfunction asymmetrically about the BAO peak. We further show that inconfiguration space the relative velocity has a localized, distinctivesignature in the three-point galaxy correlation function (3PCF). Inparticular, we find that a multipole decomposition is a favourable wayto isolate the relative velocity in the 3PCF, and that there is a strongsignature in the l = 1 multipole for triangles with two sides around theBAO scale. Finally, we investigate a further compression of the 3PCF toa function of only one triangle side that preserves the localized natureof the relative velocity signature while also nicely separating linearfrom non-linear bias. We expect that this scheme will substantiallylessen the computational burden of finding the relative velocity in the3PCF. The relative velocity's 3PCF signature can be used to correct theshift induced in the galaxy-galaxy correlation function so that nosystematic error due to this effect is introduced into the BAO as usedfor precision cosmology.
Keywords: cosmology: theory; distance scale; large-scale structure of Universe

The Sloan Digital Sky Survey Reverberation Mapping Project: Technical Overview - Shen, Yue; Brandt, W. N.; Dawson, Kyle S.; Hall, Patrick B.; McGreer, Ian D.; Anderson, Scott F.; Chen, Yuguang; Denney, Kelly D.; Eftekharzadeh, Sarah; Fan, Xiaohui; Yang Gao; Green, Paul J.; et al. (The Astrophysical Journal Supplement Series, 2015)
The Sloan Digital Sky Survey Reverberation Mapping (SDSS-RM) project isa dedicated multi-object RM experiment that has spectroscopicallymonitored a sample of 849 broad-line quasars in a single 7deg2 field with the SDSS-III Baryon Oscillation SpectroscopicSurvey spectrograph. The RM quasar sample is flux-limited to ipsf = 21.7 mag, and covers a redshift range of 0.1 < z< 4.5 without any other cuts on quasar properties. Opticalspectroscopy was performed during 2014 January-July dark/gray time, withan average cadence of ~4 days, totaling more than 30 epochs. Supportingphotometric monitoring in the g and i bands was conducted at multiplefacilities including the Canada-France-Hawaii Telescope (CFHT) and theSteward Observatory Bok telescope in 2014, with a cadence of ~2 days andcovering all lunar phases. The RM field (R.A., decl. = 14:14:49.00,+53:05:00.0) lies within the CFHT-LS W3 field, and coincides with thePan-STARRS 1 (PS1) Medium Deep Field MD07, with three prior years ofmulti-band PS1 light curves. The SDSS-RM six month baseline program aimsto detect time lags between the quasar continuum and broad line region(BLR) variability on timescales of up to several months (in the observed
Keywords: black hole physics; galaxies: active; line: profiles; quasars: general; surveys

Characterizing unknown systematics in large scale structure surveys - Agarwal, Nishant; Ho, Shirley; Myers, Adam D.; Seo, Hee-Jong; Ross, Ashley J.; Bahcall, Neta; Brinkmann, Jonathan; Eisenstein, Daniel J.; Muna, Demitri; Palanque-Delabrouille, Nathalie; Pâris, Isabelle; Petitjean, Patrick; et al. (Journal of Cosmology and Astro-Particle Physics, 2014)
Photometric large scale structure (LSS) surveys probe the largestvolumes in the Universe, but are inevitably limited by systematicuncertainties. Imperfect photometric calibration leads to biases in ourmeasurements of the density fields of LSS tracers such as galaxies andquasars, and as a result in cosmological parameter estimation. Earlierstudies have proposed using cross-correlations between differentredshift slices or cross-correlations between different surveys toreduce the effects of such systematics. In this paper we develop amethod to characterize unknown systematics. We demonstrate that while wedo not have sufficient information to correct for unknown systematics inthe data, we can obtain an estimate of their magnitude. We define aparameter to estimate contamination from unknown systematics usingcross-correlations between different redshift slices and proposediscarding bins in the angular power spectrum that lie outside a certaincontamination tolerance level. We show that this method improvesestimates of the bias using simulated data and further apply it tophotometric luminous red galaxies in the Sloan Digital Sky Survey as acase study.

The clustering of Galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: including covariance matrix errors - Percival, Will J.; Ross, Ashley J.; Sánchez, Ariel G.; Samushia, Lado; Burden, Angela; Crittenden, Robert; Cuesta, Antonio J.; Magana, Mariana Vargas; Manera, Marc; Beutler, Florian; Chuang, Chia-Hsun; Eisenstein, Daniel J.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We present improved methodology for including covariance matrices in theerror budget of Baryon Oscillation Spectroscopic Survey (BOSS) galaxyclustering measurements, revisiting Data Release 9 (DR9) analyses, anddescribing a method that is used in DR10/11 analyses presented incompanion papers. The precise analysis method adopted is becomingincreasingly important, due to the precision that BOSS can now reach:even using as many as 600 mock catalogues to estimate covariance oftwo-point clustering measurements can still lead to an increase in theerrors of ˜20 per cent, depending on how the cosmologicalparameters of interest are measured. In this paper, we extend previouswork on this contribution to the error budget, deriving formulae forerrors measured by integrating over the likelihood, and to thedistribution of recovered best-fitting parameters fitting thesimulations also used to estimate the covariance matrix. Both aresituations that previous analyses of BOSS have considered. We apply theformulae derived to baryon acoustic oscillation (BAO) and redshift-spacedistortion (RSD) measurements from BOSS in our companion papers. Tofurther aid these analyses, we consider the optimum number of bins touse for two-point measurements using the monopole power spectrum orcorrelation function for BAO, and the monopole and quadrupole moments ofthe correlation function for anisotropic-BAO and RSD measurements.
Keywords: cosmology: observations; distance scale; large-scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: measuring DA and H at z = 0.57 from the baryon acoustic peak in the Data Release 9 spectroscopic Galaxy sample - Anderson, Lauren; Aubourg, Eric; Bailey, Stephen; Beutler, Florian; Bolton, Adam S.; Brinkmann, J.; Brownstein, Joel R.; Chuang, Chia-Hsun; Cuesta, Antonio J.; Dawson, Kyle S.; Eisenstein, Daniel J.; Ho, Shirley; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We present measurements of the angular diameter distance to and Hubbleparameter at z = 0.57 from the measurement of the baryon acoustic peakin the correlation of galaxies from the Sloan Digital Sky Survey IIIBaryon Oscillation Spectroscopic Survey. Our analysis is based on asample from Data Release 9 of 264 283 galaxies over 3275 square degreesin the redshift range 0.43 < z < 0.70. We use two differentmethods to provide robust measurement of the acoustic peak positionacross and along the line of sight in order to measure the cosmologicaldistance scale. We find DA(0.57) = 1408 ± 45 Mpc andH(0.57) = 92.9 ± 7.8 km s-1 Mpc-1 for ourfiducial value of the sound horizon. These results from the anisotropicfitting are fully consistent with the analysis of the sphericallyaveraged acoustic peak position presented in Anderson et al. Ourdistance measurements are a close match to the predictions of thestandard cosmological model featuring a cosmological constant and zerospatial curvature.
Keywords: cosmological parameters; cosmology: observations; dark energy; distance scale; large scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: measuring growth rate and geometry with anisotropic clustering - Samushia, Lado; Reid, Beth A.; White, Martin; Percival, Will J.; Cuesta, Antonio J.; Zhao, Gong-bo; Ross, Ashley J.; Manera, Marc; Aubourg, Éric; Beutler, Florian; Brinkmann, Jon; Brownstein, Joel R.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We use the observed anisotropic clustering of galaxies in the BaryonOscillation Spectroscopic Survey Data Release 11 CMASS sample to measurethe linear growth rate of structure, the Hubble expansion rate and thecomoving distance scale. Our sample covers 8498 deg2 andencloses an effective volume of 6 Gpc3 at an effectiveredshift of barz = 0.57. We find fσ8 = 0.441 ±0.044, H = 93.1 ± 3.0 km s-1 Mpc-1 andDA = 1380 ± 23 Mpc when fitting the growth andexpansion rate simultaneously. When we fix the background expansion tothe one predicted by spatially flat Λ cold dark matter(ΛCDM) model in agreement with recent Planck results, we findfσ8 = 0.447 ± 0.028 (6 per cent accuracy). Whileour measurements are generally consistent with the predictions ofΛCDM and general relativity, they mildly favour models in whichthe strength of gravitational interactions is weaker than what ispredicted by general relativity. Combining our measurements with recentcosmic microwave background data results in tight constraints on basiccosmological parameters and deviations from the standard cosmologicalmodel. Separately varying these parameters, we find w = -0.983 ±0.075 (8 per cent accuracy) and γ = 0.69 ± 0.11 (16 percent accuracy) for the effective equation of state of dark energy andthe growth rate index, respectively. Both constraints are in goodagreement with the standard model values of w = -1 and γ = 0.554.
Keywords: gravitation; cosmological parameters; dark energy; dark matter; distance scale; large-scale structure of Universe

PRIMUS: Galaxy Clustering as a Function of Luminosity and Color at 0.2 < z < 1 - Skibba, Ramin A.; Smith, M. Stephen M.; Coil, Alison L.; Moustakas, John; Aird, James; Blanton, Michael R.; Bray, Aaron D.; Cool, Richard J.; Eisenstein, Daniel J.; Mendez, Alexander J.; Kenneth C. Wong; Zhu, Guangtun (The Astrophysical Journal, 2014)
We present measurements of the luminosity and color-dependence of galaxyclustering at 0.2 < z < 1.0 in the Prism Multi-object Survey. Wequantify the clustering with the redshift-space and projected two-pointcorrelation functions, ξ(rp , π) and wp(rp ), using volume-limited samples constructed from a parentsample of over ~130, 000 galaxies with robust redshifts in sevenindependent fields covering 9 deg2 of sky. We quantify howthe scale-dependent clustering amplitude increases with increasingluminosity and redder color, with relatively small errors over largevolumes. We find that red galaxies have stronger small-scale (0.1 Mpc h-1 < rp < 1 Mpc h -1)clustering and steeper correlation functions compared to blue galaxies,as well as a strong color dependent clustering within the red sequencealone. We interpret our measured clustering trends in terms of galaxybias and obtain values of b gal ≈ 0.9-2.5, quantifying howgalaxies are biased tracers of dark matter depending on their luminosityand color. We also interpret the color dependence with mock catalogs,and find that the clustering of blue galaxies is nearly constant withcolor, while redder galaxies have stronger clustering in the one-haloterm due to a higher satellite galaxy fraction. In addition, we measurethe evolution of the clustering strength and bias, and we do not detectstatistically significant departures from passive evolution. We arguethat the luminosity- and color-environment (or halo mass) relations ofgalaxies have not significantly evolved since z ~ 1. Finally, usingjackknife subsampling methods, we find that sampling fluctuations areimportant and that the COSMOS field is generally an outlier, due tohaving more overdense structures than other fields; we find that "cosmicvariance" can be a significant source of uncertainty for high-redshiftclustering measurements.
Keywords: cosmology: observations; galaxies: distances and redshifts; galaxies: evolution; galaxies: halos; galaxies: high-redshift; galaxies: statistics; large-scale structure of universe

Quasar-Lyman α forest cross-correlation from BOSS DR11: Baryon Acoustic Oscillations - Font-Ribera, Andreu; Kirkby, David; Busca, Nicolas; Miralda-Escudé, Jordi; Ross, Nicholas P.; Slosar, Anže; Rich, James; Aubourg, Éric; Bailey, Stephen; Bhardwaj, Vaishali; Bautista, Julian; Beutler, Florian; et al. (Journal of Cosmology and Astro-Particle Physics, 2014)
We measure the large-scale cross-correlation of quasars with theLyα forest absorption, using over 164,000 quasars from DataRelease 11 of the SDSS-III Baryon Oscillation Spectroscopic Survey. Weextend the previous study of roughly 60,000 quasars from Data Release 9to larger separations, allowing a measurement of the Baryonic AcousticOscillation (BAO) scale along the line of sight c/(H(z =2.36)rs) = 9.0±0.3 and across the line of sightDA(z = 2.36)/rs = 10.8±0.4, consistent withCMB and other BAO data. Using the best fit value of the sound horizonfrom Planck data (rs = 147.49 Mpc), we can translate theseresults to a measurement of the Hubble parameter of H(z = 2.36) =226±8 km s-1 Mpc-1 and of theangular diameter distance of DA(z = 2.36) = 1590±60Mpc. The measured cross-correlation function and an update of the codeto fit the BAO scale (baofit) are made publicly available.

The Tenth Data Release of the Sloan Digital Sky Survey: First Spectroscopic Data from the SDSS-III Apache Point Observatory Galactic Evolution Experiment - Ahn, Christopher P.; Alexandroff, Rachael; Allende Prieto, Carlos; Anders, Friedrich; Anderson, Scott F.; Anderton, Timothy; Andrews, Brett H.; Aubourg, Éric; Bailey, Stephen; Bastien, Fabienne A.; Bautista, Julian E.; Beers, Timothy C.; et al. (The Astrophysical Journal Supplement Series, 2014)
The Sloan Digital Sky Survey (SDSS) has been in operation since 2000April. This paper presents the Tenth Public Data Release (DR10) from itscurrent incarnation, SDSS-III. This data release includes the firstspectroscopic data from the Apache Point Observatory Galaxy EvolutionExperiment (APOGEE), along with spectroscopic data from the BaryonOscillation Spectroscopic Survey (BOSS) taken through 2012 July. TheAPOGEE instrument is a near-infrared R ~ 22,500 300 fiber spectrographcovering 1.514-1.696 μm. The APOGEE survey is studying the chemicalabundances and radial velocities of roughly 100,000 red giant starcandidates in the bulge, bar, disk, and halo of the Milky Way. DR10includes 178,397 spectra of 57,454 stars, each typically observed threeor more times, from APOGEE. Derived quantities from these spectra(radial velocities, effective temperatures, surface gravities, andmetallicities) are also included. DR10 also roughly doubles the numberof BOSS spectra over those included in the Ninth Data Release. DR10includes a total of 1,507,954 BOSS spectra comprising 927,844 galaxyspectra, 182,009 quasar spectra, and 159,327 stellar spectra selectedover 6373.2 deg2.
Keywords: atlases; catalogs; surveys

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: baryon acoustic oscillations in the Data Releases 10 and 11 Galaxy samples - Anderson, Lauren; Aubourg, Éric; Bailey, Stephen; Beutler, Florian; Bhardwaj, Vaishali; Blanton, Michael; Bolton, Adam S.; Brinkmann, J.; Brownstein, Joel R.; Burden, Angela; Chuang, Chia-Hsun; Cuesta, Antonio J.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We present a one per cent measurement of the cosmic distance scale fromthe detections of the baryon acoustic oscillations (BAO) in theclustering of galaxies from the Baryon Oscillation Spectroscopic Survey,which is part of the Sloan Digital Sky Survey III. Our results come fromthe Data Release 11 (DR11) sample, containing nearly one milliongalaxies and covering approximately 8500 square degrees and the redshiftrange 0.2 < z < 0.7. We also compare these results with those fromthe publicly released DR9 and DR10 samples. Assuming a concordanceΛ cold dark matter (ΛCDM) cosmological model, the DR11sample covers a volume of 13 Gpc3 and is the largest regionof the Universe ever surveyed at this density. We measure thecorrelation function and power spectrum, including density-fieldreconstruction of the BAO feature. The acoustic features are detected ata significance of over 7σ in both the correlation function andpower spectrum. Fitting for the position of the acoustic featuresmeasures the distance relative to the sound horizon at the drag epoch,rd, which has a value of rd,fid = 149.28 Mpc inour fiducial cosmology. We find DV = (1264 ± 25Mpc)(rd/rd,fid) at z = 0.32 and DV =(2056 ± 20 Mpc)(rd/rd,fid) at z = 0.57. At1.0 per cent, this latter measure is the most precise distanceconstraint ever obtained from a galaxy survey. Separating the clusteringalong and transverse to the line of sight yields measurements at z =0.57 of DA = (1421 ± 20Mpc)(rd/rd,fid) and H = (96.8 ± 3.4 kms-1 Mpc-1)(rd,fid/rd). Ourmeasurements of the distance scale are in good agreement with previousBAO measurements and with the predictions from cosmic microwavebackground data for a spatially flat CDM model with a cosmologicalconstant.
Keywords: cosmological parameters; cosmology: observations; dark energy; distance scale; large-scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: modelling of the luminosity and colour dependence in the Data Release 10 - Guo, Hong; Zheng, Zheng; Zehavi, Idit; Xu, Haojie; Eisenstein, Daniel J.; Weinberg, David H.; Bahcall, Neta A.; Berlind, Andreas A.; Comparat, Johan; McBride, Cameron K.; Ross, Ashley J.; Schneider, Donald P.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We investigate the luminosity and colour dependence of clustering ofCMASS galaxies in the Sloan Digital Sky Survey-III Baryon OscillationSpectroscopic Survey Data Release 10, focusing on projected correlationfunctions of well-defined samples extracted from the full catalogue of˜540 000 galaxies at z ˜ 0.5 covering about 6500deg2. The halo occupation distribution framework is adoptedto model the measurements on small and intermediate scales (from 0.02 to60 h-1 Mpc), infer the connection of galaxies to dark matterhaloes and interpret the observed trends. We find that luminous redgalaxies in CMASS reside in massive haloes of mass M ˜1013-1014 h-1 M⊙ andmore luminous galaxies are more clustered and hosted by more massivehaloes. The strong small-scale clustering requires a fraction of thesegalaxies to be satellites in massive haloes, with the fraction at thelevel of 5-8 per cent and decreasing with luminosity. The characteristicmass of a halo hosting on average one satellite galaxy above aluminosity threshold is about a factor of 8.7 larger than that of a halohosting a central galaxy above the same threshold. At a fixedluminosity, progressively redder galaxies are more strongly clustered onsmall scales, which can be explained by having a larger fraction ofthese galaxies in the form of satellites in massive haloes. Ourclustering measurements on scales below 0.4 h-1 Mpc allow usto study the small-scale spatial distribution of satellites insidehaloes. While the clustering of luminosity-threshold samples can be welldescribed by a Navarro-Frenk-White profile, that of the reddest galaxiesprefers a steeper or more concentrated profile. Finally, we also usegalaxy samples of constant number density at different redshifts tostudy the evolution of luminous red galaxies, and find the clustering tobe consistent with passive evolution in the redshift range of 0.5 ≲z ≲ 0.6.
Keywords: galaxies: distances and redshifts; galaxies: haloes; galaxies: statistics; cosmology: observations; cosmology: theory; large-scale structure of Universe

The clustering of Galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: potential systematics in fitting of baryon acoustic feature - Vargas-Magaña, Mariana; Ho, Shirley; Xu, Xiaoying; Sánchez, Ariel G.; O'Connell, Ross; Eisenstein, Daniel J.; Cuesta, Antonio J.; Percival, Will J.; Ross, Ashley J.; Aubourg, Eric; Brownstein, Joel R.; Escoffier, Stéphanie; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
Extraction of the Baryon Acoustic Oscillations (BAO) to per cent levelaccuracy is challenging and demands an understanding of many potentialsystematics to an accuracy well below 1 per cent, in order to ensurethat they do not combine significantly when compared to statisticalerror of the BAO measurement. Baryon Oscillation Spectroscopic Survey(BOSS) Data Release 11 (DR11) reaches a distance measurement with˜1 per cent statistical error and this prompts an extensive searchfor all possible sub-per cent level systematic errors which couldpreviously be safely ignored. In this paper, we analyse the potentialsystematics in BAO fitting methodology using mocks and data from BOSSDR10 and DR11. We demonstrate the robustness of the fiducial multipolefitting methodology to be at 0.1-0.2 per cent level with a wide range oftests in mock galaxy catalogues pre- and post-reconstruction. We alsofind the DR10 and DR11 data from BOSS to be robust against changes inmethodology at a similar level. This systematic error budget isincorporated into the BOSS DR10 and DR11 BAO measurements. Of the widerange of changes we have investigated, we find that when fittingpost-reconstructed data or mocks, the only change which has an effect>0.1 per cent on the best-fitting values of distance measurements isvarying the order of the polynomials to describe the broad-band terms(˜0.2 per cent). Finally, we compare an alternative methodologydenoted as Clustering Wedges with Multipoles, and find that it isconsistent with the standard approach.
Keywords: large-scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: galaxy clustering measurements in the low-redshift sample of Data Release 11 - Tojeiro, Rita; Ross, Ashley J.; Burden, Angela; Samushia, Lado; Manera, Marc; Percival, Will J.; Beutler, Florian; Brinkmann, J.; Brownstein, Joel R.; Cuesta, Antonio J.; Dawson, Kyle; Eisenstein, Daniel J.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We present the distance measurement to z = 0.32 using the eleventh datarelease (DR) of the Sloan Digital Sky Survey-III Baryon AcousticOscillation Survey (BOSS). We use 313 780 galaxies of the low-redshift(LOWZ) sample over 7341 square degrees to compute D_V=(1264 ± 25)(r_d/r_{d,fid}) - a sub 2 per cent measurement - using the baryonacoustic feature measured in the galaxy two-point correlation functionand power spectrum. We compare our results to those obtained in DR10. Westudy observational systematics in the LOWZ sample and quantifypotential effects due to photometric offsets between the northern andsouthern Galactic caps. We find the sample to be robust to allsystematic effects found to impact on the targeting of higher redshiftBOSS galaxies and that the observed north-south tensions can beexplained by either limitations in photometric calibration or by samplevariance, and have no impact on our final result. Our measurement,combined with the baryonic acoustic scale at z = 0.57, is used inAnderson et al. to constrain cosmological parameters.
Keywords: surveys; cosmology: observations; distance scale; large-scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: testing gravity with redshift space distortions using the power spectrum multipoles - Beutler, Florian; Saito, Shun; Seo, Hee-Jong; Brinkmann, Jon; Dawson, Kyle S.; Eisenstein, Daniel J.; Font-Ribera, Andreu; Ho, Shirley; McBride, Cameron K.; Montesano, Francesco; Percival, Will J.; Ross, Ashley J.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We analyse the anisotropic clustering of the Baryon OscillationSpectroscopic Survey (BOSS) CMASS Data Release 11 (DR11) sample, whichconsists of 690 827 galaxies in the redshift range 0.43 < z < 0.7and has a sky coverage of 8498 deg2. We perform our analysisin Fourier space using a power spectrum estimator suggested by Yamamotoet al. We measure the multipole power spectra in a self-consistentmanner for the first time in the sense that we provide a proper way totreat the survey window function and the integral constraint, withoutthe commonly used assumption of an isotropic power spectrum and withoutthe need to split the survey into subregions. The main cosmologicalsignals exploited in our analysis are the baryon acoustic oscillationsand the signal of redshift space distortions, both of which aredistorted by the Alcock-Paczynski effect. Together, these signals allowus to constrain the distance ratioDV(zeff)/rs(zd) = 13.89± 0.18, the Alcock-Paczynski parameterFAP(zeff) = 0.679 ± 0.031 and the growthrate of structure f(zeff)σ8(zeff) = 0.419 ±0.044 at the effective redshift zeff = 0.57. We emphasizethat our constraints are robust against possible systematicuncertainties. In order to ensure this, we perform a detailedsystematics study against CMASS mock galaxy catalogues and N-bodysimulations. We find that such systematics will lead to 3.1 per centuncertainty for fσ8 if we limit our fitting range to k= 0.01-0.20 h Mpc-1, where the statistical uncertainty isexpected to be three times larger. We did not find significantsystematic uncertainties for DV/rs orFAP. Combining our data set with Planck to test GeneralRelativity (GR) through the simple γ-parametrization, where thegrowth rate is given by f(z) = Ω ^{γ }_m(z), reveals a˜2σ tension between the data and the prediction by GR. Thetension between our result and GR can be traced back to a tension in theclustering amplitude σ8 between CMASS and Planck.
Keywords: gravitation; surveys; cosmological parameters; cosmology: observations; dark energy; large-scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: cosmological implications of the full shape of the clustering wedges in the data release 10 and 11 galaxy samples - Sánchez, Ariel G.; Montesano, Francesco; Kazin, Eyal A.; Aubourg, Eric; Beutler, Florian; Brinkmann, Jon; Brownstein, Joel R.; Cuesta, Antonio J.; Dawson, Kyle S.; Eisenstein, Daniel J.; Ho, Shirley; Honscheid, Klaus; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We explore the cosmological implications of the angle-averagedcorrelation function, ξ(s), and the clustering wedges,ξ⊥(s) and ξ∥(s), of the LOWZ andCMASS galaxy samples from Data Releases 10 and 11 of the Sloan DigitalSky Survey III (SDSS-III) Baryon Oscillation Spectroscopic Survey. Ourresults show no significant evidence for a deviation from the standardΛ cold dark matter model. The combination of the information fromour clustering measurements with recent data from the cosmic microwavebackground is sufficient to constrain the curvature of the Universe toΩk = 0.0010 ± 0.0029, the total neutrino mass to∑mν < 0.23 eV (95 per cent confidence level), theeffective number of relativistic species to Neff = 3.31± 0.27 and the dark energy equation of state to wDE =-1.051 ± 0.076. These limits are further improved by addinginformation from Type Ia supernovae and baryon acoustic oscillationsfrom other samples. In particular, this data set combination iscompletely consistent with a time-independent dark energy equation ofstate, in which case we find wDE = -1.024 ± 0.052. Weexplore the constraints on the growth rate of cosmic structures assumingf(z) = Ωm(z)γ and obtain γ =0.69 ± 0.15, consistent with the predictions of generalrelativity of γ = 0.55.
Keywords: cosmological parameters; large-scale structure of Universe

Cosmological implications of baryon acoustic oscillation (BAO) measurements - Aubourg, Éric; Bailey, Stephen; Bautista, Julian E.; Beutler, Florian; Bhardwaj, Vaishali; Bizyaev, Dmitry; Blanton, Michael; Blomqvist, Michael; Bolton, Adam S.; Bovy, Jo; Brewington, Howard; Brinkmann, J.; et al. (ArXiv e-prints, 2014)
We derive constraints on cosmological parameters and tests of darkenergy models from the combination of baryon acoustic oscillation (BAO)measurements with cosmic microwave background (CMB) and Type Iasupernova (SN) data. We take advantage of high-precision BAOmeasurements from galaxy clustering and the Ly-alpha forest (LyaF) inthe BOSS survey of SDSS-III. BAO data alone yield a high confidencedetection of dark energy, and in combination with the CMB angularacoustic scale they further imply a nearly flat universe. Combining BAO
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; General Relativity and Quantum Cosmology; High Energy Physics - Experiment

PRIMUS: The relationship between Star formation and AGN accretion - Azadi, Mojegan; Aird, James; Coil, Alison; Moustakas, John; Mendez, Alexander; Blanton, Michael; Cool, Richard; Eisenstein, Daniel; Kenneth Wong; Zhu, Guangtun (ArXiv e-prints, 2014)
We study the evidence for a symbiotic connection between active galacticnuclei (AGN) fueling and star formation by investigating therelationship between the X-ray luminosities of AGN and the starformation rates (SFRs) of their host galaxies. We identify a sample of309 AGN with X-ray luminosities $10^{41}<L_X<10^{44} $erg s$^{-1}$ at $0.2 < z < 1.2$ in the PRIMUS spectroscopicredshift survey. There is a wide range of SFR at a given $L_X$, and wedo not find a significant correlation between SFR and the observedinstantaneous $L_X$ for star forming galaxies. However, there is a weakbut significant correlation between the mean $L_X$ of detectedAGN and SFR, which likely reflects that $L_X$ varies on shortertimescales than SFR. We also find no correlation between stellar massand AGN luminosity. AGN are found in star forming and quiescentgalaxies, and both galaxy populations have a similar power-lawdistribution in the probability of hosting an AGN as a function ofspecific accretion rate. However, a higher fraction of AGN hosts areclassified as star forming with increasing $L_X$, and a starforming galaxy is $\sim2-3$ times more likely to host an AGN of a givenspecific accretion rate than a quiescent galaxy of the same stellarmass. The probability of a galaxy hosting an AGN remains constant acrossthe main sequence of star formation. These results indicate that thereis an underlying connection between star formation and the presence ofAGN, but AGN are also widespread in quiescent galaxies.
Keywords: Astrophysics - Astrophysics of Galaxies

The Redshift Evolution of the High-Mass End of the Red Sequence Luminosity Function from the SDSS-III/BOSS CMASS Sample - Montero-Dorta, Antonio D.; Bolton, Adam S.; Brownstein, Joel R.; Swanson, Molly; Dawson, Kyle; Prada, Francisco; Eisenstein, Daniel; Maraston, Claudia; Thomas, Daniel; Comparat, Johan; Chuang, Chia-Hsun; McBride, Cameron K.; et al. (ArXiv e-prints, 2014)
We present the redshift evolution of the high-mass end of the^{0.55}i-band Red Sequence Luminosity Function (RS LF) within theredshift range 0.52<z<0.65, obtained from the DR10 BOSS CMASSsample, which comprises ~ 600,000 galaxies. We have developed ananalytical method based on an unbinned maximum likelihood approach fordeconvolving the observed CMASS distribution from photometric errors andaccounting for selection effects. This procedure requires modeling thecovariance matrix for the i-band magnitude, g-r color and r-i colorusing Stripe 82 multi-epoch data. The error-deconvolved intrinsic RSdistribution is consistent with a single point in the color-color plane,which implies that the great majority of the observed scatter is due tophotometric errors. We estimate that RS completeness is ~0.80-0.85 atz≥0.52 in the CMASS sample, dropping drastically below that redshift.
Keywords: Astrophysics - Astrophysics of Galaxies

On the signature of the baryon-dark matter relative velocity in the two and three-point galaxy correlation functions - Slepian, Zachary; Eisenstein, Daniel (ArXiv e-prints, 2014)
We develop a configuration-space picture of the relative velocitybetween baryons and dark matter that clearly explains how it can shiftthe BAO scale in the galaxy-galaxy correlation function. The shiftoccurs because the relative velocity is non-zero only within the soundhorizon and thus adds to the correlation function asymmetrically aboutthe BAO peak. We further show that in configuration space the relativevelocity has a localized, distinctive signature in the three-pointgalaxy correlation function (3PCF). In particular, we find that amultipole decomposition is a favorable way to isolate the relativevelocity in the 3PCF, and that there is a strong signature in the l=1multipole for triangles with 2 sides around the BAO scale. Finally, weinvestigate a further compression of the 3PCF to a function of only onetriangle side that preserves the localized nature of the relativevelocity signature while also nicely separating linear from non-linearbias. We expect that this scheme will substantially lessen thecomputational burden of finding the relative velocity in the 3PCF. Therelative velocity's 3PCF signature can be used to correct the shiftinduced in the galaxy-galaxy correlation function so that no systematicerror due to this effect is introduced into the BAO as used forprecision cosmology.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

PRIMUS: Effect of Galaxy Environment on the Quiescent Fraction Evolution at z < 0.8 - Hahn, ChangHoon; Blanton, Michael R.; Moustakas, John; Coil, Alison L.; Cool, Richard J.; Eisenstein, Daniel J.; Skibba, Ramin A.; Kenneth C. Wong; Zhu, Guangtun (ArXiv e-prints, 2014)
We investigate the effects of galaxy environment on the evolution of thequiescent fraction ($f_Q$) from z =0.8 to 0.0 usingspectroscopic redshifts and multi-wavelength imaging data from the PRIsmMUlti-object Survey (PRIMUS) and the Sloan Digitial Sky Survey (SDSS).Our stellar mass limited galaxy sample consists of ~14,000 PRIMUSgalaxies within z = 0.2-0.8 and ~64,000 SDSS galaxies within z =0.05-0.12. We classify the galaxies as quiescent or star-forming basedon an evolving specific star formation cut, and as low or high densityenvironments based on fixed cylindrical aperture environmentmeasurements on a volume-limited environment defining population. Forquiescent and star-forming galaxies in low or high density environments,we examine the evolution of their stellar mass function (SMF). Thenusing the SMFs we compute $f_Q(M_{*})$ and quantify itsevolution within our redshift range. We find that the quiescent fractionis higher at higher masses and in denser environments. The quiescentfraction rises with cosmic time for all masses and environments. At afiducial mass of $10^{10.5}M_\odot$, from z~0.7 to 0.1, the quiescent
Keywords: Astrophysics - Astrophysics of Galaxies

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: galaxy clustering measurements in the low redshift sample of Data Release 11 - Tojeiro, Rita; Ross, Ashley J.; Burden, Angela; Samushia, Lado; Manera, Marc; Percival, Will J.; Beutler, Florian; Cuesta, Antonio J.; Dawson, Kyle; Eisenstein, Daniel J.; Ho, Shirley; Howett, Cullan; et al. (ArXiv e-prints, 2014)
We present the distance measurement to z = 0.32 using the 11th datarelease of the Sloan Digital Sky Survey-III Baryon Acoustic OscillationSurvey (BOSS). We use 313,780 galaxies of the low-redshift (LOWZ) sampleover 7,341 square-degrees to compute $D_V = (1264 ±
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: modeling of the luminosity and colour dependence in the Data Release 10 - Guo, Hong; Zheng, Zheng; Zehavi, Idit; Xu, Haojie; Eisenstein, Daniel J.; Weinberg, David H.; Bahcall, Neta A.; Berlind, Andreas A.; Comparat, Johan; McBride, Cameron K.; Ross, Ashley J.; Schneider, Donald P.; et al. (ArXiv e-prints, 2014)
We investigate the luminosity and colour dependence of clustering ofCMASS galaxies in the Sloan Digital Sky Survey-III Baryon OscillationSpectroscopic Survey Tenth Data Release. The halo occupationdistribution framework is adopted to model the projected two-pointcorrelation function measurements on small and intermediate scales (from$0.02$ to $60\,h^{-1}{\rm {Mpc}}$) and to interpret the observed trendsand infer the connection of galaxies to dark matter halos. We find thatluminous red galaxies reside in massive halos of mass$M{\sim}10^{13}$--$10^{14}\,h^{-1}{\rm M_\odot}$ and more luminousgalaxies are more clustered and hosted by more massive halos. The strongsmall-scale clustering requires a fraction of these galaxies to besatellites in massive halos, with the fraction at the level of 5--8 percent and decreasing with luminosity. The characteristic mass of a halohosting on average one satellite galaxy above a luminosity threshold isabout a factor $8.7$ larger than that of a halo hosting a central galaxyabove the same threshold. At a fixed luminosity, progressively reddergalaxies are more strongly clustered on small scales, which can beexplained by having a larger fraction of these galaxies in the form ofsatellites in massive halos. Our clustering measurements on scales below$0.4\,h^{-1}{\rm {Mpc}}$ allow us to study the small-scale spatialdistribution of satellites inside halos. While the clustering ofluminosity-threshold samples can be well described by aNavarro-Frenk-White (NFW) profile, that of the reddest galaxies prefersa steeper or more concentrated profile. Finally, we also use galaxysamples of constant number density at different redshifts to study theevolution of luminous galaxies, and find the clustering to be consistentwith passive evolution in the redshift range of $0.5 \lesssim z \lesssim0.6$.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

The clustering of Galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: including covariance matrix errors - Percival, Will J.; Ross, Ashley J.; Sánchez, Ariel G.; Samushia, Lado; Burden, Angela; Crittenden, Robert; Cuesta, Antonio J.; Magana, Mariana Vargas; Manera, Marc; Beutler, Florian; Chuang, Chia-Hsun; Eisenstein, Daniel J.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We present improved methodology for including covariance matrices in theerror budget of Baryon Oscillation Spectroscopic Survey (BOSS) galaxyclustering measurements, revisiting Data Release 9 (DR9) analyses, anddescribing a method that is used in DR10/11 analyses presented incompanion papers. The precise analysis method adopted is becomingincreasingly important, due to the precision that BOSS can now reach:even using as many as 600 mock catalogues to estimate covariance oftwo-point clustering measurements can still lead to an increase in theerrors of ˜20 per cent, depending on how the cosmologicalparameters of interest are measured. In this paper, we extend previouswork on this contribution to the error budget, deriving formulae forerrors measured by integrating over the likelihood, and to thedistribution of recovered best-fitting parameters fitting thesimulations also used to estimate the covariance matrix. Both aresituations that previous analyses of BOSS have considered. We apply theformulae derived to baryon acoustic oscillation (BAO) and redshift-spacedistortion (RSD) measurements from BOSS in our companion papers. Tofurther aid these analyses, we consider the optimum number of bins touse for two-point measurements using the monopole power spectrum orcorrelation function for BAO, and the monopole and quadrupole moments ofthe correlation function for anisotropic-BAO and RSD measurements.
Keywords: cosmology: observations; distance scale; large-scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: measuring DA and H at z = 0.57 from the baryon acoustic peak in the Data Release 9 spectroscopic Galaxy sample - Anderson, Lauren; Aubourg, Eric; Bailey, Stephen; Beutler, Florian; Bolton, Adam S.; Brinkmann, J.; Brownstein, Joel R.; Chuang, Chia-Hsun; Cuesta, Antonio J.; Dawson, Kyle S.; Eisenstein, Daniel J.; Ho, Shirley; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We present measurements of the angular diameter distance to and Hubbleparameter at z = 0.57 from the measurement of the baryon acoustic peakin the correlation of galaxies from the Sloan Digital Sky Survey IIIBaryon Oscillation Spectroscopic Survey. Our analysis is based on asample from Data Release 9 of 264 283 galaxies over 3275 square degreesin the redshift range 0.43 < z < 0.70. We use two differentmethods to provide robust measurement of the acoustic peak positionacross and along the line of sight in order to measure the cosmologicaldistance scale. We find DA(0.57) = 1408 ± 45 Mpc andH(0.57) = 92.9 ± 7.8 km s-1 Mpc-1 for ourfiducial value of the sound horizon. These results from the anisotropicfitting are fully consistent with the analysis of the sphericallyaveraged acoustic peak position presented in Anderson et al. Ourdistance measurements are a close match to the predictions of thestandard cosmological model featuring a cosmological constant and zerospatial curvature.
Keywords: cosmological parameters; cosmology: observations; dark energy; distance scale; large scale structure of Universe

The clustering of galaxies in the SDSS-III DR10 Baryon Oscillation Spectroscopic Survey: no detectable colour dependence of distance scale or growth rate measurements - Ross, Ashley J.; Samushia, Lado; Burden, Angela; Percival, Will J.; Tojeiro, Rita; Manera, Marc; Beutler, Florian; Brinkmann, J.; Brownstein, Joel R.; Carnero, Aurelio; da Costa, Luiz A. N.; Eisenstein, Daniel J.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We study the clustering of galaxies, as a function of their colour, fromData Release Ten (DR10) of the Sloan Digital Sky Survey III (SDSS-III)Baryon Oscillation Spectroscopic Survey. DR10 contains 540 505 galaxieswith 0.43 < z < 0.7; from these we select 122 967 for a `Blue'sample and 131 969 for a `Red' sample based on k + e corrected (to z =0.55) r - i colours and i-band magnitudes. The samples are chosen suchthat both contain more than 100 000 galaxies, have similar redshiftdistributions and maximize the difference in clustering amplitude. TheRed sample has a 40 per cent larger bias than the Blue(bRed/bBlue = 1.39 ± 0.04), implying thatthe Red galaxies occupy dark matter haloes with an average mass that is0.5 log10 M⊙ greater. Spherically averagedmeasurements of the correlation function, ξ0, and thepower spectrum are used to locate the position of the baryon acousticoscillation (BAO) feature of both samples. Using ξ0, weobtain distance scales, relative to the distance of our referenceΛ cold dark matter cosmology, of 1.010 ± 0.027 for the Redsample and 1.005 ± 0.031 for the Blue. After applyingreconstruction, these measurements improve to 1.013 ± 0.020 forthe Red sample and 1.008 ± 0.026 for the Blue. For each sample,measurements of ξ0 and the second multipole moment,ξ2, of the anisotropic correlation function are used todetermine the rate of structure growth, parametrized byfσ8. We find fσ8, Red = 0.511 ±0.083, fσ8, Blue = 0.509 ± 0.085 andfσ8, Cross = 0.423 ± 0.061 (from thecross-correlation between the Red and Blue samples). We use thecovariance between the bias and growth measurements obtained from eachsample and their cross-correlation to produce an optimally combinedmeasurement of fσ8, comb = 0.443 ± 0.055. Thisresult compares favourably to that of the full 0.43 < z < 0.7sample (fσ8, full = 0.422 ± 0.051) despite thefact that, in total, we use less than half of the number of galaxiesanalysed in the full sample measurement. In no instance do we detectsignificant differences in distance scale or structure growthmeasurements obtained from the Blue and Red samples. Our results areconsistent with theoretical predictions and our tests on mock samples,which predict that any colour-dependent systematic uncertainty on themeasured BAO position is less than 0.5 per cent.
Keywords: cosmology: observations; distance scale; large-scale structure of Universe

Discovery of a Dynamical Cold Point in the Heart of the Sagittarius dSph Galaxy with Observations from the APOGEE Project - Majewski, Steven R.; Hasselquist, Sten; Łokas, Ewa L.; Nidever, David L.; Frinchaboy, Peter M.; García Pérez, Ana E.; Johnston, Kathryn V.; Mészáros, Szabolcs; Shetrone, Matthew; Allende Prieto, Carlos; Beaton, Rachael L.; Beers, Timothy C.; et al. (The Astrophysical Journal Letters, 2013)
The dynamics of the core of the Sagittarius (Sgr) dwarf spheroidal(dSph) galaxy are explored using high-resolution (R ~ 22, 500), H-band,near-infrared spectra of over 1000 giant stars in the central 3deg2 of the system, of which 328 are identified as Sgrmembers. These data, among some of the earliest observations from theSloan Digital Sky Survey III/Apache Point Observatory Galactic EvolutionExperiment (APOGEE) and the largest published sample of high resolutionSgr dSph spectra to date, reveal a distinct gradient in the velocitydispersion of Sgr from 11 to 14 km s-1 for radii>0.°8 from center to a dynamical cold point of 8 kms-1 in the Sgr center—a trend differing from thatfound in previous kinematical analyses of Sgr over larger scales thatsuggests a more or less flat dispersion profile at these radii.Well-fitting mass models with either cored and cusped dark matterdistributions can be found to match the kinematical results, althoughthe cored profile succeeds with significantly more isotropic stellarorbits than required for a cusped profile. It is unlikely that the coldpoint reflects an unusual mass distribution. The dispersion gradient mayarise from variations in the mixture of populations with distinctkinematics within the dSph; this explanation is suggested (e.g., bydetection of a metallicity gradient across similar radii), but notconfirmed, by the present data. Despite these remaining uncertaintiesabout their interpretation, these early test data (including some frominstrument commissioning) demonstrate APOGEE's usefulness for precisiondynamical studies, even for fields observed at extreme airmasses.
Keywords: galaxies: dwarf; galaxies: individual: Sagittarius dSph; galaxies: interactions; galaxies: kinematics and dynamics; galaxies: stellar content; galaxies: structure

Distance Probes of Dark Energy - Kim, A.; Padmanabhan, N.; Aldering, G.; Allen, S.; Baltay, C.; Cahn, R.; D'Andrea, C.; Dalal, N.; Dawson, K.; Denney, K.; Eisenstein, D.; D. Finley; et al. (ArXiv e-prints, 2013)
This document presents the results from the Distances subgroup of theCosmic Frontier Community Planning Study (Snowmass 2013). We summarizethe current state of the field as well as future prospects andchallenges. In addition to the established probes using Type IAsupernovae and baryon acoustic oscillations, we also considerprospective methods based on clusters, active galactic nuclei,gravitational wave sirens and strong lensing time delays.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics

Observational probes of cosmic acceleration - Weinberg, David H.; Mortonson, Michael J.; Eisenstein, Daniel J.; Hirata, Christopher; Riess, Adam G.; Rozo, Eduardo (Physics Reports, 2013)
The accelerating expansion of the universe is the most surprisingcosmological discovery in many decades, implying that the universe isdominated by some form of "dark energy" with exotic physical properties,or that Einstein's theory of gravity breaks down on cosmological scales.The profound implications of cosmic acceleration have inspired ambitiousefforts to understand its origin, with experiments that aim to measurethe history of expansion and growth of structure with percent-levelprecision or higher. We review in detail the four most well establishedmethods for making such measurements: Type Ia supernovae, baryonacoustic oscillations (BAO), weak gravitational lensing, and theabundance of galaxy clusters. We pay particular attention to thesystematic uncertainties in these techniques and to strategies forcontrolling them at the level needed to exploit "Stage IV" dark energyfacilities such as BigBOSS, LSST, Euclid, and WFIRST. We briefly reviewa number of other approaches including redshift-space distortions, theAlcock-Paczynski effect, and direct measurements of the Hubble constantH0. We present extensive forecasts for constraints on thedark energy equation of state and parameterized deviations from GeneralRelativity, achievable with Stage III and Stage IV experimental programsthat incorporate supernovae, BAO, weak lensing, and cosmic microwavebackground data. We also show the level of precision required forclusters or other methods to provide constraints competitive with thoseof these fiducial programs. We emphasize the value of a balanced programthat employs several of the most powerful methods in combination, bothto cross-check systematic uncertainties and to take advantage ofcomplementary information. Surveys to probe cosmic acceleration producedata sets that support a wide range of scientific investigations, andthey continue the longstanding astronomical tradition of mapping theuniverse in ever greater detail over ever larger scales.

Characterizing unknown systematics in large scale structure surveys - Agarwal, Nishant; Ho, Shirley; Myers, Adam D.; Seo, Hee-Jong; Ross, Ashley J.; Bahcall, Neta; Brinkmann, Jonathan; Eisenstein, Daniel J.; Muna, Demitri; Palanque-Delabrouille, Nathalie; Pâris, Isabelle; Petitjean, Patrick; et al. (ArXiv e-prints, 2013)
Photometric large scale structure (LSS) surveys probe the largestvolumes in the Universe, but are inevitably limited by systematicuncertainties. Imperfect photometric calibration leads to biases in ourmeasurements of the density fields of LSS tracers such as galaxies andquasars, and as a result in cosmological parameter estimation. Earlierstudies have proposed using cross-correlations between differentredshift slices or cross-correlations between different surveys toreduce the effects of such systematics. In this paper we develop amethod to characterize unknown systematics. We demonstrate that while wedo not have sufficient information to correct for unknown systematics inthe data, we can obtain an estimate of their magnitude. We define aparameter to estimate contamination from unknown systematics usingcross-correlations between different redshift slices and proposediscarding bins in the angular power spectrum that lie outside a certaincontamination tolerance level. We show that this method improvesestimates of the bias using simulated data and further apply it tophotometric luminous red galaxies in the Sloan Digital Sky Survey as acase study.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

The DESI Experiment, a whitepaper for Snowmass 2013 - Levi, Michael; Bebek, Chris; Beers, Timothy; Blum, Robert; Cahn, Robert; Eisenstein, Daniel; Flaugher, Brenna; Honscheid, Klaus; Kron, Richard; Lahav, Ofer; McDonald, Patrick; Roe, Natalie; et al. (ArXiv e-prints, 2013)
The Dark Energy Spectroscopic Instrument (DESI) is a massivelymultiplexed fiber-fed spectrograph that will make the next major advancein dark energy in the timeframe 2018-2022. On the Mayall telescope, DESIwill obtain spectra and redshifts for at least 18 million emission-linegalaxies, 4 million luminous red galaxies and 3 million quasi-stellarobjects, in order to: probe the effects of dark energy on the expansionhistory using baryon acoustic oscillations (BAO), measure thegravitational growth history through redshift-space distortions, measurethe sum of neutrino masses, and investigate the signatures of primordialinflation. The resulting 3-D galaxy maps at z<2 and Lyman-alpha
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics; Astrophysics - Instrumentation and Methods for Astrophysics

Distance Probes of Dark Energy - Kim, A.; Padmanabhan, N.; Aldering, G.; Allen, S.; Baltay, C.; Cahn, R.; D'Andrea, C.; Dalal, N.; Dawson, K.; Denney, K.; Eisenstein, D.; D. Finley; et al. (ArXiv e-prints, 2013)
This document presents the results from the Distances subgroup of theCosmic Frontier Community Planning Study (Snowmass 2013). We summarizethe current state of the field as well as future prospects andchallenges. In addition to the established probes using Type IAsupernovae and baryon acoustic oscillations, we also considerprospective methods based on clusters, active galactic nuclei,gravitational wave sirens and strong lensing time delays.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

The Tenth Data Release of the Sloan Digital Sky Survey: First Spectroscopic Data from the SDSS-III Apache Point Observatory Galactic Evolution Experiment - Ahn, Christopher P.; Alexandroff, Rachael; Allende Prieto, Carlos; Anders, Friedrich; Anderson, Scott F.; Anderton, Timothy; Andrews, Brett H.; Aubourg, Éric; Bailey, Stephen; Bastien, Fabienne A.; Bautista, Julian E.; Beers, Timothy C.; et al. (ArXiv e-prints, 2013)
The Sloan Digital Sky Survey (SDSS) has been in operation since 2000April. This paper presents the tenth public data release (DR10) from itscurrent incarnation, SDSS-III. This data release includes the firstspectroscopic data from the Apache Point Observatory Galaxy EvolutionExperiment (APOGEE), along with spectroscopic data from the BaryonOscillation Spectroscopic Survey (BOSS) taken through 2012 July. TheAPOGEE instrument is a near-infrared R~22,500 300-fiber spectrographcovering 1.514--1.696 microns. The APOGEE survey is studying thechemical abundances and radial velocities of roughly 100,000 red giantstar candidates in the bulge, bar, disk, and halo of the Milky Way. DR10includes 178,397 spectra of 57,454 stars, each typically observed threeor more times, from APOGEE. Derived quantities from these spectra(radial velocities, effective temperatures, surface gravities, andmetallicities) are also included.DR10 also roughly doubles the number ofBOSS spectra over those included in the ninth data release. DR10includes a total of 1,507,954 BOSS spectra, comprising 927,844 galaxyspectra; 182,009 quasar spectra; and 159,327 stellar spectra, selectedover 6373.2 square degrees.
Keywords: Astrophysics - Instrumentation and Methods for Astrophysics; Astrophysics - Cosmology and Extragalactic Astrophysics; Astrophysics - Galaxy Astrophysics

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: Baryon Acoustic Oscillations in the Data Release 10 and 11 galaxy samples - Anderson, Lauren; Aubourg, Eric; Bailey, Stephen; Beutler, Florian; Bhardwaj, Vaishali; Blanton, Michael; Bolton, Adam S.; Brinkmann, J.; Brownstein, Joel R.; Burden, Angela; Chuang, Chia-Hsun; Cuesta, Antonio J.; et al. (ArXiv e-prints, 2013)
We present a one per cent measurement of the cosmic distance scale fromthe detections of the baryon acoustic oscillations in the clustering ofgalaxies from the Baryon Oscillation Spectroscopic Survey (BOSS), whichis part of the Sloan Digital Sky Survey III (SDSS-III). Our results comefrom the Data Release 11 (DR11) sample, containing nearly one milliongalaxies and covering approximately 8500 square degrees and the redshiftrange $0.2<z<0.7$. We also compare these results with those fromthe publicly released DR9 and DR10 samples. Assuming a concordance$Λ$CDM cosmological model, the DR11 sample covers a volume of13Gpc${}^3$ and is the largest region of the Universe ever surveyed atthis density. We measure the correlation function and power spectrum,including density-field reconstruction of the baryon acousticoscillation (BAO) feature. The acoustic features are detected at asignificance of over $7σ$ in both the correlation function andpower spectrum. Fitting for the position of the acoustic featuresmeasures the distance relative to the sound horizon at the drag epoch,$r_d$, which has a value of $r_{d,{\rm fid}}=149.28$Mpc in our fiducialcosmology. We find $D_V=(1264±25\,{\rm Mpc})(r_d/r_{d,{\rm fid}})$ at$z=0.32$ and $D_V=(2056±20\,{\rm Mpc})(r_d/r_{d,{\rm fid}})$ at$z=0.57$. At 1.0 per cent, this latter measure is the most precisedistance constraint ever obtained from a galaxy survey. Separating theclustering along and transverse to the line-of-sight yields measurementsat $z=0.57$ of $D_A=(1421±20\,{\rm Mpc})(r_d/r_{d,{\rm fid}})$ and$H=(96.8±3.4\,{\rm km/s/Mpc})(r_{d,{\rm fid}}/r_d)$. Our measurementsof the distance scale are in good agreement with previous BAOmeasurements and with the predictions from cosmic microwave backgrounddata for a spatially flat cold dark matter model with a cosmologicalconstant.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: single-probe measurements from CMASS and LOWZ anisotropic galaxy clustering - Chuang, Chia-Hsun; Prada, Francisco; Beutler, Florian; Eisenstein, Daniel J.; Escoffier, Stephanie; Ho, Shirley; Kneib, Jean-Paul; Manera, Marc; Nuza, Sebastian E.; Schlegel, David J.; Schneider, Donald P.; Weaver, Benjamin A.; et al. (ArXiv e-prints, 2013)
With the largest spectroscopic galaxy survey volume drawn from theSDSS-III Baryon Oscillation Spectroscopic Survey (BOSS), we can extractcosmological constraints from the measurements of redshift and geometricdistortions at quasi-linear scales (e.g. above 50 Mpc/h), which can bemodeled by perturbation theory. We analyze the broad-range shape of themonopole and quadrupole correlation functions of the BOSS Data Release11 (DR11) CMASS galaxy sample, at the effective redshift z=0.57, toobtain constraints on the Hubble expansion rate H(z), theangular-diameter distance D_A(z), the normalized growth ratef(z)σ_8(z), and the physical matter density Ω_mh^2. We provideaccurate measurements on {H^{-1}R_{fid}^{-1.0}, D_A R_{fid}^{-0.96},fσ_8(Ω_m h^2)^{0.45}}, where R_{fid}\equiv r_s/r_{s,fid}, r_sis the comoving sound horizon at the drag epoch, and r_{s,fid} is thesound scale of the fiducial cosmology used in this study. We alsoextract cosmological constraints from BOSS DR11 LOWZ sample, at theeffective redshift z=0.32, by including small scales (e.g., down to 30Mpc/h), and model small scales with Finger of God effect. The parameterswhich are not well constrained by our galaxy clustering analysis aremarginalized over with wide flat priors. Since no priors from other datasets, e.g., cosmic microwave background (CMB), are adopted and no darkenergy models are assumed, our results from BOSS CMASS and LOWZ galaxyclustering alone may be combined with other data sets, i.e., CMB, SNe,lensing or other galaxy clustering data to constrain the parameters of agiven cosmological model. We find the redshift distortion measurementsfrom most of the galaxy clustering analyses (including this study) favorWMAP9 than Planck and favor wCDM than \LambdaCDM or o\LambdaCDM. Theuncertainty on the dark energy equation of state parameter fromCMB+CMASS is about 8 per cent.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

The Clustering of Galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: Measuring growth rate and geometry with anisotropic clustering - Samushia, Lado; Reid, Beth A.; White, Martin; Percival, Will J.; Cuesta, Antonio J.; Zhao, Gong-bo; Ross, Ashley J.; Manera, Marc; Aubourg, Éric; Beutler, Florian; Brinkmann, Jon; Brownstein, Joel R.; et al. (ArXiv e-prints, 2013)
We use the observed anisotropic clustering of galaxies in the BaryonOscillation Spectroscopic Survey Data Release 11 CMASS sample to measurethe linear growth rate of structure, the Hubble expansion rate and thecomoving distance scale. Our sample covers 8498 ${\rm deg}^2$ andencloses an effective volume of 6.0 ${\rm Gpc}^3$ at an effectiveredshift of $\bar{z} = 0.57$. We find $fσ_8 = 0.441 ± 0.044$, $H= 93.1 ± 3.0\ {km\ s^{-1} Mpc^{-1}}$ and$D_{\rm A} = 1380 ± 23\ {\rm Mpc}$ when fitting the growth andexpansion rate simultaneously. When we fix the background expansion tothe one predicted by spatially-flat $Λ$CDM model in agreement withrecent Planck results, we find $fσ_8 = 0.447 ± 0.028$ (6 per centaccuracy). While our measurements are generally consistent with thepredictions of $Λ$CDM and General Relativity, they mildly favormodels in which the strength of gravitational interactions is weakerthan what is predicted by General Relativity. Combining our measurementswith recent cosmic microwave background data results in tightconstraints on basic cosmological parameters and deviations from thestandard cosmological model. Separately varying these parameters, wefind $w = -0.983 ± 0.075$ (8 per cent accuracy) and $γ = 0.69 ±0.11$ (16 per cent accuracy) for the effective equation of state of darkenergy and the growth rate index, respectively. Both constraints are ingood agreement with the standard model values of $w=-1$ and $γ =0.554$.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: Testing gravity with redshift-space distortions using the power spectrum multipoles - Beutler, Florian; Saito, Shun; Seo, Hee-Jong; Brinkmann, Jon; Dawson, Kyle S.; Eisenstein, Daniel J.; Font-Ribera, Andreu; Ho, Shirley; McBride, Cameron K.; Montesano, Francesco; Percival, Will J.; Ross, Ashley J.; et al. (ArXiv e-prints, 2013)
We analyse the anisotropic clustering of the Baryon OscillationSpectroscopic Survey (BOSS) CMASS Data Release 11 (DR11) sample, whichconsists of $690\,827$ galaxies in the redshift range $0.43 < z <0.7$ and has a sky coverage of $8\,498\,$deg$^2$. We perform ouranalysis in Fourier space using a power spectrum estimator suggested byYamamoto et al. (2006). We measure the multipole power spectra in aself-consistent manner for the first time in the sense that we provide aproper way to treat the survey window function and the integralconstraint, without the commonly used assumption of an isotropic powerspectrum and without the need to split the survey into sub-regions. Themain cosmological signals exploited in our analysis are the BaryonAcoustic Oscillations and the signal of redshift space distortions, bothof which are distorted by the Alcock-Paczynski effect. Together, thesesignals allow us to constrain the distance ratio $D_V(z_{\rmeff})/r_s(z_d) = 13.89± 0.18$, the Alcock-Paczynski parameter $F_{\rmAP}(z_{\rm eff}) = 0.679±0.031$ and the growth rate of structure$f(z_{\rm eff})σ_8(z_{\rm eff}) = 0.419±0.044$ at the effectiveredshift $z_{\rm eff}=0.57$. Combining our dataset with Planck to testGeneral Relativity (GR) through the simple $γ$-parameterisation,where the growth rate is given by $f(z) = Ω^{γ}_m(z)$, revealsa $\sim 2σ$ tension between the data and the prediction by GR. Thetension between our result and GR can be traced back to a tension in theclustering amplitude $σ_8$ between CMASS and Planck.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: cosmological implications of the full shape of the clustering wedges in the data release 10 and 11 galaxy samples - Sanchez, Ariel G.; Montesano, Francesco; Kazin, Eyal A.; Aubourg, Eric; Beutler, Florian; Brinkmann, Jon; Brownstein, Joel R.; Cuesta, Antonio J.; Dawson, Kyle S.; Eisenstein, Daniel J.; Ho, Shirley; Honscheid, Klaus; et al. (ArXiv e-prints, 2013)
We explore the cosmological implications of the angle-averagedcorrelation function, xi(s), and the clustering wedges, xi_perp(s) andxi_para(s), of the LOWZ and CMASS galaxy samples from Data Release 10and 11 of the SDSS-III Baryon Oscillation Spectroscopic Survey. Ourresults show no significant evidence for a deviation from the standardLCDM model. The combination of the information from our clusteringmeasurements with recent data from the cosmic microwave background issufficient to constrain the curvature of the Universe to Omega_k =
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

PRIMUS: Galaxy Clustering as a Function of Luminosity and Color at 0.2<z<1 - Skibba, Ramin A.; Smith, M. Stephen M.; Coil, Alison L.; Moustakas, John; Aird, James; Blanton, Michael R.; Bray, Aaron D.; Cool, Richard J.; Eisenstein, Daniel J.; Mendez, Alexander J.; Kenneth C. Wong; Zhu, Guangtun (ArXiv e-prints, 2013)
We present measurements of the luminosity and color-dependence of galaxyclustering at 0.2<z<1.0 in the PRIsm MUlti-object Survey (PRIMUS).We quantify the clustering with the redshift-space and projectedtwo-point correlation functions, xi(rp,pi) and wp(rp), usingvolume-limited samples constructed from a parent sample of over 130,000galaxies with robust redshifts in seven independent fields covering 9sq. deg. of sky. We quantify how the scale-dependent clusteringamplitude increases with increasing luminosity and redder color, withrelatively small errors over large volumes. We find that red galaxieshave stronger small-scale (0.1<rp<1 Mpc/h) clustering and steepercorrelation functions compared to blue galaxies, as well as a strongcolor dependent clustering within the red sequence alone. We interpretour measured clustering trends in terms of galaxy bias and obtain valuesbetween b_gal=0.9-2.5, quantifying how galaxies are biased tracers ofdark matter depending on their luminosity and color. We also interpretthe color dependence with mock catalogs, and find that the clustering ofblue galaxies is nearly constant with color, while redder galaxies havestronger clustering in the one-halo term due to a higher satellitegalaxy fraction. In addition, we measure the evolution of the clusteringstrength and bias, and we do not detect statistically significantdepartures from passive evolution. We argue that the luminosity- andcolor-environment (or halo mass) relations of galaxies have notsignificantly evolved since z=1. Finally, using jackknife subsamplingmethods, we find that sampling fluctuations are important and that theCOSMOS field is generally an outlier, due to having more overdensestructures than other fields; we find that 'cosmic variance' can be asignificant source of uncertainty for high-redshift clusteringmeasurements.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

Quasar-Lyman $α$ Forest Cross-Correlation from BOSS DR11 : Baryon Acoustic Oscillations - Font-Ribera, Andreu; Kirkby, David; Busca, Nicolas; Miralda-Escudé, Jordi; Ross, Nicholas P.; Slosar, Anže; Aubourg, Éric; Bailey, Stephen; Bhardwaj, Vaishali; Bautista, Julian; Beutler, Florian; Bizyaev, Dmitry; et al. (ArXiv e-prints, 2013)
We measure the large-scale cross-correlation of quasars with the Lymanalpha forest absorption, using over 164,000 quasars from Data Release 11of the SDSS-III Baryon Oscillation Spectroscopic Survey. We extend theprevious study of roughly 60,000 quasars from Data Release 9 to largerseparations, allowing a measurement of the Baryonic Acoustic Oscillation(BAO) scale along the line of sight $c/(H(z=2.36) ~ r_s) = 9.0 ± 0.3$and across the line of sight $D_A(z=2.36)~ / ~ r_s = 10.8 ± 0.4$,consistent with CMB and other BAO data. Using the best fit value of thesound horizon from Planck data ($r_s=147.49 Mpc$), we can translatethese results to a measurement of the Hubble parameter of $H(z=2.36) =226 ± 8 km/s$ and of the angular diameter distance of $D_A(z=2.36) =1590 ± 60 Mpc$. The measured cross-correlation function and an updateof the code to fit the BAO scale (baofit) are made publicly available.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

SDSS-III Baryon Oscillation Spectroscopic Survey: Analysis of Potential Systematics in Fitting of Baryon Acoustic Feature - Vargas Magaña, Mariana; Ho, Shirley; Xu, Xiaoying; Sánchez, Ariel G.; O'Connell, Ross; Eisenstein, Daniel J.; Cuesta, Antonio J.; Percival, Will J.; Ross, Ashley J.; Aubourg, Eric; Kirkby, Stéphanie Escoffier David; Manera, Marc; et al. (ArXiv e-prints, 2013)
Extraction of the Baryon Acoustic Oscillations (BAO) to percent levelaccuracy is challenging and demands an understanding of many potentialsystematic to an accuracy well below 1 per cent, in order ensure thatthey do not combine significantly when compared to statistical error ofthe BAO measurement. Sloan Digital Sky Survey (SDSS)-III BaryonOscillation Spectroscopic Survey (BOSS) SDSS Data Release Eleven (DR11)
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

The Baryon Oscillation Spectroscopic Survey of SDSS-III - Dawson, Kyle S.; Schlegel, David J.; Ahn, Christopher P.; Anderson, Scott F.; Aubourg, Éric; Bailey, Stephen; Barkhouser, Robert H.; Bautista, Julian E.; Beifiori, Alessandra; Berlind, Andreas A.; Bhardwaj, Vaishali; Bizyaev, Dmitry; et al. (The Astronomical Journal, 2013)
The Baryon Oscillation Spectroscopic Survey (BOSS) is designed tomeasure the scale of baryon acoustic oscillations (BAO) in theclustering of matter over a larger volume than the combined efforts ofall previous spectroscopic surveys of large-scale structure. BOSS uses1.5 million luminous galaxies as faint as i = 19.9 over 10,000deg2 to measure BAO to redshifts z < 0.7. Observations ofneutral hydrogen in the Lyα forest in more than 150,000 quasarspectra (g < 22) will constrain BAO over the redshift range 2.15 <z < 3.5. Early results from BOSS include the first detection of thelarge-scale three-dimensional clustering of the Lyα forest and astrong detection from the Data Release 9 data set of the BAO in theclustering of massive galaxies at an effective redshift z = 0.57. Weproject that BOSS will yield measurements of the angular diameter
Keywords: cosmology: observations; surveys

SDSS DR7 White Dwarf Catalog - Kleinman, S. J.; Kepler, S. O.; Koester, D.; Pelisoli, Ingrid; Peçanha, Viviane; Nitta, A.; Costa, J. E. S.; Krzesinski, J.; Dufour, P.; Lachapelle, F.-R.; Bergeron, P.; Yip, Ching-Wa; et al. (The Astrophysical Journal Supplement Series, 2013)
We present a new catalog of spectroscopically confirmed white dwarfstars from the Sloan Digital Sky Survey (SDSS) Data Release 7spectroscopic catalog. We find 20,407 white dwarf spectra, representing19,712 stars, and provide atmospheric model fits to 14,120 DA and 1011DB white dwarf spectra from 12,843 and 923 stars, respectively. Thesenumbers represent more than a factor of two increase in the total numberof white dwarf stars from the previous SDSS white dwarf catalogs basedon DR4 data. Our distribution of subtypes varies from previous catalogsdue to our more conservative, manual classifications of each star in ourcatalog, supplementing our automatic fits. In particular, we find alarge number of magnetic white dwarf stars whose small Zeeman splittingsmimic increased Stark broadening that would otherwise result in anoverestimated log g if fit as a non-magnetic white dwarf. We calculatemean DA and DB masses for our clean, non-magnetic sample and find the DBmean mass is statistically larger than that for the DAs.
Keywords: catalogs; magnetic fields; stars: luminosity function; mass function; surveys; white dwarfs

Baryon acoustic oscillations in the Lyα forest of BOSS quasars - Busca, N. G.; Delubac, T.; Rich, J.; Bailey, S.; Font-Ribera, A.; Kirkby, D.; Le Goff, J.-M.; Pieri, M. M.; Slosar, A.; Aubourg, É.; Bautista, J. E.; Bizyaev, D.; et al. (Astronomy and Astrophysics, 2013)
We report a detection of the baryon acoustic oscillation (BAO) featurein the three-dimensional correlation function of the transmitted fluxfraction in the Lyα forest of high-redshift quasars. The studyuses 48 640 quasars in the redshift range 2.1 ≤ z ≤ 3.5 from theBaryon Oscillation Spectroscopic Survey (BOSS) of the third generationof the Sloan Digital Sky Survey (SDSS-III). At a mean redshift z = 2.3,we measure the monopole and quadrupole components of the correlationfunction for separations in the range 20 h-1 Mpc < r <200 h-1 Mpc. A peak in the correlation function is seen at aseparation equal to (1.01 ± 0.03) times the distance expected forthe BAO peak within a concordance ΛCDM cosmology. This firstdetection of the BAO peak at high redshift, when the universe wasstrongly matter dominated, results in constraints on the angulardiameter distance DA and the expansion rate H at z = 2.3that, combined with priors on H0 and the baryon density,require the existence of dark energy. Combined with constraints derivedfrom cosmic microwave background observations, this result implies H(z =2.3) = (224 ± 8) km s-1 Mpc-1, indicatingthat the time derivative of the cosmological scale parameter ȧ =H(z = 2.3)/(1 + z) is significantly greater than that measured with BAOat z ~ 0.5. This demonstrates that the expansion was decelerating in therange 0.7 < z < 2.3, as expected from the matter domination duringthis epoch. Combined with measurements of H0, one sees thepattern of deceleration followed by acceleration characteristic of adark-energy dominated universe.Appendices are available in electronic form at <Ahref="http://www.aanda.org">http://www.aanda.org
Keywords: cosmology: observations; dark energy; large-scale structure of Universe; cosmological parameters

The BOSS Lyα Forest Sample from SDSS Data Release 9 - Lee, Khee-Gan; Bailey, Stephen; Bartsch, Leslie E.; Carithers, William; Dawson, Kyle S.; Kirkby, David; Lundgren, Britt; Margala, Daniel; Palanque-Delabrouille, Nathalie; Pieri, Matthew M.; Schlegel, David J.; Weinberg, David H.; et al. (The Astronomical Journal, 2013)
We present the BOSS Lyman-α (Lyα) Forest Sample from SDSSData Release 9, comprising 54,468 quasar spectra with z qso> 2.15 suitable for Lyα forest analysis. This data set probesthe intergalactic medium with absorption redshifts 2.0 < zα < 5.7 over an area of 3275 deg2, andencompasses an approximate comoving volume of 20 h -3Gpc3. With each spectrum, we have included several productsdesigned to aid in Lyα forest analysis: improved sky masks thatflag pixels where data may be unreliable, corrections for known biasesin the pipeline estimated noise, masks for the cores of damped Lyαsystems and corrections for their wings, and estimates of the unabsorbedcontinua so that the observed flux can be converted to a fractionaltransmission. The continua are derived using a principal component fitto the quasar spectrum redward of rest-frame Lyα (λ >1216 Å), extrapolated into the forest region and normalized by alinear function to fit the expected evolution of the Lyα forest
Keywords: intergalactic medium; methods: data analysis; quasars: absorption lines; quasars: emission lines

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: the low-redshift sample - Parejko, John K.; Sunayama, Tomomi; Padmanabhan, Nikhil; Wake, David A.; Berlind, Andreas A.; Bizyaev, Dmitry; Blanton, Michael; Bolton, Adam S.; van den Bosch, Frank; Brinkmann, Jon; Brownstein, Joel R.; da Costa, Luiz Alberto Nicolaci; et al. (Monthly Notices of the Royal Astronomical Society, 2013)
We report on the small-scale (0.5 < r < 40 h-1 Mpc)clustering of 78 895 massive (M* ˜ 1011.3M⊙) galaxies at 0.2 < z < 0.4 from the first twoyears of data from the Baryon Oscillation Spectroscopic Survey (BOSS),to be released as part of Sloan Digital Sky Survey (SDSS) Data Release 9(DR9). We describe the sample selection, basic properties of thegalaxies and caveats for working with the data. We calculate the real-and redshift-space two-point correlation functions of these galaxies,fit these measurements using halo occupation distribution (HOD)modelling within dark matter cosmological simulations, and estimate theerrors using mock catalogues. These galaxies lie in massive haloes, witha mean halo mass of 5.2 × 1013 h-1M⊙, a large-scale bias of ˜2.0 and a satellitefraction of 12 ± 2 per cent. Thus, these galaxies occupy haloeswith average masses in between those of the higher redshift BOSS CMASSsample and the original SDSS I/II luminous red galaxy sample.
Keywords: large-scale structure of Universe; galaxies: haloes; galaxies: evolution; galaxies: statistics; surveys

The Clustering of Galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: Luminosity and Color Dependence and Redshift Evolution - Guo, Hong; Zehavi, Idit; Zheng, Zheng; Weinberg, David H.; Berlind, Andreas A.; Blanton, Michael; Chen, Yanmei; Eisenstein, Daniel J.; Ho, Shirley; Kazin, Eyal; Manera, Marc; Maraston, Claudia; et al. (The Astrophysical Journal, 2013)
We measure the luminosity and color dependence and the redshiftevolution of galaxy clustering in the Sloan Digital Sky Survey-IIIBaryon Oscillation Spectroscopic Survey Ninth Data Release. We focus onthe projected two-point correlation function (2PCF) of subsets of itsCMASS sample, which includes about 260,000 galaxies over ~3300deg2 in the redshift range 0.43 < z < 0.7. To minimizethe selection effect on galaxy clustering, we construct well-definedluminosity and color subsamples by carefully accounting for the CMASSgalaxy selection cuts. The 2PCF of the whole CMASS sample, ifapproximated by a power-law, has a correlation length of r 0= 7.93 ± 0.06 h -1 Mpc and an index of γ =1.85 ± 0.01. Clear dependences on galaxy luminosity and color arefound for the projected 2PCF in all redshift bins, with more luminousand redder galaxies generally exhibiting stronger clustering and steeper2PCF. The color dependence is also clearly seen for galaxies within thered sequence, consistent with the behavior of SDSS-II main samplegalaxies at lower redshifts. At a given luminosity (k + e corrected), nosignificant evolution of the projected 2PCFs with redshift is detectedfor red sequence galaxies. We also construct galaxy samples of fixednumber density at different redshifts, using redshift-dependentmagnitude thresholds. The clustering of these galaxies in the CMASSredshift range is found to be consistent with that predicted by passiveevolution. Our measurements of the luminosity and color dependence andredshift evolution of galaxy clustering will allow for detailed modelingof the relation between galaxies and dark matter halos and newconstraints on galaxy formation and evolution.
Keywords: cosmology: observations; cosmology: theory; galaxies: distances and redshifts; galaxies: halos; galaxies: statistics; large-scale structure of universe

The clustering of galaxies in the SDSS-III DR9 Baryon Oscillation Spectroscopic Survey: constraints on primordial non-Gaussianity - Ross, Ashley J.; Percival, Will J.; Carnero, Aurelio; Zhao, Gong-bo; Manera, Marc; Raccanelli, Alvise; Aubourg, Eric; Bizyaev, Dmitry; Brewington, Howard; Brinkmann, J.; Brownstein, Joel R.; Cuesta, Antonio J.; et al. (Monthly Notices of the Royal Astronomical Society, 2013)
We analyse the density field of 264 283 galaxies observed by the SloanDigital Sky Survey (SDSS)-III Baryon Oscillation Spectroscopic Survey(BOSS) and included in the SDSS Data Release 9 (DR9). In total, the SDSSDR9 BOSS data include spectroscopic redshifts for over 400 000 galaxiesspread over a footprint of more than 3000 deg2. We measurethe power spectrum of these galaxies with redshifts 0.43 < z < 0.7in order to constrain the amount of local non-Gaussianity,f{_N_L^local}, in the primordial density field, paying particularattention to the impact of systematic uncertainties. The BOSS galaxydensity field is systematically affected by the local stellar densityand this influences the ability to accurately measure f{_N_L^local}. Inthe absence of any correction, we find (erroneously) that theprobability that f{_N_L^local} is greater than zero, P(f{_N_L^local}> 0), is 99.5 per cent. After quantifying and correcting for thesystematic bias and including the added uncertainty, we find - 45 <f{_N_L^local} < 195 at 95 per cent confidence and P(f{_N_L^local}> 0) = 91.0 per cent. A more conservative approach assumes that wehave only learnt the k dependence of the systematic bias and allows anyamplitude for the systematic correction; we find that the systematiceffect is not fully degenerate with that of f{_N_L^local}, and wedetermine that -82 < f{_N_L^local} < 178 (at 95 per centconfidence) and P(f{_N_L^local} > 0) = 68 per cent. This analysisdemonstrates the importance of accounting for the impact of Galacticforegrounds on f{_N_L^local} measurements. We outline the methods thataccount for these systematic biases and uncertainties. We expect ourmethods to yield robust constraints on f{_N_L^local} for both our ownand future large-scale structure investigations.
Keywords: cosmology: observations; (cosmology:) inflation; (cosmology:) large-scale structure of Universe

Measuring DA and H at z=0.35 from the SDSS DR7 LRGs using baryon acoustic oscillations - Xu, Xiaoying; Cuesta, Antonio J.; Padmanabhan, Nikhil; Eisenstein, Daniel J.; McBride, Cameron K. (Monthly Notices of the Royal Astronomical Society, 2013)
We present measurements of the angular diameter distanceDA(z) and the Hubble parameter H(z) at z = 0.35 using theanisotropy of the baryon acoustic oscillation (BAO) signal measured inthe galaxy clustering distribution of the Sloan Digital Sky Survey(SDSS) Data Release 7 (DR7) luminous red galaxy (LRG) sample. Our workis the first to apply density-field reconstruction to an anisotropicanalysis of the acoustic peak. Reconstruction partially removes theeffects of non-linear evolution and redshift-space distortions in orderto sharpen the acoustic signal. We present the theoretical frameworkbehind the anisotropic BAO signal and give a detailed account of thefitting model we use to extract this signal from the data. Our methodfocuses only on the acoustic peak anisotropy, rather than the moremodel-dependent anisotropic information from the broad-band power. Wetest the robustness of our analysis methods on 160 Large Suite of DarkMatter Simulation DR7 mock catalogues and find that our models areunbiased at the ˜0.2 per cent level in measuring the BAOanisotropy. After reconstruction we measure DA(z = 0.35) =1050 ± 38 Mpc and H(z = 0.35) = 84.4 ± 7.0 kms-1 Mpc-1 assuming a sound horizon ofrs = 152.76 Mpc. Note that these measurements are correlatedwith a correlation coefficient of 0.57. This represents a factor of 1.4improvement in the error on DA relative to thepre-reconstruction case; a factor of 1.2 improvement is seen for H.
Keywords: cosmological parameters; cosmology: observations; cosmology: theory; dark energy; distance scale; large-scale structure of Universe

PRIMUS: Constraints on Star Formation Quenching and Galaxy Merging, and the Evolution of the Stellar Mass Function from z = 0-1 - Moustakas, John; Coil, Alison L.; Aird, James; Blanton, Michael R.; Cool, Richard J.; Eisenstein, Daniel J.; Mendez, Alexander J.; Kenneth C. Wong; Zhu, Guangtun; Arnouts, Stéphane (The Astrophysical Journal, 2013)
We measure the evolution of the stellar mass function (SMF) from z = 0-1using multi-wavelength imaging and spectroscopic redshifts from thePRism MUlti-object Survey (PRIMUS) and the Sloan Digital Sky Survey(SDSS). From PRIMUS we construct an i < 23 flux-limited sample of~40, 000 galaxies at z = 0.2-1.0 over five fields totaling ≈5.5deg2, and from the SDSS we select ~170, 000 galaxies at z =0.01-0.2 that we analyze consistently with respect to PRIMUS to minimizesystematic errors in our evolutionary measurements. We find that the SMFof all galaxies evolves relatively little since z = 1, although we do
Keywords: galaxies: evolution; galaxies: high-redshift; large-scale structure of universe; surveys

PRIMUS: Infrared and X-Ray AGN Selection Techniques at 0.2 < z < 1.2 - Mendez, Alexander J.; Coil, Alison L.; Aird, James; Diamond-Stanic, Aleksandar M.; Moustakas, John; Blanton, Michael R.; Cool, Richard J.; Eisenstein, Daniel J.; Kenneth C. Wong; Zhu, Guangtun (The Astrophysical Journal, 2013)
We present a study of Spitzer/IRAC and X-ray active galactic nucleus(AGN) selection techniques in order to quantify the overlap, uniqueness,contamination, and completeness of each. We investigate how the overlapand possible contamination of the samples depend on the depth of boththe IR and X-ray data. We use Spitzer/IRAC imaging, Chandra andXMM-Newton X-ray imaging, and spectroscopic redshifts from the PRismMUlti-object Survey to construct galaxy and AGN samples at 0.2 < z< 1.2 over 8 deg2. We construct samples over a wide rangeof IRAC flux limits (SWIRE to GOODS depth) and X-ray flux limits (10 ksto 2 Ms). We compare IR-AGN samples defined using both the IRAC colorselection of Stern et al. and Donley et al. with X-ray-detected AGNsamples. For roughly similar depth IR and X-ray surveys, we find that
Keywords: galaxies: active; galaxies: evolution; infrared: galaxies; X-rays: galaxies

The PRIsm MUlti-object Survey (PRIMUS). II. Data Reduction and Redshift Fitting - Cool, Richard J.; Moustakas, John; Blanton, Michael R.; Burles, Scott M.; Coil, Alison L.; Eisenstein, Daniel J.; Kenneth C. Wong; Zhu, Guangtun; Aird, James; Bernstein, Rebecca A.; Bolton, Adam S.; Hogg, David W.; et al. (The Astrophysical Journal, 2013)
The PRIsm MUlti-object Survey (PRIMUS) is a spectroscopic galaxyredshift survey to z ~ 1 completed with a low-dispersion prism andslitmasks allowing for simultaneous observations of ~2500 objects over0.18 deg2. The final PRIMUS catalog includes ~130,000 robustredshifts over 9.1 deg2. In this paper, we summarize thePRIMUS observational strategy and present the data reduction detailsused to measure redshifts, redshift precision, and survey completeness.The survey motivation, observational techniques, fields, targetselection, slitmask design, and observations are presented in Coil etal. Comparisons to existing higher-resolution spectroscopic measurementsshow a typical precision of σ z /(1 + z) = 0.005.PRIMUS, both in area and number of redshifts, is the largest faintgalaxy redshift survey completed to date and is allowing for precisemeasurements of the relationship between active galactic nuclei andtheir hosts, the effects of environment on galaxy evolution, and thebuild up of galactic systems over the latter half of cosmic history.
Keywords: galaxies: distances and redshifts; galaxies: evolution; galaxies: high-redshift; large-scale structure of universe; surveys

Very Metal-poor Stars in the Outer Galactic Bulge Found by the APOGEE Survey - García Pérez, Ana E.; Cunha, Katia; Shetrone, Matthew; Majewski, Steven R.; Johnson, Jennifer A.; Smith, Verne V.; Schiavon, Ricardo P.; Holtzman, Jon; Nidever, David; Zasowski, Gail; Allende Prieto, Carlos; Beers, Timothy C.; et al. (The Astrophysical Journal Letters, 2013)
Despite its importance for understanding the nature of early stellargenerations and for constraining Galactic bulge formation models, atpresent little is known about the metal-poor stellar content of thecentral Milky Way. This is a consequence of the great distances involvedand intervening dust obscuration, which challenge optical studies.However, the Apache Point Observatory Galactic Evolution Experiment(APOGEE), a wide-area, multifiber, high-resolution spectroscopic surveywithin Sloan Digital Sky Survey III, is exploring the chemistry of allGalactic stellar populations at infrared wavelengths, with particularemphasis on the disk and the bulge. An automated spectral analysis ofdata on 2403 giant stars in 12 fields in the bulge obtained duringAPOGEE commissioning yielded five stars with low metallicity ([Fe/H]<= -1.7), including two that are very metal-poor [Fe/H] ~-2.1 by bulge standards. Luminosity-based distance estimates placethe 5 stars within the outer bulge, where 1246 of the other analyzedstars may reside. A manual reanalysis of the spectra verifies the lowmetallicities, and finds these stars to be enhanced in theα-elements O, Mg, and Si without significant α-patterndifferences with other local halo or metal-weak thick-disk stars ofsimilar metallicity, or even with other more metal-rich bulge stars.While neither the kinematics nor chemistry of these stars can yetdefinitively determine which, if any, are truly bulge members, ratherthan denizens of other populations co-located with the bulge, the newlyidentified stars reveal that the chemistry of metal-poor stars in thecentral Galaxy resembles that of metal-weak thick-disk stars at similarmetallicity.
Keywords: stars: abundances; stars: atmospheres; Galaxy: center; Galaxy: structure

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: measuring H(z) and DA(z) at z = 0.57 with clustering wedges - Kazin, Eyal A.; Sánchez, Ariel G.; Cuesta, Antonio J.; Beutler, Florian; Chuang, Chia-Hsun; Eisenstein, Daniel J.; Manera, Marc; Padmanabhan, Nikhil; Percival, Will J.; Prada, Francisco; Ross, Ashley J.; Seo, Hee-Jong; et al. (Monthly Notices of the Royal Astronomical Society, 2013)
We analyse the 2D correlation function of the Sloan Digital SkySurvey-III Baryon Oscillation Spectroscopic Survey (BOSS) CMASS sampleof massive galaxies of the ninth data release to measure cosmicexpansion H and the angular diameter distance DA at a meanredshift of <z> = 0.57. We apply, for the first time, a newcorrelation function technique called clustering wedgesξΔμ(s). Using a physically motivated model, theanisotropic baryonic acoustic feature in the galaxy sample is detectedat a significance level of 4.7σ compared to a featureless model.The baryonic acoustic feature is used to obtain model-independentconstraints cz/H/rs = 12.28 ± 0.82 (6.7 percentaccuracy) and DA/rs = 9.05 ± 0.27 (3.0 percent) with a correlation coefficient of -0.5, where rs is thesound horizon scale at the end of the baryonic drag era. We conductthorough tests on the data and 600 simulated realizations, findingrobustness of the results regardless of the details of the analysismethod. Combining this with rs constraints from the cosmicmicrowave background, we obtain H(0.57) = 90.8 ± 6.2 kms-1 Mpc-1 and DA(0.57) = 1386 ±45 Mpc. We use simulations to forecast results of the final BOSS CMASSdata set. We apply the reconstruction technique on the simulationsdemonstrating that the sharpening of the anisotropic baryonic acousticfeature should improve the detection as well as tighten constraints of Hand DA by ˜30 per cent on average.
Keywords: cosmological parameters; distance scale; large-scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: cosmological constraints from the full shape of the clustering wedges - Sánchez, Ariel G.; Kazin, Eyal A.; Beutler, Florian; Chuang, Chia-Hsun; Cuesta, Antonio J.; Eisenstein, Daniel J.; Manera, Marc; Montesano, Francesco; Nichol, Robert C.; Padmanabhan, Nikhil; Percival, Will; Prada, Francisco; et al. (Monthly Notices of the Royal Astronomical Society, 2013)
We explore the cosmological implications of the clustering wedges,ξ⊥(s) and ξ∥(s), of the CMASS DataRelease 9 sample of the Sloan Digital Sky Survey III (SDSS-III) BaryonOscillation Spectroscopic Survey. These clustering wedges are defined byaveraging the full two-dimensional correlation function, ξ(μ, s),over the ranges 0 < μ < 0.5 and 0.5 < μ < 1,respectively. These measurements allow us to constrain the parametercombinations DA(z)/rs(zd) = 9.03± 0.21 and cz/(rs(zd)H(z)) = 12.14 ±0.43 at the mean redshift of the sample, z = 0.57. We combine theinformation from the clustering wedges with recent measurements ofcosmic microwave background (CMB), baryon acoustic oscillations and TypeIa supernovae to obtain constraints on the cosmological parameters ofthe standard Λ cold dark matter (ΛCDM) model and a numberof potential extensions. The information encoded in the clusteringwedges is most useful when the dark energy equation of state is allowedto deviate from its standard ΛCDM value. The combination of alldata sets shows no evidence of a deviation from a constant dark energyequation of state, in which case we find wDE = -1.013± 0.064, in complete agreement with a cosmological constant. Weexplore potential deviations from general relativity (GR) byconstraining the growth rate f(z) = d ln D(a)/d ln a, in which case thecombination of the CMASS clustering wedges with CMB data implies f(z =0.57) = 0.719-0.096+0.092, in accordance with thepredictions of GR. Our results clearly illustrate the additionalconstraining power of anisotropic clustering measurements with respectto that of angle-averaged quantities.
Keywords: cosmological parameters; large-scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: single-probe measurements and the strong power of f(z)σ8(z) on constraining dark energy - Chuang, Chia-Hsun; Prada, Francisco; Cuesta, Antonio J.; Eisenstein, Daniel J.; Kazin, Eyal; Padmanabhan, Nikhil; Sánchez, Ariel G.; Xu, Xiaoying; Beutler, Florian; Manera, Marc; Schlegel, David J.; Schneider, Donald P.; et al. (Monthly Notices of the Royal Astronomical Society, 2013)
We present measurements of the anisotropic galaxy clustering from theData Release 9 (DR9) CMASS sample of the Sloan Digital Sky Survey(SDSS)-III Baryon Oscillation Spectroscopic Survey (BOSS). We analysethe broad-range shape of the monopole and quadrupole correlationfunctions to obtain constraints, at the effective redshift z = 0.57 ofthe sample, on the Hubble expansion rate H(z), the angular-diameterdistance DA(z), the normalized growth rate f(z)σ8(z), the physical matter densityΩmh2, and the biased amplitude of matterfluctuation bσ8(z). We obtain {H(0.57),DA(0.57), f (0.57)σ8(0.57),Ωmh2, bσ8(0.57)} =[87.6_{-6.8}^{+6.7} kms-1 Mpc-1, 1396 ± 73Mpc, 0.428 ± 0.066, 0.126_{-0.010}^{+0.008}, 1.19 ± 0.14}and their covariance matrix as well. The parameters which are not wellconstrained by our galaxy clustering analysis are marginalized over withwide flat priors. Since no priors from other data sets [i.e. cosmicmicrowave background (CMB)] are adopted and no dark energy models areassumed, our results from BOSS CMASS galaxy clustering alone may becombined with other data sets, i.e. CMB, SNe, lensing or other galaxyclustering data to constrain the parameters of a given cosmologicalmodel. We show that the major power on constraining dark energy from theanisotropic galaxy clustering signal, as compared to theangular-averaged one (monopole), arises from including the normalizedgrowth rate f (z)σ8(z). In the case of the cosmologicalmodel assuming a constant dark energy equation of state and a flatuniverse (wCDM), our single-probe CMASS constraints, combined with CMB(WMAP9+SPT), yield a value for the dark energy equation-of-stateparameter of w = -0.90 ± 0.11. Therefore, it is important toinclude f (z)σ8(z) while investigating the nature ofdark energy with current and upcoming large-scale galaxy surveys.
Keywords: cosmological parameters; cosmology: observations; distance scale; large-scale structure of Universe

Detection of Lyβ auto-correlations and Lyα-Lyβ cross-correlations in BOSS Data Release 9 - Iršič, Vid; Slosar, Anže; Bailey, Stephen; Eisenstein, Daniel J.; Font-Ribera, Andreu; Le Goff, Jean-Marc; Lundgren, Britt; McDonald, Patrick; O'Connell, Ross; Palanque-Delabrouille, Nathalie; Petitjean, Patrick; Rich, Jim; et al. (Journal of Cosmology and Astro-Particle Physics, 2013)
The Lyman-β forest refers to a region in the spectra of distantquasars that lies between the rest-frame Lyman-β and Lyman-γemissions. The forest in this region is dominated by a combination ofabsorption due to resonant Lyα and Lyβ scattering. Whenconsidering the 1D Lyβ forest in addition to the 1D Lyαforest, the full statistical description of the data requires four 1Dpower spectra: Lyα and Lyβ auto-power spectra and theLyα-Lyβ real and imaginary cross-power spectra. We describehow these can be measured using an optimal quadratic estimator thatnaturally disentangles Lyα and Lyβ contributions. Using asample of approximately 60,000 quasar sight-lines from the BOSS DataRelease 9, we make the measurement of the one-dimensional power spectrumof fluctuations due to the Lyβ resonant scattering. While we havenot corrected our measurements for resolution damping of the power andother systematic effects carefully enough to use them for cosmologicalconstraints, we can robustly conclude the following: i) Lyβ powerspectrum and Lyα-Lyβ cross spectra are detected with highstatistical significance; ii) the cross-correlation coefficient is ≈1 on large scales; iii) the Lyβ measurements are contaminated bythe associated OVI absorption, which is analogous to the SiIIIcontamination of the Lyα forest. Measurements of the Lyβforest will allow extension of the usable path-length for the Lyαmeasurements while allowing a better understanding of the physics ofintergalactic medium and thus more robust cosmological constraints.

Discovery of a Dynamical Cold Point in the Heart of the Sagittarius dSph Galaxy with Observations from the APOGEE Project - Majewski, Steven R.; Hasselquist, Sten; Łokas, Ewa L.; Nidever, David L.; Frinchaboy, Peter M.; García Pérez, Ana E.; Johnston, Kathryn V.; Mészáros, Szabolcs; Shetrone, Matthew; Allende Prieto, Carlos; Beaton, Rachael L.; Beers, Timothy C.; et al. (The Astrophysical Journal Letters, 2013)
The dynamics of the core of the Sagittarius (Sgr) dwarf spheroidal(dSph) galaxy are explored using high-resolution (R ~ 22, 500), H-band,near-infrared spectra of over 1000 giant stars in the central 3deg2 of the system, of which 328 are identified as Sgrmembers. These data, among some of the earliest observations from theSloan Digital Sky Survey III/Apache Point Observatory Galactic EvolutionExperiment (APOGEE) and the largest published sample of high resolutionSgr dSph spectra to date, reveal a distinct gradient in the velocitydispersion of Sgr from 11 to 14 km s–1 for radii>0.°8 from center to a dynamical cold point of 8 kms–1 in the Sgr center—a trend differing from thatfound in previous kinematical analyses of Sgr over larger scales thatsuggests a more or less flat dispersion profile at these radii.Well-fitting mass models with either cored and cusped dark matterdistributions can be found to match the kinematical results, althoughthe cored profile succeeds with significantly more isotropic stellarorbits than required for a cusped profile. It is unlikely that the coldpoint reflects an unusual mass distribution. The dispersion gradient mayarise from variations in the mixture of populations with distinctkinematics within the dSph; this explanation is suggested (e.g., bydetection of a metallicity gradient across similar radii), but notconfirmed, by the present data. Despite these remaining uncertaintiesabout their interpretation, these early test data (including some frominstrument commissioning) demonstrate APOGEE's usefulness for precisiondynamical studies, even for fields observed at extreme airmasses.
Keywords: galaxies: dwarf; galaxies: individual: Sagittarius dSph; galaxies: interactions; galaxies: kinematics and dynamics; galaxies: stellar content; galaxies: structure

PRIMUS: An Observationally Motivated Model to Connect the Evolution of the Active Galactic Nucleus and Galaxy Populations out to z ~ 1 - Aird, James; Coil, Alison L.; Moustakas, John; Diamond-Stanic, Aleksandar M.; Blanton, Michael R.; Cool, Richard J.; Eisenstein, Daniel J.; Kenneth C. Wong; Zhu, Guangtun (The Astrophysical Journal, 2013)
We present an observationally motivated model to connect the activegalactic nucleus (AGN) and galaxy populations at 0.2 < z < 1.0 andpredict the AGN X-ray luminosity function (XLF). We start withmeasurements of the stellar mass function of galaxies (from the PrismMulti-object Survey) and populate galaxies with AGNs using models forthe probability of a galaxy hosting an AGN as a function of specificaccretion rate. Our model is based on measurements indicating that thespecific accretion rate distribution is a universal function across awide range of host stellar masses with slope γ1 ≈-0.65 and an overall normalization that evolves with redshift. Wetest several simple assumptions to extend this model to high specificaccretion rates (beyond the measurements) and compare the predictionsfor the XLF with the observed data. We find good agreement with a modelthat allows for a break in the specific accretion rate distribution at apoint corresponding to the Eddington limit, a steep power-law tail tosuper-Eddington ratios with slope γ _2=-2.1^{+0.3}_{-0.5}, and ascatter of 0.38 dex in the scaling between black hole and host stellarmass. Our results show that samples of low luminosity AGNs are dominatedby moderately massive galaxies ( {M_*}\sim 10^{10}{--}10^{11} M_\odot)growing with a wide range of accretion rates due to the shape of thegalaxy stellar mass function rather than a preference for AGN activityat a particular stellar mass. Luminous AGNs may be a severely skewedpopulation with elevated black hole masses relative to their hostgalaxies and in rare phases of rapid accretion.
Keywords: galaxies: active; galaxies: evolution; X-rays: galaxies

Solving large scale structure in ten easy steps with COLA - Tassev, Svetlin; Zaldarriaga, Matias; Eisenstein, Daniel J. (Journal of Cosmology and Astro-Particle Physics, 2013)
We present the COmoving Lagrangian Acceleration (COLA) method: an N-bodymethod for solving for Large Scale Structure (LSS) in a frame that iscomoving with observers following trajectories calculated in LagrangianPerturbation Theory (LPT). Unlike standard N-body methods, the COLAmethod can straightforwardly trade accuracy at small-scales in order togain computational speed without sacrificing accuracy at large scales.This is especially useful for cheaply generating large ensembles ofaccurate mock halo catalogs required to study galaxy clustering and weaklensing, as those catalogs are essential for performing detailed erroranalysis for ongoing and future surveys of LSS. As an illustration, weran a COLA-based N-body code on a box of size 100 Mpc/h with particlesof mass ≈ 5 × 109Msolar/h. Running thecode with only 10 timesteps was sufficient to obtain an accuratedescription of halo statistics down to halo masses of at least1011Msolar/h. This is only at a modest speedpenalty when compared to mocks obtained with LPT. A standard detailedN-body run is orders of magnitude slower than our COLA-based code. Thespeed-up we obtain with COLA is due to the fact that we calculate thelarge-scale dynamics exactly using LPT, while letting the N-body codesolve for the small scales, without requiring it to capture exactly theinternal dynamics of halos. Achieving a similar level of accuracy inhalo statistics without the COLA method requires at least 3 times moretimesteps than when COLA is employed.

The Baryon Oscillation Spectroscopic Survey of SDSS-III - Dawson, Kyle S.; Schlegel, David J.; Ahn, Christopher P.; Anderson, Scott F.; Aubourg, Éric; Bailey, Stephen; Barkhouser, Robert H.; Bautista, Julian E.; Beifiori, Alessandra; Berlind, Andreas A.; Bhardwaj, Vaishali; Bizyaev, Dmitry; et al. (The Astronomical Journal, 2013)
The Baryon Oscillation Spectroscopic Survey (BOSS) is designed tomeasure the scale of baryon acoustic oscillations (BAO) in theclustering of matter over a larger volume than the combined efforts ofall previous spectroscopic surveys of large-scale structure. BOSS uses1.5 million luminous galaxies as faint as i = 19.9 over 10,000deg2 to measure BAO to redshifts z < 0.7. Observations ofneutral hydrogen in the Lyα forest in more than 150,000 quasarspectra (g < 22) will constrain BAO over the redshift range 2.15 <z < 3.5. Early results from BOSS include the first detection of thelarge-scale three-dimensional clustering of the Lyα forest and astrong detection from the Data Release 9 data set of the BAO in theclustering of massive galaxies at an effective redshift z = 0.57. Weproject that BOSS will yield measurements of the angular diameter
Keywords: cosmology: observations; surveys

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: the low-redshift sample - Parejko, John K.; Sunayama, Tomomi; Padmanabhan, Nikhil; Wake, David A.; Berlind, Andreas A.; Bizyaev, Dmitry; Blanton, Michael; Bolton, Adam S.; van den Bosch, Frank; Brinkmann, Jon; Brownstein, Joel R.; da Costa, Luiz Alberto Nicolaci; et al. (Monthly Notices of the Royal Astronomical Society, 2013)
We report on the small-scale (0.5 < r < 40 h-1 Mpc)clustering of 78 895 massive (M* ˜ 1011.3M&sun;) galaxies at 0.2 < z < 0.4 from the first twoyears of data from the Baryon Oscillation Spectroscopic Survey (BOSS),to be released as part of Sloan Digital Sky Survey (SDSS) Data Release 9(DR9). We describe the sample selection, basic properties of thegalaxies and caveats for working with the data. We calculate the real-and redshift-space two-point correlation functions of these galaxies,fit these measurements using halo occupation distribution (HOD)modelling within dark matter cosmological simulations, and estimate theerrors using mock catalogues. These galaxies lie in massive haloes, witha mean halo mass of 5.2 × 1013 h-1M&sun;, a large-scale bias of ˜2.0 and a satellitefraction of 12 ± 2 per cent. Thus, these galaxies occupy haloeswith average masses in between those of the higher redshift BOSS CMASSsample and the original SDSS I/II luminous red galaxy sample.
Keywords: large-scale structure of Universe; galaxies: haloes; galaxies: evolution; galaxies: statistics; surveys

The clustering of galaxies in the SDSS-III DR9 Baryon Oscillation Spectroscopic Survey: constraints on primordial non-Gaussianity - Ross, Ashley J.; Percival, Will J.; Carnero, Aurelio; Zhao, Gong-bo; Manera, Marc; Raccanelli, Alvise; Aubourg, Eric; Bizyaev, Dmitry; Brewington, Howard; Brinkmann, J.; Brownstein, Joel R.; Cuesta, Antonio J.; et al. (Monthly Notices of the Royal Astronomical Society, 2013)
We analyse the density field of 264 283 galaxies observed by the SloanDigital Sky Survey (SDSS)-III Baryon Oscillation Spectroscopic Survey(BOSS) and included in the SDSS Data Release 9 (DR9). In total, the SDSSDR9 BOSS data include spectroscopic redshifts for over 400 000 galaxiesspread over a footprint of more than 3000 deg2. We measurethe power spectrum of these galaxies with redshifts 0.43 < z < 0.7in order to constrain the amount of local non-Gaussianity,f{_N_L^local}, in the primordial density field, paying particularattention to the impact of systematic uncertainties. The BOSS galaxydensity field is systematically affected by the local stellar densityand this influences the ability to accurately measure f{_N_L^local}. Inthe absence of any correction, we find (erroneously) that theprobability that f{_N_L^local} is greater than zero, P(f{_N_L^local}> 0), is 99.5 per cent. After quantifying and correcting for thesystematic bias and including the added uncertainty, we find - 45 <f{_N_L^local} < 195 at 95 per cent confidence and P(f{_N_L^local}> 0) = 91.0 per cent. A more conservative approach assumes that wehave only learnt the k dependence of the systematic bias and allows anyamplitude for the systematic correction; we find that the systematiceffect is not fully degenerate with that of f{_N_L^local}, and wedetermine that -82 < f{_N_L^local} < 178 (at 95 per centconfidence) and P(f{_N_L^local} > 0) = 68 per cent. This analysisdemonstrates the importance of accounting for the impact of Galacticforegrounds on f{_N_L^local} measurements. We outline the methods thataccount for these systematic biases and uncertainties. We expect ourmethods to yield robust constraints on f{_N_L^local} for both our ownand future large-scale structure investigations.
Keywords: cosmology: observations; (cosmology:) inflation; (cosmology:) large-scale structure of Universe

PRIMUS: An observationally motivated model to connect the evolution of the AGN and galaxy populations out to z~1 - Aird, James; Coil, Alison L.; Moustakas, John; Diamond-Stanic, Aleksandar M.; Blanton, Michael R.; Cool, Richard J.; Eisenstein, Daniel J.; Kenneth C. Wong; Zhu, Guangtun (ArXiv e-prints, 2013)
We present an observationally motivated model to connect the AGN andgalaxy populations at 0.2<z<1.0 and predict the AGN X-rayluminosity function (XLF). We start with measurements of the stellarmass function of galaxies (from the Prism Multi-object Survey) andpopulate galaxies with AGNs using models for the probability of a galaxyhosting an AGN as a function of specific accretion rate (the rate ofsupermassive black hole growth scaled relative to the host stellarmass). Our model is based on measurements indicating that the specificaccretion rate distribution is a universal function across a wide rangeof host stellar mass with slope gamma_1=0.65 and an overallnormalization that evolves strongly with redshift. We test severalsimple assumptions to extend this model to high specific accretion rates(beyond the measurements) and compare the predictions for the XLF withthe observed data. We find good agreement with a model that allows for abreak in the specific accretion rate distribution at a pointcorresponding to the Eddington limit, with a steep power-law tail tosuper-Eddington ratios with slope gamma_2=-2.1 +0.3 -0.5. We convertbetween specific accretion rate and Eddington ratio by assuming ascaling between black hole mass and host stellar mass with an intrinsicscatter of +/-0.38 dex. Our results show that samples of low luminosityAGNs are dominated by moderately massive galaxies (M* ~ 10^{10-11}M_sun) growing with a wide range of accretion rates -- a consequence ofthe shape of the galaxy stellar mass function rather than a preferencefor AGN activity at a particular stellar mass. The observed populationof the most luminous AGN may be severely skewed to the most extremesources with elevated black hole masses relative to their host galaxiesand in rare phases of very rapid accretion.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

PRIMUS: Constraints on Star Formation Quenching and Galaxy Merging, and the Evolution of the Stellar Mass Function From z=0-1 - Moustakas, John; Coil, Alison; Aird, James; Blanton, Michael R.; Cool, Richard J.; Eisenstein, Daniel J.; Mendez, Alexander J.; Kenneth C. Wong; Zhu, Guangtun; Arnouts, Stephane (ArXiv e-prints, 2013)
We measure the evolution of the stellar mass function (SMF) from z=0-1using multi-wavelength imaging and spectroscopic redshifts from thePRism MUlti-object Survey (PRIMUS) and the Sloan Digital Sky Survey(SDSS). From PRIMUS we construct an i<23 flux-limited sample of~40,000 galaxies at z=0.2-1.0 over five fields totaling ~5.5 deg^2, andfrom the SDSS we select ~170,000 galaxies at z=0.01-0.2 that we analyzeconsistently with respect to PRIMUS to minimize systematic errors in ourevolutionary measurements. We find that the SMF of all galaxies evolvesrelatively little since z=1, although we do find evidence for mass
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

SDSS DR7 White Dwarf Catalog - Kleinman, S. J.; Kepler, S. O.; Koester, D.; Pelisoli, Ingrid; Peçanha, Viviane; Nitta, A.; Costa, J. E. S.; Krzesinski, J.; Dufour, P.; Lachapelle, F.-R.; Bergeron, P.; Yip, Ching-Wa; et al. (The Astrophysical Journal Supplement Series, 2013)
We present a new catalog of spectroscopically confirmed white dwarfstars from the Sloan Digital Sky Survey (SDSS) Data Release 7spectroscopic catalog. We find 20,407 white dwarf spectra, representing19,712 stars, and provide atmospheric model fits to 14,120 DA and 1011DB white dwarf spectra from 12,843 and 923 stars, respectively. Thesenumbers represent more than a factor of two increase in the total numberof white dwarf stars from the previous SDSS white dwarf catalogs basedon DR4 data. Our distribution of subtypes varies from previous catalogsdue to our more conservative, manual classifications of each star in ourcatalog, supplementing our automatic fits. In particular, we find alarge number of magnetic white dwarf stars whose small Zeeman splittingsmimic increased Stark broadening that would otherwise result in anoverestimated log g if fit as a non-magnetic white dwarf. We calculatemean DA and DB masses for our clean, non-magnetic sample and find the DBmean mass is statistically larger than that for the DAs.
Keywords: catalogs; magnetic fields; stars: luminosity function; mass function; surveys; white dwarfs

Very Metal-poor Stars in the Outer Galactic Bulge Found by the Apogee Survey - García Pérez, Ana E.; Cunha, Katia; Shetrone, Matthew; Majewski, Steven R.; Johnson, Jennifer A.; Smith, Verne V.; Schiavon, Ricardo P.; Holtzman, Jon; Nidever, David; Zasowski, Gail; Allende Prieto, Carlos; Beers, Timothy C.; et al. (ArXiv e-prints, 2013)
Despite its importance for understanding the nature of early stellargenerations and for constraining Galactic bulge formation models, atpresent little is known about the metal-poor stellar content of thecentral Milky Way. This is a consequence of the great distances involvedand intervening dust obscuration, which challenge optical studies.However, the Apache Point Observatory Galactic Evolution Experiment(APOGEE), a wide-area, multifiber, high-resolution spectroscopic surveywithin Sloan Digital Sky Survey III (SDSS-III), is exploring thechemistry of all Galactic stellar populations at infrared wavelengths,with particular emphasis on the disk and the bulge. An automatedspectral analysis of data on 2,403 giant stars in twelve fields in thebulge obtained during APOGEE commissioning yielded five stars with lowmetallicity([Fe/H]$\le-1.7$), including two that are very metal-poor[Fe/H]$\sim-2.1$ by bulge standards. Luminosity-based distance estimatesplace the five stars within the outer bulge, where other 1,246 of theanalyzed stars may reside. A manual reanalysis of the spectra verifiesthe low metallicities, and finds these stars to be enhanced in the$α$-elements O, Mg, and Si without significant $α$-patterndifferences with other local halo or metal-weak thick-disk stars ofsimilar metallicity, or even with other more metal-rich bulge stars.While neither the kinematics nor chemistry of these stars can yetdefinitively determine which, if any, are truly bulge members, ratherthan denizens of other populations co-located with the bulge, thenewly-identified stars reveal that the chemistry of metal-poor stars inthe central Galaxy resembles that of metal-weak thick-disk stars atsimilar metallicity.
Keywords: Astrophysics - Solar and Stellar Astrophysics; Astrophysics - Galaxy Astrophysics

AGES: The AGN and Galaxy Evolution Survey - Kochanek, C. S.; Eisenstein, D. J.; Cool, R. J.; Caldwell, N.; Assef, R. J.; Jannuzi, B. T.; Jones, C.; Murray, S. S.; Forman, W. R.; Dey, A.; Brown, M. J. I.; Eisenhardt, P.; et al. (The Astrophysical Journal Supplement Series, 2012)
The AGN and Galaxy Evolution Survey (AGES) is a redshift surveycovering, in its standard fields, 7.7 deg2 of the Boötesfield of the NOAO Deep Wide-Field Survey. The final sample consists of23,745 redshifts. There are well-defined galaxy samples in 10 bands (theBW , R, I, J, K, IRAC 3.6, 4.5, 5.8, and 8.0 μm, and MIPS24 μm bands) to a limiting magnitude of I < 20 mag forspectroscopy. For these galaxies, we obtained 18,163 redshifts from asample of 35,200 galaxies, where random sparse sampling was used todefine statistically complete sub-samples in all 10 photometric bands.
Keywords: cosmology: observations; galaxies: evolution; galaxies: general; quasars: general

AGES: the AGN and Galaxy Evolution Survey (Kochanek+, 2012) - Kochanek, C. S.; Eisenstein, D. J.; Cool, R. J.; Caldwell, N.; Assef, R. J.; Jannuzi, B. T.; Jones, C.; Murray, S. S.; Forman, W. R.; Dey, A.; Brown, M. J. I.; Eisenhardt, P.; et al. (VizieR Online Data Catalog, 2012)
The observations were made with Hectospec, a 300 fiber, 1 degree fieldof view, robotic spectrograph for the 6.5m MMT telescope at Mt. Hopkins,from 2004 April to 2007 July. The wavelength range is 3700-9200Åwith a pixel scale of 1.2Å and a spectral resolution of 6Å(i.e., roughly R~1000).(7 data files).
Keywords: Active gal. nuclei; Galaxies: IR; Photometry: infrared; Photometry: ultraviolet; Redshifts; QSOs; Surveys

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: analysis of potential systematics - Ross, Ashley J.; Percival, Will J.; Sánchez, Ariel G.; Samushia, Lado; Ho, Shirley; Kazin, Eyal; Manera, Marc; Reid, Beth; White, Martin; Tojeiro, Rita; McBride, Cameron K.; Xu, Xiaoying; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
We analyse the density field of galaxies observed by the Sloan DigitalSky Survey (SDSS)-III Baryon Oscillation Spectroscopic Survey (BOSS)included in the SDSS Data Release Nine (DR9). DR9 includes spectroscopicredshifts for over 400 000 galaxies spread over a footprint of 3275deg2. We identify, characterize and mitigate the impact ofsources of systematic uncertainty on large-scale clusteringmeasurements, both for angular moments of the redshift-space correlationfunction, ξℓ(s), and the spherically averaged powerspectrum, P(k), in order to ensure that robust cosmological constraintswill be obtained from these data. A correlation between the projecteddensity of stars and the higher redshift (0.43 < z < 0.7) galaxysample (the approximately constant stellar mass threshold 'CMASS'sample) due to imaging systematics imparts a systematic error that islarger than the statistical error of the clustering measurements atscales s > 120 h-1 Mpc or k < 0.01 h Mpc-1.We find that these errors can be ameliorated by weighting galaxies basedon their surface brightness and the local stellar density. Theclustering of CMASS galaxies found in the Northern and Southern Galacticfootprints of the survey generally agrees to within 2σ. We usemock galaxy catalogues that simulate the CMASS selection function todetermine that randomly selecting galaxy redshifts in order to simulatethe radial selection function of a random sample imparts the leastsystematic error on ξℓ(s) measurements and that thissystematic error is negligible for the spherically averaged correlationfunction, ξ0. We find a peak in ξ0 ats˜ 200 h-1 Mpc, with a corresponding feature withperiod ˜0.03 h Mpc-1 in P(k), and find features atleast as strong in 4.8 per cent of the mock galaxy catalogues,concluding this feature is likely to be a consequence of cosmicvariance. The methods we recommend for the calculation of clusteringmeasurements using the CMASS sample are adopted in companion papers thatlocate the position of the baryon acoustic oscillation feature,constrain cosmological models using the full shape of ξ0and measure the rate of structure growth.
Keywords: cosmology: observations; distance scale; large-scale structure of Universe

Evidence of Galaxy Cluster Motions with the Kinematic Sunyaev-Zel'dovich Effect - Hand, Nick; Addison, Graeme E.; Aubourg, Eric; Battaglia, Nick; Battistelli, Elia S.; Bizyaev, Dmitry; Bond, J. Richard; Brewington, Howard; Brinkmann, Jon; Brown, Benjamin R.; Das, Sudeep; Dawson, Kyle S.; et al. (Physical Review Letters, 2012)
Using high-resolution microwave sky maps made by the Atacama CosmologyTelescope, we for the first time present strong evidence for motions ofgalaxy clusters and groups via microwave background temperaturedistortions due to the kinematic Sunyaev-Zel’dovich effect. Galaxyclusters are identified by their constituent luminous galaxies observedby the Baryon Oscillation Spectroscopic Survey, part of the SloanDigital Sky Survey III. We measure the mean pairwise momentum ofclusters, with a probability of the signal being due to random errors of0.002, and the signal is consistent with the growth of cosmic structurein the standard model of cosmology.
Keywords: Observational cosmology; Distances; redshifts; radial velocities; spatial distribution of galaxies; Galaxy clusters; Background radiations

The Galaxy Optical Luminosity Function from the AGN and Galaxy Evolution Survey - Cool, Richard J.; Eisenstein, Daniel J.; Kochanek, Christopher S.; Brown, Michael J. I.; Caldwell, Nelson; Dey, Arjun; Forman, William R.; Hickox, Ryan C.; Jannuzi, Buell T.; Jones, Christine; Moustakas, John; Murray, Stephen S. (The Astrophysical Journal, 2012)
We present the galaxy optical luminosity function for the redshift range0.05 < z < 0.75 from the AGN and Galaxy Evolution Survey, aspectroscopic survey of 7.6 deg2 in the Boötes field ofthe NOAO Deep Wide-Field Survey. Our statistical sample is composed of12,473 galaxies with known redshifts down to I = 20.4 (AB). Our resultsat low redshift are consistent with those from Sloan Digital Sky Survey;at higher redshift, we find strong evidence for evolution in theluminosity function, including differential evolution between blue andred galaxies. We find that the luminosity density evolves as (1 +z)(0.54 ± 0.64) for red galaxies and (1 + z)(1.64± 0.39) for blue galaxies.
Keywords: galaxies: luminosity function; mass function; galaxies: statistics

Measuring D_A and H at z=0.35 from the SDSS DR7 LRGs using baryon acoustic oscillations - Xu, Xiaoying; Cuesta, Antonio J.; Padmanabhan, Nikhil; Eisenstein, Daniel J.; McBride, Cameron K. (ArXiv e-prints, 2012)
We present measurements of the angular diameter distance D_A(z) and theHubble parameter H(z) at z=0.35 using the anisotropy of the baryonacoustic oscillation (BAO) signal measured in the galaxy clusteringdistribution of the Sloan Digital Sky Survey (SDSS) Data Release 7 (DR7)Luminous Red Galaxies (LRG) sample. Our work is the first to applydensity-field reconstruction to an anisotropic analysis of the acousticpeak. Reconstruction partially removes the effects of non-linearevolution and redshift-space distortions in order to sharpen theacoustic signal. We present the theoretical framework behind theanisotropic BAO signal and give a detailed account of the fitting modelwe use to extract this signal from the data. Our method focuses only onthe acoustic peak anisotropy, rather than the more model-dependentanisotropic information from the broadband power. We test the robustnessof our analysis methods on 160 LasDamas DR7 mock catalogues and find
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

Observational Probes of Cosmic Acceleration - Weinberg, David H.; Mortonson, Michael J.; Eisenstein, Daniel J.; Hirata, Christopher; Riess, Adam G.; Rozo, Eduardo (ArXiv e-prints, 2012)
The accelerating expansion of the universe is the most surprisingcosmological discovery in many decades, implying that the universe isdominated by some form of "dark energy" with exotic physical properties,or that Einstein's theory of gravity breaks down on cosmological scales.The profound implications of cosmic acceleration have inspired ambitiousexperimental efforts to measure the history of expansion and growth ofstructure with percent-level precision or higher. We review in detailthe four most well established methods for making such measurements:Type Ia supernovae, baryon acoustic oscillations (BAO), weakgravitational lensing, and galaxy clusters. We pay particular attentionto the systematic uncertainties in these techniques and to strategiesfor controlling them at the level needed to exploit "Stage IV" darkenergy facilities such as BigBOSS, LSST, Euclid, and WFIRST. We brieflyreview a number of other approaches including redshift-spacedistortions, the Alcock-Paczynski test, and direct measurements of H_0.We present extensive forecasts for constraints on the dark energyequation of state and parameterized deviations from GR, achievable withStage III and Stage IV experimental programs that incorporatesupernovae, BAO, weak lensing, and CMB data. We also show the level ofprecision required for other methods to provide constraints competitivewith those of these fiducial programs. We emphasize the value of abalanced program that employs several of the most powerful methods incombination, both to cross-check systematic uncertainties and to takeadvantage of complementary information. Surveys to probe cosmicacceleration produce data sets with broad applications, and theycontinue the longstanding astronomical tradition of mapping the universein ever greater detail over ever larger scales.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

PRIMUS: The Dependence of AGN Accretion on Host Stellar Mass and Color - Aird, James; Coil, Alison L.; Moustakas, John; Blanton, Michael R.; Burles, Scott M.; Cool, Richard J.; Eisenstein, Daniel J.; Smith, M. Stephen M.; Kenneth C. Wong; Zhu, Guangtun (The Astrophysical Journal, 2012)
We present evidence that the incidence of active galactic nuclei (AGNs)and the distribution of their accretion rates do not depend on thestellar masses of their host galaxies, contrary to previous studies. Weuse hard (2-10 keV) X-ray data from three extragalactic fields (XMM-LSS,COSMOS, and ELAIS-S1) with redshifts from the Prism Multi-object Surveyto identify 242 AGNs with L 2-10 keV = 1042-44 ergs-1 within a parent sample of ~25,000 galaxies at 0.2 < z< 1.0 over ~3.4 deg2 and to i ~ 23. We find that althoughthe fraction of galaxies hosting an AGN at fixed X-ray luminosity risesstrongly with stellar mass, the distribution of X-ray luminosities isindependent of mass. Furthermore, we show that the probability that agalaxy will host an AGN can be defined by a universal Eddington ratiodistribution that is independent of the host galaxy stellar mass and hasa power-law shape with slope -0.65. These results demonstrate that AGNsare prevalent at all stellar masses in the range 9.5 and that the samephysical processes regulate AGN activity in all galaxies in this stellarmass range. While a higher AGN fraction may be observed in massivegalaxies, this is a selection effect related to the underlying Eddingtonratio distribution. We also find that the AGN fraction drops rapidlybetween z ~ 1 and the present day and is moderately enhanced (factor ~2)in galaxies with blue or green optical colors. Consequently, while AGNactivity and star formation appear to be globally correlated, we do notfind evidence that the presence of an AGN is related to the quenching ofstar formation or the color transformation of galaxies.
Keywords: galaxies: active; galaxies: evolution; X-rays: galaxies

The quasars MMT-BOSS pilot survey (Ross+, 2012) - Ross, N. P.; Myers, A. D.; Sheldon, E. S.; Yeche, C.; Strauss, M. A.; Bovy, J.; Kirkpatrick, J. A.; Richards, G. T.; Aubourg, E.; Blanton, M. R.; Brandt, W. N.; Carithers, W. C.; et al. (VizieR Online Data Catalog, 2012)
The Sloan Digital Sky Survey is now in its third phase (SDSS-III;Eisenstein et al. 2011AJ....142...72E) and is carrying out a combinationof four interleaved surveys that will continue until the summer of 2014.One of those surveys, the Baryon Oscillation Spectroscopic Survey(BOSS), commenced operations in late 2009 and is using essentially allthe dark time for SDSS-III. BOSS uses the same 2.5m Sloan Foundationtelescope that was used in SDSS-I/II, but since BOSS will observefainter targets, the fiber-fed spectrographs have been significantlyupgraded. These upgrades include: new CCDs with improved blue and redresponse; 1000 2" instead of 640 3" optical diameter fibers; higherthroughput gratings over a spectral range of 3600-10000Å at aresolution of about 2000, and improved optics.Prior to the commencement of BOSS spectroscopy, we carried outspectroscopy of quasar candidates selected from co-added photometry inSDSS Stripe 82. Observations of these candidates were carried out inqueue mode between 2008 September and 2009 January using the Hectospecmulti-fiber spectrograph on the 6.5m Multiple Mirror Telescope (MMT). InTables 14 and 15, we provide positions, PSF photometry (as observed,uncorrected for Galactic extinction), and redshifts for confirmedquasars from the MMT survey. Objects that are not flagged Primary in theCAS are listed separately (table 15).(2 data files).
Keywords: Photometry: SDSS; Redshifts; QSOs; Surveys

The SDSS-III Baryon Oscillation Spectroscopic Survey: Quasar Target Selection for Data Release Nine - Ross, Nicholas P.; Myers, Adam D.; Sheldon, Erin S.; Yèche, Christophe; Strauss, Michael A.; Bovy, Jo; Kirkpatrick, Jessica A.; Richards, Gordon T.; Aubourg, Éric; Blanton, Michael R.; Brandt, W. N.; Carithers, William C.; et al. (The Astrophysical Journal Supplement Series, 2012)
The SDSS-III Baryon Oscillation Spectroscopic Survey (BOSS), a five-yearspectroscopic survey of 10,000 deg2, achieved first light inlate 2009. One of the key goals of BOSS is to measure the signature ofbaryon acoustic oscillations (BAOs) in the distribution of Lyαabsorption from the spectra of a sample of ~150,000 z > 2.2 quasars.Along with measuring the angular diameter distance at z ≈ 2.5, BOSSwill provide the first direct measurement of the expansion rate of theuniverse at z > 2. One of the biggest challenges in achieving thisgoal is an efficient target selection algorithm for quasars in theredshift range 2.2 < z < 3.5, where their colors tend to overlapthose of the far more numerous stars. During the first year of the BOSSsurvey, quasar target selection (QTS) methods were developed and testedto meet the requirement of delivering at least 15 quasarsdeg-2 in this redshift range, with a goal of 20 out of 40targets deg-2 allocated to the quasar survey. To achievethese surface densities, the magnitude limit of the quasar targets wasset at g <= 22.0 or r <= 21.85. While detection of the BAOsignature in the distribution of Lyα absorption in quasar spectradoes not require a uniform target selection algorithm, many otherastrophysical studies do. We have therefore defined a uniformly selectedsubsample of 20 targets deg-2, for which the selection
Keywords: cosmology: observations; intergalactic medium; quasars: absorption lines; quasars: general; surveys; techniques: miscellaneous

The Apache Point Observatory Galactic Evolution Experiment: First Detection of High-velocity Milky Way Bar Stars - Nidever, David L.; Zasowski, Gail; Majewski, Steven R.; Bird, Jonathan; Robin, Annie C.; Martinez-Valpuesta, Inma; Beaton, Rachael L.; Schönrich, Ralph; Schultheis, Mathias; Wilson, John C.; Skrutskie, Michael F.; O'Connell, Robert W.; et al. (The Astrophysical Journal Letters, 2012)
Commissioning observations with the Apache Point Observatory GalacticEvolution Experiment (APOGEE), part of the Sloan Digital Sky Survey III,have produced radial velocities (RVs) for ~4700 K/M-giant stars in theMilky Way (MW) bulge. These high-resolution (R ~ 22, 500), high-S/N(>100 per resolution element), near-infrared (NIR; 1.51-1.70 μm)spectra provide accurate RVs (epsilonV ~ 0.2 kms-1) for the sample of stars in 18 Galactic bulge fieldsspanning -1° <l < 20°, |b| < 20°, and δ >-32°. This represents the largest NIR high-resolution spectroscopicsample of giant stars ever assembled in this region of the Galaxy. Acold (σV ~ 30 km s-1), high-velocity peak (VGSR ≈ +200 km s-1) is found to comprise a
Keywords: Galaxy: bulge; Galaxy: kinematics and dynamics; Galaxy: structure; surveys

Baryon Acoustic Oscillations in the Ly-α\ forest of BOSS quasars - Busca, Nicolás G.; Delubac, Timothée; Rich, James; Bailey, Stephen; Font-Ribera, Andreu; Kirkby, David; Le Goff, J.-M.; Pieri, Matthew M.; Slosar, Anze; Aubourg, Éric; Bautista, Julian E.; Bizyaev, Dmitry; et al. (ArXiv e-prints, 2012)
We report a detection of the baryon acoustic oscillation (BAO) featurein the three-dimensional correlation function of the transmitted fluxfraction in the \Lya forest of high-redshift quasars. The study uses48,640 quasars in the redshift range $2.1\le z \le 3.5$ from the BaryonOscillation Spectroscopic Survey (BOSS) of the third generation of theSloan Digital Sky Survey (SDSS-III). At a mean redshift $z=2.3$, wemeasure the monopole and quadrupole components of the correlationfunction for separations in the range $20\hMpc<r<200\hMpc$. A peakin the correlation function is seen at a separation equal to$(1.01±0.03)$ times the distance expected for the BAO peak within aconcordance $Λ$CDM cosmology. This first detection of the BAO peakat high redshift, when the universe was strongly matter dominated,results in constraints on the angular diameter distance $\da$ and theexpansion rate $H$ at $z=2.3$ that, by themselves, require the existenceof dark energy. Combined with constraints derived from Cosmic MicrowaveBackground (CMB) observations, this result implies$H(z=2.3)=(224±8){\rm km s^{-1}Mpc^{-1}}$, indicating that the timederivative of the cosmological scale parameter $\dot{a}=H(z=2.3)/(1+z)$is significantly greater than that measured with BAO at $z\sim0.5$. Thisdemonstrates that the expansion was decelerating in the range$0.7<z<2.3$, as expected from the matter domination during thisepoch. Combined with measurements of $H_0$, one sees the pattern ofdeceleration followed by acceleration characteristic of a dark-energydominated universe.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

The BOSS Emission-Line Lens Survey. II. Investigating Mass-density Profile Evolution in the SLACS+BELLS Strong Gravitational Lens Sample - Bolton, Adam S.; Brownstein, Joel R.; Kochanek, Christopher S.; Shu, Yiping; Schlegel, David J.; Eisenstein, Daniel J.; Wake, David A.; Connolly, Natalia; Maraston, Claudia; Arneson, Ryan A.; Weaver, Benjamin A. (The Astrophysical Journal, 2012)
We present an analysis of the evolution of the central mass-densityprofile of massive elliptical galaxies from the SLACS and BELLS stronggravitational lens samples over the redshift interval z ≈ 0.1-0.6,based on the combination of strong-lensing aperture mass and stellarvelocity-dispersion constraints. We find a significant trend towardsteeper mass profiles (parameterized by the power-law density model withρvpropr -γ) at later cosmic times, with magnitude d< γ > /dz = -0.60 ± 0.15. We show that the combinedlens-galaxy sample is consistent with a non-evolving distribution ofstellar velocity dispersions. Considering possible additional dependenceof <γ > on lens-galaxy stellar mass, effective radius, andSérsic index, we find marginal evidence for shallower massprofiles at higher masses and larger sizes, but with a significance thatis subdominant to the redshift dependence. Using the results ofpublished Monte Carlo simulations of spectroscopic lens surveys, weverify that our mass-profile evolution result cannot be explained bylensing selection biases as a function of redshift. Interpreted as atrue evolutionary signal, our result suggests that major dry mergersinvolving off-axis trajectories play a significant role in the evolutionof the average mass-density structure of massive early-type galaxiesover the past 6 Gyr. We also consider an alternative non-evolutionaryhypothesis based on variations in the strong-lensing measurementaperture with redshift, which would imply the detection of an"inflection zone" marking the transition between the baryon-dominatedand dark-matter halo-dominated regions of the lens galaxies. Furtherobservations of the combined SLACS+BELLS sample can constrain thispicture more precisely, and enable a more detailed investigation of themultivariate dependences of galaxy mass structure across cosmic time.Based on observations made with the NASA/ESA Hubble Space Telescope,obtained at the Space Telescope Science Institute, which is operated bythe Association of Universities for Research in Astronomy, Inc., underNASA contract NAS 5-26555. These observations are associated withprograms 10174, 10494, 10587, 10798, 10886, and 12209.
Keywords: galaxies: elliptical and lenticular; cD; galaxies: evolution; galaxies: structure; gravitational lensing: strong

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: cosmological implications of the large-scale two-point correlation function - Sánchez, Ariel G.; Scóccola, C. G.; Ross, A. J.; Percival, W.; Manera, M.; Montesano, F.; Mazzalay, X.; Cuesta, A. J.; Eisenstein, D. J.; Kazin, E.; McBride, C. K.; Mehta, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
We obtain constraints on cosmological parameters from the sphericallyaveraged redshift-space correlation function of the CMASS Data Release 9(DR9) sample of the Baryonic Oscillation Spectroscopic Survey (BOSS). Wecombine this information with additional data from recent cosmicmicrowave background (CMB), supernova and baryon acoustic oscillationmeasurements. Our results show no significant evidence of deviationsfrom the standard flat Λ cold dark matter model, whose basicparameters can be specified by Ωm = 0.285 ±0.009, 100 Ωb = 4.59 ± 0.09, ns =0.961 ± 0.009, H0 = 69.4 ± 0.8 kms-1 Mpc-1 and σ8 = 0.80 ±0.02. The CMB+CMASS combination sets tight constraints on the curvatureof the Universe, with Ωk = -0.0043 ± 0.0049, andthe tensor-to-scalar amplitude ratio, for which we find r < 0.16 atthe 95 per cent confidence level (CL). These data show a clear signatureof a deviation from scale invariance also in the presence of tensormodes, with ns < 1 at the 99.7 per cent CL. We deriveconstraints on the fraction of massive neutrinos of fν< 0.049 (95 per cent CL), implying a limit of ∑mν< 0.51 eV. We find no signature of a deviation from a cosmologicalconstant from the combination of all data sets, with a constraint ofwDE = -1.033 ± 0.073 when this parameter is assumedtime-independent, and no evidence of a departure from this value when itis allowed to evolve as wDE(a) = w0 +wa(1 - a). The achieved accuracy on our cosmologicalconstraints is a clear demonstration of the constraining power ofcurrent cosmological observations.
Keywords: cosmological parameters; large-scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: measuring structure growth using passive galaxies - Tojeiro, Rita; Percival, Will J.; Brinkmann, Jon; Brownstein, Joel R.; Eisenstein, Daniel J.; Manera, Marc; Maraston, Claudia; McBride, Cameron K.; Muna, Demitri; Reid, Beth; Ross, Ashley J.; Ross, Nicholas P.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
We explore the benefits of using a passively evolving population ofgalaxies to measure the evolution of the rate of structure growthbetween z = 0.25 and 0.65 by combining data from the Sloan Digital SkySurvey (SDSS) I/II and SDSS-III surveys. The large-scale linear bias ofa population of dynamically passive galaxies, which we select from bothsurveys, is easily modelled. Knowing the bias evolution breaksdegeneracies inherent to other methodologies, and decreases theuncertainty in measurements of the rate of structure growth and thenormalization of the galaxy power spectrum by up to a factor of 2. If wetranslate our measurements into a constraint on σ8(z =0) assuming a concordance cosmological model and general relativity(GR), we find that using a bias model improves our uncertainty by afactor of nearly 1.5. Our results are consistent with a flat Λcold dark matter model and with GR.
Keywords: surveys; Cosmology: observations; dark energy; large-scale structure of Universe

The Milky Way's Circular-velocity Curve between 4 and 14 kpc from APOGEE data - Bovy, Jo; Allende Prieto, Carlos; Beers, Timothy C.; Bizyaev, Dmitry; da Costa, Luiz N.; Cunha, Katia; Ebelke, Garrett L.; Eisenstein, Daniel J.; Frinchaboy, Peter M.; Elia García Pérez, Ana; Girardi, Léo; Hearty, Fred R.; et al. (The Astrophysical Journal, 2012)
We measure the Milky Way's rotation curve over the Galactocentric range4 kpc <~ R <~ 14 kpc from the first year of data from the ApachePoint Observatory Galactic Evolution Experiment. We model theline-of-sight velocities of 3365 stars in 14 fields with b = 0°between 30° <= l <= 210° out to distances of 10 kpc usingan axisymmetric kinematical model that includes a correction for theasymmetric drift of the warm tracer population (σ R ≈ 35 km s-1). We determine the local value of thecircular velocity to be Vc (R 0) = 218 ± 6km s-1 and find that the rotation curve isapproximately flat with a local derivative between -3.0 kms-1 kpc-1 and 0.4 kms-1 kpc-1. We also measure the Sun'sposition and velocity in the Galactocentric rest frame, finding thedistance to the Galactic center to be 8 kpc < R 0 < 9kpc, radial velocity V R, &sun; = -10 ± 1 kms-1, and rotational velocity V phi, &sun;= 242+10 - 3 km s-1, ingood agreement with local measurements of the Sun's radial velocity andwith the observed proper motion of Sgr A*. We investigate varioussystematic uncertainties and find that these are limited to offsets atthe percent level, ~2 km s-1 in Vc .Marginalizing over all the systematics that we consider, we find thatVc (R 0) < 235 km s-1 at
Keywords: Galaxy: disk; Galaxy: fundamental parameters; Galaxy: general; Galaxy: kinematics and dynamics; Galaxy: structure; stars: kinematics and dynamics

Performance of the Apache Point Observatory Galactic Evolution Experiment (APOGEE) high-resolution near-infrared multi-object fiber spectrograph - Wilson, John C.; Hearty, F.; Skrutskie, M. F.; Majewski, S. R.; Schiavon, R.; Eisenstein, D.; Gunn, J.; Holtzman, J.; Nidever, D.; Gillespie, B.; Weinberg, D.; Blank, B.; et al. (Society of Photo-Optical Instrumentation Engineers (SPIE) Conference Series, 2012)
The Apache Point Observatory Galactic Evolution Experiment (APOGEE) usesa dedicated 300-fiber, narrow-band near-infrared (1.51-1.7 μm), highresolution (R~22,500) spectrograph to survey approximately 100,000 giantstars across the Milky Way. This three-year survey, in operation sincelate-summer 2011 as part of the Sloan Digital Sky Survey III (SDSS III),will revolutionize our understanding of the kinematical and chemicalenrichment histories of all Galactic stellar populations. We present theperformance of the instrument from its first year in operation. Theinstrument is housed in a separate building adjacent to the 2.5-m SDSStelescope and fed light via approximately 45-meter fiber runs from thetelescope. The instrument design includes numerous innovations includinga gang connector that allows simultaneous connection of all fibers witha single plug to a telescope cartridge that positions the fibers on thesky, numerous places in the fiber train in which focal ratio degradationhad to be minimized, a large mosaic-VPH (290 mm x 475 mmelliptically-shaped recorded area), an f/1.4 six-element refractivecamera featuring silicon and fused silica elements with diameters aslarge as 393 mm, three near-infrared detectors mounted in a 1 x 3 mosaicwith sub-pixel translation capability, and all of these componentshoused within a custom, LN2-cooled, stainless steel vacuum cryostat withdimensions 1.4-m x 2.3-m x 1.3-m.

Science opportunities with the near-IR camera (NIRCam) on the James Webb Space Telescope (JWST) - Beichman, Charles A.; Rieke, Marcia; Eisenstein, Daniel; Greene, Thomas P.; Krist, John; McCarthy, Don; Meyer, Michael; Stansberry, John (Society of Photo-Optical Instrumentation Engineers (SPIE) Conference Series, 2012)
The Near-Infrared Camera (NIRCam) on the James Webb Space Telescope(JWST) offers revolutionary gains in sensitivity throughout the 1-5μm region. NIRCam will enable great advances in all areas ofastrophysics, from the composition of objects in our own Kuiper Belt andthe physical properties of planets orbiting nearby stars to theformation of stars and the detection of the youngest galaxies in theUniverse. NIRCam also plays an important role in initial alignment ofJWST and the long term maintenance of its image quality. NIRCam ispresently undergoing instrument Integration and Test in preparation fordelivery to the JWST project. Key near-term milestones include thecompletion of cryogenic testing of the entire instrument; demonstrationof scientific and wavefront sensing performance requirements; testing ofreplacement H2RG detectors arrays; and an analysis of coronagraphicperformance in light of measured telescope wavefront characteristics.This paper summarizes the performance of NIRCam, the scientific andeducation/outreach goals of the science team, and some results of theon-going testing program.

SDSS Quasar Catalog, DR9Q (Paris+, 2012) - Paris, I.; Petitjean, P.; Aubourg, E.; Bailey, S.; Ross, N. P.; Myers, A. D.; Strauss, M. A.; Anderson, S. F.; Arnau, E.; Bautista, J.; Bizyaev, D.; Bolton, A. S.; et al. (VizieR Online Data Catalog, 2012)
The SDSS-DR9 Quasar Catalog presents photometric and spectroscopicproperties of 87,822 quasars observed by the SDSS-III/BOSS survey. Weprovide the catalog in the form of a fits file but also an ascii file.We also provide a supplemental list containing 949 quasars with exactlythe same format as the main catalog.(4 data files).
Keywords: Surveys; QSOs; Active gal. nuclei

Spectral Classification and Redshift Measurement for the SDSS-III Baryon Oscillation Spectroscopic Survey - Bolton, Adam S.; Schlegel, David J.; Aubourg, Éric; Bailey, Stephen; Bhardwaj, Vaishali; Brownstein, Joel R.; Burles, Scott; Chen, Yan-Mei; Dawson, Kyle; Eisenstein, Daniel J.; Gunn, James E.; Knapp, G. R.; et al. (The Astronomical Journal, 2012)
We describe the automated spectral classification, redshiftdetermination, and parameter measurement pipeline in use for the BaryonOscillation Spectroscopic Survey (BOSS) of the Sloan Digital Sky SurveyIII (SDSS-III) as of the survey's ninth data release (DR9), encompassing831,000 moderate-resolution optical spectra. We give a review of thealgorithms employed, and describe the changes to the pipeline that havebeen implemented for BOSS relative to previous SDSS-I/II versions,including new sets of stellar, galaxy, and quasar redshift templates.For the color-selected "CMASS" sample of massive galaxies at redshift0.4 <~ z <~ 0.8 targeted by BOSS for the purposes of large-scalecosmological measurements, the pipeline achieves an automated
Keywords: methods: data analysis; surveys; techniques: spectroscopic

A 2 per cent distance to z = 0.35 by reconstructing baryon acoustic oscillations - I. Methods and application to the Sloan Digital Sky Survey - Padmanabhan, Nikhil; Xu, Xiaoying; Eisenstein, Daniel J.; Scalzo, Richard; Cuesta, Antonio J.; Mehta, Kushal T.; Kazin, Eyal (Monthly Notices of the Royal Astronomical Society, 2012)
We present the first application to density field reconstruction to agalaxy survey to undo the smoothing of the baryon acoustic oscillation(BAO) feature due to non-linear gravitational evolution and therebyimprove the precision of the distance measurements possible. We applythe reconstruction technique to the clustering of galaxies from theSloan Digital Sky Survey (SDSS) Data Release 7 (DR7) luminous red galaxy(LRG) sample, sharpening the BAO feature and achieving a 1.9 per centmeasurement of the distance to z = 0.35. We update the reconstructionalgorithm of Eisenstein et al. to account for the effects of surveygeometry as well as redshift-space distortions and validate it on 160LasDamas simulations. We demonstrate that reconstruction sharpens theBAO feature in the angle averaged galaxy correlation function, reducingthe non-linear smoothing scale Σnl from 8.1 to 4.4 Mpch-1. Reconstruction also significantly reduces the effects ofredshift-space distortions at the BAO scale, isotropizing thecorrelation function. This sharpened BAO feature yields an unbiaseddistance estimate (<0.2 per cent) and reduces the scatter from 3.3 to2.1 per cent. We demonstrate the robustness of these results to thevarious reconstruction parameters, including the smoothing scale, thegalaxy bias and the linear growth rate. Applying this reconstructionalgorithm to the SDSS LRG DR7 sample improves the significance of theBAO feature in these data from 3.3σ for the unreconstructedcorrelation function to 4.2σ after reconstruction. We estimate arelative distance scale DV/rs to z = 0.35 of 8.88± 0.17, where rs is the sound horizon andDV≡(DA2H-1)1/3 is a combination of the angular diameter distanceDA and Hubble parameter H. Assuming a sound horizon of 154.25Mpc, this translates into a distance measurement DV(z = 0.35)= 1.356 ± 0.025 Gpc. We find that reconstruction reduces thedistance error in the DR7 sample from 3.5 to 1.9 per cent, equivalent toa survey with three times the volume of SDSS.
Keywords: cosmological parameters; cosmology: observations; dark energy; distance scale; large-scale structure of Universe

A 2 per cent distance to z = 0.35 by reconstructing baryon acoustic oscillations - II. Fitting techniques - Xu, Xiaoying; Padmanabhan, Nikhil; Eisenstein, Daniel J.; Mehta, Kushal T.; Cuesta, Antonio J. (Monthly Notices of the Royal Astronomical Society, 2012)
We present results from fitting the baryon acoustic oscillation (BAO)signal in the correlation function obtained from the first applicationof density-field reconstruction to a galaxy redshift survey, namely theSloan Digital Sky Survey (SDSS) Data Release 7 (DR7) luminous red galaxy(LRG) catalogue. Reconstruction works to partially remove the effects ofnon-linear structure growth on the BAO by reconstructing the linearmatter density field from the observed galaxy density field using thecontinuity equation. We also introduce more careful approaches forderiving a suitable covariance matrix and fitting model for galaxycorrelation functions. Our covariance matrix technique guarantees smoothdiagonal and off-diagonal terms by fitting a modified Gaussiancovariance matrix to that calculated from mock catalogues. Our proposedfitting model is effective at removing broad-band effects such asredshift-space distortions, scale-dependent bias and any artefactsintroduced by assuming the wrong model cosmology. These all aid inobtaining a more accurate measurement of the acoustic scale and itserror. We validate these techniques on 160 mock catalogues derived fromthe LasDamas simulations in real and redshift space. We then apply thesetechniques to the DR7 LRG sample and find that the error on the acousticscale decreases from ˜3.5 per cent before reconstruction to˜1.9 per cent after reconstruction. We also see an increase in ourBAO detection confidence from ˜3σ to ˜4σ afterreconstruction with our confidence level in measuring the correctacoustic scale increasing from ˜3σ to ˜5σ. Usingthe mean of the acoustic scale probability distributions produced fromour fits, we find Dv/rs = 8.89 ± 0.31before reconstruction and 8.88 ± 0.17 after reconstruction.
Keywords: cosmological parameters; cosmology: observations; cosmology: theory; distance scale; large-scale structure of Universe

A 2 per cent distance to z = 0.35 by reconstructing baryon acoustic oscillations - III. Cosmological measurements and interpretation - Mehta, Kushal T.; Cuesta, Antonio J.; Xu, Xiaoying; Eisenstein, Daniel J.; Padmanabhan, Nikhil (Monthly Notices of the Royal Astronomical Society, 2012)
We use the 2 per cent distance measurement from our reconstructed baryonacoustic oscillations (BAOs) signature using the Sloan Digital SkySurvey (SDSS) Data Release 7 (DR7) luminous red galaxies fromPadmanabhan et al. and Xu et al. combined with cosmic microwavebackground data from Wilkinson Microwave Anisotropy Probe (WMAP7) tomeasure parameters for various cosmological models. We find a 1.7 percent measurement of H0 = 69.8 ± 1.2 km s-1Mpc-1 and a 5.0 per cent measurement ofΩm=0.280±0.014 for a flat universe with a cosmologicalconstant. These measurements of H0 and Ωmare robust against a range of underlying models for the expansionhistory. We measure the dark energy equation of state parameter w =-0.97 ± 0.17, which is consistent with a cosmological constant.If curvature is allowed to vary, we find that the Universe is consistentwith a flat geometry (ΩK = -0.004 ± 0.005). Wealso use a combination of the 6 Degree Field Galaxy Survey BAO data,WiggleZ Dark Energy Survey data, Type Ia supernovae data and a localmeasurement of the Hubble constant to explore cosmological models withmore parameters. Finally, we explore the effect of varying the energydensity of relativistic particles on the measurement of H0.
Keywords: cosmological parameters; cosmology: observations; cosmology: theory; distance scale; large-scale structure of Universe

Acoustic Scale from the Angular Power Spectra of SDSS-III DR8 Photometric Luminous Galaxies - Seo, Hee-Jong; Ho, Shirley; White, Martin; Cuesta, Antonio J.; Ross, Ashley J.; Saito, Shun; Reid, Beth; Padmanabhan, Nikhil; Percival, Will J.; de Putter, Roland; Schlegel, David J.; Eisenstein, Daniel J.; et al. (The Astrophysical Journal, 2012)
We measure the acoustic scale from the angular power spectra of theSloan Digital Sky Survey III (SDSS-III) Data Release 8 imaging catalogthat includes 872, 921 galaxies over ~10,000 deg2 between0.45 < z < 0.65. The extensive spectroscopic training set of theBaryon Oscillation Spectroscopic Survey luminous galaxies allows preciseestimates of the true redshift distributions of galaxies in our imagingcatalog. Utilizing the redshift distribution information, we buildtemplates and fit to the power spectra of the data, which are measuredin our companion paper, to derive the location of Baryon acousticoscillations (BAOs) while marginalizing over many free parameters toexclude nearly all of the non-BAO signal. We derive the ratio of theangular diameter distance to the sound horizon scale DA(z)/rs = 9.212+0.416 - 0.404 at z= 0.54, and therefore DA (z) = 1411 ± 65 Mpc at z =0.54; the result is fairly independent of assumptions on the underlyingcosmology. Our measurement of angular diameter distance DA(z) is 1.4σ higher than what is expected for the concordanceΛCDM, in accordance to the trend of other spectroscopic BAOmeasurements for z >~ 0.35. We report constraints on cosmologicalparameters from our measurement in combination with the WMAP7 data andthe previous spectroscopic BAO measurements of SDSS and WiggleZ. Werefer to our companion papers (Ho et al. de Putter et al.) forinvestigations on information of the full power spectrum.
Keywords: distance scale; cosmological parameters; cosmology: observations; large-scale structure of universe

The BOSS Lyman-alpha Forest Sample from SDSS Data Release 9 - Lee, Khee-Gan; Bailey, Stephen; Bartsch, Leslie E.; Carithers, William; Dawson, Kyle S.; Kirkby, David; Lundgren, Britt; Margala, Daniel; Palanque-Delabrouille, Nathalie; Pieri, Matthew M.; Schlegel, David J.; Weinberg, David H.; et al. (ArXiv e-prints, 2012)
We present the BOSS Lyman-alpha (Lya) Forest Sample from SDSS DataRelease 9, comprising 54,468 quasar spectra with zqso > 2.15 suitablefor Lya forest analysis. This data set probes the intergalactic mediumwith absorption redshifts 2.0 < z_alpha < 5.7 over an area of 3275square degrees, and encompasses an approximate comoving volume of 20h^-3 Gpc^3. With each spectrum, we have included several productsdesigned to aid in Lya forest analysis: improved sky masks that flagpixels where data may be unreliable, corrections for known biases in thepipeline estimated noise, masks for the cores of damped Lya systems andcorrections for their wings, and estimates of the unabsorbed continua sothat the observed flux can be converted to a fractional transmission.The continua are derived using a principal component fit to the quasarspectrum redwards of restframe Lya (lambda > 1216 Ang), extrapolatedinto the forest region and normalized by a linear function to fit theexpected evolution of the Lya forest mean-flux. The estimated continuum
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: measurements of the growth of structure and expansion rate at z = 0.57 from anisotropic clustering - Reid, Beth A.; Samushia, Lado; White, Martin; Percival, Will J.; Manera, Marc; Padmanabhan, Nikhil; Ross, Ashley J.; Sánchez, Ariel G.; Bailey, Stephen; Bizyaev, Dmitry; Bolton, Adam S.; Brewington, Howard; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
We analyse the anisotropic clustering of massive galaxies from the SloanDigital Sky Survey III Baryon Oscillation Spectroscopic Survey (BOSS)Data Release 9 (DR9) sample, which consists of 264 283 galaxies in theredshift range 0.43 < z < 0.7 spanning 3275 deg2. Bothpeculiar velocities and errors in the assumed redshift-distance relation('Alcock-Paczynski effect') generate correlations between clusteringamplitude and orientation with respect to the line of sight. Togetherwith the sharp baryon acoustic oscillation (BAO) standard ruler, ourmeasurements of the broad-band shape of the monopole and quadrupolecorrelation functions simultaneously constrain the comoving angulardiameter distance (2190 ± 61 Mpc) to z = 0.57, the Hubbleexpansion rate at z = 0.57 (92.4 ± 4.5 km s-1Mpc-1) and the growth rate of structure at that same redshift(dσ8/d ln a = 0.43 ± 0.069). Our analysisprovides the best current direct determination of both DA andH in galaxy clustering data using this technique. If we further assume aΛcold dark matter expansion history, our growth constrainttightens to dσ8/d ln a = 0.415 ± 0.034. Incombination with the cosmic microwave background, our measurements ofDA, H and dσ8/d ln a all separately requiredark energy at z > 0.57, and when combined implyΩΛ = 0.74 ± 0.016, independent of theUniverse's evolution at z < 0.57. All of these constraints assumescale-independent linear growth, and assume general relativity tocompute both O(10 per cent) non-linear model corrections and our errors.In our companion paper, Samushia et al., we explore further cosmologicalimplications of these observations.
Keywords: galaxies: haloes; galaxies: statistics; cosmological parameters; large-scale structure of Universe

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: Luminosity and Color Dependence and Redshift Evolution - Guo, Hong; Zehavi, Idit; Zheng, Zheng; Weinberg, David H.; Berlind, Andreas A.; Blanton, Michael; Chen, Yanmei; Eisenstein, Daniel J.; Ho, Shirley; Kazin, Eyal; Manera, Marc; Maraston, Claudia; et al. (ArXiv e-prints, 2012)
We measure the luminosity and color dependence and the redshiftevolution of galaxy clustering in the Sloan Digital Sky Survey-IIIBaryon Oscillation Spectroscopic Survey Ninth Data Release. We focus onthe projected two-point correlation function (2PCF) of subsets of itsCMASS sample, which includes about 260,000 galaxies over ~3,300 sq. degin the redshift range 0.43<z<0.7. To minimize the selection effecton galaxy clustering, we construct well-defined luminosity and colorsubsamples by carefully accounting for the CMASS galaxy selection cuts.The 2PCF of the whole CMASS sample, if approximated by a power-law, hasa correlation length of r_0=7.93±0.06Mpc/h and an index ofγ=1.85±0.01. Clear dependences on galaxy luminosity and color arefound for the projected 2PCF in all redshift bins, with more luminousand redder galaxies generally exhibiting stronger clustering and steeper2PCF. The color dependence is also clearly seen for galaxies within thered sequence, consistent with the behavior of SDSS-II main samplegalaxies at lower redshifts. At a given luminosity (k+e corrected), nosignificant evolution of the projected 2PCFs with redshift is detectedfor red sequence galaxies. We also construct galaxy samples of fixednumber density at different redshifts, using redshift-dependentmagnitude thresholds. The clustering of these galaxies in the CMASSredshift range is found to be consistent with that predicted by passiveevolution. Our measurements of the luminosity and color dependence andredshift evolution of galaxy clustering will allow for detailed modelingof the relation between galaxies and dark matter halos and newconstraints on galaxy formation and evolution.
Keywords: Astrophysics - Cosmology and Extragalactic Astrophysics

Clustering of Sloan Digital Sky Survey III Photometric Luminous Galaxies: The Measurement, Systematics, and Cosmological Implications - Ho, Shirley; Cuesta, Antonio; Seo, Hee-Jong; de Putter, Roland; Ross, Ashley J.; White, Martin; Padmanabhan, Nikhil; Saito, Shun; Schlegel, David J.; Schlafly, Eddie; Seljak, Uros; Hernández-Monteagudo, Carlos; et al. (The Astrophysical Journal, 2012)
The Sloan Digital Sky Survey (SDSS) surveyed 14,555 deg2, anddelivered over a trillion pixels of imaging data. We present a study ofgalaxy clustering using 900,000 luminous galaxies with photometricredshifts, spanning between z = 0.45 and z = 0.65, constructed from theSDSS using methods described in Ross et al. This data set spans 11,000deg2 and probes a volume of 3 h -3Gpc3, making it the largest volume ever used for galaxyclustering measurements. We describe in detail the construction of thesurvey window function and various systematics affecting ourmeasurement. With such a large volume, high-precision cosmologicalconstraints can be obtained given careful control and understanding ofthe observational systematics. We present a novel treatment of theobservational systematics and its applications to the clustering signalsfrom the data set. In this paper, we measure the angular clusteringusing an optimal quadratic estimator at four redshift slices with an
Keywords: cosmological parameters; dark energy; dark matter; distance scale

The Ninth Data Release of the Sloan Digital Sky Survey: First Spectroscopic Data from the SDSS-III Baryon Oscillation Spectroscopic Survey - Ahn, Christopher P.; Alexandroff, Rachael; Allende Prieto, Carlos; Anderson, Scott F.; Anderton, Timothy; Andrews, Brett H.; Aubourg, Éric; Bailey, Stephen; Balbinot, Eduardo; Barnes, Rory; Bautista, Julian; Beers, Timothy C.; et al. (The Astrophysical Journal Supplement Series, 2012)
The Sloan Digital Sky Survey III (SDSS-III) presents the firstspectroscopic data from the Baryon Oscillation Spectroscopic Survey(BOSS). This ninth data release (DR9) of the SDSS project includes535,995 new galaxy spectra (median z ~ 0.52), 102,100 new quasar spectra(median z ~ 2.32), and 90,897 new stellar spectra, along with the datapresented in previous data releases. These spectra were obtained withthe new BOSS spectrograph and were taken between 2009 December and 2011July. In addition, the stellar parameters pipeline, which determinesradial velocities, surface temperatures, surface gravities, andmetallicities of stars, has been updated and refined with improvementsin temperature estimates for stars with T eff < 5000 K andin metallicity estimates for stars with [Fe/H] > -0.5. DR9 includesnew stellar parameters for all stars presented in DR8, including starsfrom SDSS-I and II, as well as those observed as part of the SEGUE-2.The astrometry error introduced in the DR8 imaging catalogs has beencorrected in the DR9 data products. The next data release for SDSS-IIIwill be in Summer 2013, which will present the first data from theAPOGEE along with another year of data from BOSS, followed by the finalSDSS-III data release in 2014 December.
Keywords: atlases; catalogs; surveys

The Sloan Digital Sky Survey quasar catalog: ninth data release - Pâris, I.; Petitjean, P.; Aubourg, É.; Bailey, S.; Ross, N. P.; Myers, A. D.; Strauss, M. A.; Anderson, S. F.; Arnau, E.; Bautista, J.; Bizyaev, D.; Bolton, A. S.; et al. (Astronomy and Astrophysics, 2012)
We present the Data Release 9 Quasar (DR9Q) catalog from the BaryonOscillation Spectroscopic Survey (BOSS) of the Sloan Digital Sky SurveyIII. The catalog includes all BOSS objects that were targeted as quasarcandidates during the survey, are spectrocopically confirmed as quasarsvia visual inspection, have luminosities Mi[z = 2] < -20.5(in a ΛCDM cosmology with H0 = 70 km s-1Mpc-1, ΩM = 0.3, andΩΛ = 0.7) and either display at least oneemission line with full width at half maximum (FWHM) larger than 500 kms-1 or, if not, have interesting/complex absorption features.It includes as well, known quasars (mostly from SDSS-I and II) that werereobserved by BOSS. This catalog contains 87 822 quasars (78 086 are newdiscoveries) detected over 3275 deg2 with robustidentification and redshift measured by a combination of principalcomponent eigenspectra newly derived from a training set of 8632 spectrafrom SDSS-DR7. The number of quasars with z > 2.15 (61 931) is ~2.8times larger than the number of z > 2.15 quasars previously known.Redshifts and FWHMs are provided for the strongest emission lines (C iv,C iii], Mg ii). The catalog identifies 7533 broad absorption linequasars and gives their characteristics. For each object the catalogpresents five-band (u, g, r, i, z) CCD-based photometry with typicalaccuracy of 0.03 mag, and information on the morphology and selectionmethod. The catalog also contains X-ray, ultraviolet, near-infrared, andradio emission properties of the quasars, when available, from otherlarge-area surveys. The calibrated digital spectra cover the wavelengthregion 3600-10 500 Å at a spectral resolution in the range 1300< R < 2500; the spectra can be retrieved from the SDSS CatalogArchive Server. We also provide a supplemental list of an additional 949quasars that have been identified, among galaxy targets of the BOSS oramong quasar targets after DR9 was frozen.Catalog is only available at the CDS via anonymous ftp tocdsarc.u-strasbg.fr (130.79.128.5) or via <Ahref="http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/548/A66">http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/548/A66
Keywords: catalogs; surveys; quasars: general

The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: baryon acoustic oscillations in the Data Release 9 spectroscopic galaxy sample - Anderson, Lauren; Aubourg, Eric; Bailey, Stephen; Bizyaev, Dmitry; Blanton, Michael; Bolton, Adam S.; Brinkmann, J.; Brownstein, Joel R.; Burden, Angela; Cuesta, Antonio J.; da Costa, Luiz A. N.; Dawson, Kyle S.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
We present measurements of galaxy clustering from the Baryon OscillationSpectroscopic Survey (BOSS), which is part of the Sloan Digital SkySurvey III (SDSS-III). These use the Data Release 9 (DR9) CMASS sample,which contains 264 283 massive galaxies covering 3275 square degreeswith an effective redshift z = 0.57 and redshift range 0.43 < z <0.7. Assuming a concordance ΛCDM cosmological model, this samplecovers an effective volume of 2.2 Gpc3, and represents thelargest sample of the Universe ever surveyed at this density,n¯≈3×10-4 h-3 Mpc 3. We measure theangle-averaged galaxy correlation function and power spectrum, includingdensity-field reconstruction of the baryon acoustic oscillation (BAO)feature. The acoustic features are detected at a significance of5σ in both the correlation function and power spectrum. Combiningwith the SDSS-II luminous red galaxy sample, the detection significanceincreases to 6.7σ. Fitting for the position of the acousticfeatures measures the distance to z = 0.57 relative to the sound horizonDV/rs = 13.67 ± 0.22 at z = 0.57. Assuminga fiducial sound horizon of 153.19 Mpc, which matches cosmic microwavebackground constraints, this corresponds to a distance DV (z= 0.57) = 2094 ± 34 Mpc. At 1.7 per cent, this is the mostprecise distance constraint ever obtained from a galaxy survey. We placethis result alongside previous BAO measurements in a cosmologicaldistance ladder and find excellent agreement with the current supernovameasurements. We use these distance measurements to constrain variouscosmological models, finding continuing support for a flat Universe witha cosmological constant.
Keywords: cosmological parameters; cosmology: observations; dark energy; distance scale; large-scale structure of Universe

The BOSS Emission-Line Lens Survey (BELLS). I. A Large Spectroscopically Selected Sample of Lens Galaxies at Redshift ~0.5 - Brownstein, Joel R.; Bolton, Adam S.; Schlegel, David J.; Eisenstein, Daniel J.; Kochanek, Christopher S.; Connolly, Natalia; Maraston, Claudia; Pandey, Parul; Seitz, Stella; Wake, David A.; Wood-Vasey, W. Michael; Brinkmann, Jon; et al. (The Astrophysical Journal, 2012)
We present a catalog of 25 definite and 11 probable strong galaxy-galaxygravitational lens systems with lens redshifts 0.4 <~ z <~ 0.7,discovered spectroscopically by the presence of higher-redshift emissionlines within the Baryon Oscillation Spectroscopic Survey (BOSS) ofluminous galaxies, and confirmed with high-resolution Hubble SpaceTelescope (HST) images of 44 candidates. Our survey extends themethodology of the Sloan Lens Advanced Camera for Surveys survey (SLACS)to higher redshift. We describe the details of the BOSS spectroscopiccandidate detections, our HST ACS image processing and analysis methods,and our strong gravitational lens modeling procedure. We report BOSSspectroscopic parameters and ACS photometric parameters for allcandidates, and mass-distribution parameters for the best-fit singularisothermal ellipsoid models of definite lenses. Our sample to date wasselected using only the first six months of BOSS survey-qualityspectroscopic data. The full five-year BOSS database should produce asample of several hundred strong galaxy-galaxy lenses and in combinationwith SLACS lenses at lower redshift, strongly constrain the redshiftevolution of the structure of elliptical, bulge-dominated galaxies as afunction of luminosity, stellar mass, and rest-frame color, therebyproviding a powerful test for competing theories of galaxy formation andevolution.Based on observations made with the NASA/ESA Hubble Space Telescope,obtained at the Space Telescope Science Institute, which is operated bythe Association of Universities for Research in Astronomy, Inc., underNASA contract NAS 5-26555. These observations are associated withprogram 12209. Based on spectroscopic data from the Baryon OscillationSpectroscopic Survey of the Sloan Digital Sky Survey III.

Morphology and Size Differences Between Local and High-redshift Luminous Infrared Galaxies - Rujopakarn, Wiphu; Rieke, George H.; Eisenstein, Daniel J.; Juneau, Stéphanie (The Astrophysical Journal, 2011)
We show that the star-forming regions in high-redshift luminous andultraluminous infrared galaxies (LIRGs and ULIRGs) and submillimetergalaxies (SMGs) have similar physical scales to those in local normalstar-forming galaxies. To first order, their higher infrared (IR)luminosities result from higher luminosity surface density. We also finda good correlation between the IR luminosity and IR luminosity surfacedensity in starburst galaxies across over five orders of magnitude of IRluminosity from local normal galaxies to z ~ 2 SMGs. The intenselystar-forming regions of local ULIRGs are significantly smaller thanthose in their high-redshift counterparts and hence divergesignificantly from this correlation, indicating that the ULIRGs foundlocally are a different population from the high-redshift ULIRGs andSMGs. Based on this relationship, we suggest that luminosity surfacedensity should serve as a more accurate indicator for the IR emittingenvironment, and hence the observable properties, of star-forminggalaxies than their IR luminosity. We demonstrate this approach byshowing that ULIRGs at z ~ 1 and a lensed galaxy at z ~ 2.5 exhibitaromatic features agreeing with local LIRGs that are an order ofmagnitude less luminous, but have similar IR luminosity surface density.A consequence of this relationship is that the aromatic emissionstrength in star-forming galaxies will appear to increase at z>1 fora given IR luminosity compared to their local counterparts.

PRIMUS: Obscured Star Formation on the Red Sequence - Zhu, Guangtun; Blanton, Michael R.; Burles, Scott M.; Coil, Alison L.; Cool, Richard J.; Eisenstein, Daniel J.; Moustakas, John; Kenneth C. Wong; Aird, James (The Astrophysical Journal, 2011)
We quantify the fraction of galaxies at moderate redshifts (0.1 < z< 0.5) that appear red-and-dead in the optical, but in fact containobscured star formation detectable in the infrared (IR), with the PRIsmMUlti-object Survey (PRIMUS). PRIMUS has measured ~120,000 robust

MARVELS-1b: A Short-period, Brown Dwarf Desert Candidate from the SDSS-III Marvels Planet Search - Lee, Brian L.; Ge, Jian; Fleming, Scott W.; Stassun, Keivan G.; Gaudi, B. Scott; Barnes, Rory; Mahadevan, Suvrath; Eastman, Jason D.; Wright, Jason; Siverd, Robert J.; Gary, Bruce; Ghezzi, Luan; et al. (The Astrophysical Journal, 2011)
We present a new short-period brown dwarf (BD) candidate around the starTYC 1240-00945-1. This candidate was discovered in the first year of theMulti-object APO Radial Velocity Exoplanets Large-area Survey (MARVELS),which is part of the Sloan Digital Sky Survey (SDSS) III, and wedesignate the BD as MARVELS-1b. MARVELS uses the technique of dispersedfixed-delay interferometery to simultaneously obtain radial velocity(RV) measurements for 60 objects per field using a single, custom-builtinstrument that is fiber fed from the SDSS 2.5 m telescope. From our 20RV measurements spread over a ~370 day time baseline, we derive aKeplerian orbital fit with semi-amplitude K = 2.533 ± 0.025 kms-1, period P = 5.8953 ± 0.0004 days, and eccentricityconsistent with circular. Independent follow-up RV data confirm theorbit. Adopting a mass of 1.37 ± 0.11 M sun for theslightly evolved F9 host star, we infer that the companion has a minimummass of 28.0 ± 1.5 M Jup, a semimajor axis 0.071± 0.002 AU assuming an edge-on orbit, and is probably tidallysynchronized. We find no evidence for coherent intrinsic variability ofthe host star at the period of the companion at levels greater than afew millimagnitudes. The companion has an a priori transit probability

PRIMUS: Enhanced Specific Star Formation Rates in Close Galaxy Pairs - Kenneth C. Wong; Blanton, Michael R.; Burles, Scott M.; Coil, Alison L.; Cool, Richard J.; Eisenstein, Daniel J.; Moustakas, John; Zhu, Guangtun; Arnouts, Stéphane (The Astrophysical Journal, 2011)
Tidal interactions between galaxies can trigger star formation, whichcontributes to the global star formation rate (SFR) density of theuniverse and could be a factor in the transformation of blue,star-forming galaxies to red, quiescent galaxies over cosmic time. Weinvestigate tidally triggered star formation in isolated close galaxypairs drawn from the Prism Multi-Object Survey (PRIMUS), alow-dispersion prism redshift survey that has measured ~120,000 robustgalaxy redshifts over 9.1 deg2 out to z ~ 1. We select asample of galaxies in isolated galaxy pairs at redshifts 0.25 <= z<= 0.75, with no other objects within a projected separation of 300 h-1 kpc and Δz/(1 + z) = 0.01, and compare them to acontrol sample of isolated galaxies to test for systematic differencesin their rest-frame FUV - r and NUV - r colors as a proxy for relativespecific star formation rates (SSFRs). We find that galaxies inrp <= 50 h -1 kpc pairs have bluerdust-corrected UV - r colors on average than the control galaxies by-0.134 ± 0.045 mag in FUV - r and -0.075 ± 0.038 mag in

Clustering of Obscured and Unobscured Quasars in the Boötes Field: Placing Rapidly Growing Black Holes in the Cosmic Web - Hickox, Ryan C.; Myers, Adam D.; Brodwin, Mark; Alexander, David M.; Forman, William R.; Jones, Christine; Murray, Stephen S.; Brown, Michael J. I.; Cool, Richard J.; Kochanek, Christopher S.; Dey, Arjun; Jannuzi, Buell T.; et al. (The Astrophysical Journal, 2011)
We present the first measurement of the spatial clustering ofmid-infrared-selected obscured and unobscured quasars, using a sample inthe redshift range 0.7 < z < 1.8 selected from the 9deg2 Boötes multiwavelength survey. Recently, theSpitzer Space Telescope and X-ray observations have revealed largepopulations of obscured quasars that have been inferred from models ofthe X-ray background and supermassive black hole evolution. To date,little is known about obscured quasar clustering, which allows us tomeasure the masses of their host dark matter halos and explore theirrole in the cosmic evolution of black holes and galaxies. In this study,we use a sample of 806 mid-infrared-selected quasars and ≈250,000galaxies to calculate the projected quasar-galaxy cross-correlationfunction wp (R). The observed clustering yieldscharacteristic dark matter halo masses of log(M halo [h-1 M sun]) = 12.7+0.4 -0.6and 13.3+0.3 -0.4 for unobscured quasars (QSO-1s)and obscured quasars (Obs-QSOs), respectively. The results for QSO-1sare in excellent agreement with previous measurements for opticallyselected quasars, while we conclude that the Obs-QSOs are at least asstrongly clustered as the QSO-1s. We test for the effects of photometricredshift errors on the optically faint Obs-QSOs, and find that ourmethod yields a robust lower limit on the clustering; photo-z errors maycause us to underestimate the clustering amplitude of the Obs-QSOs by at

The Eighth Data Release of the Sloan Digital Sky Survey: First Data from SDSS-III - Aihara, Hiroaki; Allende Prieto, Carlos; An, Deokkeun; Anderson, Scott F.; Aubourg, Éric; Balbinot, Eduardo; Beers, Timothy C.; Berlind, Andreas A.; Bickerton, Steven J.; Bizyaev, Dmitry; Blanton, Michael R.; Bochanski, John J.; et al. (The Astrophysical Journal Supplement Series, 2011)
The Sloan Digital Sky Survey (SDSS) started a new phase in 2008 August,with new instrumentation and new surveys focused on Galactic structureand chemical evolution, measurements of the baryon oscillation featurein the clustering of galaxies and the quasar Lyα forest, and aradial velocity search for planets around ~8000 stars. This paperdescribes the first data release of SDSS-III (and the eighth countingfrom the beginning of the SDSS). The release includes five-band imagingof roughly 5200 deg2 in the southern Galactic cap, bringingthe total footprint of the SDSS imaging to 14,555 deg2, orover a third of the Celestial Sphere. All the imaging data have beenreprocessed with an improved sky-subtraction algorithm and a final,self-consistent photometric recalibration and flat-field determination.This release also includes all data from the second phase of the SloanExtension for Galactic Understanding and Exploration (SEGUE-2),consisting of spectroscopy of approximately 118,000 stars at both highand low Galactic latitudes. All the more than half a million stellarspectra obtained with the SDSS spectrograph have been reprocessedthrough an improved stellar parameter pipeline, which has betterdetermination of metallicity for high-metallicity stars.

Galaxy Bias and Its Effects on the Baryon Acoustic Oscillation Measurements - Mehta, Kushal T.; Seo, Hee-Jong; Eckel, Jonathan; Eisenstein, Daniel J.; Metchnik, Marc; Pinto, Philip; Xu, Xiaoying (The Astrophysical Journal, 2011)
The baryon acoustic oscillation (BAO) feature in the clustering ofmatter in the universe serves as a robust standard ruler and hence canbe used to map the expansion history of the universe. We use high forceresolution simulations to analyze the effects of galaxy bias on themeasurements of the BAO signal. We apply a variety of Halo OccupationDistributions (HODs) and produce biased mass tracers to mimic differentgalaxy populations. We investigate whether galaxy bias changes thenonlinear shifts on the acoustic scale relative to the underlying darkmatter distribution presented by Seo et al. For the less biased HODmodels (b < 3), we do not detect any shift in the acoustic scale

Gas Kinematics in Lyα Nebulae - Yang, Yujin; Zabludoff, Ann; Jahnke, Knud; Eisenstein, Daniel; Davé, Romeel; Shectman, Stephen A.; Kelson, Daniel D. (The Astrophysical Journal, 2011)
Exploring the origin of Lyα nebulae ("blobs") at high redshiftrequires measurements of their gas kinematics that are impossible withonly the resonant, optically thick Lyα line. To define gas motionsrelative to the systemic velocity of the blob, the Lyα line mustbe compared with an optically thin line like Hα λ6563,which is not much altered by radiative transfer effects and is moreconcentrated about the galaxies embedded in the nebula's core. We obtainoptical and near-IR (NIR) spectra of the two brightest Lyα blobs(CDFS-LAB01 and CDFS-LAB02) from the Yang et al. sample using theMagellan/Magellan Echellette Spectrograph optical and Very LargeTelescope/SINFONI NIR spectrographs. Both the Lyα and Hαlines confirm that these blobs lie at the survey redshift, z ~ 2.3.Within each blob, we detect several Hα sources, which roughlycorrespond to galaxies seen in Hubble Space Telescope rest-frame UVimages. The Hα detections show that these galaxies have largeinternal velocity dispersions (σ v = 130-190 kms-1) and that, in the one system (LAB01), where we canreliably extract profiles for two Hα sources, their velocitydifference is Δv ~ 440 km s-1. The presence of multiplegalaxies within the blobs, and those galaxies' large velocitydispersions and large relative motion, is consistent with our previousfinding that Lyα blobs inhabit massive dark matter halos that willevolve into those typical of present-day rich clusters and that theembedded galaxies may eventually become brightest cluster galaxies. Todetermine whether the gas near the embedded galaxies is predominantlyinfalling or outflowing, we compare the Lyα and Hα linecenters, finding that Lyα is not offset (ΔvLyα = +0 km s-1) in LAB01 and redshifted byonly +230 km s-1 in LAB02. These offsets are small comparedto those of Lyman break galaxies, which average +450 km s-1and extend to about +700 km s-1. In LAB02, we detect C IIλ1334 and Si II λ1526 absorption lines, whose bluewardshifts of ~200 km s-1 are consistent with the small outflowimplied by the redward shift of Lyα. We test and rule out thesimplest infall models and those outflow models with super/hyperwinds,which require large outflow velocities. Because of the unknown geometryof the gas distribution and the possibility of multiple sources ofLyα emission embedded in the blobs, a larger sample and moresophisticated models are required to test more complex or a wider rangeof infall and outflow scenarios.

SDSS-III: Massive Spectroscopic Surveys of the Distant Universe, the Milky Way, and Extra-Solar Planetary Systems - Eisenstein, Daniel J.; Weinberg, David H.; Agol, Eric; Aihara, Hiroaki; Allende Prieto, Carlos; Anderson, Scott F.; Arns, James A.; Aubourg, Éric; Bailey, Stephen; Balbinot, Eduardo; Barkhouser, Robert; Beers, Timothy C.; et al. (The Astronomical Journal, 2011)
Building on the legacy of the Sloan Digital Sky Survey (SDSS-I and II),SDSS-III is a program of four spectroscopic surveys on three scientificthemes: dark energy and cosmological parameters, the history andstructure of the Milky Way, and the population of giant planets aroundother stars. In keeping with SDSS tradition, SDSS-III will provideregular public releases of all its data, beginning with SDSS DataRelease 8 (DR8), which was made public in 2011 January and includesSDSS-I and SDSS-II images and spectra reprocessed with the latestpipelines and calibrations produced for the SDSS-III investigations.This paper presents an overview of the four surveys that compriseSDSS-III. The Baryon Oscillation Spectroscopic Survey will measureredshifts of 1.5 million massive galaxies and Lyα forest spectraof 150,000 quasars, using the baryon acoustic oscillation feature oflarge-scale structure to obtain percent-level determinations of thedistance scale and Hubble expansion rate at z < 0.7 and at z ≈2.5. SEGUE-2, an already completed SDSS-III survey that is thecontinuation of the SDSS-II Sloan Extension for Galactic Understandingand Exploration (SEGUE), measured medium-resolution (R =λ/Δλ ≈ 1800) optical spectra of 118,000 stars ina variety of target categories, probing chemical evolution, stellarkinematics and substructure, and the mass profile of the dark matterhalo from the solar neighborhood to distances of 100 kpc. APOGEE, theApache Point Observatory Galactic Evolution Experiment, will obtainhigh-resolution (R ≈ 30,000), high signal-to-noise ratio (S/N >=100 per resolution element), H-band (1.51 μm < λ < 1.70μm) spectra of 105 evolved, late-type stars, measuringseparate abundances for ~15 elements per star and creating the firsthigh-precision spectroscopic survey of all Galactic stellar populations(bulge, bar, disks, halo) with a uniform set of stellar tracers andspectral diagnostics. The Multi-object APO Radial Velocity ExoplanetLarge-area Survey (MARVELS) will monitor radial velocities of more than8000 FGK stars with the sensitivity and cadence (10-40 m s-1,~24 visits per star) needed to detect giant planets with periods up totwo years, providing an unprecedented data set for understanding theformation and dynamical evolution of giant planet systems. As of 2011January, SDSS-III has obtained spectra of more than 240,000 galaxies,29,000 z >= 2.2 quasars, and 140,000 stars, including 74,000 velocitymeasurements of 2580 stars for MARVELS.

The Lyman-α forest in three dimensions: measurements of large scale flux correlations from BOSS 1st-year data - Slosar, Anže; Font-Ribera, Andreu; Pieri, Matthew M.; Rich, James; Le Goff, Jean-Marc; Aubourg, Éric; Brinkmann, Jon; Busca, Nicolas; Carithers, Bill; Charlassier, Romain; Cortês, Marina; Croft, Rupert; et al. (Journal of Cosmology and Astro-Particle Physics, 2011)
Using a sample of approximately 14,000 z > 2.1 quasars observed inthe first year of the Baryon Oscillation Spectroscopic Survey (BOSS), wemeasure the three-dimensional correlation function of absorption in theLyman-α forest. The angle-averaged correlation function oftransmitted flux (F = e-τ) is securely detected outto comoving separations of 60 h-1Mpc, the firstdetection of flux correlations across widely separated sightlines. Aquadrupole distortion of the redshift-space correlation function bypeculiar velocities, the signature of the gravitational instabilityorigin of structure in the Lyman-α forest, is also detected athigh significance. We obtain a good fit to the data assuming lineartheory redshift-space distortion and linear bias of the transmittedflux, relative to the matter fluctuations of a standard ΛCDMcosmological model (inflationary cold dark matter with a cosmological

The PRIsm MUlti-object Survey (PRIMUS). I. Survey Overview and Characteristics - Coil, Alison L.; Blanton, Michael R.; Burles, Scott M.; Cool, Richard J.; Eisenstein, Daniel J.; Moustakas, John; Kenneth C. Wong; Zhu, Guangtun; Aird, James; Bernstein, Rebecca A.; Bolton, Adam S.; Hogg, David W. (The Astrophysical Journal, 2011)
We present the PRIsm MUlti-object Survey (PRIMUS), a spectroscopic faintgalaxy redshift survey to z ~ 1. PRIMUS uses a low-dispersion prism andslitmasks to observe ~2500 objects at once in a 0.18 deg2field of view, using the Inamori Magellan Areal Camera and Spectrographcamera on the Magellan I Baade 6.5 m telescope at Las CampanasObservatory. PRIMUS covers a total of 9.1 deg2 of sky to adepth of i AB ~ 23.5 in seven different deep,multi-wavelength fields that have coverage from the Galaxy EvolutionExplorer, Spitzer, and either XMM or Chandra, as well as multiple-bandoptical and near-IR coverage. PRIMUS includes ~130,000 robust redshiftsof unique objects with a redshift precision of σ z /(1+ z) ~ 0.005. The redshift distribution peaks at z ~ 0.6 and extends toz = 1.2 for galaxies and z = 5 for broad-line active galactic nuclei.The motivation, observational techniques, fields, target selection,slitmask design, and observations are presented here, with a briefsummary of the redshift precision; a forthcoming paper presents the datareduction, redshift fitting, redshift confidence, and surveycompleteness. PRIMUS is the largest faint galaxy survey undertaken to

Constraining Halo Occupation Properties of X-Ray Active Galactic Nuclei Using Clustering of Chandra Sources in the Boötes Survey Region - Starikova, S.; Cool, R.; Eisenstein, D.; Forman, W.; Jones, C.; Hickox, R.; Kenter, A.; Kochanek, C.; Kravtsov, A.; Murray, S. S.; Vikhlinin, A. (The Astrophysical Journal, 2011)
We present one of the most precise measurements to date of the spatialclustering of X-ray-selected active galactic nuclei (AGNs) using asample derived from the Chandra X-ray Observatory survey in theBoötes field. The real-space two-point correlation function over aredshift interval from z = 0.17 to z ~ 3 is well described by the powerlaw, ξ(r) = (r/r 0)-γ, for comovingseparations r <~ 20 h -1 Mpc. We find γ = 1.84± 0.12 and r 0 consistent with no redshift trendwithin the sample (varying between r 0 = 5.5 ± 0.6 h-1 Mpc for langzrang = 0.37 and r 0 = 6.9± 1.0 h -1 Mpc for langzrang = 1.28).Furthermore, we are able to measure the projections of the two-pointcorrelation function both on the sky plane and in the line of sight. Weuse these measurements to show that the Chandra/Boötes AGNs arepredominantly located at the centers of dark matter halos with circularvelocity v max > 320 km s-1 or M180 > 4.1 × 1012 h -1 Msun, and tend to avoid satellite galaxies in halos of this orhigher mass. The halo occupation properties inferred from the clusteringproperties of Chandra/Boötes AGNs—the mass scale of theparent dark matter halos, the lack of significant redshift evolution ofthe clustering length, and the low satellite fraction—are broadlyconsistent with the Hopkins et al. scenario of quasar activity triggeredby mergers of similarly sized galaxies.

Baryon acoustic oscillations in the Sloan Digital Sky Survey Data Release 7 galaxy sample - Percival, Will J.; Reid, Beth A.; Eisenstein, Daniel J.; Bahcall, Neta A.; Budavari, Tamas; Frieman, Joshua A.; Fukugita, Masataka; Gunn, James E.; Ivezić, Željko; Knapp, Gillian R.; Kron, Richard G.; Loveday, Jon; et al. (Monthly Notices of the Royal Astronomical Society, 2010)
The spectroscopic Sloan Digital Sky Survey (SDSS) Data Release 7 (DR7)galaxy sample represents the final set of galaxies observed using theoriginal SDSS target selection criteria. We analyse the clustering ofgalaxies within this sample, including both the luminous red galaxy andmain samples, and also include the 2-degree Field Galaxy Redshift Surveydata. In total, this sample comprises 893319 galaxies over9100deg2. Baryon acoustic oscillations (BAO) are observed inpower spectra measured for different slices in redshift; this allows usto constrain the distance-redshift relation at multiple epochs. Weachieve a distance measure at redshift z = 0.275, ofrs(zd)/DV(0.275) = 0.1390 +/- 0.0037(2.7 per cent accuracy), where rs(zd) is thecomoving sound horizon at the baryon-drag epoch, DV(z)≡ [(1 +z)2D2Acz/H(z)]1/3,DA(z) is the angular diameter distance and H(z) is the Hubbleparameter. We find an almost independent constraint on the ratio ofdistances DV(0.35)/DV(0.2) = 1.736 +/- 0.065,which is consistent at the 1.1σ level with the best-fittingΛ cold dark matter model obtained when combining our z = 0.275distance constraint with the Wilkinson Microwave Anisotropy Probe 5-year(WMAP5) data. The offset is similar to that found in previous analysesof the SDSS DR5 sample, but the discrepancy is now of lowersignificance, a change caused by a revised error analysis and a changein the methodology adopted, as well as the addition of more data. UsingWMAP5 constraints on Ωbh2 andΩch2, and combining our BAO distancemeasurements with those from the Union supernova sample, places a tightconstraint on Ωm = 0.286 +/- 0.018 and H0 =68.2 +/- 2.2kms-1Mpc-1 that is robust to allowingΩk ≠ 0 and w ≠ -1. This result is independent ofthe behaviour of dark energy at redshifts greater than those probed bythe BAO and supernova measurements. Combining these data sets with thefull WMAP5 likelihood constraints provides tight constraints on bothΩk = -0.006 +/- 0.008 and w = -0.97 +/- 0.10 for aconstant dark energy equation of state.

Cosmological constraints from the clustering of the Sloan Digital Sky Survey DR7 luminous red galaxies - Reid, Beth A.; Percival, Will J.; Eisenstein, Daniel J.; Verde, Licia; Spergel, David N.; Skibba, Ramin A.; Bahcall, Neta A.; Budavari, Tamas; Frieman, Joshua A.; Fukugita, Masataka; Gott, J. Richard; Gunn, James E.; et al. (Monthly Notices of the Royal Astronomical Society, 2010)
We present the power spectrum of the reconstructed halo density fieldderived from a sample of luminous red galaxies (LRGs) from the SloanDigital Sky Survey (SDSS) Seventh Data Release (DR7). The halo powerspectrum has a direct connection to the underlying dark matter power fork <= 0.2hMpc-1, well into the quasi-linear regime. Thisenables us to use a factor of ~8 more modes in the cosmological analysisthan an analysis with kmax = 0.1hMpc-1, as wasadopted in the SDSS team analysis of the DR4 LRG sample. The observedhalo power spectrum for 0.02 < k < 0.2hMpc-1 is wellfitted by our model: χ2 = 39.6 for 40 degrees of freedomfor the best-fitting Λ cold dark matter (ΛCDM) model. Wefind Ωmh2(ns/0.96)1.2= 0.141+0.010-0.012 for a power-law primordialpower spectrum with spectral index ns andΩbh2 = 0.02265 fixed, consistent with cosmicmicrowave background measurements. The halo power spectrum alsoconstrains the ratio of the comoving sound horizon at the baryon-dragepoch to an effective distance to z = 0.35:rs/DV(0.35) =0.1097+0.0039-0.0042. Combining the halo powerspectrum measurement with the Wilkinson Microwave Anisotropy Probe(WMAP) 5 year results, for the flat ΛCDM model we findΩm = 0.289 +/- 0.019 and H0 = 69.4 +/-1.6kms-1Mpc-1. Allowing for massive neutrinos inΛCDM, we find eV at the 95 per cent confidence level. If weinstead consider the effective number of relativistic speciesNeff as a free parameter, we find Neff =4.8+1.8-1.7. Combining also with the Kowalski etal. supernova sample, we find Ωtot = 1.011 +/- 0.009and w = -0.99 +/- 0.11 for an open cosmology with constant dark energyequation of state w. The power spectrum and a module to calculate thelikelihoods are publicly available athttp://lambda.gsfc.nasa.gov/toolbox/lrgdr/.

The Sloan Digital Sky Survey Quasar Catalog. V. Seventh Data Release - Schneider, Donald P.; Richards, Gordon T.; Hall, Patrick B.; Strauss, Michael A.; Anderson, Scott F.; Boroson, Todd A.; Ross, Nicholas P.; Shen, Yue; Brandt, W. N.; Fan, Xiaohui; Inada, Naohisa; Jester, Sebastian; et al. (The Astronomical Journal, 2010)
We present the fifth edition of the Sloan Digital Sky Survey (SDSS)Quasar Catalog, which is based upon the SDSS Seventh Data Release. Thecatalog, which contains 105,783 spectroscopically confirmed quasars,represents the conclusion of the SDSS-I and SDSS-II quasar survey. Thecatalog consists of the SDSS objects that have luminosities larger thanMi = -22.0 (in a cosmology with H 0 = 70 kms-1 Mpc-1, Ω M = 0.3, andΩΛ = 0.7), have at least one emission line withFWHM larger than 1000 km s-1 or have interesting/complexabsorption features, are fainter than i ≈ 15.0, and have highlyreliable redshifts. The catalog covers an area of ≈9380deg2. The quasar redshifts range from 0.065 to 5.46, with amedian value of 1.49; the catalog includes 1248 quasars at redshiftsgreater than 4, of which 56 are at redshifts greater than 5. The catalogcontains 9210 quasars with i < 18; slightly over half of the entrieshave i < 19. For each object the catalog presents positions accurateto better than 0farcs1 rms per coordinate, five-band (ugriz) CCD-basedphotometry with typical accuracy of 0.03 mag, and information on themorphology and selection method. The catalog also contains radio,near-infrared, and X-ray emission properties of the quasars, whenavailable, from other large-area surveys. The calibrated digital spectracover the wavelength region 3800-9200 Å at a spectral resolutionof ~= 2000; the spectra can be retrieved from the SDSS public database

The Evolution of the Star Formation Rate of Galaxies at 0.0 <= z <= 1.2 - Rujopakarn, Wiphu; Eisenstein, Daniel J.; Rieke, George H.; Papovich, Casey; Cool, Richard J.; Moustakas, John; Jannuzi, Buell T.; Kochanek, Christopher S.; Rieke, Marcia J.; Dey, Arjun; Eisenhardt, Peter; Murray, Steve S.; et al. (The Astrophysical Journal, 2010)
We present the 24 μm rest-frame luminosity function (LF) ofstar-forming galaxies in the redshift range 0.0 <= z <= 0.6constructed from 4047 spectroscopic redshifts from the AGN and GalaxyEvolution Survey of 24 μm selected sources in the Boötes fieldof the NOAO Deep Wide-Field Survey. This sample provides the bestavailable combination of large area (9 deg2), depth, andstatistically complete spectroscopic observations, allowing us to probethe evolution of the 24 μm LF of galaxies at low and intermediateredshifts while minimizing the effects of cosmic variance. In order touse the observed 24 μm luminosity as a tracer for star formation,active galactic nuclei (AGNs) that could contribute significantly at 24μm are identified and excluded from our star-forming galaxy samplebased on their mid-IR spectral energy distributions or the detection ofX-ray emission. Optical emission line diagnostics are considered for AGNidentification, but we find that 24 μm emission from opticallyselected AGNs is usually from star-forming activity and therefore shouldnot be excluded. The evolution of the 24 μm LF of star-forminggalaxies for redshifts of z <= 0.65 is consistent with a pureluminosity evolution where the characteristic 24 μm luminosityevolves as (1 + z)3.8±0.3. We extend our evolutionarystudy to encompass 0.0 <= z <= 1.2 by combining our data with thatof the Far-Infrared Deep Extragalactic Legacy Survey. Over this entireredshift range, the evolution of the characteristic 24 μm luminosityis described by a slightly shallower power law of (1 +z)3.4±0.2. We find a local star formation rate densityof (1.09 ± 0.21) × 10-2 M sunyr-1 Mpc-3, and that it evolves as (1 +z)3.5±0.2 over 0.0 <= z <= 1.2. These estimatesare in good agreement with the rates using optical and UV fluxescorrected for the effects of intrinsic extinction in the observedsources. This agreement confirms that star formation at z <~ 1.2 isrobustly traced by 24 μm observations and that it largely occurs inobscured regions of galaxies.

A New Statistic for Analyzing Baryon Acoustic Oscillations - Xu, X.; White, M.; Padmanabhan, N.; Eisenstein, D. J.; Eckel, J.; Mehta, K.; Metchnik, M.; Pinto, P.; Seo, H.-J. (The Astrophysical Journal, 2010)
We introduce a new statistic ωell(rs ) formeasuring and analyzing large-scale structure and particularly thebaryon acoustic oscillations. ωell(rs ) is aband-filtered, configuration space statistic that is easily implementedand has advantages over the traditional power spectrum and correlationfunction estimators. Unlike these estimators,ωell(rs ) can localize most of the acousticinformation into a single dip at the acoustic scale while avoidingsensitivity to the poorly constrained large-scale power (i.e., theintegral constraint) through the use of a localized and compensatedfilter. It is also sensitive to anisotropic clustering through paircounting and does not require any binning of data. We measure the shiftin the acoustic peak due to nonlinear effects using the monopoleω0(rs ) derived from subsampled dark matter(DM) catalogs as well as from mock galaxy catalogs created via halooccupation distribution modeling. All of these are drawn from 44realizations of 10243 particle DM simulations in a 1 h-1 Gpc box at z = 1. We compare these shifts with thoseobtained from the power spectrum and conclude that the results agree. Wetherefore expect that distance measurements obtained fromω0(rs ) and P(k) will be consistent witheach other. We also show that it is possible to extract the same amountof acoustic information by fitting over a finite range using eitherω0(rs ) or P(k) derived from equal volumesurveys.

Strong Field-to-field Variation of Lyα Nebulae Populations at z ~= 2.3 - Yang, Yujin; Zabludoff, Ann; Eisenstein, Daniel; Davé, Romeel (The Astrophysical Journal, 2010)
Understanding the nature of distant Lyα nebulae, aka "blobs," andconnecting them to their present-day descendants requires constrainingtheir number density, clustering, and large-scale environment. Tomeasure these basic quantities, we conduct a deep narrowband imagingsurvey in four different fields, Chandra Deep Field South (CDFS),Chandra Deep Field North (CDFN), and two COSMOS subfields, for a totalsurvey area of 1.2 deg2. We discover 25 blobs at z = 2.3 withLyα luminosities of L Lyα= (0.7-8) ×1043 erg s-1 and isophotal areas of Aiso = 10-60 sq arcsec. The transition from compact Lyαemitters (LAEs; A iso ~ a few sq arcsec) to extendedLyα blobs (A iso > 10 sq arcsec) is continuous,suggesting a single family perhaps governed by similar emissionmechanisms. Surprisingly, most blobs (16/25) are in one survey field,the CDFS. The six brightest, largest blobs with L Lyαgsim 1.5×1043 erg s-1 and A iso> 16 sq arcsec lie only in the CDFS. These large, bright blobs have a

High-precision Predictions for the Acoustic Scale in the Nonlinear Regime - Seo, Hee-Jong; Eckel, Jonathan; Eisenstein, Daniel J.; Mehta, Kushal; Metchnik, Marc; Padmanabhan, Nikhil; Pinto, Phillip; Takahashi, Ryuichi; White, Martin; Xu, Xiaoying (The Astrophysical Journal, 2010)
We measure shifts of the acoustic scale due to nonlinear growth andredshift distortions to a high precision using a very large volume ofhigh-force-resolution simulations. We compare results from various setsof simulations that differ in their force, volume, and mass resolution.We find a consistency within 1.5σ for shift values from differentsimulations and derive shift α(z) - 1 = (0.300 ± 0.015)

Extended Lyα Nebulae at z sime 2.3: An Extremely Rare and Strongly Clustered Population? - Yang, Yujin; Zabludoff, Ann; Tremonti, Christy; Eisenstein, Daniel; Davé, Romeel (The Astrophysical Journal, 2009)
To obtain an unbiased sample of bright Lyα blobs (L_{Lyα}≳ 10^{43} erg s-1), we have undertaken a blind,wide-field, narrowband imaging survey in the National Optical AstronomyObservatory Deep Wide Field Survey Boötes field with the StewardBok 2.3 m telescope. After searching over 4.82 deg2 at z =2.3, we discover four Lyα blobs with L_{Lyα} = 1.6-5.3× 1043 erg s-1, isophotal areas of 28-57⊓⊔, and broad Lyα line profiles (Δv = 900-1250km s-1). In contrast with the extended Lyα halosassociated with high-z radio galaxies, none of our four blobs areradio-loud. The X-ray luminosities and optical spectra of these blobsare diverse. Two blobs (3 and 4) are X-ray detected with LX(2-7 keV) = 2-4 × 1044 erg s-1 and havebroad optical emission lines (C IV) characteristic of active galactic

Host Galaxies, Clustering, Eddington Ratios, and Evolution of Radio, X-Ray, and Infrared-Selected AGNs - Hickox, Ryan C.; Jones, Christine; Forman, William R.; Murray, Stephen S.; Kochanek, Christopher S.; Eisenstein, Daniel; Jannuzi, Buell T.; Dey, Arjun; Brown, Michael J. I.; Stern, Daniel; Eisenhardt, Peter R.; Gorjian, Varoujan; et al. (The Astrophysical Journal, 2009)
We explore the connection between different classes of active galacticnuclei (AGNs) and the evolution of their host galaxies, by deriving hostgalaxy properties, clustering, and Eddington ratios of AGNs selected inthe radio, X-ray, and infrared (IR) wavebands. We study a sample of 585AGNs at 0.25 < z < 0.8 using redshifts from the AGN and GalaxyEvolution Survey (AGES). We select AGNs with observations in the radioat 1.4 GHz from the Westerbork Synthesis Radio Telescope, X-rays fromthe Chandra XBoötes Survey, and mid-IR from the Spitzer IRACShallow Survey. The radio, X-ray, and IR AGN samples show only modestoverlap, indicating that to the flux limits of the survey, theyrepresent largely distinct classes of AGNs. We derive host galaxy colorsand luminosities, as well as Eddington ratios, for obscured or opticallyfaint AGNs. We also measure the two-point cross-correlation between AGNsand galaxies on scales of 0.3-10 h -1 Mpc, and derive typicaldark matter halo masses. We find that: (1) radio AGNs are mainly foundin luminous red sequence galaxies, are strongly clustered (with Mhalo ~ 3 × 1013 h -1 Msun), and have very low Eddington ratios λ lsim10-3 (2) X-ray-selected AGNs are preferentially found ingalaxies that lie in the "green valley" of color-magnitude space and areclustered similar to the typical AGES galaxies (M halo ~1013 h -1 M sun), with 10-3lsim λ lsim 1; (3) IR AGNs reside in slightly bluer, slightlyless luminous galaxies than X-ray AGNs, are weakly clustered (Mhalo lsim 1012 h -1 M sun),and have λ>10-2. We interpret these results interms of a simple model of AGN and galaxy evolution, whereby a "quasar"phase and the growth of the stellar bulge occurs when a galaxy's darkmatter halo reaches a critical mass between ~1012 and1013 M sun. After this event, star formationceases and AGN accretion shifts from radiatively efficient (optical- andIR-bright) to radiatively inefficient (optically faint, radio-bright)modes.

The Star Formation and Nuclear Accretion Histories of Normal Galaxies in the Ages Survey - Watson, Casey R.; Kochanek, Christopher S.; Forman, William R.; Hickox, Ryan C.; Jones, Christine J.; Brown, Michael J. I.; Brand, Kate; Dey, Arjun; Jannuzi, Buell T.; Kenter, Almus T.; Murray, Steve S.; Vikhlinin, Alexey; et al. (The Astrophysical Journal, 2009)
We combine IR, optical, and X-ray data from the overlapping, 9.3deg2 NOAO Deep Wide-Field Survey, AGN and Galaxy EvolutionSurvey (AGES), and XBoötes Survey to measure the X-ray evolution of6146 normal galaxies as a function of absolute optical luminosity,redshift, and spectral type over the largely unexplored redshift range0.1 lsim z lsim 0.5. Because only the closest or brightest of thegalaxies are individually detected in X-rays, we use a stacking analysisto determine the mean properties of the sample. Our results suggest thatX-ray emission from spectroscopically late-type galaxies is dominated bystar formation, while that from early-type galaxies is dominated by acombination of hot gas and active galactic nucleus (AGN) emission. Wefind that the mean star formation and supermassive black hole accretionrate densities evolve like ~(1 + z)3±1, in agreementwith the trends found for samples of bright, individually detectablestarburst galaxies and AGN. Our work also corroborates the results ofmany previous stacking analyses of faint source populations, withimproved statistics.

Mid-Infrared Galaxy Luminosity Functions from the AGN and Galaxy Evolution Survey - Dai, X.; Assef, R. J.; Kochanek, C. S.; Brodwin, M.; Brown, M. J. I.; Caldwell, N.; Cool, R. J.; Dey, A.; Eisenhardt, P.; Eisenstein, D.; Gonzalez, A. H.; Jannuzi, B. T.; et al. (The Astrophysical Journal, 2009)
We present galaxy luminosity functions at 3.6, 4.5, 5.8, and 8.0 μmmeasured by combining photometry from the IRAC Shallow Survey withredshifts from the AGN and Galaxy Evolution Survey (AGES) of the NOAODeep Wide-Field Survey Boötes field. The well defined IRAC samplescontain 3800-5800 galaxies for the 3.6-8.0 μm bands withspectroscopic redshifts and z < 0.6. We obtained relatively completeluminosity functions in the local redshift bin of z < 0.2 for allfour IRAC channels that are well fitted by Schechter functions. Afteranalyzing the samples for the whole redshift range, we found significantevolution in the luminosity functions for all four IRAC channels thatcan be fitted as an evolution in M * with redshift, ΔM* = Qz. While we measured Q = 1.2 ± 0.4 and 1.1± 0.4 in the 3.6 and 4.5 μm bands consistent with thepredictions from a passively evolving population, we obtained Q = 1.8± 1.1 in the 8.0 μm band consistent with other evolving starformation rate estimates. We compared our luminosity functions with thepredictions of semianalytical galaxy formation and found the bestagreement at 3.6 and 4.5 μm, rough agreement at 8.0 μm, and alarge mismatch at 5.8 μm. These models also predicted a comparableQ-value to our luminosity functions at 8.0 μm, but predicted smallervalues at 3.6 and 4.5 μm. We also measured the luminosity functionsseparately for early- and late-type galaxies. While the luminosityfunctions of late-type galaxies resemble those for the total population,the luminosity functions of early-type galaxies in the 3.6 and 4.5 μmbands indicate deviations from the passive evolution model, especiallyfrom the measured flat luminosity density evolution. Combining ourestimates with other measurements in the literature, we found 53

The Seventh Data Release of the Sloan Digital Sky Survey - Abazajian, Kevork N.; Adelman-McCarthy, Jennifer K.; Agüeros, Marcel A.; Allam, Sahar S.; Allende Prieto, Carlos; An, Deokkeun; Anderson, Kurt S. J.; Anderson, Scott F.; Annis, James; Bahcall, Neta A.; Bailer-Jones, C. A. L.; Barentine, J. C.; et al. (The Astrophysical Journal Supplement Series, 2009)
This paper describes the Seventh Data Release of the Sloan Digital SkySurvey (SDSS), marking the completion of the original goals of the SDSSand the end of the phase known as SDSS-II. It includes 11,663deg2 of imaging data, with most of the ~2000 deg2increment over the previous data release lying in regions of lowGalactic latitude. The catalog contains five-band photometry for 357million distinct objects. The survey also includes repeat photometry ona 120° long, 2fdg5 wide stripe along the celestial equator in theSouthern Galactic Cap, with some regions covered by as many as 90individual imaging runs. We include a co-addition of the best of thesedata, going roughly 2 mag fainter than the main survey over 250deg2. The survey has completed spectroscopy over 9380deg2 the spectroscopy is now complete over a large contiguousarea of the Northern Galactic Cap, closing the gap that was present inprevious data releases. There are over 1.6 million spectra in total,including 930,000 galaxies, 120,000 quasars, and 460,000 stars. The datarelease includes improved stellar photometry at low Galactic latitude.The astrometry has all been recalibrated with the second version of theUSNO CCD Astrograph Catalog, reducing the rms statistical errors at thebright end to 45 milliarcseconds per coordinate. We further quantify asystematic error in bright galaxy photometry due to poor skydetermination; this problem is less severe than previously reported forthe majority of galaxies. Finally, we describe a series of improvementsto the spectroscopic reductions, including better flat fielding andimproved wavelength calibration at the blue end, better processing ofobjects with extremely strong narrow emission lines, and an improveddetermination of stellar metallicities.

An Observational Determination of the Proton to Electron Mass Ratio in the Early Universe - Thompson, Rodger I.; Bechtold, Jill; Black, John H.; Eisenstein, Daniel; Fan, Xiaohui; Kennicutt, Robert C.; Martins, Carlos; Prochaska, J. Xavier; Shirley, Yancey L. (The Astrophysical Journal, 2009)
In an effort to resolve the discrepancy between two measurements of thefundamental constant μ, the proton to electron mass ratio, at earlytimes in the universe we reanalyze the same data used in the earlierstudies. Our analysis of the molecular hydrogen absorption lines inarchival Very Large Telescope/Ultraviolet and Visible EchelleSpectrometer (UVES) spectra of the damped Lyman alpha systems in thequasi-stellar objects Q0347-383 and Q0405-443 yields a combinedmeasurement of a Δμ/μ value of (-7 ± 8) ×10-6, consistent with no change in the value of μ over atime span of 11.5 Gyr. Here, we define Δμ as (μ z - μ0) where μ z is the value of μat a redshift of z and μ0 is the present-day value. Ournull result is consistent with the recent measurements of King et al.,Δμ/μ = (2.6 ± 3.0) × 10-6, andinconsistent with the positive detection of a change in μ by Reinholdet al. Both of the previous studies and this study are based on the samedata but with differing analysis methods. Improvements in the wavelengthcalibration over the UVES pipeline calibration is a key element in bothof the null results. This leads to the conclusion that the fundamentalconstant μ is unchanged to an accuracy of 10-5 over the

The Spitzer Deep, Wide-field Survey - Ashby, M. L. N.; Stern, D.; Brodwin, M.; R Griffith; Eisenhardt, P.; Kozłowski, S.; Kochanek, C. S.; Bock, J. J.; Borys, C.; Brand, K.; Brown, M. J. I.; Cool, R.; et al. (The Astrophysical Journal, 2009)
The Spitzer Deep, Wide-Field Survey (SDWFS) is a four-epoch infraredsurvey of 10 deg2 in the Boötes field of the NOAO DeepWide-Field Survey using the IRAC instrument on the Spitzer SpaceTelescope. SDWFS, a Spitzer Cycle 4 Legacy project, occupies a uniqueposition in the area-depth survey space defined by other Spitzersurveys. The four epochs that make up SDWFS permit—for the firsttime—the selection of infrared-variable and high proper motionobjects over a wide field on timescales of years. Because of its largesurvey volume, SDWFS is sensitive to galaxies out to z ~ 3 withrelatively little impact from cosmic variance for all but the richestsystems. The SDWFS data sets will thus be especially useful forcharacterizing galaxy evolution beyond z ~ 1.5. This paper explains theSDWFS observing strategy and data processing, presents the SDWFS mosaicsand source catalogs, and discusses some early scientific findings. Thepublicly released, full-depth catalogs contain 6.78, 5.23, 1.20, and0.96 × 105 distinct sources detected to the average5σ, 4''-diameter, aperture-corrected limits of 19.77, 18.83,16.50, and 15.82 Vega mag at 3.6, 4.5, 5.8, and 8.0 μm, respectively.The SDWFS number counts and color-color distribution are consistent withother, earlier Spitzer surveys. At the 6 minute integration time of the

Halo Occupation Distribution Modeling of Clustering of Luminous Red Galaxies - Zheng, Zheng; Zehavi, Idit; Eisenstein, Daniel J.; Weinberg, David H.; Jing, Y. P. (The Astrophysical Journal, 2009)
We perform halo occupation distribution (HOD) modeling to interpretsmall-scale and intermediate-scale clustering of 35,000 luminousearly-type galaxies and their cross-correlation with a reference imagingsample of normal L * galaxies in the Sloan Digital SkySurvey. The modeling results show that most of these luminous redgalaxies (LRGs) are central galaxies residing in massive halos oftypical mass M~ a few times 1013-1014 h-1 M sun, while a few percent of them have to besatellites within halos in order to produce the strong auto-correlationsexhibited on smaller scales. The mean luminosity Lc ofcentral LRGs increases with the host halo mass, with a rough scalingrelation of Lc vprop M 0.5. The halo mass requiredto host on average one satellite LRG above a luminosity threshold isfound to be about 10 times higher than that required to host a centralLRG above the same threshold. We find that in massive halos thedistribution of L * galaxies roughly follows that of the darkmatter and their mean occupation number scales with halo mass as M1.5. The HOD modeling results also allow for an intuitiveunderstanding of the scale-dependent luminosity dependence of thecross-correlation between LRGs and L * galaxies. Constraintson the LRG HOD provide tests for models of formation and evolution ofmassive galaxies, and they are also useful for cosmological parameterinvestigations. In one of the appendices, we provide LRG HOD parameterswith dependence on cosmology inferred from modeling the two-pointauto-correlation functions of LRGs.

The Sloan Digital Sky Survey Quasar Lens Search. II. Statistical Lens Sample from the Third Data Release - Inada, Naohisa; Oguri, Masamune; Becker, Robert H.; Shin, Min-Su; Richards, Gordon T.; Hennawi, Joseph F.; White, Richard L.; Pindor, Bartosz; Strauss, Michael A.; Kochanek, Christopher S.; Johnston, David E.; Gregg, Michael D.; et al. (The Astronomical Journal, 2008)
We report the first results of our systematic search for strongly lensedquasars using the spectroscopically confirmed quasars in the SloanDigital Sky Survey (SDSS). Among 46,420 quasars from the SDSS DataRelease 3 (~4188 deg2), we select a subsample of 22,683quasars that are located at redshifts between 0.6 and 2.2 and arebrighter than the Galactic extinction-corrected i-band magnitude of19.1. We identify 220 lens candidates from the quasar subsample, forwhich we conduct extensive and systematic follow-up observations inoptical and near-infrared wavebands, in order to construct a completelensed quasar sample at image separations between 1'' and 20'' and fluxratios of faint to bright lensed images larger than 10-0.5.We construct a statistical sample of 11 lensed quasars. Ten of these aregalaxy-scale lenses with small image separations (~ 1''-2'') and one isa large separation (15'') system which is produced by a massive clusterof galaxies, representing the first statistical sample of lensed quasarsincluding both galaxy- and cluster-scale lenses. The Data Release 3spectroscopic quasars contain an additional 11 lensed quasars outsidethe statistical sample.

The Sloan Digital Sky Survey Quasar Lens Search. III. Constraints on Dark Energy from the Third Data Release Quasar Lens Catalog - Oguri, Masamune; Inada, Naohisa; Strauss, Michael A.; Kochanek, Christopher S.; Richards, Gordon T.; Schneider, Donald P.; Becker, Robert H.; Fukugita, Masataka; Gregg, Michael D.; Hall, Patrick B.; Hennawi, Joseph F.; Johnston, David E.; et al. (The Astronomical Journal, 2008)
We present cosmological results from the statistics of lensed quasars inthe Sloan Digital Sky Survey (SDSS) Quasar Lens Search. By taking properaccount of the selection function, we compute the expected number ofquasars lensed by early-type galaxies and their image separationdistribution assuming a flat universe, which is then compared with sevenlenses found in the SDSS Data Release 3 to derive constraints on darkenergy under strictly controlled criteria. For a cosmological constantmodel (w = -1) we obtain ΩΛ =0.74+0.11 -0.15(stat.)+0.13-0.06(syst.). Allowing w to be a free parameter we findΩM = 0.26+0.07-0.06(stat.)+0.03 -0.05(syst.) and w =-1.1 ± 0.6(stat.)+0.3 -0.5(syst.) whencombined with the constraint from the measurement of baryon acousticoscillations in the SDSS luminous red galaxy sample. Our results are ingood agreement with earlier lensing constraints obtained using radiolenses, and provide additional confirmation of the presence of darkenergy consistent with a cosmological constant, derived independently oftype Ia supernovae.

Low-Resolution Spectral Templates for Galaxies from 0.2 to 10 μm - Assef, R. J.; Kochanek, C. S.; Brodwin, M.; Brown, M. J. I.; Caldwell, N.; Cool, R. J.; Eisenhardt, P.; Eisenstein, D.; Gonzalez, A. H.; Jannuzi, B. T.; Jones, C.; McKenzie, E.; et al. (The Astrophysical Journal, 2008)
We built an optimal basis of low-resolution templates for galaxies overthe wavelength range from 0.2 to 10 μm using a variant of thealgorithm presented by Budavari and coworkers. We derived them using 11bands of photometry from the NDWFS, FLAMEX, zBoötes, and IRACShallow surveys for 16,033 galaxies in the NDWFS Boötes field withspectroscopic redshifts measured by the AGN and Galaxy Evolution Survey.We also developed algorithms to accurately determine photometricredshifts, K-corrections, and bolometric luminosities using thesetemplates. Our photometric redshifts have an accuracy of

Large-Scale Anisotropic Correlation Function of SDSS Luminous Red Galaxies - Okumura, Teppei; Matsubara, Takahiko; Eisenstein, Daniel J.; Kayo, Issha; Hikage, Chiaki; Szalay, Alexander S.; Schneider, Donald P. (The Astrophysical Journal, 2008)
We study the large-scale anisotropic two-point correlation functionusing 46,760 luminous red galaxies at redshifts 0.16-0.47 from the SloanDigital Sky Survey. We measure the correlation function as a function ofseparations parallel and perpendicular to the line of sight in order totake account of anisotropy of the large-scale structure in redshiftspace. We find a slight signal of baryonic features in the anisotropiccorrelation function, i.e., a ``baryon ridge'' corresponding to a baryonacoustic peak in the spherically averaged correlation function, whichhas already been reported using the same sample. The baryon ridge hasprimarily a spherical structure with a known radius in comovingcoordinates. It enables us to divide the redshift distortion effectsinto dynamical and geometrical components and provides furtherconstraints on cosmological parameters, including the dark energyequation-of-state. With an assumption of a flat Λ cosmology, wefind the best-fit values ofΩm=0.218+0.047-0.037 and

On the Stellar Populations in Faint Red Galaxies in the Hubble Ultra Deep Field - Stutz, Amelia M.; Papovich, Casey; Eisenstein, Daniel J. (The Astrophysical Journal, 2008)
We study the nature of faint red-selected galaxies at z~2-3 using theHubble Ultra Deep Field (HUDF) and Spitzer Infrared Array Camera (IRAC)photometry. Given the magnitude limit of the HST data, we detectcandidate galaxies to HAB<26 mag, probing lower luminosity(lower mass) galaxies at these redshifts. We identify 32 galaxiessatisfying the (J110-H160)AB>1.0 magcolor selection, 16 of which have unblended [3.6 μm] and [4.5 μm]photometry from Spitzer. Using this multiwavelength data set, we derivephotometric redshifts, masses, and stellar population parameters forthese objects. We find that the selected objects span a diverse range ofproperties over a large range of redshifts, 1<~z<~3.5. Asubstantial fraction (11/32) of the(J110-H160)AB>1.0 mag populationappear to be lower redshift (z<~2.5), heavily obscured dusty galaxiesor edge-on spiral galaxies, while others (12/32) appear to be galaxiesat 2<~z<~3.5 whose light at rest-frame optical wavelengths isdominated by evolved stellar populations. We argue that longerwavelength data (>~1 μm, rest frame) are essential forinterpreting the properties of the stellar populations in red-selectedgalaxies at these redshifts. Interestingly, by including Spitzer data,many candidates for galaxies dominated by evolved stellar populationsare rejected, and for only a subset of the sample (6/16) do the datafavor this interpretation. These objects have a surface density of ~1arcmin-2. We place an upper limit on the space density ofcandidate massive evolved galaxies with 2.5AB160<=26 mag ofn=6.6+2.0-3.0×10-4Mpc-3, with a corresponding upper limit on the stellar massdensity ofρ*=5.6+4.4-2.8×107Msolar Mpc-3. The z>2.5 objects that aredominated by evolved stellar populations have a space density at mostone-third that of z~0 red early-type galaxies. Therefore, at leasttwo-thirds of present-day early-type galaxies assemble or evolve intotheir current configuration at redshifts below 2.5. We find a dearth ofcandidates for low-mass (<~2×1010 Msolar)galaxies at 1.5

The Sixth Data Release of the Sloan Digital Sky Survey - Adelman-McCarthy, Jennifer K.; Agüeros, Marcel A.; Allam, Sahar S.; Allende Prieto, Carlos; Anderson, Kurt S. J.; Anderson, Scott F.; Annis, James; Bahcall, Neta A.; Bailer-Jones, C. A. L.; Baldry, Ivan K.; Barentine, J. C.; Bassett, Bruce A.; et al. (The Astrophysical Journal Supplement Series, 2008)
This paper describes the Sixth Data Release of the Sloan Digital SkySurvey. With this data release, the imaging of the northern Galactic capis now complete. The survey contains images and parameters of roughly287 million objects over 9583 deg2, including scans over alarge range of Galactic latitudes and longitudes. The survey alsoincludes 1.27 million spectra of stars, galaxies, quasars, and blank sky(for sky subtraction) selected over 7425 deg2 . This releaseincludes much more stellar spectroscopy than was available in previousdata releases and also includes detailed estimates of stellartemperatures, gravities, and metallicities. The results of improvedphotometric calibration are now available, with uncertainties of roughly

A Cryogenic Liquid-Mirror Telescope on the Moon to Study the Early Universe - Angel, Roger; Worden, Simon P.; Borra, Ermanno F.; Eisenstein, Daniel J.; Foing, Bernard; Hickson, Paul; Josset, Jean-Luc; Ma, Ki Bui; Seddiki, Omar; Sivanandam, Suresh; Thibault, Simon; van Susante, Paul (The Astrophysical Journal, 2008)
We have studied the feasibility and scientific potential of zenithobserving liquid-mirror telescopes having 20-100 m diameters located onthe Moon. They would carry out deep infrared surveys to study thedistant universe and follow up discoveries made with the 6 m James WebbSpace Telescope (JWST), with more detailed images and spectroscopicstudies. They could detect objects 100 times fainter than JWST,observing the first high-redshift stars in the early universe and theirassembly into galaxies. We explored the scientific opportunities, keytechnologies, and optimum location of such telescopes. We havedemonstrated critical technologies. For example, the primary mirrorwould necessitate a high-reflectivity liquid that does not evaporate inthe lunar vacuum and remains liquid at less than 100 K. We have made acrucial demonstration by successfully coating an ionic liquid that hasnegligible vapor pressure. We also successfully experimented with aliquid mirror spinning on a superconducting bearing, as will be neededfor the cryogenic, vacuum environment of the telescope. We haveinvestigated issues related to lunar locations, concluding thatlocations within a few kilometers of a pole are ideal for deep sky coverand long integration times. We have located ridges and crater rimswithin 0.5° of the north pole that are illuminated for at least somesun angles during lunar winter, providing power and temperature control.We also have identified potential problems, like lunar dust. Issuesraised by our preliminary study demand additional in-depth analyses.These issues must be fully examined as part of a scientific debate thatwe hope to start with the present article.

Observing dark energy - Eisenstein, Daniel J. (Classical and Quantum Gravity, 2008)
I review the observational evidence for dark energy, arguing that thelarge-scale structure observed at low redshift and in the cosmicmicrowave background offers a strong corroboration of the supernova Iaresults. The angular scale of the acoustic oscillations in the cosmicmicrowave background strongly support a nearly flat universe, while manyarguments from low-redshift cosmology support a matter density around

Passive Evolution of Galaxy Clustering - Seo, Hee-Jong; Eisenstein, Daniel J.; Zehavi, Idit (The Astrophysical Journal, 2008)
We present a numerical study of the evolution of galaxy clustering whengalaxies flow passively from high redshift, respecting the continuityequation throughout. While passive flow is a special case of galaxyevolution, it allows a well-defined study of galaxy ancestry and servesas an interesting limit to be compared to nonpassive cases. We usedissipationless N-body simulations, assign galaxies to massive halos atz=1 and 2 using various halo occupation distribution (HOD) models, andtrace these galaxy particles to lower redshift while conserving theirnumber. We find that passive flow results in an asymptotic convergenceat low redshift in the HOD and in galaxy clustering on scales above ~3h-1 Mpc for a wide range of initial HODs. As galaxies becomeless biased with respect to mass asymptotically with time, the HODparameters evolve such that M1/Mmin decreaseswhile α converges toward unity, whereg(M)>=exp(-Mmin/M)[1+(M/M1)α].The satellite populations converge toward the Poisson distribution atlow redshift. The convergence is robust for different number densitiesand is enhanced when galaxies evolve from higher redshift. We compareour results with the observed luminous red galaxy (LRG) sample from SDSSthat has the same number density. We claim that if LRGs have experienceda strict passive flow, their g(M)> should be close toa power law with an index of unity in halo mass. Discrepancies could bedue to dry galaxy merging or new members arising between the initial andthe final redshifts. The spatial distribution of passively flowinggalaxies within halos appears on average more concentrated than the halomass profile at low redshift. The evolution of bias for passivelyflowing galaxies is consistent with linear bias evolution onquasi-linear as well as large scales.

A molecular probe of dark energy - Thompson, Rodger I.; Bechtold, Jill; Eisenstein, Daniel; Fan, Xiaohui; Arnett, David; Martins, Carlos; Kennicutt, Robert; Black, John (Advances in Space Research, 2008)
Many theoretical models of dark energy invoke rolling scaler fieldswhich in turn predict time varying values of the fundamental constants.Establishing the value of the fundamental constants at various times inthe universe can probe and test the various dark energy theories. One ofthe constants that is predicted to vary is the ratio of the electron toproton mass μ. It was established early on that molecular spectra aresensitive to the value of μ and can be used as probes of that value.This article describes the use of the spectrum of molecular hydrogen inhigh redshift Damped Lyman Alpha systems (DLAs) as a sensitive probe ofthe time evolution of μ.

Luminosity Function Constraints on the Evolution of Massive Red Galaxies since z ~ 0.9 - Cool, Richard J.; Eisenstein, Daniel J.; Fan, Xiaohui; Fukugita, Masataka; Jiang, Linhua; Maraston, Claudia; Meiksin, Avery; Schneider, Donald P.; Wake, David A. (The Astrophysical Journal, 2008)
We measure the evolution of the luminous red galaxy (LRG) luminosityfunction in the redshift range 0.12, minimizing the impact oflarge-scale structure on our results. We find that the LRG populationhas evolved little beyond the passive fading of its stellar populationssince z~0.9. Based on our luminosity function measurements and assuminga nonevolving Salpeter stellar initial mass function, we find that themost massive (L>3L*) red galaxies have grown by less than

Nonlinear Structure Formation and the Acoustic Scale - Seo, Hee-Jong; Siegel, Ethan R.; Eisenstein, Daniel J.; White, Martin (The Astrophysical Journal, 2008)
We present high signal-to-noise ratio measurements of the acoustic scalein the presence of nonlinear growth and redshift distortions using 320h-3 Gpc3 of cosmological particle-meshsimulations. Using simple fitting methods, we obtain robust measurementsof the acoustic scale with scatter close to that predicted by the Fishermatrix. We detect and quantify the shift in the acoustic scale byanalyzing the power spectrum: we detect at greater than 5 σ adecrease in the acoustic scale in the real-space matter power spectrum

Towards a pure ZZ Ceti instability strip - Castanheira, B. G.; Kepler, S. O.; Costa, A. F. M.; Giovannini, O.; Robinson, E. L.; Winget, D. E.; Kleinman, S. J.; Nitta, A.; Eisenstein, D.; Koester, D.; Santos, M. G. (Astronomy and Astrophysics, 2007)
Context: We have observed again two stars inside the ZZ Ceti instabilitystrip that were previously classified as not-observed-to-vary (NOV) byMukadam et al. (2004) and found them to be low-amplitude variables. Someevidence points to a pure ZZ Ceti instability strip; other evidencecontests it. Aims: The two stars previously classified as NOVhave Sloan Digital Sky Survey (SDSS) spectroscopic effectivetemperatures that place them inside the ZZ Ceti instability strip, andthey were "contaminating" the strip as constant stars, which couldindicate that the instability strip was no longer a simple evolutionarystage. A pure instability strip indicates that pulsation is a normalphase which all DAs must go through. Methods: We used effectivetemperatures derived from SDSS optical spectra by comparing them withmodel atmospheres to look for pulsators through time-resolved photometryand stars previously classified as NOV. Results: Our new resultsindicate, but do not prove, a pure instability strip, because there arestill other NOV stars that need to be observed again. Additionally, wehave discovered five other ZZ Ceti stars based on their effectivetemperatures.Partially based on observations at Observatório do Pico dosDias/LNA; the Southern Astrophysical Research telescope, a collaborationbetween CNPq-Brazil, NOAO, UNC, and MSU; and McDonald Observatory of TheUniversity of Texas at Austin.

MegaZ-LRG: a photometric redshift catalogue of one million SDSS luminous red galaxies - Collister, Adrian; Lahav, Ofer; Blake, Chris; Cannon, Russell; Croom, Scott; Drinkwater, Michael; Edge, Alastair; Eisenstein, Daniel; Loveday, Jon; Nichol, Robert; Pimbblet, Kevin; de Propris, Roberto; et al. (Monthly Notices of the Royal Astronomical Society, 2007)
We describe the construction of MegaZ-LRG, a photometric redshiftcatalogue of over one million luminous red galaxies (LRGs) in theredshift range 0.4 < z < 0.7 with limiting magnitude i < 20.The catalogue is selected from the imaging data of the Sloan Digital SkySurvey (SDSS) Data Release 4. The 2dF-SDSS LRG and Quasar (2SLAQ)spectroscopic redshift catalogue of 13000 intermediate-redshift LRGsprovides a photometric redshift training set, allowing use of ANNz, aneural network-based photometric-redshift estimator. The rms photometricredshift accuracy obtained for an evaluation set selected from the 2SLAQsample is σz = 0.049 averaged over all galaxies, andσz = 0.040 for a brighter subsample (i < 19.0). Thecatalogue is expected to contain ~5 per cent stellar contamination. TheANNz code is used to compute a refined star/galaxy probability based ona range of photometric parameters; this allows the contaminationfraction to be reduced to 2 per cent with negligible loss of genuinegalaxies. The MegaZ-LRG catalogue is publicly available on the WorldWide Web from http://www.2slaq.info.

Measuring the Matter Density Using Baryon Oscillations in the SDSS - Percival, Will J.; Nichol, Robert C.; Eisenstein, Daniel J.; Weinberg, David H.; Fukugita, Masataka; Pope, Adrian C.; Schneider, Donald P.; Szalay, Alex S.; Vogeley, Michael S.; Zehavi, Idit; Bahcall, Neta A.; Brinkmann, Jon; et al. (The Astrophysical Journal, 2007)
We measure the cosmological matter density by observing the positions ofbaryon acoustic oscillations in the clustering of galaxies in the SloanDigital Sky Survey (SDSS). We jointly analyze the main galaxies and LRGsin the SDSS DR5 sample, using over half a million galaxies in total. The

The Shape of the Sloan Digital Sky Survey Data Release 5 Galaxy Power Spectrum - Percival, Will J.; Nichol, Robert C.; Eisenstein, Daniel J.; Frieman, Joshua A.; Fukugita, Masataka; Loveday, Jon; Pope, Adrian C.; Schneider, Donald P.; Szalay, Alex S.; Tegmark, Max; Vogeley, Michael S.; Weinberg, David H.; et al. (The Astrophysical Journal, 2007)
We present a Fourier analysis of the clustering of galaxies in thecombined main galaxy and LRG SDSS DR5 sample. The aim of our analysis isto consider how well we can measure the cosmological matter densityusing the signature of the horizon at matter-radiation equality embeddedin the large-scale power spectrum. The new data constrain the powerspectrum on scales 100-600 h-1 Mpc with significantly higherprecision than previous analyses of just the SDSS main galaxies, due toour larger sample and the inclusion of the LRGs. This improvement meansthat we can now reveal a discrepancy between the shape of the measuredpower and linear CDM models on scales 0.01 hMpc-1-1, with linear model fitsfavoring a lower matter density (ΩM=0.22+/-0.04) onscales 0.01 h Mpc-1-1 and ahigher matter density (ΩM=0.32+/-0.01) when smallerscales are included, assuming a flat ΛCDM model with h=0.73 andns=0.96. This discrepancy could be explained byscale-dependent bias, and by analyzing subsamples of galaxies, we findthat the ratio of small-scale to large-scale power increases with galaxyluminosity, so all of the SDSS galaxies cannot trace the same powerspectrum shape over 0.01 h Mpc-1-1. However, the data are insufficient to clearly show aluminosity-dependent change in the largest scale at which a significantincrease in clustering is observed, although they do not rule out suchan effect. Significant scale-dependent galaxy bias on large scales,which changes with the r-band luminosity of the galaxies, couldpotentially explain differences in our ΩM estimates anddifferences previously observed between 2dFGRS and SDSS power spectraand the resulting parameter constraints.

Constraints on the Cosmic Near-Infrared Background Excess from NICMOS Deep Field Observations - Thompson, Rodger I.; Eisenstein, Daniel; Fan, Xiaohui; Rieke, Marcia; Kennicutt, Robert C. (The Astrophysical Journal, 2007)
NICMOS observations of the resolved object fluxes in the Hubble DeepField-North and the Hubble Ultra Deep Field are significantly below thefluxes attributed to a 1.4-1.8 μm near-infrared background excess(NIRBE) from previous low spatial resolution NIRS measurements. Testsplacing sources in the NICMOS image with fluxes sufficient to accountfor the NIRBE indicate that the NIRBE flux must be either flat on scalesgreater than 100" or clumped on scales of several arcminutes to avoiddetection in the NICMOS image. A fluctuation analysis of the new NICMOSdata shows a fluctuation spectrum consistent with that found at the samewavelength in deep 2MASS calibration images. The fluctuation analysisshows that the majority of the fluctuation power comes from resolvedgalaxies at redshifts of 1.5 and less and that the fluctuations observedin the earlier deep 2MASS observations can be completely accounted forwith normal low-redshift galaxies. Neither the NICMOS direct fluxmeasurements nor the fluctuation analysis require an additionalcomponent of near-infrared flux other than the flux from normal resolvedgalaxies in the redshift range between 0 and 7. The residualfluctuations in the angular range between 1" and 10" is 1-2 nWm-2 sr-1, which is at or above several predictionsof fluctuations from high redshift Population III objects, butinconsistent with attributing the entire NIRBE to high-redshiftgalaxies.

New Hubble Space Telescope Discoveries of Type Ia Supernovae at z >= 1: Narrowing Constraints on the Early Behavior of Dark Energy - Riess, Adam G.; Strolger, Louis-Gregory; Casertano, Stefano; Ferguson, Henry C.; Mobasher, Bahram; Gold, Ben; Challis, Peter J.; Filippenko, Alexei V.; Jha, Saurabh; Li, Weidong; Tonry, John; Foley, Ryan; et al. (The Astrophysical Journal, 2007)
We have discovered 21 new Type Ia supernovae (SNe Ia) with the HubbleSpace Telescope (HST) and have used them to trace the history of cosmicexpansion over the last 10 billion yr. These objects, which include 13spectroscopically confirmed SNe Ia at z>=1, were discovered during 14epochs of reimaging of the GOODS fields North and South over 2 yr withthe Advanced Camera for Surveys on HST. Together with a recalibrationof our previous HST-discovered SNe Ia, the full sample of 23 SNe Ia atz>=1 provides the highest redshift sample known. Combining these datawith previous SN Ia data sets, we measured H(z) at discrete,

A robust estimator of the small-scale galaxy correlation function - Padmanabhan, Nikhil; White, Martin; Eisenstein, Daniel J. (Monthly Notices of the Royal Astronomical Society, 2007)
We present a new estimator, ω, of the small-scale galaxycorrelation function that is robust against the effects ofredshift-space distortions and large-scale structures. The estimator isa weighted integral of the redshift space or angular correlationfunction and is a convolution of the real-space correlation functionwith a localized filter. This allows a direct comparison with theory,without modelling redshift-space distortions and the large-scalecorrelation function. This has a number of advantages over the moretraditional wp estimator, including (i) an insensitivity tolarge-scale structures and the details of the truncation of theline-of-sight integral, (ii) a well-localized kernel in ξ(r) and(iii) being unbinned. We discuss how this estimator would be used inpractice, applying it to a sample of mock galaxies selected from theMillennium simulation.

Deposition of metal films on an ionic liquid as a basis for a lunar telescope - Borra, Ermanno F.; Seddiki, Omar; Angel, Roger; Eisenstein, Daniel; Hickson, Paul; Seddon, Kenneth R.; Worden, Simon P. (Nature, 2007)
An optical/infrared telescope of 20-100m aperture located on the Moonwould be able to observe objects 100 to 1,000 times fainter than theproposed next generation of space telescopes. The infrared region of thespectrum is particularly important for observations of objects atredshifts z>7. The apparent simplicity and low mass of a liquidmirror telescope, compared with a traditional pointable glass mirror,suggest that the concept should be considered further. A previouslyproposed liquid mirror telescope, based upon a spinning liquid metallicalloy, is not appropriate for infrared applications, which will requirea liquid below 130K. Here we report the successful coating of an ionicliquid with silver. The surface is smooth and the silver coating isstable on a timescale of months. The underlying ionic liquid does notevaporate in a vacuum and remains liquid down to a temperature of 175K.Given that there are ~106 simple and ~1018 ternaryionic liquids, it should be possible to synthesize liquids with evenlower melting temperatures.

The clustering of luminous red galaxies in the Sloan Digital Sky Survey imaging data - Padmanabhan, Nikhil; Schlegel, David J.; Seljak, Uroš; Makarov, Alexey; Bahcall, Neta A.; Blanton, Michael R.; Brinkmann, Jonathan; Eisenstein, Daniel J.; Finkbeiner, Douglas P.; Gunn, James E.; Hogg, David W.; Ivezić, Željko; et al. (Monthly Notices of the Royal Astronomical Society, 2007)
We present the 3D real-space clustering power spectrum of a sample of~600000 luminous red galaxies measured by the Sloan Digital Sky Survey,using photometric redshifts. These galaxies are old, elliptical systemswith strong 4000-Å breaks, and have accurate photometric redshiftswith an average error of Δz = 0.03. This sample of galaxies rangesfrom redshift z = 0.2 to 0.6 over 3528 deg2 of the sky,probing a volume of 1.5h-3Gpc3, making it thelargest volume ever used for galaxy clustering measurements. We measurethe angular clustering power spectrum in eight redshift slices and usewell-calibrated redshift distributions to combine these into ahigh-precision 3D real-space power spectrum from k = 0.005 to k =1hMpc-1. We detect power on gigaparsec scales, beyond theturnover in the matter power spectrum, at a ~2σ significance for k< 0.01hMpc-1, increasing to 5.5σ for k <0.02hMpc-1. This detection of power is on scalessignificantly larger than those accessible to current spectroscopicredshift surveys. We also find evidence for baryonic oscillations, bothin the power spectrum, as well as in fits to the baryon density, at a2.5 σ confidence level. The large volume and resulting smallstatistical errors on the power spectrum allow us to constrain both theamplitude and the scale dependence of the galaxy bias in cosmologicalfits. The statistical power of these data to constrain cosmology is ~1.7times better than previous clustering analyses. Varying the matterdensity and baryon fraction, we find ΩM = 0.30 +/-0.03, and Ωb/ΩM = 0.18 +/- 0.04, for afixed Hubble constant of 70kms-1Mpc-1 and ascale-invariant spectrum of initial perturbations. The detection ofbaryonic oscillations also allows us to measure the comoving distance toz = 0.5; we find a best-fitting distance of 1.73 +/- 0.12Gpc,corresponding to a 6.5 per cent error on the distance. These resultsdemonstrate the ability to make precise clustering measurements withphotometric surveys.

On the Robustness of the Acoustic Scale in the Low-Redshift Clustering of Matter - Eisenstein, Daniel J.; Seo, Hee-Jong; White, Martin (The Astrophysical Journal, 2007)
We discuss the effects of nonlinear structure formation on the signatureof acoustic oscillations in the late-time galaxy distribution. We arguethat the dominant nonlinear effect is the differential motion of pairsof tracers separated by 150 Mpc. These motions are driven by bulk flowsand cluster formation and are much smaller than the acoustic scaleitself. We present a model for the nonlinear evolution based on thedistribution of pairwise Lagrangian displacements that provides aquantitative model for the degradation of the acoustic signature, evenfor biased tracers in redshift space. The Lagrangian displacementdistribution can be calibrated with a significantly smaller set ofsimulations than would be needed to construct a precise power spectrum.By connecting the acoustic signature in the Fourier basis with that inthe configuration basis, we show that the acoustic signature is morerobust than the usual Fourier-space intuition would suggest, because thebeat frequency between the peaks and troughs of the acousticoscillations is a very small wavenumber that is well inside the linearregime. We argue that any possible shift of the acoustic scale is

The three-point correlation function of luminous red galaxies in the Sloan Digital Sky Survey - Kulkarni, Gauri V.; Nichol, Robert C.; Sheth, Ravi K.; Seo, Hee-Jong; Eisenstein, Daniel J.; Gray, Alexander (Monthly Notices of the Royal Astronomical Society, 2007)
We present measurements of the redshift-space three-point correlationfunction of 50967 luminous red galaxies (LRGs) from Data Release 3 (DR3)of the Sloan Digital Sky Survey (SDSS). We have studied the shapedependence of the reduced three-point correlation function(Qz(s, q, θ)) on three different scales, s = 4, 7 and10h-1Mpc, and over the range of 1 < q < 3 and 0°< θ < 180°. On small scales (s = 4h-1Mpc),Qz is nearly constant, with little change as a function of qand θ. However, there is evidence for a shallow U-shapedbehaviour (with θ) which is expected from theoretical modellingof Qz(s, q, θ). On larger scales (s = 7 and10h-1Mpc), the U-shaped anisotropy in Qz (withθ) is more clearly detected. We compare this shape dependence inQz(s, q, θ) with that seen in mock galaxy catalogueswhich were generated by populating the dark matter haloes in largeN-body simulations with mock galaxies using various halo occupationdistributions (HOD). We find that the combination of the observed numberdensity of LRGs, the (redshift-space) two-point correlation function andQz(s, q, θ) provides a strong constraint on theallowed HOD parameters (Mmin, M1,α) andbreaks key degeneracies between these parameters. For example, ourobserved Qz(s, q, θ) disfavours mock catalogues thatoverpopulate massive dark matter haloes with many LRG satellites. Wealso estimate the linear bias of LRGs to be b = 1.87 +/- 0.07 inexcellent agreement with other measurements.

Improving Cosmological Distance Measurements by Reconstruction of the Baryon Acoustic Peak - Eisenstein, Daniel J.; Seo, Hee-Jong; Sirko, Edwin; Spergel, David N. (The Astrophysical Journal, 2007)
The baryon acoustic oscillations are a promising route to the precisionmeasure of the cosmological distance scale and hence the measurement ofthe time evolution of dark energy. We show that the nonlineardegradation of the acoustic signature in the correlations oflow-redshift galaxies is a correctable process. By suitablereconstruction of the linear density field, one can sharpen the acousticpeak in the correlation function or, equivalently, restore the higherharmonics of the oscillations in the power spectrum. With this, one canachieve better measurements of the acoustic scale for a given surveyvolume. Reconstruction is particularly effective at low redshift, wherethe nonlinearities are worse but where the dark energy density ishighest. At z=0.3, we find that one can reduce the sample variance errorbar on the acoustic scale by at least a factor of 2 and in principle bynearly a factor of 4. We discuss the significant implications ourresults have for the design of galaxy surveys aimed at measuring thedistance scale through the acoustic peak.

The Local Galaxy 8 μm Luminosity Function - Huang, J.-S.; Ashby, M. L. N.; Barmby, P.; Brodwin, M.; Brown, M. J. I.; Caldwell, N.; Cool, R. J.; Eisenhardt, P.; Eisenstein, D.; Fazio, G. G.; Le Floc'h, E.; Green, P.; et al. (The Astrophysical Journal, 2007)
A Spitzer Space Telescope survey in the NOAO Deep Wide Field inBoötes provides a complete, 8 μm-selected sample of galaxies toa limiting (Vega) magnitude of 13.5. In the 6.88 deg2 field

Improved Forecasts for the Baryon Acoustic Oscillations and Cosmological Distance Scale - Seo, Hee-Jong; Eisenstein, Daniel J. (The Astrophysical Journal, 2007)
We present the cosmological distance errors achievable using thebaryonic acoustic oscillations as a standard ruler. We begin from aFisher matrix formalism that is upgraded from earlier Seo and Eisensteinwork. We isolate the information from the baryonic peaks by excludingdistance information from other less robust sources. Meanwhile, weaccommodate the Lagrangian displacement distribution into the Fishermatrix calculation to reflect the gradual loss of information in scaleand in time due to nonlinear growth, nonlinear bias, and nonlinearredshift distortions. We then show that we can contract themultidimensional Fisher matrix calculations into a two-dimensional oreven one-dimensional formalism with physically motivated approximations.We present the resulting fitting formula for the cosmological distanceerrors from galaxy redshift surveys as a function of survey parametersand nonlinearity, which saves us going through the 12 dimensional Fishermatrix calculations. Finally, we show excellent agreement between thedistance error estimates from the revised Fisher matrix and theprecision on the distance scale recovered from N-body simulations.

Evidence for a z < 8 Origin of the Source-subtracted Near-Infrared Background - Thompson, Rodger I.; Eisenstein, Daniel; Fan, Xiaohui; Rieke, Marcia; Kennicutt, Robert C. (The Astrophysical Journal, 2007)
This paper extends our previous fluctuation analysis of thenear-infrared background at 1.6 μm to the 1.1 μm (F110W) image ofthe Hubble Ultra Deep Field. When all detectable sources are removed,the ratio of fluctuation power in the two images is consistent with theratio expected for faint, z<8, sources, and is inconsistent with theexpected ratio for galaxies with z>8. We also use numericallyredshifted model galaxy spectral energy distributions for 50 and 10 Myrold galaxies to predict the expected fluctuation power at 3.6 and 4.5μm to compare with recent Spitzer observations. The predictedfluctuation power for galaxies at z=0-12 matches the observed Spitzerfluctuation power, while the predicted power for z>13 galaxies ismuch higher than the observed values. As was found in the 1.6 μm(F160W) analysis, the fluctuation power in the source-subtracted F110Wimage is 2 orders of magnitude below the power in the image with allsources present. This leads to the conclusion that the 0.8-1.8 μmnear-infrared background is due to resolved galaxies in the redshiftrange z<8, with the majority of power in the redshift range of0.5-1.5.

NICMOS measurements of the near-infrared background - Thompson, R.; Eisenstein, D.; Fan, X.; Rieke, M.; Kennicutt, R. (Nuovo Cimento B Serie, 2007)
We present preliminary results of an ESO-VLT large programme (AMAZE)aimed at determining the evolution of the mass-metallicity relation atz~3 by means of deep near-IR spectroscopy. Gas metallicities and stellarmasses are measured for an initial sample of nine star forming galaxiesat z~3.3. When compared with previous surveys, the mass-metallicityrelation inferred at z~3.3 shows an evolution significantly strongerthan observed at lower redshifts. There are also some indications thatthe metallicity evolution of low mass galaxies is stronger relative tohigh mass systems, an effect which can be considered as the chemicalversion of the galaxy downsizing. The mass-metallicity relation observedat z~3.3 is difficult to reconcile with the predictions of somehierarchical evolutionary models. We shortly discuss the possibleimplications of such discrepancies.

Dark energy and curvature from a future baryonic acoustic oscillation survey using the Lyman-α forest - McDonald, Patrick; Eisenstein, Daniel J. (Physical Review D, 2007)
We explore the requirements for a Lyman-α forest survey designedto measure the angular diameter distance and Hubble parameter at2≲z≲4 using the standard ruler provided by baryonic acousticoscillations (BAO). The goal would be to obtain a high enough density ofsources to probe the three-dimensional density field on the scale of theBAO feature. A percent-level measurement in this redshift range canalmost double the Dark Energy Task Force figure of merit, relative tothe case with only a similar precision measurement at z˜1, if theUniverse is not assumed to be flat. This improvement is greater than theone obtained by doubling the size of the z˜1 survey, with Planckand a weak Sloan Digital Sky Survey-like z=0.3 BAO measurement assumedin each case. Galaxy BAO surveys at z˜1 may be able to make aneffective Lyα forest measurement simultaneously at minimal addedcost, because the required number density of quasars is relativelysmall. We discuss the constraining power as a function of area,magnitude limit (density of quasars), resolution, and signal-to-noise ofthe spectra. For example, a survey covering 2000 sq. deg. and achievingS/N=1.8 per Å at g=23 (˜40quasars per sq. deg.) with anR≳250 spectrograph is sufficient to measure both the radial and

The Fifth Data Release of the Sloan Digital Sky Survey - Adelman-McCarthy, Jennifer K.; Agüeros, Marcel A.; Allam, Sahar S.; Anderson, Kurt S. J.; Anderson, Scott F.; Annis, James; Bahcall, Neta A.; Bailer-Jones, Coryn A. L.; Baldry, Ivan K.; Barentine, J. C.; Beers, Timothy C.; Belokurov, V.; et al. (The Astrophysical Journal Supplement Series, 2007)
This paper describes the Fifth Data Release (DR5) of the Sloan DigitalSky Survey (SDSS). DR5 includes all survey quality data taken through2005 June and represents the completion of the SDSS-I project (whosesuccessor, SDSS-II, will continue through mid-2008). It includesfive-band photometric data for 217 million objects selected over 8000deg2 and 1,048,960 spectra of galaxies, quasars, and starsselected from 5713 deg2 of that imaging data. These numbers

Radio galaxies in the 2SLAQ Luminous Red Galaxy Survey - I. The evolution of low-power radio galaxies to z ~ 0.7 - Sadler, Elaine M.; Cannon, Russell D.; Mauch, Tom; Hancock, Paul J.; Wake, David A.; Ross, Nic; Croom, Scott M.; Drinkwater, Michael J.; Edge, Alastair C.; Eisenstein, Daniel; Hopkins, Andrew M.; Johnston, Helen M.; et al. (Monthly Notices of the Royal Astronomical Society, 2007)
We have combined optical data from the 2dF-SDSS (Sloan Digital SkySurvey) LRG (Luminous Red Galaxy) and QSO (quasi-stellar object) (2SLAQ)redshift survey with radio measurements from the 1.4GHz VLA (Very LargeArray) FIRST (Faint Images of the Radio Sky at Twenty-cm) and NVSS (NRAOVLA Sky Survey) surveys to identify a volume-limited sample of 391 radiogalaxies at redshift 0.4 < z < 0.7. By determining an accurateradio luminosity function for luminous early-type galaxies in thisredshift range, we can investigate the cosmic evolution of theradio-galaxy population over a wide range in radio luminosity.The low-power radio galaxies in our LRG sample (those with 1.4GHz radioluminosities in the range 1024 to1025WHz-1, corresponding to Fanaroff-Riley I (FRI)radio galaxies in the local Universe) undergo significant cosmicevolution over the redshift range 0 < z < 0.7, consistent withpure luminosity evolution of the form (1 + z)k, where k = 2.0+/- 0.3. Our results appear to rule out (at the 6-7σ level) modelsin which low-power radio galaxies undergo no cosmic evolution. The mostpowerful radio galaxies in our sample (with radio luminosities above1026WHz-1) may undergo more rapid evolution overthe same redshift range.The evolution seen in the low-power radio-galaxy population implies thatthe total energy input into massive early-type galaxies from activegalactic nucleus (AGN) heating increases with redshift, and was at least50 per cent higher at z ~ 0.55 (the median redshift of the 2SLAQ LRGsample) than in the local universe.

The 2dF-SDSS LRG and QSO Survey: the LRG 2-point correlation function and redshift-space distortions - Ross, Nicholas P.; da Ângela, J.; Shanks, T.; Wake, David A.; Cannon, Russell D.; Edge, A. C.; Nichol, R. C.; Outram, P. J.; Colless, Matthew; Couch, Warrick J.; Croom, Scott M.; de Propris, Roberto; et al. (Monthly Notices of the Royal Astronomical Society, 2007)
We present a clustering analysis of luminous red galaxies (LRGs) usingnearly 9000 objects from the final, three-year catalogue of the 2dF-SDSSLRG and QSO (2SLAQ) Survey. We measure the redshift-space two-pointcorrelation function, ξ(s) and find that, at the mean LRG redshift ofshows the characteristic downturn at small scales(<~1h-1Mpc) expected from line-of-sight velocitydispersion. We fit a double power law to ξ(s) and measure anamplitude and slope of s0 =17.3+2.5-2.0h-1Mpc,γ = 1.03 +/-0.07 at small scales (s < 4.5h-1Mpc) and s0 =9.40 +/- 0.19h-1Mpc,γ = 2.02 +/- 0.07 at large scales(s > 4.5h-1Mpc). In the semiprojected correlationfunction, wp(σ), we find a simple power law withγ = 1.83 +/- 0.05 and r0 = 7.30 +/-0.34h-1Mpc fits the data in the range 0.4 < σ <50h-1Mpc, although there is evidence of a steeper power lawat smaller scales. A single power law also fits the deprojectedcorrelation function ξ(r), with a correlation length of r0= 7.45 +/- 0.35h-1Mpc and a power-law slope of γ = 1.72+/- 0.06 in the 0.4 < r < 50h-1Mpc range. But it is inthe LRG angular correlation function that the strongest evidence fornon-power-law features is found where a slope of γ = -2.17 +/-0.07 is seen at 1 < r < 10h-1Mpc with a flatter γ= -1.67 +/- 0.07 slope apparent at r <~ 1h-1Mpc scales.We use the simple power-law fit to the galaxy ξ(r), under theassumption of linear bias, to model the redshift-space distortions inthe 2D redshift-space correlation function, ξ(σ, π). We fitfor the LRG velocity dispersion, wz, the density parameter,Ωm and β(z), where β(z) =Ω0.6m/b and b is the linear bias parameter.We find values of wz =330kms-1,Ωm =0.10+0.35-0.10 and β = 0.40 +/- 0.05. The lowvalues for wz and β reflect the high bias of the LRGsample. These high-redshift results, which incorporate theAlcock-Paczynski effect and the effects of dynamical infall, start tobreak the degeneracy between Ωm and β found inlow-redshift galaxy surveys such as 2dFGRS. This degeneracy is furtherbroken by introducing an additional external constraint, which is thevalue β(z = 0.1) = 0.45 from 2dFGRS, and then considering theevolution of clustering from z ~ 0 to zLRG ~ 0.55. With thesecombined methods we find Ωm(z = 0) = 0.30 +/- 0.15 andβ(z = 0.55) = 0.45 +/- 0.05. Assuming these values, we find a valuefor b(z = 0.55) = 1.66 +/- 0.35. We show that this is consistent with asimple `high-peak' bias prescription which assumes that LRGs have aconstant comoving density and their clustering evolves purely undergravity.

Measuring the Baryon Acoustic Oscillation scale using the Sloan Digital Sky Survey and 2dF Galaxy Redshift Survey - Percival, Will J.; Cole, Shaun; Eisenstein, Daniel J.; Nichol, Robert C.; Peacock, John A.; Pope, Adrian C.; Szalay, Alexander S. (Monthly Notices of the Royal Astronomical Society, 2007)
We introduce a method to constrain general cosmological models usingBaryon Acoustic Oscillation (BAO) distance measurements from galaxysamples covering different redshift ranges, and apply this method toanalyse samples drawn from the Sloan Digital Sky Survey (SDSS) and 2dFGalaxy Redshift Survey (2dFGRS). BAOs are detected in the clustering ofthe combined 2dFGRS and SDSS main galaxy samples, and measure thedistance-redshift relation at z = 0.2. BAOs in the clustering of theSDSS luminous red galaxies measure the distance-redshift relation at z =0.35. The observed scales of the BAOs calculated from these samples andfrom the combined sample are jointly analysed using estimates of thecorrelated errors, to constrain the form of the distance measureDV(z) ≡ [(1 +z)2D2Acz/H(z)]1/3. HereDA is the angular diameter distance, and H(z) is the Hubbleparameter. This gives rs/DV(0.2) = 0.1980 +/-0.0058 and rs/DV(0.35) = 0.1094 +/- 0.0033(1σ errors), with a correlation coefficient of 0.39, wherers is the comoving sound horizon scale at recombination.Matching the BAOs to have the same measured scale at all redshifts thengives DV(0.35)/DV(0.2) = 1.812 +/- 0.060. Therecovered ratio is roughly consistent with that predicted by the higherredshift Supernova Legacy Survey (SNLS) supernova data for Λ colddark matter cosmologies, but does require slightly stronger cosmologicalacceleration at a low redshift. If we force the cosmological model to beflat with constant w, then we find Ωm = 0.249 +/- 0.018and w = -1.004 +/- 0.089 after combining with the SNLS data, andincluding the WMAP measurement of the apparent acoustic horizon angle inthe cosmic microwave background.

A Large Population of Mid-Infrared-selected, Obscured Active Galaxies in the Boötes Field - Hickox, R. C.; Jones, C.; Forman, W. R.; Murray, S. S.; Brodwin, M.; Brown, M. J. I.; Eisenhardt, P. R.; Stern, D.; Kochanek, C. S.; Eisenstein, D.; Cool, R. J.; Jannuzi, B. T.; et al. (The Astrophysical Journal, 2007)
We identify a population of 640 obscured and 839 unobscured AGNs atredshifts 0.72 NOAO Deep Wide-Field Survey (NDWFS) region inBoötes. We select AGNs on the basis of Spitzer IRAC colors obtainedby the IRAC Shallow Survey. Redshifts are obtained from opticalspectroscopy or photometric redshift estimators. We classify theIR-selected AGNs as IRAGN 1 (unobscured) and IRAGN 2 (obscured) using asimple criterion based on the observed optical to mid-IR color, with aselection boundary of R-[4.5]=6.1, where R and [4.5] are the Vegamagnitudes in the R and IRAC 4.5 μm bands, respectively. We verifythis selection using X-ray stacking analyses with data from the ChandraXBoötes survey, as well as optical photometry from NDWFS andspectroscopy from MMT/AGES. We show that (1) these sources are indeedAGNs, and (2) the optical/IR color selection separates obscured sources(with average NH~3×1022 cm-2obtained from X-ray hardness ratios, and optical colors and morphologiestypical of galaxies) and unobscured sources (with no X-ray absorption,

SDSS J102111.02+491330.4: A Newly Discovered Gravitationally Lensed Quasar - Pindor, Bart; Eisenstein, Daniel J.; Gregg, Michael D.; Becker, Robert H.; Inada, Naohisa; Oguri, Masamune; Hall, Patrick B.; Johnston, David E.; Richards, Gordon T.; Schneider, Donald P.; Turner, Edwin L.; Brasi, Guido; et al. (The Astronomical Journal, 2006)
We report follow-up observations of two gravitational lens candidatesidentified in the Sloan Digital Sky Survey (SDSS) data set. We haveconfirmed that SDSS J102111.02+491330.4 is a previously unknowngravitationally lensed quasar. This lens system exhibits two images of az=1.72 quasar, with an image separation of 1.14"+/-0.04". Optical andnear-IR imaging of the system reveals the presence of the lensing galaxybetween the two quasar images. Observations of SDSS J112012.12+671116.0indicate that it is more likely a binary quasar than a gravitationallens. This system has two quasars at a redshift of z=1.49, with anangular separation of 1.49"+/-0.02". However, the two quasars havemarkedly different spectral energy distributions, and no lens galaxy isapparent in optical and near-IR images of this system. We also present alist of 31 SDSS lens candidates that follow-up observations haveconfirmed are not gravitational lenses.Observations reported here were obtained at the MMT Observatory, a jointfacility of the University of Arizona and the Smithsonian Institution.

A Snapshot Survey for Gravitational Lenses among z>=4.0 Quasars. II. Constraints on the 4.0<z<5.4 Quasar Population - Richards, Gordon T.; Haiman, Zoltán; Pindor, Bartosz; Strauss, Michael A.; Fan, Xiaohui; Eisenstein, Daniel; Schneider, Donald P.; Bahcall, Neta A.; Brinkmann, J.; Fukugita, Masataka (The Astronomical Journal, 2006)
We report on i-band snapshot observations of 157 Sloan Digital SkySurvey quasars at 4.0-3.8 (3 σ), assuming a break in the quasar luminosityfunction at M*1450~-24.5. This constraint isconsiderably stronger than the limit of β>-4.63 obtained fromthe absence of lensing in four z>5.7 quasars. Such constraints areimportant to our understanding of the true space density ofhigh-redshift quasars and the ionization state of the early universe.Based on observations made with the NASA/ESA Hubble Space Telescope,obtained at the Space Telescope Science Institute, which is operated bythe Association of Universities for Research in Astronomy, Inc., underNASA contract NAS5-26555. These observations are associated with program9472.

The White Dwarf Luminosity Function from Sloan Digital Sky Survey Imaging Data - Harris, Hugh C.; Munn, Jeffrey A.; Kilic, Mukremin; Liebert, James; Williams, Kurtis A.; von Hippel, Ted; Levine, Stephen E.; Monet, David G.; Eisenstein, Daniel J.; Kleinman, S. J.; Metcalfe, T. S.; Nitta, Atsuko; et al. (The Astronomical Journal, 2006)
A sample of white dwarfs is selected from the Sloan Digital Sky Survey(SDSS) Data Release 3 using their reduced proper motions, based onimproved proper motions from combined SDSS and USNO-B data. NumerousSDSS and follow-up spectra (Kilic and coworkers) are used to quantifycompleteness and contamination of the sample; kinematics models are usedto understand and correct for velocity-dependent selection biases. Aluminosity function is constructed covering the range7bol<16, and its sensitivity to various assumptionsand selection limits is discussed. The white dwarf luminosity functionbased on 6000 stars is remarkably smooth and rises nearly monotonicallyto Mbol=15.3. It then drops abruptly, although the smallnumber of low-luminosity stars in the sample and their unknownatmospheric composition prevent quantitative conclusions about thisdecline. Stars are identified that may have high tangential velocities,and a preliminary luminosity function is constructed for them.

The Fourth Data Release of the Sloan Digital Sky Survey - Adelman-McCarthy, Jennifer K.; Agüeros, Marcel A.; Allam, Sahar S.; Anderson, Kurt S. J.; Anderson, Scott F.; Annis, James; Bahcall, Neta A.; Baldry, Ivan K.; Barentine, J. C.; Berlind, Andreas; Bernardi, Mariangela; Blanton, Michael R.; et al. (The Astrophysical Journal Supplement Series, 2006)
This paper describes the Fourth Data Release of the Sloan Digital SkySurvey (SDSS), including all survey-quality data taken through 2004June. The data release includes five-band photometric data for 180million objects selected over 6670 deg2 and 673,280 spectraof galaxies, quasars, and stars selected from 4783 deg2 ofthose imaging data using the standard SDSS target selection algorithms.

Broadband Optical Properties of Massive Galaxies: The Dispersion around the Field Galaxy Color-Magnitude Relation Out to z~0.4 - Cool, Richard J.; Eisenstein, Daniel J.; Johnston, David; Scranton, Ryan; Brinkmann, Jon; Schneider, Donald P.; Zehavi, Idit (The Astronomical Journal, 2006)
Using a sample of nearly 20,000 massive early-type galaxies selectedfrom the Sloan Digital Sky Survey, we study the color-magnitude relationfor the most luminous (L>~2.2L*) field galaxies in theredshift range 0.1

SDSS J103913.70+533029.7: A Super Star Cluster in the Outskirts of a Galaxy Merger - Knapp, Gillian R.; Tremonti, Christy A.; Rockosi, Constance M.; Schlegel, David J.; Yanny, Brian; Beers, Timothy C.; Allende Prieto, Carlos; Wilhelm, Ron; Lupton, Robert H.; Gunn, James E.; Niederste-Ostholt, Martin; Schneider, Donald P.; et al. (The Astronomical Journal, 2006)
We describe the serendipitous discovery in the spectroscopic data of theSloan Digital Sky Survey of a starlike object, SDSS J103913.70+533029.7,at a heliocentric radial velocity of +1012 km s-1. Itsproximity in position and velocity to the spiral galaxy NGC 3310suggests an association with the galaxy. At this distance, SDSSJ103913.70+533029.7 has the luminosity of a super star cluster and aprojected distance of 17 kpc from NGC 3310. Its spectroscopic andphotometric properties imply a mass of >106Msolar and an age close to that of the tidal shells seenaround NGC 3310, suggesting that it formed in the event that formed theshells.

A Catalog of Spectroscopically Selected Close Binary Systems from the Sloan Digital Sky Survey Data Release Four - Silvestri, Nicole M.; Hawley, Suzanne L.; West, Andrew A.; Szkody, Paula; Bochanski, John J.; Eisenstein, Daniel J.; McGehee, Peregrine; Schmidt, Gary D.; Smith, J. Allyn; Wolfe, Michael A.; Harris, Hugh C.; Kleinman, Scot J.; et al. (The Astronomical Journal, 2006)
We present a spectroscopic sample of 747 detached close binary systemsfrom the Sloan Digital Sky Survey (SDSS) Fourth Data Release. Themajority of these binaries consist of a white dwarf primary and alow-mass secondary (typically M dwarf) companion. We have determined thetemperature and gravity for 496 of the white dwarf primaries and thespectral type and magnetic activity properties for 661 of the low-masssecondaries. We have estimated the distances for each of the whitedwarf-main-sequence star binaries and use white dwarf evolutionary gridsto establish the age of each binary system from the white dwarf coolingtimes. With respect to a spectroscopically identified sample of ~8000isolated M dwarf stars in the SDSS, the M dwarf secondaries showenhanced activity with a higher active fraction at a given spectraltype. The white dwarf temperatures and gravities are similar to thedistribution of ~1900 DA white dwarfs from the SDSS. The ages of thebinaries in this study range from ~0.5 Myr to nearly 3 Gyr (average age~0.20 Gyr).

Discovery of eleven new ZZ Ceti stars - Castanheira, B. G.; Kepler, S. O.; Mullally, F.; Winget, D. E.; Koester, D.; Voss, B.; Kleinman, S. J.; Nitta, A.; Eisenstein, D. J.; Napiwotzki, R.; Reimers, D. (Astronomy and Astrophysics, 2006)
We report the discovery of eleven new ZZ Cetis using telescopes at OPD(Observatório do Pico dos Dias/LNA) in Brazil, the 4.1 m SOAR(Southern Astrophysical Research) telescope at Cerro Pachon, Chile, andthe 2.1 m Otto Struve telescope at McDonald observatory. The candidateswere selected from the SDSS (Sloan Digital Sky Survey) and SPY (ESO SNIa progenitor survey), based on their Teff obtained fromoptical spectra fitting. This selection criterion yields the highest

Probing Galaxy Formation with He II Cooling Lines - Yang, Yujin; Zabludoff, Ann I.; Davé, Romeel; Eisenstein, Daniel J.; Pinto, Philip A.; Katz, Neal; Weinberg, David H.; Barton, Elizabeth J. (The Astrophysical Journal, 2006)
Using high-resolution cosmological simulations, we study hydrogen andhelium gravitational cooling radiation from gas accretion by younggalaxies. We focus on the He II cooling lines, which arise from gas witha different temperature history (Tmax~105 K) thanH I line-emitting gas. We examine whether three major atomic coolinglines, H I λ1216, He II λ1640, and He II λ304, areobservable, finding that Lyα and He II λ1640 coolingemission at z=2-3 are potentially detectable with deep narrowband(R>100) imaging and/or spectroscopy from the ground. While theexpected strength of H I λ1216 cooling emission depends stronglyon the treatment of the self-shielded phase of the IGM in thesimulations, our predictions for the He II λ1640 line are morerobust, because the He II emissivity is negligible belowT~104.5 K and less sensitive to the UV background. AlthoughHe II λ1640 cooling emission is fainter than Lyα by atleast a factor of 10 and, unlike Lyα, might not be resolvedspatially with current observational facilities, it is more suitable tostudy gas accretion in the galaxy formation process because it isoptically thin and less contaminated by the recombination lines fromstar-forming galaxies. The He II λ1640 line can be used todistinguish among mechanisms for powering the so-called Lyαblobs-including gravitational cooling radiation, photoionization bystellar populations, and starburst-driven superwinds-because (1) He IIλ1640 emission is limited to very low metallicity[log(Z/Zsolar)<~-5.3] and Population III stars and (2) theblob's kinematics are probed unambiguously through the He II line width,which for cooling radiation is narrower (σ<400 kms-1) than typical wind speeds.

SDSS Preburst Observations of Recent Gamma-Ray Burst Fields - Cool, Richard J.; Eisenstein, Daniel J.; Hogg, David W.; Blanton, Michael R.; Schlegel, David J.; Brinkmann, J.; Schneider, Donald P.; Vanden Berk, Daniel E. (Publications of the Astronomical Society of the Pacific, 2006)
We present Sloan Digital Sky Survey (SDSS) photometry and spectroscopyin the fields of 27 gamma-ray bursts observed by Swift, including burstslocalized by Swift, HETE-2, and INTEGRAL, after 2004 December. Afterthis bulk release, we plan to provide individual releases of similardata shortly after the localization of future bursts falling in the SDSSsurvey area. These data provide a solid basis for the astrometric andphotometric calibration of follow-up afterglow searches and monitoring.Furthermore, the images provided with this release will allow observersto find transient objects up to a magnitude fainter than is possiblewith Digitized Sky Survey images.

A Spectroscopic Survey of Faint Quasars in the SDSS Deep Stripe. I. Preliminary Results from the Co-added Catalog - Jiang, Linhua; Fan, Xiaohui; Cool, Richard J.; Eisenstein, Daniel J.; Zehavi, Idit; Richards, Gordon T.; Scranton, Ryan; Johnston, David; Strauss, Michael A.; Schneider, Donald P.; Brinkmann, J. (The Astronomical Journal, 2006)
In this paper we present the first results of a deep spectroscopicsurvey of faint quasars in the Sloan Digital Sky Survey (SDSS) SouthernSurvey, a deep survey carried out by repeatedly imaging a 270deg2 area. Quasar candidates were selected from the deep datawith good completeness over 02, contains 414 quasars, and

Very Small Scale Clustering and Merger Rate of Luminous Red Galaxies - Masjedi, Morad; Hogg, David W.; Cool, Richard J.; Eisenstein, Daniel J.; Blanton, Michael R.; Zehavi, Idit; Berlind, Andreas A.; Bell, Eric F.; Schneider, Donald P.; Warren, Michael S.; Brinkmann, Jon (The Astrophysical Journal, 2006)
We present the small-scale (0.01 Mpc-1 Mpc)projected correlation function wp(rp) andreal-space correlation function ξ(r) of 24,520 luminous early-typegalaxies from the Sloan Digital Sky Survey (SDSS) Luminous Red Galaxy(LRG) sample (0.16-2 power law over more than 4 orders of magnitudein separation r. This result is too steep at small scales to beexplained in current versions of the halo model for galaxy clustering.We infer an LRG-LRG merger rate of <~0.6×104Gyr-1 Gpc-3 for this sample. This result suggeststhat the LRG-LRG mergers are not the main mode of mass growth for LRGsat z<0.36.

An MMT Hectospec Redshift Survey of 24 μm Sources in the Spitzer First Look Survey - Papovich, Casey; Cool, Richard; Eisenstein, Daniel; Le Floc'h, Emeric; Fan, Xiaohui; Kennicutt, Robert C., Jr.; Smith, J. D. T.; Rieke, G. H.; Vestergaard, Marianne (The Astronomical Journal, 2006)
We present a spectroscopic survey using the MMT Hectospec fiberspectrograph of 24 μm sources selected with the Spitzer SpaceTelescope in the Spitzer First Look Survey. We report 1296 new redshiftsfor 24 μm sources, including 599 with fν(24μm)>=1 mJy. Combined with 291 additional redshifts for sourcesfrom the Sloan Digital Sky Survey (SDSS), our observing program was

The Scale Dependence of Relative Galaxy Bias: Encouragement for the ``Halo Model'' Description - Blanton, Michael R.; Eisenstein, Daniel; Hogg, David W.; Zehavi, Idit (The Astrophysical Journal, 2006)
We investigate the relationship between the colors, luminosities, andenvironments of galaxies in the Sloan Digital Sky Survey spectroscopicsample, using environmental measurements on scales ranging from 0.2 to 6h-1 Mpc. We find that (1) the relationship between color andenvironment persists even to the lowest luminosities we probe(Mr-5log10h~-14) (2) at luminosities and colors for which thegalaxy correlation function has a large amplitude, it also has a steepslope; and (3) in regions of a given overdensity on small scales (1h-1 Mpc), the overdensity on large scales (6 h-1Mpc) does not appear to relate to the recent star formation history ofthe galaxies. Of these results, the last has the most immediateapplication to galaxy formation theory. In particular, it lends supportto the notion that a galaxy's properties are related only to the mass ofits host dark matter halo, and not to the larger scale environment.Based on observations obtained with the Sloan Digital Sky Survey.

Hot DB White Dwarfs from the Sloan Digital Sky Survey - Eisenstein, Daniel J.; Liebert, James; Koester, Detlev; Kleinmann, S. J.; Nitta, Atsuko; Smith, Paul S.; Barentine, J. C.; Brewington, Howard J.; Brinkmann, J.; Harvanek, Michael; Krzesiński, Jurek; Neilsen, Eric H., Jr.; et al. (The Astronomical Journal, 2006)
We present ugriz photometry and optical spectroscopy for 28 DB and DOwhite dwarfs with temperatures between 28,000 and 45,000 K. About 10 ofthese are particularly well observed; the remainder are candidates.These are the hottest DB stars yet found, and they populate the ``DBgap'' between the hotter DO stars and the familiar DB stars cooler than30,000 K. Nevertheless, after carefully matching the survey volumes wefind that the ratio of DA stars to DB stars is a factor of 2.5 larger at30,000 than at 20,000 K, suggesting that the ``DB gap'' is indeeddeficient and that some kind of atmospheric transformation takes place

The Discovery of Three New z>5 Quasars in the AGN and Galaxy Evolution Survey - Cool, Richard J.; Kochanek, Christopher S.; Eisenstein, Daniel J.; Stern, Daniel; Brand, Kate; Brown, Michael J. I.; Dey, Arjun; Eisenhardt, Peter R.; Fan, Xiaohui; Gonzalez, Anthony H.; Green, Richard F.; Jannuzi, Buell T.; et al. (The Astronomical Journal, 2006)
We present the discovery of three z>5 quasars in the AGN and GalaxyEvolution Survey spectroscopic observations of the NOAO Deep Wide-FieldSurvey (NDWFS) Bootes Field. These quasars were selected as part of alarger Spitzer mid-infrared quasar sample, with no selection based onoptical colors. The highest redshift object, NDWFS J142516.3+325409, atz=5.85, is the lowest luminosity z>5.8 quasar currently known. Wecompare mid-infrared techniques for identifying z>5 quasars to moretraditional optical techniques and show that mid-infrared colors allowfor the selection of high-redshift quasars even at redshifts at whichquasars lie near the optical stellar locus and at z>7, where opticalselection is impossible. Using the superb multiwavelength coverageavailable in the NDWFS Bootes field, we construct the spectral energydistributions (SEDs) of high-redshift quasars from observedBW band to 24 μm (rest-frame 600 Å-3.7 μm). Weshow that the three high-redshift quasars have quite similar SEDs, andthe rest-frame composite SED of low-redshift quasars from the literatureshows little evolution compared to our high-redshift objects. We comparethe number of z>5 quasars we have discovered to the expected numberfrom published quasar luminosity functions. While analyses of the quasarluminosity function are tenuous based on only three objects, we findthat a relatively steep luminosity function with Ψ~L-3.2provides the best agreement with the number of high-redshift quasarsdiscovered in our survey.

Chandra Observations of SDSS J1004+4112: Constraints on the Lensing Cluster and Anomalous X-Ray Flux Ratios of the Quadruply Imaged Quasar - Ota, Naomi; Inada, Naohisa; Oguri, Masamune; Mitsuda, Kazuhisa; Richards, Gordon T.; Suto, Yasushi; Brandt, W. N.; Castander, Francisco J.; Fujimoto, Ryuichi; Hall, Patrick B.; Keeton, Charles R.; Nichol, Robert C.; et al. (The Astrophysical Journal, 2006)
We present results from Chandra observations of SDSS J1004+4112, astrongly lensed quasar system with a maximum image separation of 15".All four bright images of the quasar, as well as resolved X-ray emissionoriginating from the lensing cluster, are clearly detected. The emissionfrom the lensing cluster extends out to approximately 1.5 arcmin. Wemeasure the bolometric X-ray luminosity and temperature of the lensingcluster to be 4.7×1044 ergs s-1 and 6.4 keV,consistent with the luminosity-temperature relation for distantclusters. The mass estimated from the X-ray observation shows excellentagreement with the mass derived from gravitational lensing. The X-rayflux ratios of the quasar images differ markedly from the optical fluxratios, and the combined X-ray spectrum of the images possesses anunusually strong Fe Kα emission line, both of which are indicativeof microlensing.

Star Formation History of the Hubble Ultra Deep Field: Comparison with the Hubble Deep Field-North - Thompson, Rodger I.; Eisenstein, Daniel; Fan, Xiaohui; Dickinson, Mark; Illingworth, Garth; Kennicutt, Robert C., Jr. (The Astrophysical Journal, 2006)
We use the NICMOS Treasury and ACS HUDF images to measure theextinction-corrected star formation history for 4681 galaxies in theregion common to both images using the star formation rate distributionfunction and other techniques similar to those employed with the NICMOSand WFPC2 images in the HDFN. Unlike the HDFN, the NICMOS region of theHUDF appears to lack highly luminous and high star formation rategalaxies at redshifts beyond 3. The HUDF provides a region that iscompletely uncorrelated to the HDFN and therefore provides anindependent measure of the star formation history of the universe. Thecombined HUDF and HDFN star formation rates show an average rate of 0.2Msolar yr-1 Mpc-3. The average SFR ofthe combined fields at z=1-3 is 0.29 Msolar yr-1Mpc-3, while the average at z=4-6 is 1.2 Msolaryr-1 Mpc-3. The SFRs at all redshifts are within 3σ of the average over all redshifts.

Black Hole Masses and Eddington Ratios at 0.3 < z < 4 - Kollmeier, Juna A.; Onken, Christopher A.; Kochanek, Christopher S.; Gould, Andrew; Weinberg, David H.; Dietrich, Matthias; Cool, Richard; Dey, Arjun; Eisenstein, Daniel J.; Jannuzi, Buell T.; Le Floc'h, Emeric; Stern, Daniel (The Astrophysical Journal, 2006)
We study the distribution of Eddington luminosity ratios,Lbol/LEdd, of active galactic nuclei (AGNs)discovered in the AGN and Galaxy Evolution Survey (AGES). We combineHβ, Mg II, and C IV line widths with continuum luminosities toestimate black hole (BH) masses in 407 AGNs, covering the redshift rangez~0.3-4 and the bolometric luminosity rangeLbol~1045-1047 ergs s-1. Thesample consists of X-ray or mid-infrared (24 μm) point sources withoptical magnitude R<=21.5 mag and optical emission-line spectracharacteristic of AGNs. For the range of luminosity and redshift probedby AGES, the distribution of estimated Eddington ratios is welldescribed as log-normal, with a peak atLbol/LEdd~=1/4 and a dispersion of 0.3 dex. Sinceadditional sources of scatter are minimal, this dispersion must accountfor contributions from the scatter between estimated and true BH massand the scatter between estimated and true bolometric luminosity.Therefore, we conclude that (1) neither of these sources of error cancontribute more than ~0.3 dex rms, and (2) the true Eddington ratios ofoptically luminous AGNs are even more sharply peaked. Because the massestimation errors must be smaller than ~0.3 dex, we can also investigatethe distribution of Eddington ratios at fixed BH mass. We show for thefirst time that the distribution of Eddington ratios at fixed BH mass ispeaked, and that the dearth of AGNs at a factor of ~10 below Eddingtonis real and not an artifact of sample selection. These results providestrong evidence that supermassive BHs gain most of their mass whileradiating close to the Eddington limit, and they suggest that thefueling rates in luminous AGNs are ultimately determined by BHself-regulation of the accretion flow rather than galactic-scaledynamical disturbances.Observations reported here were obtained at the MMT Observatory (MMTO),a joint facility of the University of Arizona and the SmithsonianInstitution.

The Radial Velocity Experiment (RAVE): First Data Release - Steinmetz, M.; Zwitter, T.; Siebert, A.; Watson, F. G.; Freeman, K. C.; Munari, U.; Campbell, R.; Williams, M.; Seabroke, G. M.; Wyse, R. F. G.; Parker, Q. A.; Bienaymé, O.; et al. (The Astronomical Journal, 2006)
We present the first data release of the Radial Velocity Experiment(RAVE), an ambitious spectroscopic survey to measure radial velocitiesand stellar atmosphere parameters (temperature, metallicity, and surfacegravity) of up to one million stars using the Six Degree Fieldmultiobject spectrograph on the 1.2 m UK Schmidt Telescope of theAnglo-Australian Observatory. The RAVE program started in 2003,obtaining medium-resolution spectra (median R=7500) in the Ca-tripletregion (8410-8795 Å) for southern hemisphere stars drawn from theTycho-2 and SuperCOSMOS catalogs, in the magnitude range 92. The average signal-to-noise ratio of

The 2dF-SDSS LRG and QSO (2SLAQ) Luminous Red Galaxy Survey - Cannon, Russell; Drinkwater, Michael; Edge, Alastair; Eisenstein, Daniel; Nichol, Robert; Outram, Phillip; Pimbblet, Kevin; de Propris, Roberto; Roseboom, Isaac; Wake, David; Allen, Paul; Bland-Hawthorn, Joss; et al. (Monthly Notices of the Royal Astronomical Society, 2006)
We present a spectroscopic survey of almost 15000 candidateintermediate-redshift luminous red galaxies (LRGs) brighter than i =19.8, observed with 2dF on the Anglo-Australian Telescope. The targetswere selected photometrically from the Sloan Digital Sky Survey (SDSS)and lie along two narrow equatorial strips covering 180 deg2.Reliable redshifts were obtained for 92 per cent of the targets and theselection is very efficient: over 90 per cent have 0.45 < z < 0.8.More than 80 per cent of the ~11000 red galaxies have pureabsorption-line spectra consistent with a passively evolving old stellarpopulation. The redshift, photometric and spatial distributions of theLRGs are described. The 2SLAQ data will be released publicly frommid-2006, providing a powerful resource for observational cosmology andthe study of galaxy evolution.

The 2df SDSS LRG and QSO survey: evolution of the luminosity function of luminous red galaxies to z = 0.6 - Wake, David A.; Nichol, Robert C.; Eisenstein, Daniel J.; Loveday, Jon; Edge, Alastair C.; Cannon, Russell; Smail, Ian; Schneider, Donald P.; Scranton, Ryan; Carson, Daniel; Ross, Nicholas P.; Brunner, Robert J.; et al. (Monthly Notices of the Royal Astronomical Society, 2006)
We present new measurements of the luminosity function (LF) of luminousred galaxies (LRGs) from the Sloan Digital Sky Survey (SDSS) and the 2dFSDSS LRG and Quasar (2SLAQ) survey. We have carefully quantified, andcorrected for, uncertainties in the K and evolutionary corrections,differences in the colour selection methods, and the effects ofphotometric errors, thus ensuring we are studying the same galaxypopulation in both surveys. Using a limited subset of 6326 SDSS LRGs(with 0.17 < z < 0.24) and 1725 2SLAQ LRGs (with 0.5 < z <0.6), for which the matching colour selection is most reliable, we findno evidence for any additional evolution in the LRG LF, over thisredshift range, beyond that expected from a simple passive evolutionmodel. This lack of additional evolution is quantified using thecomoving luminosity density of SDSS and 2SLAQ LRGs, brighter thanM0.2r - 5 log h0.7 = -22.5, which are2.51 +/- 0.03 × 10-7LsolarMpc-3and 2.44 +/- 0.15 ×10-7LsolarMpc-3, respectively (<10per cent uncertainty). We compare our LFs to the COMBO-17 data and findexcellent agreement over the same redshift range. Together, thesesurveys show no evidence for additional evolution (beyond passive) inthe LF of LRGs brighter than M0.2r - 5 logh0.7 = -21 (or brighter than ~L*). We test our SDSS and 2SLAQLFs against a simple `dry merger' model for the evolution of massive redgalaxies and find that at least half of the LRGs at z ~= 0.2 mustalready have been well assembled (with more than half their stellarmass) by z ~= 0.6. This limit is barely consistent with recent resultsfrom semi-analytical models of galaxy evolution.

Photometric Redshifts in the IRAC Shallow Survey - Brodwin, M.; Brown, M. J. I.; Ashby, M. L. N.; Bian, C.; Brand, K.; Dey, A.; Eisenhardt, P. R.; Eisenstein, D. J.; Gonzalez, A. H.; Huang, J.-S.; Jannuzi, B. T.; Kochanek, C. S.; et al. (The Astrophysical Journal, 2006)
Accurate photometric redshifts are calculated for nearly 200,000galaxies to a 4.5 μm flux limit of ~13 μJy in the 8.5deg2 Spitzer IRAC Shallow Survey. Using a hybrid photometricredshift algorithm incorporating both neural net and template-fittingtechniques, calibrated with over 15,000 spectroscopic redshifts, a

A Catalog of Spectroscopically Confirmed White Dwarfs from the Sloan Digital Sky Survey Data Release 4 - Eisenstein, Daniel J.; Liebert, James; Harris, Hugh C.; Kleinman, S. J.; Nitta, Atsuko; Silvestri, Nicole; Anderson, Scott A.; Barentine, J. C.; Brewington, Howard J.; Brinkmann, J.; Harvanek, Michael; Krzesiński, Jurek; et al. (The Astrophysical Journal Supplement Series, 2006)
We present a catalog of 9316 spectroscopically confirmed white dwarfsfrom the Sloan Digital Sky Survey Data Release 4. We have selected thestars through photometric cuts and spectroscopic modeling, backed up bya set of visual inspections. About 6000 of the stars are newdiscoveries, roughly doubling the number of spectroscopically confirmedwhite dwarfs. We analyze the stars by performing temperature and surfacegravity fits to grids of pure hydrogen and helium atmospheres. Among therare outliers are a set of presumed helium-core DA white dwarfs withestimated masses below 0.3 Msolar, including two candidatesthat may be the lowest-mass yet found. We also present a list of 928 hotsubdwarfs.

The 2dF-SDSS LRG and QSO Survey: the star formation histories of luminous red galaxies - Roseboom, Isaac G.; Pimbblet, Kevin A.; Drinkwater, Michael J.; Cannon, Russell D.; de Propris, Roberto; Edge, Alastair C.; Eisenstein, Daniel J.; Nichol, Robert C.; Smail, Ian; Wake, David A.; Bland-Hawthorn, Joss; Bridges, Terry J.; et al. (Monthly Notices of the Royal Astronomical Society, 2006)
We present a detailed investigation into the recent star formationhistories of 5697 luminous red galaxies (LRGs) based on the Hδ(4101 Å), and [OII] (3727 Å) lines and the D4000 index. LRGsare luminous (L > 3L*) galaxies which have been selected to havephotometric properties consistent with an old, passively evolvingstellar population. For this study, we utilize LRGs from the recentlycompleted 2dF-SDSS LRG and QSO Survey (2SLAQ). Equivalent widths of theHδ and [OII] lines are measured and used to define three spectraltypes, those with only strong Hδ absorption (k+a), those withstrong [OII] in emission (em) and those with both (em+a). All other LRGsare considered to have passive star formation histories. The vastmajority of LRGs are found to be passive (~80 per cent); however,significant numbers of k+a (2.7 per cent), em+a (1.2 per cent) and emLRGs (8.6 per cent) are identified. An investigation into the redshiftdependence of the fractions is also performed. A sample of SDSS MAINgalaxies with colours and luminosities consistent with the 2SLAQ LRGs isselected to provide a low-redshift comparison. While the em and em+afractions are consistent with the low-redshift SDSS sample, the fractionof k+a LRGs is found to increase significantly with redshift. Thisresult is interpreted as an indication of an increasing amount of recentstar formation activity in LRGs with redshift. By considering theexpected lifetime of the k+a phase, the number of LRGs which willundergo a k+a phase can be estimated. A crude comparison of thisestimate with the predictions from semi-analytic models of galaxyformation shows that the predicted level of k+a and em+a activities isnot sufficient to reconcile the predicted mass growth for massive earlytypes in a hierarchical merging scenario.

Cosmological constraints from the SDSS luminous red galaxies - Tegmark, Max; Eisenstein, Daniel J.; Strauss, Michael A.; Weinberg, David H.; Blanton, Michael R.; Frieman, Joshua A.; Fukugita, Masataka; Gunn, James E.; Hamilton, Andrew J. S.; Knapp, Gillian R.; Nichol, Robert C.; Ostriker, Jeremiah P.; et al. (Physical Review D, 2006)
We measure the large-scale real-space power spectrum P(k) using luminousred galaxies (LRGs) in the Sloan Digital Sky Survey (SDSS) and use thismeasurement to sharpen constraints on cosmological parameters from theWilkinson Microwave Anisotropy Probe (WMAP). We employ a matrix-basedpower spectrum estimation method using Pseudo-Karhunen-Loèveeigenmodes, producing uncorrelated minimum-variance measurements in 20k-bands of both the clustering power and its anisotropy due toredshift-space distortions, with narrow and well-behaved windowfunctions in the range 0.01h/Mpcm and the baryon fraction in goodagreement with WMAP. Within the context of flat ΛCDM models, ourLRG measurements complement WMAP by sharpening the constraints on thematter density, the neutrino density and the tensor amplitude by about afactor of 2, giving Ωm=0.24±0.02 (1σ),

The Small-Scale Clustering of Luminous Red Galaxies via Cross-Correlation Techniques - Eisenstein, Daniel J.; Blanton, Michael; Zehavi, Idit; Bahcall, Neta; Brinkmann, Jon; Loveday, Jon; Meiksin, Avery; Schneider, Don (The Astrophysical Journal, 2005)
We present the small-scale (0.2-7 h-1 Mpc) cross-correlationsbetween 32,000 luminous early-type galaxies and a reference sample of 16million normal galaxies from the Sloan Digital Sky Survey (SDSS). Ourmethod allows us to construct the spherically averaged, real-spacecross-correlation function between the spectroscopic luminous red galaxy(LRG) sample and galaxies from the SDSS imaging. We report thecross-correlation as a function of scale, luminosity, and redshift. Wefind very strong luminosity dependences in the clustering amplitudes, upto a factor of 4 over a factor of 4 in luminosity, and we measure thisdependence with a high signal-to-noise ratio. The luminosity dependenceof bias is found to depend on scale, with more variation on smallerscales. The clustering as a function of scale is not a power law butinstead has a dip at 1 h-1 Mpc and an excess on small scales.The fraction of red galaxies within the L* sample surroundingLRGs is a strong function of scale, as expected. However, the fractionof red galaxies evolves in redshift similarly on small and large scales,suggesting that cluster and field populations are changing in the samemanner. The results highlight the advantage on small scales of usingcross-correlation methods as a means of avoiding shot noise in samplesof rare galaxies.

The Third Data Release of the Sloan Digital Sky Survey - Abazajian, Kevork; Adelman-McCarthy, Jennifer K.; Agüeros, Marcel A.; Allam, Sahar S.; Anderson, Kurt S. J.; Anderson, Scott F.; Annis, James; Bahcall, Neta A.; Baldry, Ivan K.; Bastian, Steven; Berlind, Andreas; Bernardi, Mariangela; et al. (The Astronomical Journal, 2005)
This paper describes the Third Data Release of the Sloan Digital SkySurvey (SDSS). This release, containing data taken up through 2003 June,includes imaging data in five bands over 5282 deg2,photometric and astrometric catalogs of the 141 million objects detectedin these imaging data, and spectra of 528,640 objects selected over 4188deg2. The pipelines analyzing both images and spectroscopyare unchanged from those used in our Second Data Release.

The Intermediate-Scale Clustering of Luminous Red Galaxies - Zehavi, Idit; Eisenstein, Daniel J.; Nichol, Robert C.; Blanton, Michael R.; Hogg, David W.; Brinkmann, Jon; Loveday, Jon; Meiksin, Avery; Schneider, Donald P.; Tegmark, Max (The Astrophysical Journal, 2005)
We report the intermediate-scale (0.3-40 h-1 Mpc) clusteringof 35,000 luminous early-type galaxies at redshifts 0.16-0.44 from theSloan Digital Sky Survey. We present the redshift space two-pointcorrelation function ξ(s), the projected correlation functionwp(rp), and the deprojected real space correlationfunction ξ(r), for approximately volume-limited samples. As expected,the galaxies are highly clustered, with the correlation length varyingfrom 9.8+/-0.2 to 11.2 +/- 0.2 h-1 Mpc, dependent on thespecific luminosity range. For the -23.2g<-21.2sample, the inferred bias relative to that of L* galaxies is1.84+/-0.11 for1h-1Mpcp<~10h-1Mpc, with yetstronger clustering on smaller scales. We detect luminosity-dependentbias within the sample but see no evidence for redshift evolutionbetween z=0.2 and z=0.4. We find a clear indication for deviations froma power-law in the real space correlation function, with a dip at ~2h-1 Mpc scales and an upturn on smaller scales. The precisionmeasurements of these clustering trends offer new avenues for the studyof the formation and evolution of these massive galaxies.

Covariance of the one-dimensional mass power spectrum - Zhan, Hu; Eisenstein, Daniel (Monthly Notices of the Royal Astronomical Society, 2005)
We analyse the covariance of the one-dimensional mass power spectrumalong lines of sight. The covariance reveals the correlation betweendifferent modes of fluctuations in the cosmic density field and givesthe sample variance error for measurements of the mass power spectrum.For Gaussian random fields, the covariance matrix is diagonal. Asexpected, the variance of the measured one-dimensional mass powerspectrum is inversely proportional to the number of lines of sight thatare sampled from each random field. The correlation between lines ofsight in a single field may alter the covariance. However, lines ofsight that are sampled far apart are only weakly correlated, so thatthey can be treated as independent samples. Using N-body simulations, wefind that the covariance matrix of the one-dimensional mass powerspectrum is not diagonal for the cosmic density field due to thenon-Gaussianity and that the variance is much higher than that ofGaussian random fields. From the covariance, one will be able todetermine the cosmic variance in the measured one-dimensional mass powerspectrum as well as to estimate how many lines of sight are needed toachieve a target precision.

The Sloan Digital Sky Survey u-band Galaxy Survey: luminosity functions and evolution - Baldry, I. K.; Glazebrook, K.; Budavári, T.; Eisenstein, D. J.; Annis, J.; Bahcall, N. A.; Blanton, M. R.; Brinkmann, J.; Csabai, I.; Heckman, T. M.; H Lin; Loveday, J.; et al. (Monthly Notices of the Royal Astronomical Society, 2005)
We construct and analyse a u-band selected galaxy sample from the SloanDigital Sky Survey (SDSS) Southern Survey, which covers275deg2. The sample includes 43223 galaxies withspectroscopic redshifts in the range 0.005 < z < 0.3 and with 14.5< u < 20.5. The signal-to-noise (S/N) ratio in the u-bandPetrosian aperture is improved by co-adding multiple epochs of imagingdata and by including sky-subtraction corrections. Luminosity functionsfor the near-UV 0.1u band (λ~ 322 +/- 26nm) aredetermined in redshift slices of width 0.02, which show a highlysignificant evolution in M* of -0.8 +/- 0.1 mag between z= 0 and 0.3;with M*-5 logh70=-18.84 +/- 0.05 (AB mag), logφ*=-2.06+/- 0.03 (h370Mpc-3) andlogρL= 19.11 +/- 0.02(h70WHz-1Mpc-3) at z= 0.1. Thefaint-end slope determined for z < 0.06 is given by α=-1.05 +/-0.08. This is in agreement with recent determinations from the GalaxyEvolution Explorer at shorter wavelengths. Comparing our z < 0.3luminosity density measurements with 0.2 < z < 1.2 fromClassifying Objects by Medium Band Observations in 17 Filters(COMBO-17), we find that the 280-nm density evolves asρL~ (1 +z)β with β= 2.1 +/- 0.2; andfind no evidence for any change in slope over this redshift range. Bycomparing with other measurements of cosmic star formation history, weestimate that the effective dust attenuation at 280nm has increased by0.8 +/- 0.3mag between z= 0 and 1.

Cosmic Homogeneity Demonstrated with Luminous Red Galaxies - Hogg, David W.; Eisenstein, Daniel J.; Blanton, Michael R.; Bahcall, Neta A.; Brinkmann, J.; Gunn, James E.; Schneider, Donald P. (The Astrophysical Journal, 2005)
We test the homogeneity of the universe at z~0.3 with the luminous redgalaxy (LRG) spectroscopic sample of the Sloan Digital Sky Survey.First, the mean number N(R) of LRGs within completely surveyedLRG-centered spheres of comoving radius R is shown to be proportional toR3 at radii greater than R~70h-1Mpc. The test hasthe virtue that it does not rely on the assumption that the LRG samplehas a finite mean density; its results show, however, that there is sucha mean density. Second, the survey sky area is divided into 10 disjointsolid angular regions, and the fractional rms density variations of theLRG sample in the redshift range 0.27h-3Mpc3) regions is found

Calibrating photometric redshifts of luminous red galaxies - Padmanabhan, Nikhil; Budavári, Tamás; Schlegel, David J.; Bridges, Terry; Brinkmann, Jonathan; Cannon, Russell; Connolly, Andrew J.; Croom, Scott M.; Csabai, István; Drinkwater, Michael; Eisenstein, Daniel J.; Hewett, Paul C.; et al. (Monthly Notices of the Royal Astronomical Society, 2005)
We discuss the construction of a photometric redshift catalogue ofluminous red galaxies (LRGs) from the Sloan Digital Sky Survey (SDSS),emphasizing the principal steps necessary for constructing such acatalogue: (i) photometrically selecting the sample, (ii) measuringphotometric redshifts and their error distributions, and (iii)estimating the true redshift distribution. We compare two photometricredshift algorithms for these data and find that they give comparableresults. Calibrating against the SDSS and SDSS-2dF (Two Degree Field)spectroscopic surveys, we find that the photometric redshift accuracy isσ~ 0.03 for redshifts less than 0.55 and worsens at higherredshift (~0.06 for z < 0.7). These errors are caused by photometricscatter, as well as systematic errors in the templates, filter curvesand photometric zero-points. We also parametrize the photometricredshift error distribution with a sum of Gaussians and use this modelto deconvolve the errors from the measured photometric redshiftdistribution to estimate the true redshift distribution. We pay specialattention to the stability of this deconvolution, regularizing themethod with a prior on the smoothness of the true redshift distribution.The methods that we develop are applicable to general photometricredshift surveys.

Discovery of a Fifth Image of the Large Separation Gravitationally Lensed Quasar SDSS J1004+4112 - Inada, Naohisa; Oguri, Masamune; Keeton, Charles R.; Eisenstein, Daniel J.; Castander, Francisco J.; Chiu, Kuenley; Hall, Patrick B.; Hennawi, Joseph F.; Johnston, David E.; Pindor, Bartosz; Richards, Gordon T.; Rix, Hans-Walter Rix; et al. (Publications of the Astronomical Society of Japan, 2005)
We report on the discovery of a fifth lensed image in the largeseparation lensed quasar system SDSS J1004 + 4112. A faint point sourcelocated 0.''2 from the center of the brightest galaxy in the lensingcluster was detected in images taken with the Advanced Camera forSurveys (ACS) and the Near Infrared Camera and Multi-Object Spectrometer(NICMOS) on the Hubble Space Telescope. The flux ratio between the pointsource and the brightest lensed component in the ACS image is similar tothat in the NICMOS image. The location and brightness of the pointsource are consistent with lens model predictions for a lensed image. Wetherefore conclude that the point source is likely to be a fifth lensedimage of the source quasar. In addition, the NICMOS image reveals thelensed host galaxy of the source quasar, which can strongly constrainthe structure of the lensing critical curves, and thereby the massdistribution of the lensing cluster.

Eleven New DA White Dwarf Variable Stars from the Sloan Digital Sky Survey - Mullally, F.; Thompson, S. E.; Castanheira, B. G.; Winget, D. E.; Kepler, S. O.; Eisenstein, D. J.; Kleinman, S. J.; Nitta, Atsuko (The Astrophysical Journal, 2005)
We report the discovery of 11 new variable DA white dwarf (ZZ Ceti)stars. Candidates were selected by deriving temperatures from model fitsto spectra obtained from the Sloan Digital Sky Survey (SDSS). We alsofind objects whose temperatures and gravities indicate they lie withinthe instability strip for pulsation but were not observed to vary.Although the temperatures are based on relatively low signal-to-noiseratio spectra, an impure strip is unexpected, which if confirmed, hasimplications for DA asteroseismology. This work brings the total numberof published variable DA white dwarf stars to 82.

The Near-Infrared Camera and Multi-Object Spectrometer Ultra Deep Field: Observations, Data Reduction, and Galaxy Photometry - Thompson, Rodger I.; Illingworth, Garth; Bouwens, Rychard; Dickinson, Mark; Eisenstein, Daniel; Fan, Xiaohui; Franx, Marijn; Riess, Adam; Rieke, Marcia J.; Schneider, Glenn; Stobie, Elizabeth; Toft, Sune; et al. (The Astronomical Journal, 2005)
This paper describes the observations and data reduction techniques forthe version 2.0 images and catalog of the Near-Infrared Camera andMulti-Object Spectrometer Ultra Deep Field (NICMOS UDF) Treasuryprogram. All sources discussed in this paper are based on detections inthe combined NICMOS F110W and F160W bands only. The NICMOS images aredrizzled to 0.09" pixel-1 and aligned to the Advanced Camerafor Surveys UDF F850LP image, which was rebinned to the same pixelscale. These form the NICMOS version 2.0 UDF images. The catalog sourcesare chosen with a conservative detection limit to avoid the inclusion ofnumerous spurious sources. The catalog contains 1293 objects in the144''×144'' NICMOS subfield of the UDF. The5 σ signal-to-noise ratio level is an average 0.6" diameteraperture AB magnitude of 27.7 at 1.1 and 1.6 μm. The catalog sources,listed in order of right ascension, satisfy a minimum signal-to-noiseratio criterion of 1.4 σ in at least seven contiguous pixels ofthe combined F110W and F160W image.

The Sloan Digital Sky Survey Quasar Catalog. III. Third Data Release - Schneider, Donald P.; Hall, Patrick B.; Richards, Gordon T.; Vanden Berk, Daniel E.; Anderson, Scott F.; Fan, Xiaohui; Jester, Sebastian; Stoughton, Chris; Strauss, Michael A.; SubbaRao, Mark; Brandt, W. N.; Gunn, James E.; et al. (The Astronomical Journal, 2005)
We present the third edition of the Sloan Digital Sky Survey (SDSS)Quasar Catalog. The catalog consists of the 46,420 objects in the SDSSThird Data Release that have luminosities larger than Mi=-22(in a cosmology with H0=70 km s-1Mpc-1, ΩM=0.3, andΩΛ=0.7), have at least one emission line withFWHM larger than 1000 km s-1 or are unambiguously broadabsorption line quasars, are fainter than i=15.0, and have highlyreliable redshifts. The area covered by the catalog is ~4188deg2. The quasar redshifts range from 0.08 to 5.41, with amedian value of 1.47; the high-redshift sample includes 520 quasars atredshifts greater than 4, of which 17 are at redshifts greater than 5.For each object the catalog presents positions accurate to better than0.2" rms per coordinate, five-band (ugriz) CCD-based photometry withtypical accuracy of 0.03 mag, and information on the morphology andselection method. The catalog also contains radio, near-infrared, andX-ray emission properties of the quasars, when available, from otherlarge-area surveys. The calibrated digital spectra cover the wavelengthregion 3800-9200 Å at a spectral resolution of ~=2000 the spectracan be retrieved from the public database using the information providedin the catalog. A total of 44,221 objects in the catalog were discoveredby the SDSS; 28,400 of the SDSS discoveries are reported here for thefirst time.

Magnetic White Dwarfs from the SDSS. II. The Second and Third Data Releases - Vanlandingham, Karen M.; Schmidt, Gary D.; Eisenstein, Daniel J.; Harris, Hugh C.; Anderson, Scott F.; Hall, Patrick B.; Liebert, James; Schneider, Donald P.; Silvestri, Nicole M.; Stinson, Gregory S.; Wolfe, Michael A. (The Astronomical Journal, 2005)
Fifty-two magnetic white dwarfs have been identified in spectroscopicobservations from the Sloan Digital Sky Survey (SDSS) obtained betweenmid-2002 and the end of 2004, including Data Releases 2 and 3. Althoughnot as numerous or diverse as the discoveries from the first datarelease, the collection exhibits polar field strengths ranging from 1.5to ~1000 MG and includes two new unusual atomic DQA examples, amolecular DQ, and five stars that show hydrogen in fields above 500 MG.The highest field example, SDSS J2346+3853, may be the most stronglymagnetic white dwarf yet discovered. Analysis of the photometric dataindicates that the magnetic sample spans the same temperature range asfor nonmagnetic white dwarfs from the SDSS, and support is found forprevious claims that magnetic white dwarfs tend to have larger massesthan their nonmagnetic counterparts. A glaring exception to this trendis the apparently low-gravity object SDSS J0933+1022, which may have ahistory involving a close binary companion.A portion of the results presented here were obtained with the MMTObservatory, a facility operated jointly by the University of Arizonaand the Smithsonian Institution.

Relationship between Environment and the Broadband Optical Properties of Galaxies in the Sloan Digital Sky Survey - Blanton, Michael R.; Eisenstein, Daniel; Hogg, David W.; Schlegel, David J.; Brinkmann, J. (The Astrophysical Journal, 2005)
We examine the relationship between environment and the luminosities,surface brightnesses, colors, and profile shapes of luminous galaxies inthe Sloan Digital Sky Survey (SDSS). For the SDSS sample, galaxy coloris the galaxy property most predictive of the local environment. Galaxycolor and luminosity-measures of the star formation history-jointlycomprise the most predictive pair of properties. At fixed luminosity andcolor, density is not closely related to surface brightness or toSérsic index-measures of galaxy structure. In the text, wediscuss what measurable residual relationships exist, generally findingthat at red colors and fixed luminosity, the mean density decreases atthe highest surface brightnesses and Sérsic indices. In general,these results suggest that the structural properties of galaxies areless closely related to galaxy environment than are their masses andstar formation histories.Based on observations obtained with the Sloan Digital Sky Survey.

Interpreting the Relationship between Galaxy Luminosity, Color, and Environment - Berlind, Andreas A.; Blanton, Michael R.; Hogg, David W.; Weinberg, David H.; Davé, Romeel; Eisenstein, Daniel J.; Katz, Neal (The Astrophysical Journal, 2005)
We study the relationship between galaxy luminosity, color, andenvironment in a cosmological simulation of galaxy formation. Using asimple prescription to assign colors and luminosities to simulatedgalaxies, we compare the predicted relationship with that observed forSDSS galaxies and find that the model successfully predicts most of thequalitative features seen in the data, but also shows some interestingdifferences. Specifically, the simulation predicts that the localdensity around bright red galaxies is a strong increasing function ofluminosity, but does not depend much on color at fixed luminosity.Moreover, we show that these trends are due to central galaxies in darkmatter halos whose baryonic masses correlate strongly with halo mass.The simulation also predicts that the local density around blue galaxiesis a strong increasing function of color, but does not depend much onluminosity at fixed color. We show that these trends are due tosatellite galaxies in halos whose stellar ages correlate with halo mass.Finally, the simulation fails to predict the luminosity dependence ofenvironments observed around low-luminosity red galaxies. However, weshow that this is most likely due to the simulation's limitedresolution. A study of a higher resolution, smaller volume simulationsuggests that this dependence is caused by the fact that alllow-luminosity red galaxies are satellites in massive halos, whereasintermediate-luminosity red galaxies are a mixture of satellites inmassive halos, and central galaxies in less massive halos.

A Deep-Field Infrared Observatory Near the Lunar Pole - Borra, E. F.; Seddiki, O.; Angel, J. R. P.; Worden, S. P.; Eisenstein, D.; Silvanandam, S.; Hickson, P.; Ma, K. (Journal of the Royal Astronomical Society of Canada, 2005)
A study has been made of the feasibility and scientific potential of a20-to 100-m aperture astronomical telescope at the lunar pole, with itsprimary mirror made of spinning liquid at < 100 K. Such a telescope,equipped with imaging and multiplexed spectroscopic instruments for adeep-infrared survey, would be revolutionary in its power to study thedistant Universe, including the formation of the first stars and theirassembly into galaxies. Our study explored the scientific opportunities,key technologies, and optimum location of such a Lunar Liquid MirrorTelescope (LLMT). An optical design for a 20- m telescope withdiffraction limited imaging over a 15-arcminute field has beendeveloped. It would be used to follow up on discoveries made with the6-m James Webb Space Telescope, with more detailed images andspectroscopic studies, as well as to detect objects 100 times fainter,such as the first high-redshift star in the early Universe. Amodel wasmade of a liquid mirror spinning on a superconducting bearing, as willbe needed for the cryogenic, vacuum environment of the LLMT. Reflectivesilver coatings have been deposited for the first time on a liquidsurface, needed to make infrared mirrors at ~80 K. Issues relating topolar locations have been explored. Dust on the optics or in a thinatmosphere, though unlikely to be problematic at the poles, should beinvestigated in-situ. Issues relating to polar locations have beenexplored. Locations at or within a few km of a pole are preferred fordeep-sky cover, and allow for long integration times by simpleinstrument rotation. This revolutionary mission concept could provide ascientific focus to NASA's planned exploration of the Moon, just ascurrently HST stands as a major achievement of its Shuttle Program.

Mid-Infrared Selection of Active Galaxies - Stern, Daniel; Eisenhardt, Peter; Gorjian, Varoujan; Kochanek, Christopher S.; Caldwell, Nelson; Eisenstein, Daniel; Brodwin, Mark; Brown, Michael J. I.; Cool, Richard; Dey, Arjun; Green, Paul; Jannuzi, Buell T.; et al. (The Astrophysical Journal, 2005)
Mid-infrared photometry provides a robust technique for identifyingactive galaxies. While the ultraviolet to mid-infrared (λ<~5μm) continuum of stellar populations is dominated by the compositeblackbody curve and peaks at approximately 1.6 μm, the ultraviolet tomid-infrared continuum of active galactic nuclei (AGNs) is dominated bya power law. Consequently, with a sufficient wavelength baseline, onecan easily distinguish AGNs from stellar populations. Mirroring thetendency of AGNs to be bluer than galaxies in the ultraviolet, wheregalaxies (and stars) sample the blue, rising portion of stellar spectra,AGNs tend to be redder than galaxies in the mid-infrared, where galaxiessample the red, falling portion of the stellar spectra. We report onSpitzer Space Telescope mid-infrared colors, derived from the IRACShallow Survey, of nearly 10,000 spectroscopically identified sourcesfrom the AGN and Galaxy Evolution Survey. On the basis of thisspectroscopic sample, we find that simple mid-infrared color criteriaprovide remarkably robust separation of active galaxies from normal

Discovery of fourteen new ZZ Cetis with SOAR - Kepler, S. O.; Castanheira, B. G.; Saraiva, M. F. O.; Nitta, A.; Kleinman, S. J.; Mullally, F.; Winget, D. E.; Eisenstein, D. J. (Astronomy and Astrophysics, 2005)
We report the discovery of fourteen new ZZ Cetis with the 4.1 m SouthernAstrophysical Research telescope, at Cerro Pachon, in Chile. Thecandidates were selected from the SDSS (Sloan Digital Sky Survey) DAwhite dwarf stars with Teff obtained from the optical spectrafit, inside the ZZ Ceti instability strip. Considering these stars aremulti-periodic pulsators and the pulsations propagate to the nucleus ofthe star, they carry information on the structure of the star andevolution of the progenitors. The ZZ Cetis discovered till 2003 aremainly within 100 pc from the Sun, and probe only the solar vicinity.The recently discovered ones, and those reported here, may sample adistinct population as they were selected mainly perpendicular to thegalactic disk and cover a distance up to ≈ 400 pc.

SDSS J024634.11-082536.2: A New Gravitationally Lensed Quasar from the Sloan Digital Sky Survey - Inada, Naohisa; Burles, Scott; Gregg, Michael D.; Becker, Robert H.; Schechter, Paul L.; Eisenstein, Daniel J.; Oguri, Masamune; Castander, Francisco J.; Hall, Patrick B.; Johnston, David E.; Pindor, Bartosz; Richards, Gordon T.; et al. (The Astronomical Journal, 2005)
We report the discovery of a new two-image gravitationally lensedquasar, SDSS J024634.11-082536.2 (SDSS J0246-0825). This object wasselected as a lensed quasar candidate from the Sloan Digital Sky Survey(SDSS) by the same algorithm that was used to discover other SDSS lensedquasars (e.g., SDSS J0924+0219). Multicolor imaging with the MagellanConsortium's Walter Baade 6.5 m telescope and spectroscopic observationsusing the W. M. Keck Observatory's Keck II telescope confirm that SDSSJ0246-0825 consists of two lensed images (Δθ=1.04") of asource quasar at z=1.68. Imaging observations with the Keck I telescopeand the Hubble Space Telescope reveal an extended object between the twoquasar components, which is likely to be a lensing galaxy of thissystem. From the absorption lines in the spectra of the quasarcomponents and the apparent magnitude of the galaxy, combined with theexpected absolute magnitude from the Faber-Jackson relation, we estimatethe redshift of the lensing galaxy to be z=0.724. A highly distortedring is visible in the Hubble Space Telescope images, which is likely tobe the lensed host galaxy of the source quasar. Simple mass modelingpredicts the possibility that there is a small (faint) lensing objectnear the primary lensing galaxy.Based on observations with the NASA/ESA Hubble Space Telescope, obtainedat the Space Telescope Science Institute, which is operated by theAssociation of Universities for Research in Astronomy (AURA), Inc.,under NASA contract NAS5-26555. These observations are associated withHST program 9744.

Detection of the Baryon Acoustic Peak in the Large-Scale Correlation Function of SDSS Luminous Red Galaxies - Eisenstein, Daniel J.; Zehavi, Idit; Hogg, David W.; Scoccimarro, Roman; Blanton, Michael R.; Nichol, Robert C.; Scranton, Ryan; Seo, Hee-Jong; Tegmark, Max; Zheng, Zheng; Anderson, Scott F.; Annis, Jim; et al. (The Astrophysical Journal, 2005)
We present the large-scale correlation function measured from aspectroscopic sample of 46,748 luminous red galaxies from the SloanDigital Sky Survey. The survey region covers 0.72 h-3Gpc3 over 3816 deg2 and 0.16-1 Mpcseparation that is an excellent match to the predicted shape andlocation of the imprint of the recombination-epoch acoustic oscillationson the low-redshift clustering of matter. This detection demonstratesthe linear growth of structure by gravitational instability betweenz~1000 and the present and confirms a firm prediction of the standardcosmological theory. The acoustic peak provides a standard ruler bywhich we can measure the ratio of the distances to z=0.35 and z=1089 to

Baryonic Acoustic Oscillations in Simulated Galaxy Redshift Surveys - Seo, Hee-Jong; Eisenstein, Daniel J. (The Astrophysical Journal, 2005)
Baryonic acoustic oscillations imprinted in the galaxy power spectrumprovide a promising tool for probing the cosmological distance scale anddark energy. We present results from a suite of cosmological N-bodysimulations aimed at investigating possible systematic errors in therecovery of cosmological distances. We show the robustness of baryonicpeaks against nonlinearity, redshift distortions, and mild biases withinthe linear and quasi-linear regime at various redshifts. While mildlybiased tracers follow the matter power spectrum well, redshiftdistortions do partially obscure baryonic features in redshift spacecompared to real space. We calculate the statistical constraints oncosmological distortions from N-body results and compare these to theanalytic results from a Fisher matrix formalism. We conclude that theangular diameter distance will be constrained as well as in our previousFisher matrix calculations while the Hubble parameter will be lessconstrained because of nonlinear redshift distortions.

Dark energy and cosmic sound [review article] - Eisenstein, D. J. (New Astronomy Reviews, 2005)
I describe how acoustic oscillations imprinted into the late-timecorrelations of galaxies by baryonic physics at the epoch ofrecombination can be used as a cosmological standard ruler. Measurementsof this length scale by large galaxy surveys would allow us to computethe angular diameter distance to and Hubble parameter at the redshiftsof the survey. This in turn offers a robust way to measure theacceleration of the universe. I briefly present calculations of thestatistical performance from baseline surveys; full details of themethods and results are available in Seo and Eisenstein [ApJ, 598 (2003)720]. I discuss the advantages and disadvantages of the acousticoscillation method relative to other dark energy probes.

Lyα flux power spectrum and its covariance - Zhan, Hu; Davé, Romeel; Eisenstein, Daniel; Katz, Neal (Monthly Notices of the Royal Astronomical Society, 2005)
We analyse the flux power spectrum and its covariance using simulatedLyα forests. We find that pseudo-hydro techniques are goodapproximations of hydrodynamical simulations at high redshift. However,the pseudo-hydro techniques fail at low redshift because they areinsufficient for characterizing some components of the low-redshiftintergalactic medium, notably the warm-hot intergalactic medium. Hence,to use the low-redshift Lyα flux power spectrum to constraincosmology, one would need realistic hydrodynamical simulations. Bycomparing (one-dimensional) mass statistics with flux statistics, weshow that the non-linear transform between density and flux quenches thefluctuations so that the flux power spectrum is much less sensitive tocosmological parameters than the one-dimensional mass power spectrum.The covariance of the flux power spectrum is nearly Gaussian. As such,the uncertainties of the underlying mass power spectrum could still belarge, even though the flux power spectrum can be precisely determinedfrom a small number of lines of sight.

The Dependence on Environment of the Color-Magnitude Relation of Galaxies - Hogg, David W.; Blanton, Michael R.; Brinchmann, Jarle; Eisenstein, Daniel J.; Schlegel, David J.; Gunn, James E.; McKay, Timothy A.; Rix, Hans-Walter; Bahcall, Neta A.; Brinkmann, J.; Meiksin, Avery (The Astrophysical Journal Letters, 2004)
The distribution in color and absolute magnitude is presented for 55,158galaxies taken from the Sloan Digital Sky Survey in the redshift range0.08-1 Mpc and line-of-sighthalf-length 8 h-1 Mpc. In all environments, bulge-dominatedgalaxies (defined to be those with radial profiles best fitted withlarge Sérsic indices) have a color-magnitude diagram dominated byred galaxies for which the mode of the color distribution at fixedabsolute magnitude depends linearly on absolute magnitude. Although themost luminous galaxies reside preferentially in high-density regions andblue galaxies reside preferentially in low-density regions, there isonly a barely detectable variation with overdensity in the color (zeropoint) or slope of the linear relation between the mode color andluminosity [<0.02 mag in 0.1(g-r) or (B-V)]. These resultsconstrain variations with environmental density in the ages or

Selection and Photometric Properties of K+A Galaxies - Quintero, Alejandro D.; Hogg, David W.; Blanton, Michael R.; Schlegel, David J.; Eisenstein, Daniel J.; Gunn, James E.; Brinkmann, J.; Fukugita, Masataka; Glazebrook, Karl; Goto, Tomotsugu (The Astrophysical Journal, 2004)
Two different simple measurements of galaxy star formation rate withdifferent timescales are compared empirically on 156,395 fiber spectraof galaxies with r<17.77 mag taken from the Sloan Digital Sky Surveyin the redshift range 0.05-4h3Mpc-3Gyr-1 atredshift z~0.1. These events are taking place in the field; the K+Agalaxies found in this study do not primarily lie in the high-densityenvironments or clusters typical of bulge-dominated populations.

A Snapshot Survey for Gravitational Lenses among z>=4.0 Quasars. I. The z>5.7 Sample - Richards, Gordon T.; Strauss, Michael A.; Pindor, Bartosz; Haiman, Zoltán; Fan, Xiaohui; Eisenstein, Daniel; Schneider, Donald P.; Bahcall, Neta A.; Brinkmann, J.; Brunner, Robert (The Astronomical Journal, 2004)
Over the last few years, the Sloan Digital Sky Survey (SDSS) hasdiscovered several hundred quasars with redshift between 4.0 and 6.4.Including the effects of magnification bias, one expects a priori thatan appreciable fraction of these objects are gravitationally lensed. Wehave used the Advanced Camera for Surveys on the Hubble Space Telescopeto carry out a snapshot imaging survey of high-redshift SDSS quasars tosearch for gravitationally split lenses. This paper, the first in aseries reporting the results of the survey, describes snapshotobservations of four quasars at z=5.74, 5.82, 5.99, and 6.30,respectively. We find that none of these objects has a lensed companionwithin 5 mag with a separation larger than 0.3" within 2.5 mag we canrule out companions within 0.1". Based on the nondetection of stronglensing in these four systems, we constrain the z~6 luminosity functionto a slope of β>-4.63 (3 σ), assuming a break in thequasar luminosity function at M*1450=-24.1. Wediscuss the implications of this constraint on the ionizing backgrounddue to quasars in the early universe. Given that these quasars are nothighly magnified, estimates of the masses of their central engines bythe Eddington argument must be taken seriously, possibly challengingmodels of black hole formation.

SDSS J115517.35+634622.0: A Newly Discovered Gravitationally Lensed Quasar - Pindor, Bart; Eisenstein, Daniel J.; Inada, Naohisa; Gregg, Michael D.; Becker, Robert H.; Brinkmann, Jon; Burles, Scott; Frieman, Joshua A.; Johnston, David E.; Richards, Gordon T.; Schneider, Donald P.; Scranton, Ryan; et al. (The Astronomical Journal, 2004)
We report the discovery of SDSS J115517.35+634622.0, a previouslyunknown gravitationally lensed quasar. The lens system exhibits twoimages of a z=2.89 quasar, with an image separation of 1.832"+/-0.007".Near-IR imaging of the system reveals the presence of the lensing galaxybetween the two quasar images. Based on absorption features seen in theSloan Digital Sky Survey (SDSS) spectrum, we determine a lens galaxyredshift of z=0.1756. The lens is rather unusual in that one of thequasar images is only 0.22"+/-0.07" (~0.1 Reff) from thecenter of the lens galaxy, and photometric modeling indicates that thisimage is significantly brighter than predicted by a SIS model. Thissystem was discovered in the course of an ongoing search for stronglylensed quasars in the data set from the SDSS.

Sloan Digital Sky Survey Spectroscopic Lens Search. I. Discovery of Intermediate-Redshift Star-forming Galaxies behind Foreground Luminous Red Galaxies - Bolton, Adam S.; Burles, Scott; Schlegel, David J.; Eisenstein, Daniel J.; Brinkmann, J. (The Astronomical Journal, 2004)
We present a catalog of 49 spectroscopic strong gravitational lenscandidates selected from a Sloan Digital Sky Survey sample of 50,996luminous red galaxies. Potentially lensed star-forming galaxies aredetected through the presence of background oxygen and hydrogen nebularemission lines in the spectra of these massive foreground galaxies. Thismultiline selection eliminates the ambiguity of single-lineidentification and provides a very promising sample of candidategalaxy-galaxy lens systems at low to intermediate redshift, withforeground redshifts ranging from 0.16 to 0.49 and background redshiftsfrom 0.25 to 0.81. Any lenses confirmed within our sample would beimportant new probes of early-type galaxy mass distributions, providingcomplementary constraints to those obtained from currently known lensedhigh-redshift quasars.Based in part on observations obtained with the 6.5 m Clay telescope ofthe Magellan Consortium.

Observations and Theoretical Implications of the Large-Separation Lensed Quasar SDSS J1004+4112 - Oguri, Masamune; Inada, Naohisa; Keeton, Charles R.; Pindor, Bartosz; Hennawi, Joseph F.; Gregg, Michael D.; Becker, Robert H.; Chiu, Kuenley; Zheng, Wei; Ichikawa, Shin-ichi; Suto, Yasushi; Turner, Edwin L.; et al. (The Astrophysical Journal, 2004)
We study the recently discovered gravitational lens SDSS J1004+4112, thefirst quasar lensed by a cluster of galaxies. It consists of four imageswith a maximum separation of 14.62". The system was selected from thephotometric data of the Sloan Digital Sky Survey (SDSS) and has beenconfirmed as a lensed quasar at z=1.734 on the basis of deep imaging andspectroscopic follow-up observations. We present color-magnituderelations for galaxies near the lens plus spectroscopy of three centralcluster members, which unambiguously confirm that a cluster at z=0.68 isresponsible for the large image separation. We find a wide range of lensmodels consistent with the data, and despite considerable diversity theysuggest four general conclusions: (1) the brightest cluster galaxy andthe center of the cluster potential well appear to be offset by severalkiloparsecs; (2) the cluster mass distribution must be elongated in thenorth-south direction, which is consistent with the observeddistribution of cluster galaxies; (3) the inference of a large tidalshear (~0.2) suggests significant substructure in the cluster; and (4)enormous uncertainty in the predicted time delays between the imagesmeans that measuring the delays would greatly improve constraints on themodels. We also compute the probability of such large-separation lensingin the SDSS quasar sample on the basis of the cold dark matter model.The lack of large-separation lenses in previous surveys and thediscovery of one in SDSS together imply a mass fluctuation normalization

SDSS J1335+0118: A New Two-Image Gravitational Lens - Oguri, Masamune; Inada, Naohisa; Castander, Francisco J.; Gregg, Michael D.; Becker, Robert H.; Ichikawa, Shin-ichi; Pindor, Bartosz; Brinkmann, Jonathan; Eisenstein, Daniel J.; Frieman, Joshua A.; Hall, Patrick B.; Johnston, David E.; et al. (Publications of the Astronomical Society of Japan, 2004)
We report on the discovery of the two-image gravitationally lensedquasar SDSSJ1335 + 0118. The object was selected as a lens candidatefrom the Sloan Digital Sky Survey. The imaging and spectroscopicfollow-up observations confirm that the system exhibits twogravitationally lensed images of a quasar at z = 1.57. The imageseparation is 1''.56. We also detect an extended component between thetwo quasar images, likely to be a lensing galaxy. Preliminary massmodeling predicts a differential time delay, Δt of ˜30h-1 day, assuming the redshift of the lens galaxy to be 0.5.

The Three-Dimensional Power Spectrum of Galaxies from the Sloan Digital Sky Survey - Tegmark, Max; Blanton, Michael R.; Strauss, Michael A.; Hoyle, Fiona; Schlegel, David; Scoccimarro, Roman; Vogeley, Michael S.; Weinberg, David H.; Zehavi, Idit; Berlind, Andreas; Budavari, Tamás; Connolly, Andrew; et al. (The Astrophysical Journal, 2004)
We measure the large-scale real-space power spectrum P(k) by using asample of 205,443 galaxies from the Sloan Digital Sky Survey, covering2417 effective square degrees with mean redshift z~0.1. We employ amatrix-based method using pseudo-Karhunen-Loève eigenmodes,producing uncorrelated minimum-variance measurements in 22 k-bands ofboth the clustering power and its anisotropy due to redshift-spacedistortions, with narrow and well-behaved window functions in the range0.02hMpc-1-1. We pay particularattention to modeling, quantifying, and correcting for potentialsystematic errors, nonlinear redshift distortions, and the artificialred-tilt caused by luminosity-dependent bias. Our results are robust toomitting angular and radial density fluctuations and are consistentbetween different parts of the sky. Our final result is a measurement ofthe real-space matter power spectrum P(k) up to an unknown overallmultiplicative bias factor. Our calculations suggest that this biasfactor is independent of scale to better than a few percent fork<0.1hMpc-1, thereby making our results useful forprecision measurements of cosmological parameters in conjunction withdata from other experiments such as the Wilkinson Microwave AnisotropyProbe satellite. The power spectrum is not well-characterized by asingle power law but unambiguously shows curvature. As a simplecharacterization of the data, our measurements are well fitted by a flatscale-invariant adiabatic cosmological model withhΩm=0.213+/-0.023 and σ8=0.89+/-0.02for L* galaxies, when fixing the baryon fractionΩb/Ωm=0.17 and the Hubble parameterh=0.72; cosmological interpretation is given in a companion paper.

Star Formation at z ~ 6: The Hubble Ultra Deep Parallel Fields - Bouwens, R. J.; Illingworth, G. D.; Thompson, R. I.; Blakeslee, J. P.; Dickinson, M. E.; Broadhurst, T. J.; Eisenstein, D. J.; Fan, X.; Franx, M.; Meurer, G.; van Dokkum, P. (The Astrophysical Journal Letters, 2004)
We report on the i-dropouts detected in two exceptionally deep AdvancedCamera for Surveys fields (B435, V606,i775, and z850 with 10σ limits of 28.8,29.0, 28.5, and 27.8, respectively) taken in parallel with the UltraDeep Field Near-Infrared Camera and Multi-Object Spectrometerobservations. Using an i-z>1.4 cut, we find 30 i-dropouts over 21arcmin2 down to z850,AB=28.1, or 1.4 i-dropoutsarcmin-2, with significant field-to-field variation (asexpected from cosmic variance). This extends i-dropout searches some~0.9 mag further down the luminosity function than was possible in theGreat Observatories Origins Deep Survey (GOODS) fields, yielding a ~7times increase in surface density. An estimate of the size evolution forUV-bright objects is obtained by comparing the composite radial fluxprofile of the bright i-dropouts (z850,AB<27.2) withscaled versions of the Hubble Deep Field-North and -South U-dropouts.The best fit is found with a(1+z)-1.57+0.50-0.53 scaling in size(for fixed luminosity), extending lower redshift (1-2.8 innumber and (1+z)0.1 in luminosity, suggesting a rest-framecontinuum UV luminosity density at z~6 that is just0.38+0.09-0.07 times that at z~3.8. Our inclusionof the size evolution makes the present estimate lower than previous z~6estimates.Based on observations made with the NASA/ESA Hubble Space Telescope,which is operated by the Association of Universities for Research inAstronomy, Inc., under NASA contract NAS5-26555. These observations areassociated with program 9803.

A Helium White Dwarf of Extremely Low Mass - Liebert, James; Bergeron, P.; Eisenstein, Daniel; Harris, H. C.; Kleinman, S. J.; Nitta, Atsuko; Krzesinski, Jurek (The Astrophysical Journal Letters, 2004)
We analyze the spectrum of an unusually low mass white dwarf, SDSSJ123410.37-022802.9 (0335-264-52000), found in our recent, white dwarfcatalog from the first data release (DR1) of the Sloan Digital SkySurvey (SDSS). Two independent, model atmosphere fits result in anaccurate determination of atmospheric and stellar parameters. The morehands-on analysis yields Teff=17,470+/-750 K andlogg=6.38+/-0.05. We argue that the object cannot be a main-sequence Astar, a horizontal-branch star, or a subdwarf B star. Instead, it isinterpreted as a very low mass white dwarf with a core composed ofhelium, with mass ~0.18-0.19 Msolar, similar to thatpublished previously for the unusual companion to the millisecond pulsarJ1012+5307. The star probably remains in a binary, perhaps even with anundiscovered or dead pulsar companion. However, the companion might be amore ordinary star, provided Roche lobe mass transfer began shortlyafter the now-visible component left the main sequence. A second SDSSlow-mass white dwarf candidate is also analyzed, but the spectrum forthis fainter object is of poorer quality. The sample appears to includeadditional, similar candidates, worthy of more accurate observation.Correct identification of any additional white dwarfs of extremely lowmass requires careful observation and interpretation.

A Catalog of Spectroscopically Identified White Dwarf Stars in the First Data Release of the Sloan Digital Sky Survey - Kleinman, S. J.; Harris, Hugh C.; Eisenstein, Daniel J.; Liebert, James; Nitta, Atsuko; Krzesiński, Jurek; Munn, Jeffrey A.; Dahn, Conard C.; Hawley, Suzanne L.; Pier, Jeffrey R.; Schmidt, Gary; Silvestri, Nicole M.; et al. (The Astrophysical Journal, 2004)
We present the full spectroscopic white dwarf and hot subdwarf samplefrom the Sloan Digital Sky Survey (SDSS) first data release, DR1. Wefind 2551 white dwarf stars of various types, 240 hot subdwarf stars,and an additional 144 objects we have identified as uncertain whitedwarf stars. Of the white dwarf stars, 1888 are nonmagnetic DA types and171 are nonmagnetic DBs. The remaining (492) objects consist of alldifferent types of white dwarf stars: DO, DQ, DC, DH, DZ, hybrid starssuch as DAB, etc., and those with nondegenerate companions. We fit theDA and DB spectra with a grid of models to determine the Teffand logg for each object. For all objects, we provide coordinates,proper motions, SDSS photometric magnitudes, and enough information toretrieve the spectrum/image from the SDSS public database. This catalognearly doubles the known sample of spectroscopically identified whitedwarf stars. In the DR1 imaged area of the sky, we increase the knownsample of white dwarf stars by a factor of 8.5. We also comment onseveral particularly interesting objects in this sample.

Cosmological parameters from SDSS and WMAP - Tegmark, Max; Strauss, Michael A.; Blanton, Michael R.; Abazajian, Kevork; Dodelson, Scott; Sandvik, Havard; Wang, Xiaomin; Weinberg, David H.; Zehavi, Idit; Bahcall, Neta A.; Hoyle, Fiona; Schlegel, David; et al. (Physical Review D, 2004)
We measure cosmological parameters using the three-dimensional powerspectrum P(k) from over 200 000 galaxies in the Sloan Digital Sky Survey(SDSS) in combination with Wilkinson Microwave Anisotropy Probe (WMAP)and other data. Our results are consistent with a “vanilla”flat adiabatic cold dark matter model with a cosmological constantwithout tilt (ns=1), running tilt, tensor modes, or massiveneutrinos. Adding SDSS information more than halves the WMAP-only errorbars on some parameters, tightening 1σ constraints on the Hubbleparameter from h≈0.74+0.18-0.07 toh≈0.70+0.04-0.03, on the matter density fromΩm≈0.25±0.10 toΩm≈0.30±0.04 (1σ) and on neutrino

Cosmological Parameters from Eigenmode Analysis of Sloan Digital Sky Survey Galaxy Redshifts - Pope, Adrian C.; Matsubara, Takahiko; Szalay, Alexander S.; Blanton, Michael R.; Eisenstein, Daniel J.; Gray, Jim; Jain, Bhuvnesh; Bahcall, Neta A.; Brinkmann, Jon; Budavari, Tamas; Connolly, Andrew J.; Frieman, Joshua A.; et al. (The Astrophysical Journal, 2004)
We present estimates of cosmological parameters from the application ofthe Karhunen-Loève transform to the analysis of thethree-dimensional power spectrum of density fluctuations using SloanDigital Sky Survey galaxy redshifts. We use Ωmh andfb=Ωb/Ωm to describe theshape of the power spectrum, σL8g for the(linearly extrapolated) normalization, and β to parameterize lineartheory redshift-space distortions. On scales k<~0.16hMpc-1, our maximum likelihood values areΩmh=0.264+/-0.043, fb=0.286+/-0.065,σL8g=0.966+/-0.048, and β=0.45+/-0.12.When we take a prior on Ωb from the Wilkinson MicrowaveAnisotropy Probe (WMAP), we find Ωmh=0.207+/-0.030,which is in excellent agreement with WMAP and the Two-Degree Field. Thisindicates that we have reasonably measured the gross shape of the powerspectrum, but we have difficulty breaking the degeneracy betweenΩmh and fb, because the baryon oscillationsare not resolved in the current spectroscopic survey window function.

The Second Data Release of the Sloan Digital Sky Survey - Abazajian, Kevork; Adelman-McCarthy, Jennifer K.; Agüeros, Marcel A.; Allam, Sahar S.; Anderson, Kurt; Anderson, Scott F.; Annis, James; Bahcall, Neta A.; Baldry, Ivan K.; Bastian, Steven; Berlind, Andreas; Bernardi, Mariangela; et al. (The Astronomical Journal, 2004)
The Sloan Digital Sky Survey (SDSS) has validated and made publiclyavailable its Second Data Release. This data release consists of 3324deg2 of five-band (ugriz) imaging data with photometry forover 88 million unique objects, 367,360 spectra of galaxies, quasars,stars, and calibrating blank sky patches selected over 2627deg2 of this area, and tables of measured parameters from

A Quasar without Broad Lyα Emission - Hall, Patrick B.; Snedden, Stephanie A.; Niederste-Ostholt, Martin; Eisenstein, Daniel J.; Strauss, Michael A.; York, Donald G.; Schneider, Donald P. (The Astronomical Journal, 2004)
The z=3.02 quasar SDSS J095253.83+011421.9 exhibits broad metal-lineemission (C IV FWHM~=9000 km s-1), but broad Lyαemission is not present. Instead, only a narrow Lyα line isobserved (FWHM~=1140 km s-1). The large CIV/Lyα ratioin the broad-line region (BLR) emission from this object can be matchedmost closely by a BLR dominated by gas at very high densities(1015 cm-3), which suppresses the Lyαemission, and illuminated by an incident power law extending to ~200μm, which yields increased emission from purely collisionally excitedcoolant lines (such as C IV, N V, and O VI) but not from recombinationlines like Lyα. However, the strong C III emission predicted bythis model is not observed, and the observed broad C III] emission mustcome from a lower density BLR component and should be accompanied bybroad Lyα emission, which is not observed. The least unlikelyexplanation for this spectrum seems to be that any intrinsic broadLyα emission is removed by smooth N V absorption in the red wingof the Lyα emission line and by smooth Lyα absorption in theblue wing of the Lyα emission line. This postulated smoothabsorption would be in addition to the strong, associated, narrowabsorption seen in numerous ions. Smooth absorption in Lyα, N V,and O VI, but not in C IV, would be unusual, but not impossible,although it is suspicious that the postulated absorption must almostexactly cancel the postulated intrinsic broad emission. We conclude thatthe spectrum of SDSS J0952+0114 appears unique (among ~=3600 SDSSspectra of quasars at z>2.12) because of some combination of unusualparameters, and we discuss possible observations to determine thecombination of circumstances responsible for the spectrum.

SDSS data management and photometric quality assessment - Ivezić, Ž.; Lupton, R. H.; Schlegel, D.; Boroski, B.; Adelman-McCarthy, J.; Yanny, B.; Kent, S.; Stoughton, C.; Finkbeiner, D.; Padmanabhan, N.; Rockosi, C. M.; Gunn, J. E.; et al. (Astronomische Nachrichten, 2004)
We summarize the Sloan Digital Sky Survey data acquisition andprocessing steps, and describe runQA, a pipeline designed for automateddata quality assessment. In particular, we show how the position of thestellar locus in color-color diagrams can be used to estimate theaccuracy of photometric zeropoint calibration to better than 0.01 mag in0.03 deg2 patches. Using this method, we estimate thattypical photometric zeropoint calibration errors for SDSS imaging dataare not larger than ˜0.01 mag in the g, r, and i bands, 0.02 magin the z band, and 0.03 mag in the u band (root-mean-scatter forzeropoint offsets).

Sloan Digital Sky Survey Imaging of Low Galactic Latitude Fields: Technical Summary and Data Release - Finkbeiner, Douglas P.; Padmanabhan, Nikhil; Schlegel, David J.; Carr, Michael A.; Gunn, James E.; Rockosi, Constance M.; Sekiguchi, Maki; Lupton, Robert H.; Knapp, G. R.; Ivezić, Željko; Blanton, Michael R.; Hogg, David W.; et al. (The Astronomical Journal, 2004)
The Sloan Digital Sky Survey (SDSS) mosaic camera and telescope haveobtained five-band optical-wavelength imaging near the Galactic planeoutside of the nominal survey boundaries. These additional data wereobtained during commissioning and subsequent testing of the SDSSobserving system, and they provide unique wide-area imaging data inregions of high obscuration and star formation, including numerous youngstellar objects, Herbig-Haro objects, and young star clusters. Becausethese data are outside the survey regions in the Galactic caps, they arenot part of the standard SDSS data releases. This paper presents imagingdata for 832 square degrees of sky (including repeats), in thestar-forming regions of Orion, Taurus, and Cygnus. About 470deg2 are now released to the public, with the remainder tofollow at the time of SDSS Data Release 4. The public data in Orioninclude the star-forming region NGC 2068/NGC 2071/HH 24 and a large partof Barnard's loop.

A Second Stellar Color Locus: a Bridge from White Dwarfs to M stars - Smolčić, Vernesa; Ivezić, Željko; Knapp, Gillian R.; Lupton, Robert H.; Pavlovski, Krešimir; Ilijić, Saša; Schlegel, David; Smith, J. Allyn; McGehee, Peregrine M.; Silvestri, Nicole M.; Hawley, Suzanne L.; Rockosi, Constance; et al. (The Astrophysical Journal Letters, 2004)
We report the discovery of a locus of binary stars in the Sloan DigitalSky Survey (SDSS) g-r versus u-g color-color diagram that connects thecolors of white dwarfs and M dwarfs. While its contrast with respect tothe main stellar locus is only ~1:2300, this previously unrecognizedfeature includes 863 stars from the SDSS Data Release 1 (DR1). Theposition and shape of the feature are in good agreement with predictionsof a simple binary star model that consists of a white dwarf and an Mdwarf, with the components' luminosity ratio controlling the positionalong this binary system locus. SDSS DR1 spectra for 47 of these objectsstrongly support this model. The absolute magnitude-color distributioninferred for the white dwarf component is in good agreement with themodels of Bergeron et al.

Theoretical uncertainty in baryon oscillations - Eisenstein, Daniel; White, Martin (Physical Review D, 2004)
We discuss the systematic uncertainties in the recovery of dark energyproperties from the use of baryon acoustic oscillations as a standardruler. We demonstrate that while unknown relativistic components in theuniverse prior to recombination would alter the sound speed, theinferences for dark energy from low-redshift surveys are unchanged solong as the microwave background anisotropies can measure the redshiftof matter-radiation equality, which they can do to sufficient accuracy.The mismeasurement of the radiation and matter densities themselves (asopposed to their ratio) would manifest as an incorrect prediction forthe Hubble constant at low-redshift. In addition, these anomalies doproduce subtle but detectable features in the microwave anisotropies.

Galaxies at z~7-8: z850-Dropouts in the Hubble Ultra Deep Field - Bouwens, R. J.; Thompson, R. I.; Illingworth, G. D.; Franx, M.; van Dokkum, P. G.; Fan, X.; Dickinson, M. E.; Eisenstein, D. J.; Rieke, M. J. (The Astrophysical Journal Letters, 2004)
We have detected likely z~7-8 galaxies in the144''×144'' Near-Infrared Camera andMulti-Object Spectrometer (NICMOS) observations of the Hubble Ultra DeepField. Objects are required to be >=3 σ detections in bothNICMOS bands, J110 and H160. The selectioncriteria for this sample are(z850-J110)AB>0.8,(z850-J110)AB>0.66(J110-H160)AB+0.8,(J110-H160)AB<1.2 and no detectionat less than 8500 Å. The five selected sources have totalmagnitudes H160,AB~27. Four of the five sources are quiteblue compared to typical lower redshift dropout galaxies and areclustered within a 1 arcmin2 region. Because all five sourcesare near the limit of the NICMOS data, we have carefully evaluated theirreality. Each of the candidates is visible in different splits of thedata and a median stack. We analyzed several noise images and estimatethe number of spurious sources to be 1+/-1. A search using anindependent reduction of this same data set clearly revealed three ofthe five candidates and weakly detected a fourth candidate, suggestingthat the contamination could be higher. For comparison with predictionsfrom lower redshift samples, we take a conservative approach and adoptfour z~7-8 galaxies as our sample. With the same detection criteria onsimulated data sets, assuming no evolution from z~3.8, we predict 10sources at z~7-8, or 14 if we use a more realistic (1+z)-1size scaling. We estimate that the rest-frame continuum UV (~1800Å) luminosity density at z~7.5 (integrated down to0.3L*z=3) is just0.20+0.12-0.08 times that found at z~3.8 (or0.20+0.23-0.12 times this quantity includingcosmic variance). Effectively this sets an upper limit on the luminositydensity down to 0.3L*z=3 and is consistent withsignificant evolution at the bright end of the luminosity function fromz~7.5 to 3.8. Even with the lower UV luminosity density at z~7.5, itappears that galaxies could still play an important role in reionizationat these redshifts, although definitive measurements remain to be made.Based on observations made with the NASA/ESA Hubble Space Telescope,which is operated by the Association of Universities for Research inAstronomy, Inc., under NASA contract NAS 5-26555.

The Application of Photometric Redshifts to the SDSS Early Data Release - Csabai, István; Budavári, Tamás; Connolly, Andrew J.; Szalay, Alexander S.; Győry, Zsuzsanna; Benítez, Narciso; Annis, Jim; Brinkmann, Jon; Eisenstein, Daniel; Fukugita, Masataka; Gunn, Jim; Kent, Stephen; et al. (The Astronomical Journal, 2003)
The Early Data Release (EDR) from the Sloan Digital Sky Survey providesone of the largest multicolor photometric catalogs currently availableto the astronomical community. In this paper we present the firstapplication of photometric redshifts to the ~6 million extended sourcesin these data (with 1.8 million sources having r'<21). Utilizing arange of photometric redshift techniques, from empirical to template andhybrid techniques, we investigate the statistical and systematicuncertainties present in the redshift estimates for the EDR data. Forr'<21, we find that the redshift estimates provide realistic redshifthistograms with an rms uncertainty in the photometric redshift relationof 0.035 at r'<18 and rising to 0.1 at r'<21. We conclude bydescribing how these photometric redshifts and derived quantities, suchas spectral type, rest-frame colors, and absolute magnitudes, are storedin the SDSS database. We provide sample queries for searching onphotometric redshifts and list the current caveats and issues thatshould be understood before using these photometric redshifts instatistical analyses of the SDSS galaxies.

Average Spectra of Massive Galaxies in the Sloan Digital Sky Survey - Eisenstein, Daniel J.; Hogg, David W.; Fukugita, Masataka; Nakamura, Osamu; Bernardi, Mariangela; Finkbeiner, Douglas P.; Schlegel, David J.; Brinkmann, J.; Connolly, Andrew J.; Csabai, István; Gunn, James E.; Ivezić, Željko; et al. (The Astrophysical Journal, 2003)
We combine Sloan Digital Sky Survey spectra of 22,000 luminous, red,bulge-dominated galaxies to get high signal-to-noise ratio averagespectra in the rest-frame optical and ultraviolet (2600-7000 Å).The average spectra of these massive, quiescent galaxies are early typewith weak emission lines and with absorption lines indicating anapparent excess of α-elements over solar abundance ratios. We makeaverage spectra of subsamples selected by luminosity, environment, andredshift. The average spectra are remarkable in their similarity. Whatvariations do exist in the average spectra as a function of luminosityand environment are found to form a nearly one-parameter family inspectrum space. We present a high signal-to-noise ratio spectrum of thevariation. We measure the properties of the variation with a modifiedversion of the Lick index system and compare to model spectra fromstellar population syntheses. The variation may be a combination of ageand chemical abundance differences, but the conservative conclusion isthat the quality of the data considerably exceeds the current state ofthe models.

The Overdensities of Galaxy Environments as a Function of Luminosity and Color - Hogg, David W.; Blanton, Michael R.; Eisenstein, Daniel J.; Gunn, James E.; Schlegel, David J.; Zehavi, Idit; Bahcall, Neta A.; Brinkmann, Jon; Csabai, Istvan; Schneider, Donald P.; Weinberg, David H.; York, Donald G. (The Astrophysical Journal Letters, 2003)
We study the mean environments of galaxies in the Sloan Digital SkySurvey (SDSS) as a function of rest-frame luminosity and color.Overdensities in galaxy number are estimated in 8 and 1 h-1Mpc spheres centered on 115,000 galaxies taken from the SDSSspectroscopic sample. We find that, at constant color, overdensity isindependent of luminosity for galaxies with the blue colors of spirals.This suggests that at fixed star formation history, spiral-galaxy massis a very weak function of environment. Overdensity does depend onluminosity for galaxies with the red colors of early types; bothlow-luminosity and high-luminosity red galaxies are found to be inhighly overdense regions.

Early-Type Galaxies in the Sloan Digital Sky Survey. I. The Sample - Bernardi, Mariangela; Sheth, Ravi K.; Annis, James; Burles, Scott; Eisenstein, Daniel J.; Finkbeiner, Douglas P.; Hogg, David W.; Lupton, Robert H.; Schlegel, David J.; SubbaRao, Mark; Bahcall, Neta A.; Blakeslee, John P.; et al. (The Astronomical Journal, 2003)
A sample of nearly 9000 early-type galaxies, in the redshift range0.01<=z<=0.3, was selected from the Sloan Digital Sky Survey(SDSS) using morphological and spectral criteria. This paper describeshow the sample was selected, presents examples of images andseeing-corrected fits to the observed surface brightness profiles,describes our method for estimating K-corrections, and shows that theSDSS spectra are of sufficiently high quality to measure velocitydispersions accurately. It also provides catalogs of the measuredphotometric and spectroscopic parameters. In related papers, these dataare used to study how early-type galaxy observables, includingluminosity, effective radius, surface brightness, color, and velocitydispersion, are correlated with one another.

Early-type Galaxies in the Sloan Digital Sky Survey. II. Correlations between Observables - Bernardi, Mariangela; Sheth, Ravi K.; Annis, James; Burles, Scott; Eisenstein, Daniel J.; Finkbeiner, Douglas P.; Hogg, David W.; Lupton, Robert H.; Schlegel, David J.; SubbaRao, Mark; Bahcall, Neta A.; Blakeslee, John P.; et al. (The Astronomical Journal, 2003)
A magnitude-limited sample of nearly 9000 early-type galaxies, in theredshift range 0.01<=z<=0.3, was selected from the Sloan DigitalSky Survey using morphological and spectral criteria. The sample wasused to study how early-type galaxy observables, including luminosity L,effective radius Ro, surface brightness Io, color,and velocity dispersion σ, are correlated with one another.Measurement biases are understood with mock catalogs that reproduce allof the observed scaling relations and their dependences on fittingtechnique. At any given redshift, the intrinsic distribution ofluminosities, sizes, and velocity dispersions in our sample are allapproximately Gaussian. A maximum likelihood analysis shows thatσ~L0.25+/-0.012,Ro~L0.63+/-0.025, andRo~I-0.75+/-0.02 in the r* band. In addition, themass-to-light ratio within the effective radius scales asMo/L~L0.14+/-0.02 orMo/L~M0.22+/-0.05o, and galaxies withlarger effective masses have smaller effective densities:Δo~M-0.52+/-0.03o. Theserelations are approximately the same in the g*, i*, and z* bands.Relative to the population at the median redshift in the sample,galaxies at lower and higher redshifts have evolved only little, withmore evolution in the bluer bands. The luminosity function is consistentwith weak passive luminosity evolution and a formation time of about 9Gyr ago.

Early-Type Galaxies in the Sloan Digital Sky Survey. III. The Fundamental Plane - Bernardi, Mariangela; Sheth, Ravi K.; Annis, James; Burles, Scott; Eisenstein, Daniel J.; Finkbeiner, Douglas P.; Hogg, David W.; Lupton, Robert H.; Schlegel, David J.; SubbaRao, Mark; Bahcall, Neta A.; Blakeslee, John P.; et al. (The Astronomical Journal, 2003)
A magnitude-limited sample of nearly 9000 early-type galaxies in theredshift range 0.01<=z<=0.3 was selected from the Sloan DigitalSky Survey (SDSS) using morphological and spectral criteria. Thefundamental plane relation in this sample isRo~σ1.49+/-0.05I-0.75+/-0.01oin the r* band. It is approximately the same in the g*, i*, and z*bands. Relative to the population at the median redshift in the sample,galaxies at lower and higher redshifts have evolved only a little. Ifthe fundamental plane is used to quantify this evolution, then theapparent magnitude limit can masquerade as evolution; once thisselection effect has been accounted for, the evolution is consistentwith that of a passively evolving population that formed the bulk of itsstars about 9 Gyr ago. One of the principal advantages of the SDSSsample over previous samples is that the galaxies in it lie inenvironments ranging from isolation in the field to the dense cores ofclusters. The fundamental plane shows that galaxies in dense regions areslightly different from galaxies in less dense regions.

Deprojecting Densities from Angular Cross-Correlations - Eisenstein, Daniel J. (The Astrophysical Journal, 2003)
We present a model-independent, spherically symmetric density estimatorto be used in the cross-correlation of imaging catalogs with objects ofknown redshift. The estimator is a simple modification of the usualprojected density estimator, with weightings that produce a sphericalaperture rather than a cylindrical one.

Estimating Fixed-Frame Galaxy Magnitudes in the Sloan Digital Sky Survey - Blanton, Michael R.; Brinkmann, J.; Csabai, István; Doi, Mamoru; Eisenstein, Daniel; Fukugita, Masataka; Gunn, James E.; Hogg, David W.; Schlegel, David J. (The Astronomical Journal, 2003)
Broadband measurements of flux for galaxies at different redshiftsmeasure different regions of the rest-frame galaxy spectrum. Certainastronomical questions, such as the evolution of the luminosity functionof galaxies, require transforming these inherently redshift-dependentmagnitudes into redshift-independent quantities. To prepare to addressthese astronomical questions, investigated in detail in subsequentpapers, we fit spectral energy distributions (SEDs) to broadbandphotometric observations in the context of the optical observations ofthe Sloan Digital Sky Survey (SDSS). Linear combinations of fourspectral templates can reproduce the five SDSS magnitudes of allgalaxies to the precision of the photometry. Expressed in theappropriate coordinate system, the locus of the coefficients multiplyingthe templates is planar and, in fact, nearly linear. The resultingreconstructed SEDs can be used to recover fixed-frame magnitudes over arange of redshifts. This process yields consistent results in the sensethat, within each sample, the intrinsic colors of similar type galaxiesare nearly constant with redshift. We compare our results with simplerinterpolation methods and galaxy spectrophotometry from the SDSS. Thesoftware that generates these results is publicly available and easilyadapted to handle a wide range of galaxy observations.Based on observations obtained with the Sloan Digital Sky Survey.

Karhunen-Loève Estimation of the Power Spectrum Parameters from the Angular Distribution of Galaxies in Early Sloan Digital Sky Survey Data - Szalay, Alexander S.; Jain, Bhuvnesh; Matsubara, Takahiko; Scranton, Ryan; Vogeley, Michael S.; Connolly, Andrew; Dodelson, Scott; Eisenstein, Daniel; Frieman, Joshua A.; Gunn, James E.; Hui, Lam; Johnston, David; et al. (The Astrophysical Journal, 2003)
We present measurements of parameters of the three-dimensional powerspectrum of galaxy clustering from 222 square degrees of early imagingdata in the Sloan Digital Sky Survey (SDSS). The projected galaxydistribution on the sky is expanded over a set of Karhunen-Loève(KL) eigenfunctions, which optimize the signal-to-noise ratio in ouranalysis. A maximum likelihood analysis is used to estimate parametersthat set the shape and amplitude of the three-dimensional power spectrumof galaxies in the SDSS magnitude-limited sample withr*<21. Our best estimates are Γ=0.188+/-0.04 andσ8L=0.915+/-0.06 (statistical errors only), for a flatuniverse with a cosmological constant. We demonstrate that ourmeasurements contain signal from scales at or beyond the peak of thethree-dimensional power spectrum. We discuss how the results scale withsystematic uncertainties, like the radial selection function. We findthat the central values satisfy the analytically estimated scalingrelation. We have also explored the effects of evolutionary corrections,various truncations of the KL basis, seeing, sample size, and limitingmagnitude. We find that the impact of most of these uncertainties staywithin the 2 σ uncertainties of our fiducial result.

SDSS J092455.87+021924.9: An Interesting Gravitationally Lensed Quasar from the Sloan Digital Sky Survey - Inada, Naohisa; Becker, Robert H.; Burles, Scott; Castander, Francisco J.; Eisenstein, Daniel; Hall, Patrick B.; Johnston, David E.; Pindor, Bartosz; Richards, Gordon T.; Schechter, Paul L.; Sekiguchi, Maki; White, Richard L.; et al. (The Astronomical Journal, 2003)
We report the discovery of a new gravitationally lensed quasar from theSloan Digital Sky Survey, SDSS J092455.87+021924.9 (SDSS J0924+0219).This object was selected from among known SDSS quasars by an algorithmthat was designed to select another known SDSS lensed quasar (SDSSJ1226-0006A,B). Five separate components, three of which are unresolved,are identified in photometric follow-up observations obtained with theMagellan Consortium's 6.5 m Walter Baade Telescope at Las CampanasObservatory. Two of the unresolved components (designated A and B) areconfirmed to be quasars with z=1.524; the velocity difference is lessthan 100 km s-1 according to spectra taken with the W. M.Keck Observatory's Keck II Telescope at Mauna Kea, Hawaii. A thirdstellar component, designated C, has the colors of a quasar withredshift similar to components A and B. The maximum separation of thepoint sources is 1.78". The other two sources, designated G and D, areresolved. Component G appears to be the best candidate for the lensinggalaxy. Although component D is near the expected position of the fourthlensed component in a four-image lens system, its properties are notconsistent with being the image of a quasar at z~1.5. Nevertheless, theidentical redshifts of components A and B and the presence of componentC strongly suggest that this object is a gravitational lens. Ourobservations support the idea that a foreground object reddens thefourth lensed component and that another unmodeled effect (such asmicro- or millilensing) demagnifies it, but we cannot rule out thepossibility that SDSS J0924+0219 is an example of the relatively rareclass of ``three-component'' lens systems.

Spectroscopic Discovery of the Supernova 2003dh Associated with GRB 030329 - Stanek, K. Z.; Matheson, T.; Garnavich, P. M.; Martini, P.; Berlind, P.; Caldwell, N.; Challis, P.; Brown, W. R.; Schild, R.; Krisciunas, K.; Calkins, M. L.; Lee, J. C.; et al. (The Astrophysical Journal Letters, 2003)
We present early observations of the afterglow of GRB 030329 and thespectroscopic discovery of its associated supernova SN 2003dh. Weobtained spectra of the afterglow of GRB 030329 each night from March30.12 (0.6 days after the burst) to April 8.13 (UT) (9.6 days after theburst). The spectra cover a wavelength range of 350-850 nm. The earlyspectra consist of a power-law continuum(Fν~ν-0.9) with narrow emission linesoriginating from H II regions in the host galaxy, indicating a lowredshift of z=0.1687. However, our spectra taken after 2003 April 5 showbroad peaks in flux characteristic of a supernova. Correcting for theafterglow emission, we find that the spectrum of the supernova isremarkably similar to the Type Ic ``hypernova'' SN 1998bw. While thepresence of supernovae has been inferred from the light curves andcolors of gamma-ray burst afterglows in the past, this is the firstdirect, spectroscopic confirmation that a subset of classical gamma-raybursts originate from supernovae.Based on data from the Multiple Mirror Telescope Observatory 6.5 mtelescope, the Magellan 6.5 m Clay telescope, and the Fred LawrenceWhipple Observatory 1.5 m telescope.

An Initial Survey of White Dwarfs in the Sloan Digital Sky Survey - Harris, Hugh C.; Liebert, James; Kleinman, S. J.; Nitta, Atsuko; Anderson, Scott F.; Knapp, Gillian R.; Krzesiński, Jurek; Schmidt, Gary; Strauss, Michael A.; Vanden Berk, Dan; Eisenstein, Daniel; Hawley, Suzanne; et al. (The Astronomical Journal, 2003)
An initial assessment is made of white dwarf and hot subdwarf starsobserved in the Sloan Digital Sky Survey. In a small area of sky (190square degrees), observed much like the full survey will be, 269 whitedwarfs (WDs) and 56 hot subdwarfs are identified spectroscopically whereonly 44 white dwarfs and five hot subdwarfs were known previously. Mostare ordinary DA (hydrogen atmosphere) and DB (helium) types. Inaddition, in the full survey to date, a number of WDs have been foundwith uncommon spectral types. Among these are blue DQ stars displayinglines of atomic carbon; red DQ stars showing molecular bands ofC2 with a wide variety of strengths; DZ stars where Ca andoccasionally Mg, Na, and/or Fe lines are detected; and magnetic WDs witha wide range of magnetic field strengths in DA, DB, DQ, and (probably)DZ spectral types. Photometry alone allows identification of starshotter than 12,000 K, and the density of these stars for 15-2 at Galactic latitudes of29°-62°. Spectra are obtained for roughly half of these hot

The Broadband Optical Properties of Galaxies with Redshifts 0.02<z<0.22 - Blanton, Michael R.; Hogg, David W.; Bahcall, Neta A.; Baldry, Ivan K.; Brinkmann, J.; Csabai, István; Eisenstein, Daniel; Fukugita, Masataka; Gunn, James E.; Ivezić, Željko; Lamb, D. Q.; Lupton, Robert H.; et al. (The Astrophysical Journal, 2003)
Using photometry and spectroscopy of 183,487 galaxies from the SloanDigital Sky Survey, we present bivariate distributions of pairs of sevengalaxy properties: four optical colors, surface brightness, radialprofile shape as measured by the Sérsic index, and absolutemagnitude. In addition, we present the dependence of local galaxydensity (smoothed on 8 h-1 Mpc scales) on all of theseproperties. Several classic, well-known relations among galaxyproperties are evident at extremely high signal-to-noise ratio: thecolor-color relations of galaxies, the color-magnitude relations, themagnitude-surface brightness relation, and the dependence of density oncolor and absolute magnitude. We show that most of the i-band luminositydensity in the universe is in the absolute magnitude and surfacebrightness ranges used: -23.50.1i<-17.0mag and 17<μ0.1i<24 mag in 1arcsec2 [the notation zb represents the b bandshifted blueward by a factor (1+z)]. Some of the relationships betweenparameters, in particular the color-magnitude relations, show strongercorrelations for exponential galaxies and concentrated galaxies takenseparately than for all galaxies taken together. We provide a simple setof fits of the dependence of galaxy properties on luminosity for thesetwo sets of galaxies and other quantitative details of our results.Based on observations obtained with the Sloan Digital Sky Survey.

The Velocity Dispersion Function of Early-Type Galaxies - Sheth, Ravi K.; Bernardi, Mariangela; Schechter, Paul L.; Burles, Scott; Eisenstein, Daniel J.; Finkbeiner, Douglas P.; Frieman, Joshua; Lupton, Robert H.; Schlegel, David J.; SubbaRao, Mark; Shimasaku, K.; Bahcall, Neta A.; et al. (The Astrophysical Journal, 2003)
The distribution of early-type galaxy velocity dispersions,φ(σ), is measured using a sample drawn from the Sloan DigitalSky Survey database. Its shape differs significantly from that obtainedby simply using the mean correlation between luminosity L and velocitydispersion σ to transform the luminosity function into a velocityfunction: ignoring the scatter around the mean σ-L relation is abad approximation. An estimate of the contribution from late-typegalaxies is also made, which suggests that φ(σ) is dominatedby early-type galaxies at velocities larger than ~200 km s-1.

Angular Clustering with Photometric Redshifts in the Sloan Digital Sky Survey: Bimodality in the Clustering Properties of Galaxies - Budavári, Tamás; Connolly, Andrew J.; Szalay, Alexander S.; Szapudi, István; Csabai, István; Scranton, Ryan; Bahcall, Neta A.; Brinkmann, Jon; Eisenstein, Daniel J.; Frieman, Joshua A.; Fukugita, Masataka; Gunn, James E.; et al. (The Astrophysical Journal, 2003)
Understanding the clustering of galaxies has long been a goal of modernobservational cosmology. Redshift surveys have been used to measure thecorrelation length as a function of luminosity and color. However, whensubdividing the catalogs into multiple subsets, the errors increaserapidly. Angular clustering in magnitude-limited photometric surveys hasthe advantage of much larger catalogs but suffers from a dilution of theclustering signal because of the broad radial distribution of thesample. Also, up to now it has not been possible to select uniformsubsamples based on physical parameters, such as luminosity andrest-frame color. Utilizing our photometric redshift technique, avolume-limited sample (0.10=5.77+/-0.10h-1Mpc. We find that r0increases with luminosity by a factor of 1.6 over the sampled luminosityrange, in agreement with previous redshift surveys. We also find thatboth the clustering length and the slope of the correlation functiondepend on the galaxy type. In particular, by splitting the galaxies infour groups by their rest-frame type, we find a bimodal behavior intheir clustering properties. Galaxies with spectral types similar toelliptical galaxies have a correlation length of6.59+/-0.17h-1Mpc and a slope of the angular correlationfunction of 0.96+/-0.05, while blue galaxies have a clustering length of4.51+/-0.19h-1Mpc and a slope of 0.68+/-0.09. The twointermediate color groups behave like their more extreme ``siblings''rather than showing a gradual transition in slope. We discuss thesecorrelations in the context of current cosmological models for structureformation.

The First Data Release of the Sloan Digital Sky Survey - Abazajian, Kevork; Adelman-McCarthy, Jennifer K.; Agüeros, Marcel A.; Allam, Sahar S.; Anderson, Scott F.; Annis, James; Bahcall, Neta A.; Baldry, Ivan K.; Bastian, Steven; Berlind, Andreas; Bernardi, Mariangela; Blanton, Michael R.; et al. (The Astronomical Journal, 2003)
The Sloan Digital Sky Survey (SDSS) has validated and made publiclyavailable its First Data Release. This consists of 2099 deg2of five-band (u,g,r,i,z) imaging data, 186,240 spectra of galaxies,quasars, stars and calibrating blank sky patches selected over 1360deg2 of this area, and tables of measured parameters fromthese data. The imaging data go to a depth of r~22.6 and are

Magnetic White Dwarfs from the Sloan Digital Sky Survey: The First Data Release - Schmidt, Gary D.; Harris, Hugh C.; Liebert, James; Eisenstein, Daniel J.; Anderson, Scott F.; Brinkmann, J.; Hall, Patrick B.; Harvanek, Michael; Hawley, Suzanne; Kleinman, S. J.; Knapp, Gillian R.; Krzesinski, Jurek; et al. (The Astrophysical Journal, 2003)
Beyond its goals related to the extragalactic universe, the SloanDigital Sky Survey (SDSS) is an effective tool for identifying stellarobjects with unusual spectral energy distributions. Here we report onthe 53 new magnetic white dwarfs discovered during the first two yearsof the survey, including 38 whose data are made public in the 1500deg2 First Data Release. Discoveries span the magnitude range16.3<=g<=20.5, and based on the recovery rate for previously knownmagnetic white dwarfs, the completeness of the SDSS appears to be highfor reasonably hot stars with B>~3 MG and g>~15. The new objectsnearly double the total number of known magnetic white dwarfs andinclude examples with polar field strengths Bp>500 MG, aswell as several with exotic atmospheric compositions. The improvedsample statistics and uniformity indicate that the distribution ofmagnetic white dwarfs has a broad peak in the range ~5-30 MG and a tailextending to nearly 109 G. Degenerates with polar fieldsBp>~50 MG are consistent with being descendents ofmagnetic Ap/Bp main-sequence stars, but low- and moderate-field magneticwhite dwarfs appear to imply another origin. Yet-undetected magneticF-type stars with convective envelopes that destroy the orderedunderlying field are attractive candidates.A portion of the results presented here were obtained with the MMTObservatory, a facility operated jointly by the University of Arizonaand the Smithsonian Institution.

SDSS J090334.92+502819.2: A New Gravitational Lens - Johnston, David E.; Richards, Gordon T.; Frieman, Joshua A.; Keeton, Charles R.; Strauss, Michael A.; Knapp, Gillian R.; Becker, Robert H.; White, Richard L.; Johnson, Eric T.; Ma, Zhaoming; SubbaRao, Mark; Bahcall, Neta A.; et al. (The Astronomical Journal, 2003)
We report the discovery of a new gravitationally lensed quasar from theSloan Digital Sky Survey, SDSS J090334.92+502819.2. This object wastargeted for SDSS spectroscopy as a luminous red galaxy, but manualexamination of the spectrum showed the presence of a quasar at z~=3.6 inaddition to a red galaxy at z=0.388, and the SDSS image showed a secondpossible quasar image nearby. Follow-up imaging and spectroscopyconfirmed the lensing hypothesis. In images taken at the AstrophysicalResearch Consortium 3.5 m telescope, two quasars are separated by 2.8"the lensing galaxy is clearly seen and is blended with one of the quasarimages. Spectroscopy taken at the Keck II telescope shows that thequasars have identical redshifts of z~=3.6, and both show the presenceof the same broad absorption line-like troughs. We present simple lensmodels that account for the geometry and magnifications. The lens galaxylies near two groups of galaxies and may be a part of them. The modelssuggest that the groups may contribute considerable shear that has astrong effect on the lens configuration.

SDSS White Dwarfs with Spectra Showing Atomic Oxygen and/or Carbon Lines - Liebert, James; Harris, H. C.; Dahn, C. C.; Schmidt, Gary D.; Kleinman, S. J.; Nitta, Atsuko; Krzesiński, Jurek; Eisenstein, Daniel; Smith, J. Allyn; Szkody, Paula; Hawley, Suzanne; Anderson, Scott F.; et al. (The Astronomical Journal, 2003)
We discuss 18 white dwarfs, one of which (G227-5) was previously known,whose SDSS spectra show lines of neutral and/or singly ionized carbon.At least two and perhaps four show lines of neutral or singly ionizedoxygen. Apart from the extremely hot ``PG 1159'' stars, these are thefirst white dwarfs with photospheric oxygen detected in their opticalspectra. The photometry strongly suggests that these stars lie in the11,000-30,000 K temperature range of the helium-atmosphere DB whitedwarfs, though only one of them shows weak neutral helium lines in thespectrum. Trigonometric parallaxes are known for G227-5 and another,previously known white dwarf (G35-26) showing atomic carbon lines, andthey indicate that both are massive stars. Theoretical arguments suggestthat all members of this class of rare white dwarfs are massive (~1Msolar), and this finding could explain the paucity ofmassive DB white dwarfs.

The Sloan Digital Sky Survey Quasar Catalog. II. First Data Release - Schneider, Donald P.; Fan, Xiaohui; Hall, Patrick B.; Jester, Sebastian; Richards, Gordon T.; Stoughton, Chris; Strauss, Michael A.; SubbaRao, Mark; Vanden Berk, Daniel E.; Anderson, Scott F.; Brandt, W. N.; Gunn, James E.; et al. (The Astronomical Journal, 2003)
We present the second edition of the Sloan Digital Sky Survey (SDSS)Quasar Catalog. The catalog consists of the 16,713 objects in the SDSSFirst Data Release that have luminosities larger than Mi=-22(in a cosmology with H0=70 km s-1Mpc-1, ΩM=0.3, andΩΛ=0.7), have at least one emission line withFWHM larger than 1000 km s-1, and have highly reliableredshifts. The area covered by the catalog is ~1360 deg2. Thequasar redshifts range from 0.08 to 5.41, with a median value of 1.43.For each object, the catalog presents positions accurate to better than0.2" rms per coordinate, five-band (ugriz) CCD-based photometry withtypical accuracy of 0.03 mag, and information on the morphology andselection method. The catalog also contains some radio, near-infrared,and X-ray emission properties of the quasars, when available, from otherlarge-area surveys. Calibrated digital spectra of all objects in thecatalog, covering the wavelength region 3800-9200 Å at a spectralresolution of 1800-2100, are available. This publication supersedes thefirst SDSS Quasar Catalog, which was based on material from the SDSSEarly Data Release. A summary of corrections to current quasar databasesis also provided. The majority of the objects were found in SDSScommissioning data using a multicolor selection technique. Since thequasar selection algorithm was undergoing testing during the entireobservational period covered by this catalog, care must be taken whenassembling samples from the catalog for use in statistical studies. A

Probing Dark Energy with Baryonic Acoustic Oscillations from Future Large Galaxy Redshift Surveys - Seo, Hee-Jong; Eisenstein, Daniel J. (The Astrophysical Journal, 2003)
We show that the measurement of the baryonic acoustic oscillations inlarge high-redshift galaxy surveys offers a precision route to themeasurement of dark energy. The cosmic microwave background provides thescale of the oscillations as a standard ruler that can be measured inthe clustering of galaxies, thereby yielding the Hubble parameter andangular diameter distance as a function of redshift. This, in turn,enables one to probe dark energy. We use a Fisher matrix formalism tostudy the statistical errors for redshift surveys up to z=3 and reporterrors on cosmography while marginalizing over a large number ofcosmological parameters, including a time-dependent equation of state.With redshift surveys combined with cosmic microwave backgroundsatellite data, we achieve errors of 0.037 on ΩX, 0.10on w(z=0.8), and 0.28 on dw(z)/dz for the cosmological constant model.Models with less negative w(z) permit tighter constraints. We test anddiscuss the dependence of performance on redshift, survey conditions,and the fiducial model. We find results that are competitive with theperformance of future Type Ia supernova surveys. We conclude thatredshift surveys offer a promising independent route to the measurementof dark energy.

Photometry and Spectroscopy of GRB 030329 and Its Associated Supernova 2003dh: The First Two Months - Matheson, T.; Garnavich, P. M.; Stanek, K. Z.; Bersier, D.; Holland, S. T.; Krisciunas, K.; Caldwell, N.; Berlind, P.; Bloom, J. S.; Bolte, M.; Bonanos, A. Z.; Brown, M. J. I.; et al. (The Astrophysical Journal, 2003)
We present extensive optical and infrared photometry of the afterglow ofgamma-ray burst (GRB) 030329 and its associated supernova (SN) 2003dhover the first two months after detection (2003 March 30-May 29 UT).Optical spectroscopy from a variety of telescopes is shown and, whencombined with the photometry, allows an unambiguous separation betweenthe afterglow and SN contributions. The optical afterglow of the GRB isinitially a power-law continuum but shows significant color variationsduring the first week that are unrelated to the presence of an SN. Theearly afterglow light curve also shows deviations from the typicalpower-law decay. An SN spectrum is first detectable ~7 days after theburst and dominates the light after ~11 days. The spectral evolution andthe light curve are shown to closely resemble those of SN 1998bw, apeculiar Type Ic SN associated with GRB 980425, and the time of the SNexplosion is close to the observed time of the GRB. It is now clear thatat least some GRBs arise from core-collapse SNe.

A gravitationally lensed quasar with quadruple images separated by 14.62arcseconds - Inada, Naohisa; Oguri, Masamune; Pindor, Bartosz; Hennawi, Joseph F.; Chiu, Kuenley; Zheng, Wei; Ichikawa, Shin-ichi; Gregg, Michael D.; Becker, Robert H.; Suto, Yasushi; Strauss, Michael A.; Turner, Edwin L.; et al. (Nature, 2003)
Gravitational lensing is a powerful tool for the study of thedistribution of dark matter in the Universe. The cold-dark-matter modelof the formation of large-scale structures (that is, clusters ofgalaxies and even larger assemblies) predicts the existence of quasarsgravitationally lensed by concentrations of dark matter so massive thatthe quasar images would be split by over 7arcsec. Numerous searches forlarge-separation lensed quasars have, however, been unsuccessful. All ofthe roughly 70 lensed quasars known, including the first lensed quasardiscovered, have smaller separations that can be explained in terms ofgalaxy-scale concentrations of baryonic matter. Although gravitationallylensed galaxies with large separations are known, quasars are moreuseful cosmological probes because of the simplicity of the resultinglens systems. Here we report the discovery of a lensed quasar, SDSSJ1004 + 4112, which has a maximum separation between the components of14.62arcsec. Such a large separation means that the lensing object mustbe dominated by dark matter. Our results are fully consistent withtheoretical expectations based on the cold-dark-matter model.

Sloan Digital Sky Survey: Early Data Release - Stoughton, Chris; Lupton, Robert H.; Bernardi, Mariangela; Blanton, Michael R.; Burles, Scott; Castander, Francisco J.; Connolly, A. J.; Eisenstein, Daniel J.; Frieman, Joshua A.; Hennessy, G. S.; Hindsley, Robert B.; Ivezić, Željko; et al. (The Astronomical Journal, 2002)
The Sloan Digital Sky Survey (SDSS) is an imaging and spectroscopicsurvey that will eventually cover approximately one-quarter of thecelestial sphere and collect spectra of ~106 galaxies,100,000 quasars, 30,000 stars, and 30,000 serendipity targets. In 2001June, the SDSS released to the general astronomical community its earlydata release, roughly 462 deg2 of imaging data includingalmost 14 million detected objects and 54,008 follow-up spectra. Theimaging data were collected in drift-scan mode in five bandpasses (u, g,

Higher Order Moments of the Angular Distribution of Galaxies from Early Sloan Digital Sky Survey Data - Szapudi, István; Frieman, Joshua A.; Scoccimarro, Roman; Szalay, Alexander S.; Connolly, Andrew J.; Dodelson, Scott; Eisenstein, Daniel J.; Gunn, James E.; Johnston, David; Kent, Stephen; Loveday, Jon; Meiksin, Avery; et al. (The Astrophysical Journal, 2002)
We present initial results for counts in cell statistics of the angulardistribution of galaxies in early data from the Sloan Digital Sky Survey(SDSS). We analyze a rectangular stripe 2.5d wide, coveringapproximately 160 deg2, containing over 106galaxies in the apparent magnitude range 18'<22, withareas of bad seeing, contamination from bright stars, ghosts, and highgalactic extinction masked out. This survey region, which forms part ofthe SDSS early data release, is the same as that for which two-pointangular clustering statistics have recently been computed. The third andfourth moments of the cell counts, s3 (skewness) ands4 (kurtosis), constitute the most accurate measurements todate of these quantities (for r'<21) over angular scales0.015d-0.3d. They display the approximate hierarchical scaling expectedfrom nonlinear structure formation models and are in reasonableagreement with the predictions of Λ-dominated cold dark mattermodels with galaxy biasing that suppresses higher order correlations atsmall scales. The results are, in general, consistent with previousmeasurements in the APM, EDSGC, and Deeprange surveys. These resultssuggest that the SDSS imaging data are free of systematics to a highdegree and will therefore enable determination of the skewness and

Galaxy Clustering in Early Sloan Digital Sky Survey Redshift Data - Zehavi, Idit; Blanton, Michael R.; Frieman, Joshua A.; Weinberg, David H.; Mo, Houjun J.; Strauss, Michael A.; Anderson, Scott F.; Annis, James; Bahcall, Neta A.; Bernardi, Mariangela; Briggs, John W.; Brinkmann, Jon; et al. (The Astrophysical Journal, 2002)
We present the first measurements of clustering in the Sloan Digital SkySurvey (SDSS) galaxy redshift survey. Our sample consists of 29,300galaxies with redshifts5700kms-1<=cz<=39,000kms-1, distributed inseveral long but narrow (2.5d-5°) segments, covering 690deg2. For the full, flux-limited sample, the redshift-spacecorrelation length is approximately 8 h-1 Mpc. Thetwo-dimensional correlation function ξ(rp,π) showsclear signatures of both the small-scale, ``fingers-of-God'' distortioncaused by velocity dispersions in collapsed objects and the large-scalecompression caused by coherent flows, though the latter cannot bemeasured with high precision in the present sample. The inferredreal-space correlation function is well described by a power law,ξ(r)=(r/6.1+/-0.2h-1Mpc)-1.75+/-0.03, for0.1h-1Mpc<=r<=16h-1Mpc. The galaxy pairwisevelocity dispersion is σ12~600+/-100kms-1for projected separations0.15h-1Mpc<=rp<=5h-1Mpc. When wedivide the sample by color, the red galaxies exhibit a stronger andsteeper real-space correlation function and a higher pairwise velocitydispersion than do the blue galaxies. The relative behavior ofsubsamples defined by high/low profile concentration or high/low surfacebrightness is qualitatively similar to that of the red/blue subsamples.Our most striking result is a clear measurement of scale-independentluminosity bias at r<~10h-1Mpc: subsamples with absolutemagnitude ranges centered on M*-1.5, M*, andM*+1.5 have real-space correlation functions that areparallel power laws of slope ~-1.8 with correlation lengths ofapproximately 7.4, 6.3, and 4.7 h-1 Mpc, respectively.

The Angular Power Spectrum of Galaxies from Early Sloan Digital Sky Survey Data - Tegmark, Max; Dodelson, Scott; Eisenstein, Daniel J.; Narayanan, Vijay; Scoccimarro, Roman; Scranton, Ryan; Strauss, Michael A.; Connolly, Andrew; Frieman, Joshua A.; Gunn, James E.; Hui, Lam; Jain, Bhuvnesh; et al. (The Astrophysical Journal, 2002)
We compute the angular power spectrum Cl from 1.5 milliongalaxies in early Sloan Digital Sky Survey (SDSS) data on large angularscales, l<~600. The data set covers about 160 deg2, with acharacteristic depth on the order of 1 h-1 Gpc in thefaintest (21*<22) of our four magnitude bins.Cosmological interpretations of these results are presented in acompanion paper by Dodelson and coworkers. The data in all fourmagnitude bins are consistent with a simple flat ``concordance'' modelwith nonlinear evolution and linear bias factors on the order of unity.Nonlinear evolution is particularly evident for the brightest galaxies.A series of tests suggests that systematic errors related to seeing,reddening, etc. are negligible, which bodes well for the 60-fold largersample that the SDSS is currently collecting. Uncorrelated error barsand well-behaved window functions make our measurements a convenientstarting point for cosmological model fitting.

The Three-dimensional Power Spectrum from Angular Clustering of Galaxies in Early Sloan Digital Sky Survey Data - Dodelson, Scott; Narayanan, Vijay K.; Tegmark, Max; Scranton, Ryan; Budavári, Tamas; Connolly, Andrew; Csabai, Istvan; Eisenstein, Daniel; Frieman, Joshua A.; Gunn, James E.; Hui, Lam; Jain, Bhuvnesh; et al. (The Astrophysical Journal, 2002)
Early photometric data from the Sloan Digital Sky Survey (SDSS) containangular positions for 1.5 million galaxies. In companion papers, theangular correlation function w(θ) and two-dimensional powerspectrum Cl of these galaxies are presented. Here we invertLimber's equation to extract the three-dimensional power spectrum fromthe angular results. We accomplish this using an estimate of dn/dz, theredshift distribution of galaxies in four different magnitude slices inthe SDSS photometric catalog. The resulting three-dimensional powerspectrum estimates from w(θ) and Cl agree with eachother and with previous estimates over a range in wavenumbers0.03-1)<1. The galaxies in the faintestmagnitude bin (21*<22, which have median redshiftzm=0.43) are less clustered than the galaxies in thebrightest magnitude bin (18*<19 withzm=0.17), especially on scales where nonlinearities areimportant. The derived power spectrum agrees with that of Szalay et al.,who go directly from the raw data to a parametric estimate of the powerspectrum. The strongest constraints on the shape parameter Γ comefrom the faintest galaxies (in the magnitude bin21*<22), from which we infer

Spectroscopic Target Selection in the Sloan Digital Sky Survey: The Main Galaxy Sample - Strauss, Michael A.; Weinberg, David H.; Lupton, Robert H.; Narayanan, Vijay K.; Annis, James; Bernardi, Mariangela; Blanton, Michael; Burles, Scott; Connolly, A. J.; Dalcanton, Julianne; Doi, Mamoru; Eisenstein, Daniel; et al. (The Astronomical Journal, 2002)
We describe the algorithm that selects the main sample of galaxies forspectroscopy in the Sloan Digital Sky Survey (SDSS) from the photometricdata obtained by the imaging survey. Galaxy photometric properties aremeasured using the Petrosian magnitude system, which measures flux inapertures determined by the shape of the surface brightness profile. Themetric aperture used is essentially independent of cosmological surfacebrightness dimming, foreground extinction, sky brightness, and thegalaxy central surface brightness. The main galaxy sample consists ofgalaxies with r-band Petrosian magnitudes r<=17.77 and r-bandPetrosian half-light surface brightnesses μ50<=24.5 magarcsec-2. These cuts select about 90 galaxy targets persquare degree, with a median redshift of 0.104. We carry out a number oftests to show that (1) our star-galaxy separation criterion is effectiveat eliminating nearly all stellar contamination while removing almost nogenuine galaxies, (2) the fraction of galaxies eliminated by our surface

Optical and Radio Properties of Extragalactic Sources Observed by the FIRST Survey and the Sloan Digital Sky Survey - Ivezić, Željko; Menou, Kristen; Knapp, Gillian R.; Strauss, Michael A.; Lupton, Robert H.; Vanden Berk, Daniel E.; Richards, Gordon T.; Tremonti, Christy; Weinstein, Michael A.; Anderson, Scott; Bahcall, Neta A.; Becker, Robert H.; et al. (The Astronomical Journal, 2002)
We discuss the optical and radio properties of ~30,000 FIRST (radio, 20cm, sensitive to 1 mJy) sources positionally associated within 1.5" witha Sloan Digital Sky Survey (SDSS) (optical, sensitive to r*~22.2) source

The Angular Correlation Function of Galaxies from Early Sloan Digital Sky Survey Data - Connolly, Andrew J.; Scranton, Ryan; Johnston, David; Dodelson, Scott; Eisenstein, Daniel J.; Frieman, Joshua A.; Gunn, James E.; Hui, Lam; Jain, Bhuvnesh; Kent, Stephen; Loveday, Jon; Nichol, Robert C.; et al. (The Astrophysical Journal, 2002)
The Sloan Digital Sky Survey is one of the first multicolor photometricand spectroscopic surveys designed to measure the statistical propertiesof galaxies within the local universe. In this paper we present some ofthe initial results on the angular two-point correlation functionmeasured from the early SDSS galaxy data. The form of the correlationfunction, over the magnitude interval 18*<22, isshown to be consistent with results from existing wide-field,photographic-based surveys and narrower CCD galaxy surveys. On scalesbetween 1' and 1° the correlation function is well described by apower law with an exponent of ~-0.7. The amplitude of the correlationfunction, within this angular interval, decreases with faintermagnitudes in good agreement with analysis from existing galaxy surveys.There is a characteristic break in the correlation function on scales ofapproximately 1°-2°. On small scales, θ<1',the SDSS correlation function does not appear to be consistent with thepower-law form fitted to the 1'<θ<0.5d data.

Analysis of Systematic Effects and Statistical Uncertainties in Angular Clustering of Galaxies from Early Sloan Digital Sky Survey Data - Scranton, Ryan; Johnston, David; Dodelson, Scott; Frieman, Joshua A.; Connolly, Andy; Eisenstein, Daniel J.; Gunn, James E.; Hui, Lam; Jain, Bhuvnesh; Kent, Stephen; Loveday, Jon; Narayanan, Vijay; et al. (The Astrophysical Journal, 2002)
The angular distribution of galaxies encodes a wealth of informationabout large-scale structure. Ultimately, the Sloan Digital Sky Survey(SDSS) will record the angular positions of order of 108galaxies in five bands, adding significantly to the cosmologicalconstraints. This is the first in a series of papers analyzing arectangular stripe of 2.5d×90deg from early SDSS data.We present the angular correlation function for galaxies in fourseparate magnitude bins on angular scales ranging from 0.003d to15°. Much of the focus of this paper is on potential systematiceffects. We show that the final galaxy catalog-with the mask accountingfor regions of poor seeing, reddening, bright stars, etc.-is free fromexternal and internal systematic effects for galaxies brighter thanr*=22. Our estimator of the angular correlation functionincludes the effects of the integral constraint and the mask. The fullcovariance matrix of errors in these estimates is derived using mockcatalogs with further estimates using a number of other methods. Basedon observations obtained with the Sloan Digital Sky Survey.

Correlations in the Spatial Power Spectra Inferred from Angular Clustering: Methods and Application to the Automated Plate Measuring Survey - Eisenstein, Daniel J.; Zaldarriaga, Matias (The Astrophysical Journal, 2001)
We reconsider the inference of spatial power spectra from angularclustering data and show how to include correlations in both the angularcorrelation function and the spatial power spectrum. Inclusion of thefull covariance matrices loosens the constraints on large-scalestructure inferred from the Automated Plate Measuring (APM) survey byover a factor of 2. We present a new inversion technique based onsingular-value decomposition that allows one to propagate the covariancematrix on the angular correlation function through to that of thespatial power spectrum and to reconstruct smooth power spectra withoutunderestimating the errors. Within a parameter space of the cold darkmatter (CDM) shape Γ and the amplitude σ8, wefind that the angular correlations in the APM survey constrain Γ

Probing Early Structure Formation with Far-Infrared Background Correlations - Knox, Lloyd; Cooray, Asantha; Eisenstein, Daniel; Haiman, Zoltan (The Astrophysical Journal, 2001)
The large-scale structure of high-redshift galaxies produces correlatedanisotropy in the far-infrared background (FIRB). In regions of the skywhere the thermal emission from Galactic dust is well below average,these high-redshift correlations may be the most significant source ofangular fluctuation power over a wide range of angular scales, from ~7'to ~3°, and frequencies, from ~400 to ~1000 GHz. The strength ofthis signal should allow detailed studies of the statistics of the FIRBfluctuations, including the shape of the angular power spectrum at agiven frequency and the degree of coherence between FIRB maps atdifferent frequencies. The FIRB correlations depend on and henceconstrain the redshift-dependent spectral energy distributions, numbercounts, and clustering bias of the galaxies and active nuclei thatcontribute to the background. We quantify the accuracy to which Planckand a newly proposed balloon-borne mission, Explorer of Diffuse GalacticEmissions, could constrain models of the high-redshift universe throughthe measurement of FIRB fluctuations. We conclude that the average bias

The Luminosity Function of Galaxies in SDSS Commissioning Data - Blanton, Michael R.; Dalcanton, Julianne; Eisenstein, Daniel; Loveday, Jon; Strauss, Michael A.; SubbaRao, Mark; Weinberg, David H.; Anderson, John E., Jr.; Annis, James; Bahcall, Neta A.; Bernardi, Mariangela; Brinkmann, J.; et al. (The Astronomical Journal, 2001)
In the course of its commissioning observations, the Sloan Digital SkySurvey (SDSS) has produced one of the largest redshift samples ofgalaxies selected from CCD images. Using 11,275 galaxies complete tor*=17.6 over 140 deg2, we compute the luminosityfunction of galaxies in the r* band over a range-23r*<-16 (for h=1). The result iswell-described by a Schechter function with parametersφ*=(1.46+/-0.12)×10-2 h3Mpc-3, M*=-20.83+/-0.03, and α=-1.20+/-0.03.The implied luminosity density in r* isj~(2.6+/-0.3)×108h Lsolar Mpc-3.We find that the surface brightness selection threshold has a negligibleimpact for Mr*<-18. Using subsets of the data,we measure the luminosity function in the u*, g*,i*, and z* bands as well; the slope at lowluminosities ranges from α=-1.35 to α=-1.2. We measure thebivariate distribution of r* luminosity with half-lightsurface brightness, intrinsic g*-r* color, andmorphology. In agreement with previous studies, we find that highsurface brightness, red, highly concentrated galaxies are on averagemore luminous than low surface brightness, blue, less concentratedgalaxies. An important feature of the SDSS luminosity function is theuse of Petrosian magnitudes, which measure a constant fraction of agalaxy's total light regardless of the amplitude of its surfacebrightness profile. If we synthesize results for RGKC band orbj band using these Petrosian magnitudes, we obtainluminosity densities 2 times that found by the Las Campanas RedshiftSurvey in RGKC and 1.4 times that found by the Two DegreeField Galaxy Redshift Survey in bj. However, we are able toreproduce the luminosity functions obtained by these surveys if we alsomimic their isophotal limits for defining galaxy magnitudes, which areshallower and more redshift dependent than the Petrosian magnitudes usedby the SDSS. Based on observations obtained with the Sloan Digital SkySurvey.

Spectroscopic Target Selection for the Sloan Digital Sky Survey: The Luminous Red Galaxy Sample - Eisenstein, Daniel J.; Annis, James; Gunn, James E.; Szalay, Alexander S.; Connolly, Andrew J.; Nichol, R. C.; Bahcall, Neta A.; Bernardi, Mariangela; Burles, Scott; Castander, Francisco J.; Fukugita, Masataka; Hogg, David W.; et al. (The Astronomical Journal, 2001)
We describe the target selection and resulting properties of aspectroscopic sample of luminous red galaxies (LRGs) from the imagingdata of the Sloan Digital Sky Survey (SDSS). These galaxies are selectedon the basis of color and magnitude to yield a sample of luminousintrinsically red galaxies that extends fainter and farther than themain flux-limited portion of the SDSS galaxy spectroscopic sample. Thesample is designed to impose a passively evolving luminosity andrest-frame color cut to a redshift of 0.38. Additional, yet moreluminous red galaxies are included to a redshift of ~0.5. Approximately12 of these galaxies per square degree are targeted for spectroscopy, sothe sample will number over 100,000 with the full survey. SDSScommissioning data indicate that the algorithm efficiently selectsluminous (M*g~-21.4) red galaxies, that thespectroscopic success rate is very high, and that the resulting set ofgalaxies is approximately volume limited out to z=0.38. When the SDSS iscomplete, the LRG spectroscopic sample will fill over 1 h-3Gpc3 with an approximately homogeneous population of galaxiesand will therefore be well suited to studies of large-scale structureand clusters out to z=0.5.

Foregrounds and Forecasts for the Cosmic Microwave Background - Tegmark, Max; Eisenstein, Daniel J.; Hu, Wayne; de Oliveira-Costa, Angelica (The Astrophysical Journal, 2000)
One of the main challenges facing upcoming cosmic microwave background(CMB) experiments will be to distinguish the cosmological signal fromforeground contamination. We present a comprehensive treatment of thisproblem and study how foregrounds degrade the accuracy with which theBoomerang, MAP, and Planck experiments can measure cosmologicalparameters. Our foreground model includes not only the normalization,frequency dependence, and scale dependence for each physical component,but also variations in frequency dependence across the sky. Whenestimating how accurately cosmological parameters can be measured, weinclude the important complication that foreground model parameters (weuse about 500) must be simultaneously measured from the data as well.Our results are quite encouraging: despite all these complications,precision measurements of most cosmological parameters are degraded byless than a factor of 2 for our main foreground model and by less than afactor of 5 in our most pessimistic scenario. Parameters measured thoughlarge-angle polarization signals suffer more degradation: up to 5 in themain model and 25 in the pessimistic case. The foregrounds that arepotentially most damaging and therefore most in need of further studyare vibrating dust emission and point sources, especially those in theradio frequencies. It is well known that E and B polarization containvaluable information about reionization and gravity waves, respectively.However, the cross-correlation between polarized and unpolarizedforegrounds also deserves further study, as we find that it carries thebulk of the polarization information about most other cosmologicalparameters.

The Sloan Digital Sky Survey: Technical Summary - York, Donald G.; Adelman, J.; Anderson, John E., Jr.; Anderson, Scott F.; Annis, James; Bahcall, Neta A.; Bakken, J. A.; Barkhouser, Robert; Bastian, Steven; Berman, Eileen; Boroski, William N.; Bracker, Steve; et al. (The Astronomical Journal, 2000)
The Sloan Digital Sky Survey (SDSS) will provide the data to supportdetailed investigations of the distribution of luminous and nonluminousmatter in the universe: a photometrically and astrometrically calibrateddigital imaging survey of π sr above about Galactic latitude 30°in five broad optical bands to a depth of g'~23 mag, and a spectroscopicsurvey of the approximately 106 brightest galaxies and105 brightest quasars found in the photometric object catalogproduced by the imaging survey. This paper summarizes the observationalparameters and data products of the SDSS and serves as an introductionto extensive technical on-line documentation.

Power Spectra for Cold Dark Matter and Its Variants - Eisenstein, Daniel J.; Hu, Wayne (The Astrophysical Journal, 1999)
The bulk of recent cosmological research has focused on the adiabaticcold dark matter model and its simple extensions. Here we present anaccurate fitting formula that describes the matter transfer functions ofall common variants, including mixed dark matter models. The result is afunction of wavenumber, time, and six cosmological parameters: themassive neutrino density, number of neutrino species degenerate in mass,baryon density, Hubble constant, cosmological constant, and spatialcurvature. We show how observational constraints-e.g., the shape of thepower spectrum, the abundance of clusters and damped Lyalpha systems,and the properties of the Lyalpha forest-can be extended to a wide rangeof cosmologies, which includes variations in the neutrino and baryonfractions in both high-density and low-density universes.

Cosmic Complementarity: Joint Parameter Estimation from Cosmic Microwave Background Experiments and Redshift Surveys - Eisenstein, Daniel J.; Hu, Wayne; Tegmark, Max (The Astrophysical Journal, 1999)
We study the ability of future cosmic microwave background anisotropyexperiments and redshift surveys to constrain a 13-dimensionalparameterization of the adiabatic cold dark matter model. Each alone isunable to determine all parameters to high accuracy. However, consideredtogether, one data set resolves the difficulties of the other, allowingcertain degenerate parameters to be determined with far greaterprecision. We treat in detail the degeneracies involving the classicalcosmological parameters, massive neutrinos, tensor-scalar ratio, bias,and reionization optical depth as well as how redshift surveys canresolve them. We discuss the opportunities for internal and externalconsistency checks on these measurements. Previous papers on parameterestimation have generally treated smaller parameter spaces; in directcomparisons to these works, we tend to find weaker constraints andsuggest numerical explanations for the discrepancies.

Structure of structure formation theories - Hu, Wayne; Eisenstein, Daniel J. (Physical Review D, 1999)
We study the general structure of models for structure formation, withapplications to the reverse engineering of the model from observations.Through a careful accounting of the degrees of freedom in covariantgravitational instability theory, we show that the evolution ofstructure is completely specified by the stress history of the darksector. The study of smooth, entropic, sonic, scalar anisotropic, vectoranisotropic, and tensor anisotropic stresses reveals the origin,robustness, and uniqueness of specific model phenomenology. We constructuseful and illustrative analytic solutions that cover cases withmultiple species of differing equations of state relevant to the currentgeneration of models, especially those with effectively smoothcomponents. We present a simple case study of models withphenomenologies similar to that of a ΛCDM model to highlightreverse-engineering issues. A critical-density universe dominated by asingle type of dark matter with the appropriate stress history can mimica ΛCDM model exactly.

Observationally determining the properties of dark matter - Hu, Wayne; Eisenstein, Daniel J.; Tegmark, Max; White, Martin (Physical Review D, 1999)
Determining the properties of the dark components of the universeremains one of the outstanding challenges in cosmology. We explore howupcoming CMB anisotropy measurements, galaxy power spectrum data, andsupernova (SN) distance measurements can observationally constrain theirgravitational properties with minimal assumptions on the theoreticalside. SN observations currently suggest the existence of dark matterwith an exotic equation of state p/ρ<~-1/3 that accelerates theexpansion of the universe. When combined with CMB anisotropymeasurements, SN or galaxy survey data can in principle determine theequation of state and density of this component separately, regardlessof their value, as long as the universe is spatially flat. Combiningthese pairs creates a sharp consistency check. If p/ρ>~-1/2, thenthe clustering behavior (sound speed) of the dark component can bedetermined so as to test the scalar-field ``quintessence'' hypothesis.If the exotic matter turns out instead to be simply a cosmologicalconstant (p/ρ=-1), the combination of CMB and galaxy survey datashould provide a significant detection of the remaining dark matter, theneutrino background radiation (NBR). The gross effect of its density ortemperature on the expansion rate is ill constrained as it can bemimicked by a change in the matter density. However, anisotropies of theNBR break this degeneracy and should be detectable by upcomingexperiments.

Can Baryonic Features Produce the Observed 100 H -1 MPC Clustering? - Eisenstein, Daniel J.; Hu, Wayne; Silk, Joseph; Szalay, Alexander S. (The Astrophysical Journal Letters, 1998)
We assess the possibility that baryonic acoustic oscillations inadiabatic models may explain the observations of excess power inlarge-scale structure on 100 h-1 Mpc scales. The observed locationrestricts models to two extreme areas of parameter space. In eithercase, the baryon fraction must be large ( Omega b/ Omega0>~0.3 ) in order to yield significant features. The firstregion requires Omega 0<~0.2 h to match the location,implying large blue tilts ( n>~1.4 ) to satisfy cluster abundanceconstraints. The power spectrum also continues to rise toward largerscales in these models. The second region requires Omega 0~1, implying Omega b well out of the range of big bangnucleosynthesis constraints; moreover, the peak is noticeably wider thanthe observations suggest. Testable features of both solutions are thatthey require moderate reionization and thereby generate potentiallyobservable (~1 mu K) large-angle polarization, as well as subarcminutetemperature fluctuations. In short, baryonic features in adiabaticmodels may explain the observed excess only if currently favoreddeterminations of cosmological parameters are in substantial error or ifpresent surveys do not represent a fair sample of 100 h-1 Mpcstructures.

Baryonic Features in the Matter Transfer Function - Eisenstein, Daniel J.; Hu, Wayne (The Astrophysical Journal, 1998)
We provide scaling relations and fitting formulae for adiabatic colddark matter cosmologies that account for all baryon effects in the

HOP: A New Group-Finding Algorithm for N-Body Simulations - Eisenstein, Daniel J.; Hut, Piet (The Astrophysical Journal, 1998)
We describe a new method (HOP) for identifying groups of particles inN-body simulations. Having assigned to every particle an estimate of itslocal density, we associate each particle with the densest of the Nhopparticles nearest to it. Repeating this process allows us to trace apath, within the particle set itself, from each particle in thedirection of increasing density. The path ends when it reaches aparticle that is its own densest neighbor; all particles reaching thesame such particle are identified as a group. Combined with an adaptivesmoothing kernel for finding the densities, this method is spatiallyadaptive, coordinate-free, and numerically straightforward. One canproceed to process the output by truncating groups at a particulardensity contour and combining groups that share a (possibly different)density contour. While the resulting algorithm has several user-chosenparameters, we show that the results are insensitive to most of these,the exception being the outer density cutoff of the groups.

Small-Scale Perturbations in a General Mixed Dark Matter Cosmology - Hu, Wayne; Eisenstein, Daniel J. (The Astrophysical Journal, 1998)
For a universe with massive neutrinos, cold dark matter, and baryons, wesolve the linear perturbation equations analytically in the small-scale

Cosmic Complementarity: H 0 and Omega M from Combining Cosmic Microwave Background Experiments and Redshift Surveys - Eisenstein, Daniel J.; Hu, Wayne; Tegmark, Max (The Astrophysical Journal Letters, 1998)
We show that the detection of acoustic oscillations in both upcomingcosmic microwave background (CMB) satellite experiments and

Weighing Neutrinos with Galaxy Surveys - Hu, Wayne; Eisenstein, Daniel J.; Tegmark, Max (Physical Review Letters, 1998)
We show that galaxy redshift surveys sensitively probe the neutrinomass, with eV mass neutrinos suppressing power by a factor of 2. TheSloan Digital Sky Survey can potentially detect N nearly degeneratemassive neutrino species with massmν>~0.65\(Ωmh2/0.1N\)0.8eV at better than 2σ once microwave background experiments measuretwo other cosmological parameters. Significant overlap exists betweenthis region and that implied by the Liquid Scintillator NeutrinoDetector experiment, and even mν~0.01-0.1 eV, as impliedby the atmospheric anomaly, can affect cosmological measurements.

Dynamical Mass Estimates of Large-Scale Filaments in Redshift Surveys - Eisenstein, Daniel J.; Loeb, Abraham; Turner, Edwin L. (The Astrophysical Journal, 1997)
We propose a new method to measure the mass of large-scale filaments ingalaxy redshift surveys. The method is based on the fact that the massper unit length of isothermal filaments depends only on their transversevelocity dispersion. Filaments that lie perpendicular to the line ofsight may therefore have their mass per unit length measured from theirthickness in redshift space. We present preliminary tests of the methodand find that it predicts the mass per unit length of filaments in an

Appropriate Null Hypothesis for Cosmological Birefringence - Eisenstein, Daniel J.; Bunn, Emory F. (Physical Review Letters, 1997)
A Comment on the Letter by Borge Nodland and John P. Ralston, Phys. Rev.Lett. 78, 3043 (1997). The authors of the Letter offer a Reply.

Analytic Models for the Gravitational Formation of Objects in the Universe - Eisenstein, Daniel James (Ph.D. Thesis, 1996)
In this thesis, we use analytic approximate models of cosmologicalgravitational dynamics to study a variety of astrophysical systems. Webegin with the development of a new analytic collapse model in which thecollapsing region is treated as a homogeneous triaxial ellipsoid actedon by cosmological tidal shear. By performing a Monte Carlo sampling ofthe initial conditions, the ellipsoid model can predict thedistributions of angular momenta and axis ratios of collapsing regions.We then apply this and other analytic tools to certain astrophysicalsituations. In considering the origin of the black holes that powerquasars, we consider the likelihood of objects to be formed withsufficiently little angular momentum as to proceed to collapse to ablack hole; using the ellipsoid model, we estimate the number density ofblack holes formed in this manner to be ~ 10^{-3} Mpc ^{-3}. Next, westudy the clustering of Lyalpha clouds around the massive host of thequasar and show that this can produce clouds with redshifts exceedingthat of the quasar and alter the inferred ultraviolet background fromthe analysis of the proximity effect. We then consider the variation inthe relation between halo masses and velocity dispersions caused byvariations in their merger histories and show that the resulting scatteris larger than that observed for the Tully-Fisher relation. This arguesthat the Tully-Fisher relation does not result simply from theuniversality of halo properties but rather from feedback processesduring galaxy formation. Finally, we apply an exact solution for thesteady-state, self-gravitating, isothermal cylinder to construct amethod for estimating the mass per unit length of linear structures inredshift surveys. Tests of the method against N-body simulations suggest

Can the Tully-Fisher Relation Be the Result of Initial Conditions? - Eisenstein, Daniel J.; Loeb, Abraham (The Astrophysical Journal, 1996)
We use Monte Carlo realizations of halo formation histories and aspherical accretion model to calculate the expected scatter in thevelocity dispersions of galactic halos of a given mass due todifferences in their formation times. Assuming that the rotationalvelocity of a spiral galaxy is determined by the velocity dispersion ofits halo and that its luminosity is related to its total baryonic mass,this scatter translates to a minimum intrinsic scatter in theTully-Fisher relation. For popular cosmological models we find that thescatter due to variations in formation histories is by itself greaterthan allowed by observations. Unless halos of spiral galaxies formed athigh redshift (z 1) and did not later accrete any significant amount ofmass, the Tully-Fisher relation is not likely to be the direct result ofcosmological initial conditions but rather a consequence of a subsequentfeedback process.

An analytical model for the triaxial collapse of cosmological perturbations - Eisenstein, Daniel J.; Loeb, Abraham (The Astrophysical Journal, 1995)
We present an analytical model for the nonspherical collapse ofoverdense regions out of a Gaussian random field of initial cosmologicalperturbations. The collapsing region is treated as an ellipsoid ofconstant density, acted upon by the quadrupole tidal shear from thesurrounding matter. The dynamics of the ellipsoid is set by theellipsoid self-gravity and the external quadrupole shear. Both forcesare linear in the coordinates and therefore maintain homogeneity of theellipsoid at all times. The amplitude of the external shear is evolvedinto the nonlinear regime in thin spherical shells that are allowed tomove only radially according to mass interior to them. The fulldynamical equations then reduce to a set of nine second-order ordinarydifferential equations, which reproduce the linear regime behavior butcan be evolved past turnaround, well into the nonlinear regime. Wedescribe how the initial conditions can be drawn in the appropriatecorrelated way from a random field of initial density perturbations. Themodel is applied to a restricted set of initial conditions that are moresuitable to the above approximations; most notable we focus on theproperties of rare high-density peaks (greater than of approximately = 2sigma). By considering many random realization of the initialconditions, we calculate the distributions of shapes and angular momentaacquired by objects through the coupling of their quadruole moment tothe tidal shear. The average value of the spin parameter, (mean value ofa lambda) approximately = 0.04, is found to be only weakly dependent onthe system mass, the mean cosmological density, or the initial powerspectrum of perturbations, in agreement with N-body simulations. For thecold dark matter power spectrum, most objects evolve from aquasi-spherical initial state to a pancake or filament and then tocomplete virialization. Low-spin objects tend to be more spherical. Theevolution history of shapes is primarily induced by the external shearand not by the initial triaxially of the objects. The statisticaldistribution of the triaxial shapes of collapsing region can be used totest cosmological models against galaxy surveys on large scales.

Origin of quasar progenitors from the collapse of low-spin cosmological perturbations - Eisenstein, Daniel J.; Loeb, A. (The Astrophysical Journal, 1995)
We show that seeds for quasar black holes could have originated from theinitial cosmological collapse of overdense regions with unusually smallrotation. The gas in these rare regions collapses into a compact diskthat shrinks on a short viscous timescale. Using an analytical model, wecalculate the low-pin tail of the probability distribution of angularmomenta for objects that collapse out of a Gaussian random field ofinitial density peturbations. The population of low-spin systems issignificant for any viable power spectrum of primordial densityperturbations. Most objects from just above the cosmological Jeans massapproximately 105 solar mass at high redshifts z greater thanand approximately 10. In the standard cold dark matter cosmology, thecomoving density of 106-7 solar mass objects with viscousevolution times shorter than approximately 106-7 years isapproximately 10-3(h/0.5)3/cubic Mpc, comparableto the local density of bright galaxies. The seed black holes tend toreside within larger mass systems that collapse later and supply the gasneeded for the bright quasar activity.

Probing Early Clustering with LY alpha Absorption Lines beyond the Quasar Redshift - Loeb, Abraham; Eisenstein, Daniel J. (The Astrophysical Journal, 1995)
Groups and clusters of galaxies hosting a quasar can be found throughthe detection of Lyα absorption lines beyond the quasar redshift.The effect occurs whenever the distortion to the redshift distributionof Lyα clouds induced by the cluster potential extends beyond theproximity effect of the quasar. Based on cold dark matter (CDM)cosmological models for the evolution of structure, we predict theprobability for finding lines beyond the quasar redshift(Ζabs > ΖQ) under the assumption thatthe physical properties of Lyman alpha clouds are not affected by flowson large scales (≳Mpc) in the quasi-linear regime. If quasarsrandomly sample the underlying galaxy distribution, the expected numberof lines with Ζabs > ΖQ per quasarcan be as high as ˜0.5 × [(dN/dΖ)/350] at Ζ = 2,where dN/dΖ is the number of Lyα lines per unit redshift farfrom the quasar. The probability is enhanced if quasars typically residein small groups of galaxies. A statistical excess of Lyα lines isexpected near very dim quasars or around metal absorption systems. Dueto clustering, the standard approach to the proximity effectoverestimates the ionizing background flux at high redshifts by up to afactor of ˜3. This result weakens the discrepancy between thededuced background flux and the contribution from known populations ofquasars.